Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2019)
AIM: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. METHODS: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self-reported pain was at least six on a scale from 0-10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. RESULTS: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9-14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0-4.3) and tramadol 3.0 (IQR 1.0-5.0) vs paracetamol 3.0 (IQR 0.8-5.0). The median pain reductions were all 5.0 points. CONCLUSION: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.

Adolescent with painful vesicular otitis and vertigo. - Conversano, Ester; Cozzi, Giorgio; Poropat, Federico; Di Mascio, Alberto; Salis, Simona; Grasso, Domenico Leonardo; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2019)

Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Changing Epidemiology of Liver Involvement in Children With Celiac Disease. - Benelli, Elisa; Naviglio, Samuele; De Leo, Luigina; Stera, Giacomo; Giangreco, Manuela; Ronfani, Luca; Villanacci, Vincenzo; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Available data indicate that liver involvement is present in a significant proportion of children with celiac disease (CD) at the diagnosis (elevated transaminases 15%-57%, autoimmune liver disease 1%-2%). We sought to evaluate prevalence, clinical course, and risk factors for liver involvement in a large cohort of children with CD. METHODS: Children (age 0-18 years) diagnosed with CD from March 2010 to April 2016 were enrolled. Liver involvement was considered to be present when alanine transaminase (ALT) levels were >40 U/L (hypertransaminasemia [HTS]). Patients with HTS were re-evaluated after at least 12 months of a gluten-free diet. RESULTS: CD was diagnosed in 806 patients during the study period; of these, ALT levels were available for 700 patients (86.9%), and were elevated in 27 (3.9%, HTS group); median ALT and aspartate transaminase levels in the HTS group were 57 U/L (interquartile range 49-80 U/L) and 67 U/L (interquartile range 53-85 U/L), respectively. Younger age, malabsorption symptoms, and low hemoglobin or ferritin were significantly more common in the HTS group at univariate analysis. At multivariate analysis, only age ≤4.27 years correlated with risk of liver involvement (odds ratio 3.73; 95% confidence interval: 1.61-8.66). When retested on a gluten-free diet, all but 3 patients normalized ALT levels; of these, 1 was diagnosed with sclerosing cholangitis. CONCLUSIONS: Liver involvement in celiac children is now less frequent than previously reported, possibly due to changing CD epidemiology. Younger age is the only risk factor. Associated autoimmune liver disease is rare.

An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M; Carrozzi, Marco; Skabar, Aldo; Sugden, David A; Barnett, Anna L; Henderson, Sheila E (Res Dev Disabil, 2019)
BACKGROUND: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. AIM: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. METHOD: A total of 718 Italian (IT) and 765 British (UK) children, aged 3-10 years, were individually tested on the age-appropriate items of the MABC-2 Test. RESULTS: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. CONCLUSION: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.

Facing somatic symptom disorder in the emergency department. - Cozzi, Giorgio; Barbi, Egidio (J Paediatr Child Health, 2019)
Somatic symptom disorder is a condition in which a patient's subjective report of physical symptoms is associated with distress; disruption of day-to-day functioning; or disproportionate thoughts, feelings and behaviours regarding the symptoms, whether or not they are associated with an identified medical condition. While somatic symptom disorder affects a considerable proportion of children and adolescents presenting to the emergency department (ED), it has not been well investigated in the ED literature, nor is there much formal training in, or guidelines for, how to care for affected patients in the ED. The aim of this paper is to highlight the historical clues commonly reported by these patients in order to try to help the emergency physicians recognise patients affected by a somatic symptom disorder. Adolescent age, the presence of daily subjective symptoms presenting daily for weeks or months, a long medical history record, an extensive diagnostic workup and, most of all, disproportionate functional impairment related to the symptoms are all features strongly suggestive of this disorder. Emergency physicians should become used to taking advantage of these clues to formulate a positive diagnosis of somatic symptom disorder according to the most recent diagnostic criteria. Emergency physicians have the unique opportunity to contribute to the correct diagnosis and treatment of these patients and to have a positive impact on their prognosis.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Loss-of-function mutations in cause a new form of inherited thrombocytopenia. - Marconi, Caterina; Di Buduo, Christian A; LeVine, Kellie; Barozzi, Serena; Faleschini, Michela; Bozzi, Valeria; Palombo, Flavia; McKinstry, Spencer; Lassandro, Giuseppe; Giordano, Paola; Noris, Patrizia; Balduini, Carlo L; et al. (Blood, 2019)
Inherited thrombocytopenias (ITs) are a heterogeneous group of disorders characterized by low platelet count that may result in bleeding tendency. Despite progress being made in defining the genetic causes of ITs, nearly 50% of patients with familial thrombocytopenia are affected with forms of unknown origin. Here, through exome sequencing of 2 siblings with autosomal-recessive thrombocytopenia, we identified biallelic loss-of-function variants in This gene encodes for a receptor-like PTP, PTPRJ (or CD148), which is expressed abundantly in platelets and megakaryocytes. Consistent with the predicted effects of the variants, both probands have an almost complete loss of PTPRJ at the messenger RNA and protein levels. To investigate the pathogenic role of PTPRJ deficiency in hematopoiesis in vivo, we carried out CRISPR/Cas9-mediated ablation of (the ortholog of human ) in zebrafish, which induced a significantly decreased number of CD41 thrombocytes in vivo. Moreover, megakaryocytes of our patients showed impaired maturation and profound defects in SDF1-driven migration and formation of proplatelets in vitro. Silencing of in a human megakaryocytic cell line reproduced the functional defects observed in patients' megakaryocytes. The disorder caused by mutations presented as a nonsyndromic thrombocytopenia characterized by spontaneous bleeding, small-sized platelets, and impaired platelet responses to the GPVI agonists collagen and convulxin. These platelet functional defects could be attributed to reduced activation of Src family kinases. Taken together, our data identify a new form of IT and highlight a hitherto unknown fundamental role for PTPRJ in platelet biogenesis.

Menstruation-related disseminated intravascular coagulation in an adenomyosis patient: case report and review of the literature. - Cernogoraz, Alice; Schiraldi, Luigi; Bonazza, Deborah; Ricci, Giuseppe (Gynecol Endocrinol, 2019)
Disseminated intravascular coagulation (DIC) is a high mortality coagulopathy that leads to simultaneous thrombotic and bleeding problems. It occurs as a complication in different disease as malignancies, obstetrical catastrophes, bacterial sepsis and traumas. We report on an extremely rare case of acute DIC in a patient with misdiagnosed adenomyosis and massive methrorragia which led to acute kidney failure. The patient was successfully treated with hysterectomy and blood product transfusions; however, a slight reduction of renal function persisted. We were able to confirm the cause-consequence link between adenomyosis and consumptive DIC since we saw the thrombi in the adenomyotic uterus from early hysterectomy specimen. Moreover, this is the first case, for the best of our knowledge, in which systemic consequences persist in an adenomyosis patient who developed a DIC. Early diagnose and treatment of acute DIC is essential for patient's survival and to prevent severe complications: adenomyosis should be kept in mind as a possible cause of DIC when a patient shows up with massive bleeding.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

Retrospective study showed that palpitations with tachycardia on admission to a paediatric emergency department were related to cardiac arrhythmias. - Bobbo, Marco; Amoroso, Stefano; Tamaro, Gianluca; Gesuete, Valentina; D'agata Mottolese, Biancamaria; Barbi, Egidio; Ventura, Alessandro (Acta Paediatr, 2019)
AIM: This retrospective study reviewed the prevalence and long-term prognosis of children aged 0-18 with palpitations who were admitted to the emergency department (ED) of an Italian paediatric hospital. METHODS: We examined all admissions to the ED of the IRCCS Burlo Garofolo between January 2009 and December 2015 by selecting triage diagnoses of palpitations. The hospital discharge cards were reviewed to assess vital parameters, physical examinations, diagnostic tests, cardiology consultations and final diagnoses. RESULTS: Of the 142 803 patients who attended our ED for any reason, 96 (0.07%) complained of palpitations. Despite this low prevalence, it was noteworthy that 13.5% had a real underlying arrhythmic cause and needed medical assistance. Over half (52.1%) were women and the mean age was 12.7 years. At the long-term follow-up, at a mean of 47 ± 23 months, 53.8% of patients with a cardiac arrhythmia had received medical therapy and 46.1% had undergone trans-catheter ablation for supraventricular tachycardia. A heart rate above 146 beats per minute or palpitations for more than an hour was statistically related to a cardiac arrhythmia. CONCLUSION: Palpitations were an infrequent cause of admission to our ED, but 13.5% who displayed them had an underlying cardiac arrhythmia.

When Long-Lasting Food Selectivity Leads to an Unusual Genetic Diagnosis: A Case Report. - Da Lozzo, Prisca; Magnolato, Andrea; Del Rizzo, Irene; Sirchia, Fabio; Bruno, Irene; Barbi, Egidio (J Adolesc Health, 2019)
Hereditary fructose intolerance is an autosomal recessive disorder of fructose metabolism caused by catalytic deficiency of aldolase B enzyme [1]. The disease is typically expressed when fructose- and sucrose-containing foods are first introduced in the diet; acute manifestations include nausea, vomiting, abdominal distress, and symptomatic hypoglycemia [1,2]. Chronic fructose ingestion eventually leads to poor feeding, growth retardation and gradual liver and/or renal failure [3,4]. Some patients may remain undiagnosed until adulthood because of a self-protective avoidance of sweet tasting food that prevents the development of acute toxicity from fructose containing food; however, these subjects may suffer intermittent symptoms throughout life, leading to potentially serious misdiagnosis [4]. We report the case of a patient with unrecognized hereditary fructose intolerance in which chronic gastrointestinal complaints, low body weight, and unexplained food avoidance were addressed as manifestations of an eating disorder during adolescence.

ACTN1 mutations lead to a benign form of platelet macrocytosis not always associated with thrombocytopenia. - Faleschini, Michela; Melazzini, Federica; Marconi, Caterina; Giangregorio, Tania; Pippucci, Tommaso; Cigalini, Elena; Pecci, Alessandro; Bottega, Roberta; Ramenghi, Ugo; Siitonen, Timo; Seri, Marco; Pastore, Annalisa; et al. (Br J Haematol, 2018)
The inherited thrombocytopenias (IT) are a heterogeneous group of diseases resulting from mutations in more than 30 different genes. Among them, ACTN1-related thrombocytopenia (ACTN1-RT; Online Mendelian Inheritance in Man: 615193) is one of the most recently identified forms. It has been described as a mild autosomal dominant macrothrombocytopenia caused by mutations in ACTN1, a gene encoding for one of the two non-muscle isoforms of α-actinin. We recently identified seven new unrelated families with ACTN1-RT caused by different mutations. Two of them are novel missense variants (p.Trp128Cys and p.Pro233Leu), whose pathogenic role has been confirmed by in vitro studies. Together with the 10 families we have previously described, our cohort of ACTN1-RT now consists of 49 individuals carrying ACTN1 mutations. This is the largest case series ever collected and enabled a critical evaluation of the clinical aspects of the disease. We concluded that ACTN1-RT is the fourth most frequent form of IT worldwide and it is characterized by platelet macrocytosis in all affected subjects and mild thrombocytopenia in less than 80% of cases. The risk of bleeding, either spontaneous or upon haemostatic challenge, is negligible and there are no other associated defects, either congenital or acquired. Therefore, ACTN1-RT is a benign form of IT, whose diagnosis provides affected individuals and their families with a good prognosis.

Acute small bowel obstruction in a child with a strict raw vegan diet. - Amoroso, Stefano; Scarpa, Maria-Grazia; Poropat, Federico; Giorgi, Rita; Murru, Flora Maria; Barbi, Egidio (Arch Dis Child, 2018)

Adenomyomatosis of the Gallbladder as a Cause of Recurrent Abdominal Pain. - Agrusti, Anna; Gregori, Massimo; Salviato, Tiziana; Codrich, Daniela; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abdominal Pain; Adenomyoma; Adolescent; Biopsy, Needle; Cholecystectomy; Diagnosis, Differential; Female; Gallbladder; Gallbladder Neoplasms; Humans; Immunohistochemistry; Recurrence; Risk Assessment; Severity of Illness Index; Ultrasonography, Doppler

Adolescent with intermittent haematuria. - Pillon, Roberto; Pennesi, Marco; Rabach, Ingrid; Barbi, Egidio (Arch Dis Child Educ Pract Ed, 2018)

Anaphylaxis in atypical cold urticaria: case report and review of literature. - Benelli, Elisa; Longo, Giorgio; Barbi, Egidio; Berti, Irene (Ital J Pediatr, 2018)
BACKGROUND: Cold-induced urticaria is a kind of physical urticaria characterized by the appearance of wheals after exposure to cold. The atypical form is a rare sub-type characterized by appearance of hives even in areas not directly exposed to the cold and by a negative cold stimulation test. Its diagnosis is often challenging because of the lack of specific tests and it is usually based on the patient's clinical history. Hypotension due to generalized exposure to the cold is described both in the typical and the atypical forms. CASE PRESENTATION: We describe a 9-year-old boy who, at the beginning of the summer after the first swim in the sea, developed generalized urticaria, dyspnea, conjunctival hyperemia, blurred vision and loss of strength. The child was treated with intramuscular steroid and intravenous antihistamine, and the symptoms quickly resolved. Insect bite, contact with fish and drug ingestion were denied, and no unusual food had been eaten before the swim. A tentative diagnosis was made of either aquagenic urticaria or cold urticaria, but the specific tests were negative. Although the cause was unknown, prophylactic treatment with antihistamines was prescribed but in spite of this, wheals developed all over the body, after every swim in the sea. The child then came to our attention and relying on clinical history a diagnosis of atypical cold urticaria was made: development of hives even in areas not directly exposed to cold and a negative response to the cold stimulation test, are the characteristic features of this rare form of cold urticaria. CONCLUSION: Atypical cold urticaria should be suspected in all cases of anaphylaxis related to cold exposure (i.e. contact with water) with a negative cold stimulation test.
Keywords: Anaphylaxis; Child; Cold Temperature; Humans; Male; Swimming; Urticaria

Boy with fish-mouth meatus. - Cortellazzo Wiel, Luisa; Pederiva, Federica; Castagnetti, Marco; Barbi, Egidio; Pennesi, Marco (Arch Dis Child, 2018)

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells. - Bellazzo, Arianna; Di Minin, Giulio; Valentino, Elena; Sicari, Daria; Torre, Denis; Marchionni, Luigi; Serpi, Federica; Stadler, Michael B; Taverna, Daniela; Zuccolotto, Gaia; Montagner, Isabella Monia; Rosato, Antonio; et al. (Cell Death Differ, 2018)
The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP. By efficiently downregulating DAB2IP, this miRNA enhances cancer cell motility and invasiveness, facilitating activation of NF-kB signaling and promoting expression of pro-inflammatory and pro-angiogenic factors. In addition, we found that miR-149-3p secreted by prostate cancer cells induces DAB2IP downregulation in recipient vascular endothelial cells, stimulating their proliferation and motility, thus potentially remodeling the tumor microenvironment. Finally, we found that inhibition of endogenous miR-149-3p restores DAB2IP activity and efficiently reduces tumor growth and dissemination of malignant cells. These observations suggest that miR-149-3p can promote cancer progression via coordinated inhibition of DAB2IP in tumor cells and in stromal cells.

Cerebrospinal Fluid Cytokine Expression Profile in Multiple Sclerosis and Chronic Inflammatory Demyelinating Polyneuropathy. - Bonin, Serena; Zanotta, Nunzia; Sartori, Arianna; Bratina, Alessio; Manganotti, Paolo; Trevisan, Giusto; Comar, Manola (Immunol Invest, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) analysis in patients with particular neurologic disorders is a powerful tool to evaluate specific central nervous system inflammatory markers for diagnostic needs, because CSF represents the specific immune micro-environment to the central nervous system. METHODS: CSF samples from 49 patients with multiple sclerosis (MS), chronic inflammatory demyelinating polyneuropathy (CIDP), and non-inflammatory neurologic disorders (NIND) as controls were submitted to protein expression profiles of 47 inflammatory biomarkers by multiplex Luminex bead assay to investigate possible differences in the inflammatory process for MS and CIDP. RESULTS: Our results showed differences in CSF cytokine levels in MS and CIDP; in particular, IL12 (p40) was significantly highly expressed in MS in comparison with CIDP and NIND, while SDF-1α and SCGF-β were significantly highly expressed in CIDP cohort when compared to MS and NIND. IL-9, IL-13, and IL-17 had higher expression levels in NIND if compared with the other groups. CONCLUSIONS: Our study showed that, despite some common pathogenic mechanisms, central and peripheral nervous system demyelinating diseases, such as MS and CIDP, differ in some specific inflammatory soluble proteins in CSF, underlining differences in the immune response involved in those autoimmune diseases.
Keywords: Adult; Aged; Biomarkers; Central Nervous System; Diagnosis, Differential; Female; Hematopoietic Cell Growth Factors; Humans; Interleukin-12; Lectins, C-Type; Male; Middle Aged; Multiple Sclerosis; Peripheral Nervous System; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Proteins

Characterization of multi-locus imprinting disturbances and underlying genetic defects in patients with chromosome 11p15.5 related imprinting disorders. - Fontana, L; Bedeschi, M F; Maitz, S; Cereda, A; Faré, C; Motta, S; Seresini, A; D'Ursi, P; Orro, A; Pecile, V; Calvello, M; Selicorni, A; et al. (Epigenetics, 2018)
The identification of multilocus imprinting disturbances (MLID) appears fundamental to uncover molecular pathways underlying imprinting disorders (IDs) and to complete clinical diagnosis of patients. However, MLID genetic associated mechanisms remain largely unknown. To characterize MLID in Beckwith-Wiedemann (BWS) and Silver-Russell (SRS) syndromes, we profiled by MassARRAY the methylation of 12 imprinted differentially methylated regions (iDMRs) in 21 BWS and 7 SRS patients with chromosome 11p15.5 epimutations. MLID was identified in 50% of BWS and 29% of SRS patients as a maternal hypomethylation syndrome. By next-generation sequencing, we searched for putative MLID-causative mutations in genes involved in methylation establishment/maintenance and found two novel missense mutations possibly causative of MLID: one in NLRP2, affecting ADP binding and protein activity, and one in ZFP42, likely leading to loss of DNA binding specificity. Both variants were paternally inherited. In silico protein modelling allowed to define the functional effect of these mutations. We found that MLID is very frequent in BWS/SRS. In addition, since MLID-BWS patients in our cohort show a peculiar pattern of BWS-associated clinical signs, MLID test could be important for a comprehensive clinical assessment. Finally, we highlighted the possible involvement of ZFP42 variants in MLID development and confirmed NLRP2 as causative locus in BWS-MLID.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Beckwith-Wiedemann Syndrome; Child; Child, Preschool; Chromosomes, Human, Pair 15; DNA Methylation; Female; Genomic Imprinting; Humans; Infant; Kruppel-Like Transcription Factors; Male; Mutation, Missense; Silver-Russell Syndrome; Young Adult

A Child with Diminished Linear Growth and Waddling Gait. - Tamaro, Gianluca; Pederiva, Federica; Dibello, Daniela; Gregori, Massimo; Carbone, Marco; Pantaleoni, Francesca; Dentici, Maria Lisa; Niceta, Marcello; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abnormalities, Multiple; Child; Dwarfism; Female; Gait; Humans; Osteochondrodysplasias; Radiography

The Complex Interplay between Lipids, Immune System and Interleukins in Cardio-Metabolic Diseases. - Bernardi, Stella; Marcuzzi, Annalisa; Piscianz, Elisa; Tommasini, Alberto; Fabris, Bruno (Int J Mol Sci, 2018)
Lipids and inflammation regulate each other. Early studies on this topic focused on the systemic effects that the acute inflammatory response-and interleukins-had on lipid metabolism. Today, in the era of the obesity epidemic, whose primary complications are cardio-metabolic diseases, attention has moved to the effects that the nutritional environment and lipid derangements have on peripheral tissues, where lipotoxicity leads to organ damage through an imbalance of chronic inflammatory responses. After an overview of the effects that acute inflammation has on the systemic lipid metabolism, this review will describe the lipid-induced immune responses that take place in peripheral tissues and lead to chronic cardio-metabolic diseases. Moreover, the anti-inflammatory effects of lipid lowering drugs, as well as the possibility of using anti-inflammatory agents against cardio-metabolic diseases, will be discussed.
Keywords: Anti-Inflammatory Agents; Cardiovascular Diseases; Humans; Hypolipidemic Agents; Immune System; Inflammation; Interleukins; Lipid Metabolism; Lipids; Metabolic Diseases

Cooking influence in tolerance acquisition in egg-induced acute food protein enterocolitis syndrome. - Miceli Sopo, S; Romano, A; Bersani, G; Fantacci, C; Badina, L; Longo, G; Monti, G; Viola, S; Tripodi, S; Barilaro, G; Iacono, I D; Caffarelli, C; et al. (Allergol Immunopathol (Madr), 2018)
BACKGROUND: Few studies on the age of resolution of Food Protein Induced Enterocolitis Syndrome (FPIES) induced by solid foods are available. In particular, for FPIES induced by egg, the mean age of tolerance acquisition reported in the literature ranges from 42 to 63 months. OBJECTIVE: We have assessed whether the age of tolerance acquisition in acute egg FPIES varies depending on whether the egg is cooked or raw. METHODS: We conducted a retrospective and multicentric study of children with diagnosis of acute egg FPIES seen in 10 Italian allergy units between July 2003 and October 2017. The collected data regarded sex, presence of other allergic diseases, age of onset of symptoms, kind and severity of symptoms, cooking technique of the ingested egg, outcome of the allergy test, age of tolerance acquisition. RESULTS: Sixty-one children with acute egg FPIES were enrolled, 34 (56%) males and 27 (44%) females. Tolerance to cooked egg has been demonstrated by 47/61 (77%) children at a mean age of 30.2 months. For 32 of them, tolerance to raw egg has been demonstrated at a mean age of 43.9 months. No episodes of severe adverse reaction after baked egg ingestion have been recorded. CONCLUSIONS: It is possible to perform an OFC with baked egg, to verify the possible acquisition of tolerance, at about 30 months of life in children with acute egg FPIES.

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway. - Fetoni, Anna Rita; Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Raspa, Marcello; Scavizzi, Ferdinando; Salvatore, Anna Maria; Crispino, Giulia; Tognola, Gabriella; Gentile, Giulia; Spampinato, Antonio Gianmaria; et al. (Redox Biol, 2018)
Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2 mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly in Gjb2 mice, indicating they were affected by accelerated age-related hearing loss (ARHL), or presbycusis. We linked causally the auditory phenotype of Gjb2 mice to apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, decreased nutrient delivery to the sensory epithelium via cochlear gap junctions and deregulated expression of genes that are under transcriptional control of the nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal regulator of tolerance to redox stress. Moreover, a statistically significant genome-wide association with two genes (PRKCE and TGFB1) related to the Nrf2 pathway (p-value < 4 × 10) was detected in a very large cohort of 4091 individuals, originating from Europe, Caucasus and Central Asia, with hearing phenotype (including 1076 presbycusis patients and 1290 healthy matched controls). We conclude that (i) elements of the Nrf2 pathway are essential for hearing maintenance and (ii) their dysfunction may play an important role in the etiopathogenesis of human presbycusis.
Keywords: Animals; Apoptosis; Connexin 26; Female; Gene Deletion; Male; Mice; Mice, Inbred C57BL; NF-E2-Related Factor 2; Oxidation-Reduction; Presbycusis; Signal Transduction

Cytokine profiles of women with vulvodynia: Identification of a panel of pro-inflammatory molecular targets. - Zanotta, Nunzia; Campisciano, Giuseppina; Scrimin, Federica; Blendi, Ura; Marcuzzi, Annalisa; Vincenti, Ezio; Crovella, Sergio; Comar, Manola (Eur J Obstet Gynecol Reprod Biol, 2018)
OBJECTIVE: The vulvar pain syndrome (VPS) is a multifactorial disease severely influencing the lifestyle of affected women. Among possible etiological factors, local injury, peripheral and/or central sensitization of the nervous system, and a chronic inflammatory status have been positively associated with the development of VPS. The identification of a constitutive altered local inflammatory profile in VPS women may represent an important point in the characterization of patients' phenotype as a useful marker influencing the vulvar micro-environment. The aim of this study was to investigative the possible role of the local cytokines production in women with VPS in comparison to healthy women. STUDY DESIGN: In this study were collected vaginal swabs from 57 healthy women (HC) who never suffered from VPS and from 30 patients diagnosed with vulvodynia (VPS) by at least 3 years and currently symptomatic. All patients included in this study showed the absence of Sexually Transmitted (STD) diseases and Reproductive Tract Infection. Real-time PCR was performed to assess the genomic sequences of ST pathogens. The Luminex Bio-Plex platform was used for the analysis of a panel of 48 immune factors. RESULTS: Eleven molecules, specifically involved in the pro-inflammatory pathway were significantly modulated in VPS patients in comparison to healthy women, suggesting a persistent inflammatory process. CONCLUSIONS: Therefore, these inflammatory factors could be possible biological markers involved in this disease. Nevertheless, other studies are needed to consider this specific immune profile as a valid marker of the vulvodynia.
Keywords: Adult; Aged; Cytokines; Female; Humans; Inflammation; Middle Aged; Vaginal Smears; Vulva; Vulvodynia; Women's Health

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

Does the Application of Heat Gel Pack After Eutectic Mixture of Local Anesthetic Cream Improve Venipuncture or Intravenous Cannulation Success Rate in Children? A Randomized Control Trial. - Schreiber, Silvana; Cozzi, Giorgio; Patti, Giuseppa; Taddio, Andrea; Montico, Marcella; Pierobon, Chiara; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: Needle-related procedures are the most common sources of pain for children in the hospital setting. The most used topical anesthetic, eutectic mixture of local anesthetic (EMLA) cream, may cause transient vasoconstriction. It has been postulated that this vasoconstriction may decrease vein visualization. The application of heat gel pack after removal of EMLA cream in the site of venipuncture counteracts the vasoconstriction, improving vein visualization. We assessed using a prospective randomized controlled trial whether the application of heat gel pack increases the needle procedure success rate. The primary study outcome was procedural success rate at the first attempt. METHODS: The study enrolled 400 children, 200 of whom applied heat gel pack after removing EMLA (treatment group) and 200 did not (control group). Procedural success rate at the first attempt, vein perception before procedure, procedural pain, and adverse events were recorded in both groups. RESULTS: Eighty-eight percent of the procedures were successful at the first attempt in the treatment group and 89% in the control group (P = 0.876). Vein perception was not significantly different in the 2 groups (P = 0.081). Pain score after the procedure was similar in the 2 groups. CONCLUSIONS: This study shows that the application of heat gel pack after removal of EMLA cream does not improve venipuncture or intravenous cannulation success rate.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Pain Management; Phlebotomy; Prilocaine; Prospective Studies

Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Emergency extracorporeal shockwave lithotripsy as opposed to delayed shockwave lithotripsy for the treatment of acute renal colic due to obstructive ureteral stone: a prospective randomized trial. - Bucci, Stefano; Umari, Paolo; Rizzo, Michele; Pavan, Nicola; Liguori, Giovanni; Barbone, Fabio; Trombetta, Carlo (Minerva Urol Nefrol, 2018)
BACKGROUND: The aim of this study was to assess the efficacy of emergency extracorporeal shockwave lithotripsy (eSWL) as first-line treatment in patients with acute colic due to obstructive ureteral stone. METHODS: Seventy-four patients were randomized to emergency SWL within 12 hours (eSWL group) and deferred SWL later than 3 days (dSWL group). Follow-up included ultrasound, KUB (kidney-ureter-bladder) radiography and CT (computed tomography) scan at 24 hours, 7 days, 1 and 3 months from the treatment. When necessary, repeated SWL (re-SWL) or ureteroscopy (auxiliary-URS) was performed. Preoperative and postoperative data were compared and stone free rates (SFR) and efficiency quotients (EQ) were evaluated. Analyses were performed using SAS software. RESULTS: Complete data of 70 patients were collected. 36 underwent eSWL and 34 dSWL. The mean patient age was 48.7. Mean stone size was 9.8 mm (CI 95%: 8.9-10.8). 25 (35.7%) were proximal and 45 (64.3%) distal. Mean SWL energy was 19.2 kV (CI 95%: 18.5-19.9) and mean number of shocks was 2657 (CI 95%: 2513-2802). eSWL patients needs less auxiliary-URS than dSWL patients (13.9% vs. 44.1%, P=0.039) and less re-SWL sessions (8.3% vs. 32.4%, P=0.093). SFR at 24 hours was 52.8% and 11.8% (P<0.001) and the EQ at 3 months was 79.1% and 57.5% in the eSWL and dSWL group respectively. Patients from the dSWL group spent more time in the hospital (2.21 vs. 1.36 days, P=0.046) and complication rates between the two groups were similar. CONCLUSIONS: eSWL is a safe procedure and delivers high SFR even within 24 hours especially for <10 mm stones. It is able to reduce the number of auxiliary procedures and hospitalization.
Keywords: Aged; Calculi; Emergency Medical Services; Female; Humans; Length of Stay; Lithotripsy; Male; Middle Aged; Prospective Studies; Renal Colic; Time-to-Treatment; Tomography, X-Ray Computed; Ureteral Obstruction

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic profile of patients with early onset inflammatory bowel disease. - Girardelli, Martina; Basaldella, Federica; Paolera, Sara Della; Vuch, Josef; Tommasini, Alberto; Martelossi, Stefano; Crovella, Sergio; Bianco, Anna Monica (Gene, 2018)
Inflammatory Bowel disease (IBD) is a widespread pathological condition with clinical heterogeneity and with different levels of severity. Although IBD usually occurs in young adults, onset in childhood and infancy are described in patients within the 10th and second year of age. By genome-wide association studies and meta-analysis, several genetic loci have been identified associated with an increased risk of developing IBD in Western populations with variants that may alter the normal mucosal immunity in the gastrointestinal tract. The clinical complexity and the heterogeneity of the IBD phenotype probably reflect the presence of genetic heterogeneity where different genes or combinations of them may be involved, together with environmental factors. We hypothesized that patients with early onset IBD could have either more severe genetic variants in genes associated with IBD or multiple variants in different genes. Under the multifactorial diseases is crucial to consider the small contribution of a single variant in all not only to other small variations in the same gene but also in different genes belonging to the same pathway. We performed direct gene sequencing looking for 94 variations in NOD2, ATG16L1, IL23R, IL10R, IL10 and XIAP genes previously shown as correlated with IBD both in multifactorial and in Mendelian models. All variants identified are known in literature as being associated with IBD except for three variants in the genes NOD2, IL10 and IL10RB that even though present in online databases have never been involved in association studies on IBD patients. Moreover, we coupled genetic variants identification with an accurate "in silico" analysis to verify their predictive impact on the protein structure and function. The in-silico prediction of these variants results as benign therefore even if they exhibit a very low frequency in control population being benign, they cannot be considered pathogenic as monogenic disease but fall within the multifactorial range. The variants identified in our study partially reflect the association data described in the literature but there are no significant differences with the onset of disease (VEO vs EO-IBD).
Keywords: Age of Onset; Autophagy-Related Proteins; Child; Child, Preschool; Computer Simulation; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Inflammatory Bowel Diseases; Interleukin-10; Male; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Receptors, Interleukin; Receptors, Interleukin-10; Sequence Analysis, DNA; X-Linked Inhibitor of Apoptosis Protein

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study identifies an association between variants in EFCAB4B gene and periodontal disease in an Italian isolated population. - Bevilacqua, Lorenzo; Navarra, Chiara O; Pirastu, Nicola; Lenarda, Roberto Di; Gasparini, Paolo; Robino, Antonietta (J Periodontal Res, 2018)
BACKGROUND AND OBJECTIVE: Periodontitis in one of the most prevalent dental diseases. Despite numerous studies have investigated its aetiopathogenetic factors, few works have focused on its genetic predisposition and most of them took into account only candidate genes. Therefore, we conducted a Genome Wide Association Study in an Italian isolated population aimed at uncovering genetic variants that predispose to this disorder. METHODS: Diagnosis of chronic periodontitis was made following the criteria of the American Academy of Periodontology. Patients with chronic periodontitis were grouped into different categories: slight, severe, localized and generalized. A control group composed by people without signs of periodontitis or gingivitis was defined. DNA was genotyped using 370k Illumina chips. Linear mixed model regression was used to test the association between each single nucleotide polymorphism (SNP) (independent variable) and the periodontitis status (dependent variable), controlling for confounders sex, age and smoking. The genomic kinship matrix was also used as random effect. RESULTS: Four SNPs on the gene EFCAB4B resulted significantly associated to localized periodontitis (P < 5 × 10 ), with the best hit on the rs242016 SNP (P = 1.5 × 10 ). CONCLUSION: We have identified a novel significant association between the EFCAB4B gene and localized periodontitis. These results open a new perspective in the understanding of genetic factors contributing to this common disorder.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Calcium-Binding Proteins; Chronic Periodontitis; DNA; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Young Adult

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

A Giant Ovarian Cyst in an Adolescent. - Corrias, Francesca; Pederiva, Federica; Cozzi, Giorgio; Ammar, Lydie; Cattaruzzi, Elisabetta; Lembo, Maria Antonietta; Barbi, Egidio (J Pediatr, 2018)
Keywords: Child; Cystadenoma, Serous; Female; Humans; Ovarian Neoplasms

Girl With Chest Pain. - Scarpa, Maria-Grazia; Rabach, Ingrid; Canuto, Arianna; Sanabor, Daniela; Barbi, Egidio; Schleef, Jurgen (Ann Emerg Med, 2018)

A Girl with Delayed Puberty and Bumpy Lips. - Andrade, Stefanny; Sirchia, Fabio; Faleschini, Elena; Barbi, Egidio (J Pediatr, 2018)
Keywords: Adolescent; Exons; Female; Genes, Dominant; Humans; Lip; Multiple Endocrine Neoplasia Type 2b; Neoplasm Metastasis; Puberty, Delayed; Thyroid Neoplasms; Thyroidectomy; Tongue

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

Human beta defensin-1 is involved in the susceptibility to adeno-tonsillar hypertrophy. - Zupin, Luisa; Celsi, Fulvio; Bresciani, Martina; Orzan, Eva; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2018)
INTRODUCTION: Innate immunity molecules are known to play a pivotal role in the homeostasis of the oral mucosa, permitting the presence of commensal microflora and, at the same time, providing a first line of defense against pathogens attempting to invade the oral cavity. Tonsils represent the local immune tissue in oral cavity, being able to provide a non-specific response to pathogens; however, in the presence of microbes or foreign materials present in the mouth tonsils could became infected and develop chronic inflammation, thus leading to hypertrophy. The etiology of the disease is multifactorial depending upon environmental and host factors, the latter including molecules of mucosal innate immunity. METHODS: Ninety-five children with adeno-tonsillar hypertrophy subjected to adeno-tonsillectomy were recruited at the pediatric otorhinolaryngology service of the Institute for Maternal and Child Health IRCCS Burlo Garofolo, Trieste (Italy). The specimen discarded from the surgery were used for genomic DNA extraction and genotyping, for mRNA extraction and gene expression analysis, finally the samples were cut and used to prepare slides to perform immunohistochemistry. RESULTS: Functional polymorphisms within DEFB1 gene, encoding the human beta defensin-1 (hBD-1), were analyzed finding association between DEFB1 rare haplotypes and susceptibility to adeno-tonsillar hypertrophy. DEFB1 mRNA expression was detected in the tonsils and the hBD-1 protein was localized at the epithelia of tonsils mainly in the proximity of the basal lamina. CONCLUSION: Our findings lead us to hypothesize an involvement of hBD-1 mediated innate immunity in the modulation of the susceptibility towards adeno-tonsillar hypertrophy development.
Keywords: Adenoidectomy; Adenoids; Adolescent; beta-Defensins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Hypertrophy; Immunity, Innate; Immunohistochemistry; Italy; Male; Palatine Tonsil; Tonsillectomy

Hypomorphic FANCA mutations correlate with mild mitochondrial and clinical phenotype in Fanconi anemia. - Bottega, Roberta; Nicchia, Elena; Cappelli, Enrico; Ravera, Silvia; De Rocco, Daniela; Faleschini, Michela; Corsolini, Fabio; Pierri, Filomena; Calvillo, Michaela; Russo, Giovanna; Casazza, Gabriella; Ramenghi, Ugo; et al. (Haematologica, 2018)
Fanconi anemia is a rare disease characterized by congenital malformations, aplastic anemia, and predisposition to cancer. Despite the consolidated role of the Fanconi anemia proteins in DNA repair, their involvement in mitochondrial function is emerging. The purpose of this work was to assess whether the mitochondrial phenotype, independent of genomic integrity, could correlate with patient phenotype. We evaluated mitochondrial and clinical features of 11 affected individuals homozygous or compound heterozygous for p.His913Pro and p.Arg951Gln/Trp, the two residues of FANCA that are more frequently affected in our cohort of patients. Although p.His913Pro and p.Arg951Gln proteins are stably expressed in cytoplasm, they are unable to migrate in the nucleus, preventing cells from repairing DNA. In these cells, the electron transfer between respiring complex I-III is reduced and the ATP/AMP ratio is impaired with defective ATP production and AMP accumulation. These activities are intermediate between those observed in wild-type and FANCA-/- cells, suggesting that the variants at residues His913 and Arg951 are hypomorphic mutations. Consistent with these findings, the clinical phenotype of most of the patients carrying these mutations is mild. These data further support the recent finding that the Fanconi anemia proteins play a role in mitochondria, and open up possibilities for genotype/phenotype studies based on novel mitochondrial criteria.

Imaging and therapy of ovarian cancer: clinical application of nanoparticles and future perspectives. - Di Lorenzo, Giovanni; Ricci, Giuseppe; Severini, Giovanni Maria; Romano, Federico; Biffi, Stefania (Theranostics, 2018)
Despite significant advances in cancer diagnostics and treatment, ovarian cancers (OC) continue to kill more than 150,000 women every year worldwide. Due to the relatively asymptomatic nature and the advanced stage of the disease at the time of diagnosis, OC is the most lethal gynecologic malignancy. The current treatment for advanced OC relies on the synergistic effect of combining surgical cytoreduction and chemotherapy; however, beside the fact that chemotherapy resistance is a major challenge in OC management, new imaging strategies are needed to target microscopic lesions and improve both cytoreductive surgery and patient outcomes. In this context, nanostructured probes are emerging as a new class of medical tool that can simultaneously provide imaging contrast, target tumor cells, and carry a wide range of medicines resulting in better diagnosis and therapeutic precision. Herein we summarize several exemplary efforts in nanomedicine for addressing unmet clinical needs.

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

Impact of near infrared light in pediatric blood drawing Centre on rate of first attempt success and time of procedure. - Conversano, Ester; Cozzi, Giorgio; Pavan, Matteo; Minute, Marta; Gortan, Elena; Montico, Marcella; Vecchi Brumatti, Liza; Ronfani, Luca; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Peripheral blood access and venipuncture are a stressful and painful experience in pediatric patients; moreover, it is estimated that more than one attempt is required to achieve the procedure in about one third of children. For this reason, we investigated if Near-infrared light technology routinely used, could give an advantage to venipuncture in a pediatric blood center setting. METHODS: We conducted an open, pseudo-randomized controlled trial with two parallel arms, in the blood-drawing center, with enrolment of 115 patients between 0 and 18 years, in 14 consecutive working days. Fifty-three subjects were enrolled in group 1 (VeinViewer®) and 62 in group 2 (control group). We divided patients into three subgroups considering their age (< 5 years, 6-10 years, > 10 years). The primary study outcome was to assess if the use of VeinViewer® was associated with a reduction of time to perform blood sampling. The secondary outcome was to analyze VienViewer®'s impact on first attempt success rate in blood sampling. RESULTS: No difference was found regarding the duration of blood sampling between the two groups, even after stratifying the patients into the three age subgroups. There was no difference between the two groups in the success at the first attempt in blood sampling. CONCLUSIONS: Routine use of VeinViewer® is not useful to reduce time of the procedure during venipuncture. TRIAL REGISTRATION: The study was registered with ClinicalTrials.gov, with number NCT03277092 , on September 8, 2017.
Keywords: Adolescent; Age Factors; Child; Child, Preschool; Female; Humans; Infant; Infant, Newborn; Infrared Rays; Lighting; Male; Phlebotomy; Time Factors

Inclusion cyst of anterior fontanelle. - Udina, Chiara; Calligaris, Lorenzo; Berti, Irene; Cattaruzzi, Elisabetta; Barbi, Egidio (Arch Dis Child, 2018)

Infant Analgesia With a Combination of Breast Milk, Glucose, or Maternal Holding. - Bembich, Stefano; Cont, Gabriele; Causin, Enrica; Paviotti, Giulia; Marzari, Patrizia; Demarini, Sergio (Pediatrics, 2018)
OBJECTIVES: We studied neonatal cortical brain response to 4 types of nonpharmacological analgesia (oral glucose, expressed breast milk, maternal holding plus oral glucose, breastfeeding). We aimed to assess the differential effect of oral solutions (glucose, breast milk) given alone or combined with the maternal-infant relationship (holding, breastfeeding). METHODS: Eighty healthy term newborns undergoing a heel stick were randomly assigned to 4 parallel groups of 20 infants each: group 1, infants received a glucose solution on a changing table; group 2, infants received expressed breast milk on a changing table; group 3, infants received a glucose solution in their mothers' arms; and group 4, infants were breastfed by their mothers. Cortical activation in parietal, temporal, and frontal cortices was assessed by multichannel near-infrared spectroscopy. Pain expression was also evaluated. RESULTS: Oral glucose alone or combined with maternal holding was associated with no cortical activation during heel stick. Expressed breast milk was associated with localized bilateral activation of somatosensory and motor cortices ( < .01). Breastfeeding was associated with extensive bilateral activation of somatomotor, somatosensory, and right parietal cortices ( < .01). Pain expression was lower with the maternal-infant relationship ( = .007). CONCLUSIONS: Oral glucose, either alone or combined with maternal holding, appears to block or weaken cortical pain processing. Breast milk alone is associated with localized cortical activation. Breastfeeding is associated with extensive activation and may act by extending cortical processing. Maternal relationship, both combined with oral glucose and in breastfeeding, shows the greatest analgesic effect, although the neural patterns involved are distributed differently.

Influence of polymerization time on properties of dual-curing cements in combination with high translucency monolithic zirconia. - Alovisi, Mario; Scotti, Nicola; Comba, Allegra; Manzon, Elena; Farina, Elena; Pasqualini, Damiano; Michelotto Tempesta, Riccardo; Breschi, Lorenzo; Cadenaro, Milena (J Prosthodont Res, 2018)
PURPOSE: The aim of this in vitro study was to assess conversion degree (DC), micro-hardness (MH) and bond strength of two dual-curing resin cements employed under translucent monolithic zirconia irradiated with different time protocols. METHODS: 84 square shaped samples of 1mm thickness were prepared from high translucency zirconia blocks and divided into two groups (n=24) according to the cement employed: (1) Rely-X Ultimate; (2) Panavia SA. Each group was further divided into 3 subgroups (n=8) according to the irradiation time: (a) no light; (b) 20s; (c) 120s. Light curing was performed 60s after the sample was placed on the diamond support of a FT-IR spectrophotometer with a high power multiLED lamp. Final DC% were calculated after 10min. After 24h, Vickers Test on the cement layer was performed. The same protocol was used to lute composite cylinders in order to evaluate microshear bond-strength test. ANOVA and Bonferroni tests were performed to find differences between MH and bond-strength to zirconia, while for DC% the Scheirer-Ray-Hare two-way test was used. RESULTS: The two cements reached higher DC% in subgroup (b) and (c). As concern MH, statistics showed an increase in curing time was able to improve MH significantly. Bond-strength was not affected by irradiation time only for Panavia SA. CONCLUSIONS: The first null hypothesis has to be rejected since DC% and MH of the dual-cements tested were influenced by the curing time. The second null hypothesis is partially rejected since the bond strength was influenced by the curing time only for Rely-X Ultimate.
Keywords: Composite Resins; Dental Bonding; Dental Cements; Hardness; Lansoprazole; Materials Testing; Polymerization; Resins, Synthetic; Spectrophotometry; Time Factors; Zirconium

Intranasal dexmedetomidine, as midazolam-sparing drug, for MRI in preterm neonates. - Bua, Jenny; Massaro, Marta; Cossovel, Francesca; Monasta, Lorenzo; Brovedani, Pierpaolo; Cozzi, Giorgio; Barbi, Egidio; Demarini, Sergio; Travan, Laura (Paediatr Anaesth, 2018)

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens? - Zanella, Giada; Tornese, Gianluca; Mascheroni, Elisabetta; Faleschini, Elena; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: The simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess. CASE REPORT: We report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex characteristics, whose Klinefelter syndrome was diagnosed because of reduced testicular volume. He was the first reported case of association of KS and CAH who started androgen replacement therapy in the pubertal age and whose pubertal development was described and followed up step by step. CONCLUSION: In a boy with CAH and small testicular volume, it's important to consider that hypogonadism may be masked by the adrenal androgens excess and a karyotype should be performed once testicular adrenal rests have been ruled out.
Keywords: Adolescent; Adrenal Hyperplasia, Congenital; Androgens; Follow-Up Studies; Hormone Replacement Therapy; Humans; Klinefelter Syndrome; Male; Rare Diseases; Risk Assessment; Testis

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Learning curve for the ultrasonographic diagnosis of deep endometriosis using a structured off-line training program. - Guerriero, Stefano; Pascual, M Angela; Ajossa, Silvia; Rodriguez, Ignacio; Zajicek, Michal; Rolla, Martino; Rams, Noelia Llop; Yulzari, Vered; Bardin, Ron; Buonomo, Francesca; Comparetto, Ornella; Perniciano, Maura; et al. (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: The aim of the present study was to assess the learning curves of trainees during a structured off-line/hands-on training program on the diagnosis of deep infiltrating endometriosis (DIE). METHODS: A two-week training program was conducted. One day was devoted to theoretical issues and guided off-line analysis of 10 volumes of three-dimensional (3D) ultrasound. During the following days, five sessions of real-time sonographic examinations were performed in a DIE referral center Ultrasound unit. In between sessions, the trainees analyzed four off-line sets, containing twenty-five 3D volumes each. At the end of each set, misinterpreted volumes were assessed with the trainer. One trainer and 4 trainees (all post-graduated Ob/Gyn with at least 5 years of experience in ultrasonography in Obstetrics and Gynecology but with no experience in DIE sonographic examinations) participated in the study. Presence or absence of DIE at surgery was considered as gold standard for the trainees. Trainee's results were evaluated by learning curve cumulative summation (LC-CUSUM) and the deviations of the level of trainees' performance at the control stage by CUSUM (standard CUSUM) for different locations of DIE. RESULTS: The trainees reached competence on average after 17 evaluations (range 21-14) for bladder locations, after 39 evaluations (range 60-30) for rectosigmoid locations, after 25 evaluations (range 34-14) for forniceal locations, after 44 evaluations (range 66-25) for utero-sacral locations (USL), after 21 evaluations (range 43-14) for rectovaginal septum (RVS) locations respectively, and kept the process under control with error levels of less than 4.5% until the end of the test. The overall accuracy for each trainee at the different locations ranged from 0.91 to 0.96 for bladder DIE, from 0.80 to 0.94 for recto-sigmoid DIE, from 0.90 to 0.94% for forniceal DIE, from 0.79 to 0.82 for utero-sacral ligaments DIE and from 0.89 to 0.97 for recto-vaginal septum DIE. CONCLUSIONS: The suggested two-weeks learning program based on a mix of off-line and live sessions is feasible and suggests a good performance in training for the diagnosis of DIE. This article is protected by copyright. All rights reserved.

Levels of anxiety in parents in the 24 hr before and after their child's surgery: A descriptive study. - Pomicino, Laura; Maccacari, Elena; Buchini, Sara (J Clin Nurs, 2018)
AIMS AND OBJECTIVES: To (i) investigate pre- and postoperative anxiety levels in parents of surgical patients; (ii) identify factors that affect parental anxiety; and (iii) analyse assistance provided and overall parental satisfaction to assess whether and how this aspect can impact their anxiety level. BACKGROUND: Surgery as an event generates anxiety in children and their parents. Children who are anxious before surgery are likely to develop more postoperative psychological and physiological complications than those who are not. The role parents play in influencing emotional states of their children has been well demonstrated. However, specific national programmes aimed at helping parents develop new models for coping are relatively inexistent in Italy. STUDY DESIGN: Longitudinal study. METHODS: One hundred and one parents of children undergoing surgery at a healthcare facility in Padua, Italy, completed the Italian version of the State-Trait Anxiety Inventory Form Y questionnaire. They also answered questions about their parents' socio-demographic situation, the amount and quality of preoperative information received, assistance provided and their overall satisfaction with this information. RESULTS: The preoperative level of anxiety in parents who were interviewed was higher than Italian normative data, especially in Pediatric Cardiac Surgery and Pediatric Urology departments. Mothers had a significantly higher level of anxiety than fathers. Communicating possible complications of surgical procedures increased anxiety, while providing information about pre- and postsurgery nutrition and pain management and providing local anaesthetic on children decreased parental anxiety. Parents expressed a sufficiently high level of satisfaction although they defined the hospital environment as uncomfortable. CONCLUSIONS: Aspects of care that can make hospitalisation less traumatic for parents are as follows: greater support, involving them in the treatment process, improving hospital department admission procedures and providing thorough preoperative information. RELEVANCE TO CLINICAL PRACTICE: Healthcare professionals are encouraged to pay attention to communication modalities providing detailed information to parents.
Keywords: Adaptation, Psychological; Anxiety; Child; Female; Humans; Italy; Longitudinal Studies; Male; Parents; Perioperative Period; Surgical Procedures, Operative; Surveys and Questionnaires

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

Meconium-stained amniotic fluid: a risk factor for postpartum hemorrhage. - Bouchè, Carlo; Wiesenfeld, Uri; Ronfani, Luca; Simeone, Roberto; Bogatti, Paolo; Skerk, Kristina; Ricci, Giuseppe (Ther Clin Risk Manag, 2018)
Background/aim: Clinical data with respect to the impact of meconium on the risk of maternal hemorrhage are scarce. Therefore, in this study, we aimed to determine whether meconium-stained amniotic fluid (MSAF) represents a risk factor for postpartum hemorrhage (PPH) after vaginal delivery in a large unselected population. Patients and methods: A retrospective cohort study evaluated 78,542 consecutive women who had a vaginal delivery between 24th and 44th weeks of gestation. The women who had undergone cesarean section were excluded to avoid possible bias. Postpartum blood loss was measured with graduated blood sack. Postpartum blood loss between 1,000 and 2,000 mL and >2,000 mL were classified as moderate and severe PPH, respectively. Results: A total of 74,144 patients were available for analysis. According to the color of amniotic fluid (AF), two groups of patients were identified: MSAF (n=10,997) and clear AF (n=63,147). The rates of severe and massive PPH were found to be significantly higher in the MSAF group than that of clear AF group (OR=1.3, 95% CI: 1.2-1.5, <0.001 and OR=2.5, 95% CI: 1.5-4.2, <0.001). Operative vaginal delivery rate was found to be higher in the MSAF group than that of clear AF group, but the difference was only borderline significant (OR=1.5, 95% CI: 1.0-2.2, =0.05). There were no significant differences between the MSAF and the clear AF groups with respect to episiotomies, second- or third-degree perineal tears, vaginal-perineal thrombus, cervical lacerations, vaginal births after cesarean section, twin deliveries, and placental retention rates. Conclusion: To the best of our knowledge, this is the first clinical study that has investigated the role of MSAF as a risk factor for PPH after vaginal delivery in an unselected population. Our results suggest that MSAF is significantly associated with higher risk of moderate and severe PPH than clear AF.

Multicenter randomized, double-blind controlled trial to evaluate the efficacy of laser therapy for the treatment of severe oral mucositis induced by chemotherapy in children: laMPO RCT. - Gobbo, Margherita; Verzegnassi, Federico; Ronfani, Luca; Zanon, Davide; Melchionda, Fraia; Bagattoni, Simone; Majorana, Alessandra; Bardellini, Elena; Mura, Rosamaria; Piras, Alessandra; Petris, Maria Grazia; Mariuzzi, Maria Livia; et al. (Pediatr Blood Cancer, 2018)
OBJECTIVES: To demonstrate the efficacy of laser photobiomodulation (PBM) compared to that of placebo on severe oral mucositis (OM) in pediatric oncology patients. The primary objective was the reduction of OM grade (World Health Organization [WHO] scale) 7 days after starting PBM. Secondary objectives were reduction of pain, analgesic consumption, and incidence of side effects. METHODS: One hundred and one children with WHO grade > 2 chemotherapy-induced OM were enrolled in eight Italian hospitals. Patients were randomized to either PBM or sham treatment for four consecutive days (days +1 to +4). On days +4, +7, and +11, OM grade, pain (following a 0-10 numeric pain rating scale, NRS) and need for analgesics were evaluated by an operator blinded to treatment. RESULTS: Fifty-one patients were allocated to the PBM group, and 50 were allocated to the sham group. In total, 93.7% of PBM patients and 72% of sham patients had OM grade < 3 WHO on day +7 (P = 0.01). A significant reduction of pain was registered on day +7 in the PBM versus sham group (NRS 1 [0-3] vs. 2.5 [1-5], P < 0.006). Reduced use of analgesics was reported in the PBM group, although it was not statistically significant. No significant adverse events attributable to treatment were recorded. CONCLUSIONS: PBM is a safe, feasible, and effective treatment for children affected by chemotherapy-induced OM, as it accelerates mucosal recovery and reduces pain.

Multicentre emergency department study found that paracetamol and ibuprofen were inappropriately used in 83% and 63% of paediatric cases. - Benini, Franca; Castagno, Emanuele; Barbi, Egidio; Congedi, Sabrina; Urbino, Antonio; Biban, Paolo; Calistri, Lucia; Mancusi, Rossella Letizia (Acta Paediatr, 2018)
AIM: The Pain Practice in Italian Paediatric Emergency Departments assessed how appropriately analgesic drugs were being used by Italian clinicians, based on national paediatric pain guidelines. METHODS: This was a retrospective study that involved 17 Italian members of the Pain In Pediatric Emergency Rooms group. It comprised patients up to the age of 14 years who came to hospital emergency departments with pain and were treated with paracetamol, ibuprofen or opioids, such as codeine, tramadol and morphine. RESULTS: We studied 1471 patients who were given 1593 doses of analgesics. The median time to administration of analgesia was 25 minutes. Opioids were used in 13.5% of the children, and usage increased with age and with more severe clinical conditions, such as trauma: 1.6% of children under two years, 5.9% aged 3-10 and 8.0% aged 11-14. Inappropriate doses of paracetamol, ibuprofen and opioids were used in 83%, 63% and 33% of cases, respectively. The patient's age was a critical determinant of the correct analgesic dosage; for every one-year increase in the patient's age, the probability of appropriate prescriptions rose 14.8%. CONCLUSION: The appropriate use of paracetamol and ibuprofen for paediatric pain in Italian emergency departments was very poor, but improved with age.

Needle-related pain and distress management during needle-related procedures in children with and without intellectual disability. - Pascolo, Paola; Peri, Francesca; Montico, Marcella; Funaro, Mishelle; Parrino, Roberta; Vanadia, Francesca; Rusalen, Francesca; Vecchiato, Luca; Benini, Franca; Congedi, Sabrina; Barbi, Egidio; Cozzi, Giorgio (Eur J Pediatr, 2018)
Children with intellectual disability frequently undergo needle-related procedures for diagnosis or treatment. Nevertheless, only a few studies deal with pain and distress management during the procedure in this population of children. This study aimed to investigate the number of anxiety and pain management techniques performed during needle procedure in children with intellectual disability (cases) compared to a population of children without intellectual disability (controls). This multicenter cohort study was performed from July 2016 to January 2018 in the pediatric ward of four urban hospitals in Italy. Eligible subjects were children with and without intellectual disability, from 4 to 17 years old, who needed venipuncture or intravenous cannulation for diagnosis or treatment. Use of topical anesthesia, distraction techniques, and physical or verbal comfort during procedures were recorded. Pain and anxiety scores were also recorded. Forty-seven cases and 94 controls were recruited. Three pain- and anxiety-relieving techniques were performed during the procedure in 12 (25%) cases and in 10 controls (11%); two techniques were performed in 23 (50%) cases and in 26 (28%) controls; 12 (25%) cases and 52 (55%) controls received only one.Conclusion: In this series, children with intellectual disability received significantly more relieving techniques, but experienced more pain and anxiety when compared to children without intellectual disability. What is Known: • Children with intellectual disability experience more episodes of pain than cognitively healthy ones, and almost 10% of these episodes are due to medical procedures. What is New: • Children with intellectual disability despite receiving more relieving techniques during a needle-related procedure experienced more pain and anxiety when compared to healthy children.
Keywords: Adolescent; Anxiety; Child; Child, Preschool; Cohort Studies; Female; Humans; Intellectual Disability; Italy; Male; Pain Management; Pain Measurement; Pain, Procedural; Phlebotomy

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

Non-invasive biomarkers of fetal brain development reflecting prenatal stress: An integrative multi-scale multi-species perspective on data collection and analysis. - Frasch, Martin G; Lobmaier, Silvia M; Stampalija, Tamara; Desplats, Paula; Pallarés, María Eugenia; Pastor, Verónica; Brocco, Marcela A; Wu, Hau-Tieng; Schulkin, Jay; Herry, Christophe L; Seely, Andrew J E; Metz, Gerlinde A S; et al. (Neurosci Biobehav Rev, 2018)
Prenatal stress (PS) impacts early postnatal behavioural and cognitive development. This process of 'fetal programming' is mediated by the effects of the prenatal experience on the developing hypothalamic-pituitary-adrenal (HPA) axis and autonomic nervous system (ANS). We derive a multi-scale multi-species approach to devising preclinical and clinical studies to identify early non-invasively available pre- and postnatal biomarkers of PS. The multiple scales include brain epigenome, metabolome, microbiome and the ANS activity gauged via an array of advanced non-invasively obtainable properties of fetal heart rate fluctuations. The proposed framework has the potential to reveal mechanistic links between maternal stress during pregnancy and changes across these physiological scales. Such biomarkers may hence be useful as early and non-invasive predictors of neurodevelopmental trajectories influenced by the PS as well as follow-up indicators of success of therapeutic interventions to correct such altered neurodevelopmental trajectories. PS studies must be conducted on multiple scales derived from concerted observations in multiple animal models and human cohorts performed in an interactive and iterative manner and deploying machine learning for data synthesis, identification and validation of the best non-invasive detection and follow-up biomarkers, a prerequisite for designing effective therapeutic interventions.

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Nutrient intakes in an Italian population of infants during the complementary feeding period. - Concina, Federica; Pani, Paola; Bravo, Giulia; Barbone, Fabio; Carletti, Claudia V; Knowles, Alessandra; Ronfani, Luca; Parpinel, Maria (Public Health Nutr, 2018)
OBJECTIVE: To describe the nutrient intakes of an Italian cohort of infants at 6, 9 and 12 months of age. DESIGN: Dietary data were collected using a food diary at three follow-ups (6, 9 and 12 months of age of infants). The infants' dietary data were used to estimate nutrient intakes using the Italian food composition database integrated with data from nutritional labels and the literature. The mean and standard deviation, median and interquartile range, minimum and maximum, and 5th, 25th, 75th and 95th percentiles were calculated for the daily intake of twenty-eight nutrients, with sex differences evaluated using parametric/non-parametric statistical methods. SETTING: A prospective population-based birth cohort.SubjectInfants (n 400) living in the urban area of Trieste (Italy). RESULTS: The sex distribution was fairly balanced at each follow-up. The mean daily intakes of energy and the other twenty-seven nutrients considered were greater in males at all follow-ups. In particular, a significant statistical difference was observed in higher male consumption of cholesterol at 9 months and in energy and carbohydrate intakes at 12 months (P < 0·05). The mean daily intake of proteins was greater than that recommended by the Italian Dietary Reference Values at all follow-ups. CONCLUSIONS: These preliminary results provide a useful basis for understanding the nutrient intake patterns of infants in this area of Italy during the first year of life.

Off-label drugs use in pediatric palliative care. - De Zen, Lucia; Marchetti, Federico; Barbi, Egidio; Benini, Franca (Ital J Pediatr, 2018)
BACKGROUND: Paediatric palliative care (PPC) aim to ensure the control of symptoms and the best possible quality of life for patients whose underlying disease, characterized by an unstoppable evolution and negative prognosis, no longer responds to specific treatments. The scientific evidence in this context are very deficient and, in order to obtain welfare objectives consistent with the situation, in the overwhelming majority of cases the prescription of drugs is off-label for indication of use and/or for age and/or for way of administration and/or formulation. The Agenzia Italiana del Farmaco - AIFA and the Italian Society of Palliative Care (Società Italiana di Cure Palliative - SICP), under a dedicated working group, wrote a document that collects the scientific evidence available to support the off-label use of medicines more frequently used in PPC. The goal is to certify the consolidated off-label use of these drugs and propose their use under the Law 648/96, in the absence of data from its pivotal clinical trials. Aim of the commentary is to report the conditions for this important work and to present the 10 drugs, usually used off-label in PPC and in pain therapy, now included in Law 648/96. CONCLUSION: This work is deemed essential to resolve, at least in part, the lack of availability of medicines researched and approved.

Orthopaedic challenges for mucopolysaccharidoses. - Borgo, Andrea; Cossio, Andrea; Gallone, Denise; Vittoria, Francesca; Carbone, Marco (Ital J Pediatr, 2018)
Mucopolysaccharidoses (MPS) are a group of diseases characterized by abnormal accumulation of glycosaminoglycans (GAGs). Although there are differences among the various disease types, the osteoarticular system is always involved. The aim of the present study was to establish a framework for MPS-related orthopaedic manifestations and for their treatment. The authors, affiliated to three different Italian Orthopaedic Centres, report data taken from the literature reviewed in light of their accumulated professional experience. Bone alterations make up what is known as dysostosis multiplex, involving the trunk and limbs and with typical radiological findings. Joints are affected by pathological tissue infiltrations. The cervical spinal cord is involved, with stenosis and cervical and occipitocervical instability. In MPS there is a much higher incidence of scoliosis compared with healthy subjects without any particular distinctive feature. Kyphosis of the spine is more frequent and also more severe because of its possible neurological complications, and it is localized at the thoracolumbar level with a malformed vertebra at the top of the deformity. Evolving forms, and those associated with neurological damage, require anteroposterior spine fusion. The hip is invariably involved, with dysplasia affecting the femoral neck (coxa valga), the femoral epiphysis (loss of sphericity, osteonecrosis), and the femoral acetabulum which is flared. All these features explain the tendency to progressive hip migration. Genu valgum is often found (a deviation of the physiological axis with an obtuse angle opening laterally). This deformity is often localized at the proximal tibial metaphysis; it causes functional limitations and leads to an irregular erosion of the articular cartilage. In young patients who still have the growth plate, it is possible to execute a medial hemiepiphysiodesis, a temporary inhibition of cartilage growth, with progressive axis correction. In this paper, the characterisation of clinical features and the review of treatments are divided into separate sections based on the part of the body involved. The conclusions of each section are presented as a summary. One section discusses the high risk of anaesthesia-related complications requiring the collaboration of specifically trained personnel.
Keywords: Bone Diseases; Humans; Mucopolysaccharidoses; Orthopedic Procedures

Paediatric Home Artificial Nutrition in Italy: Report from 2016 Survey on Behalf of Artificial Nutrition Network of Italian Society for Gastroenterology, Hepatology and Nutrition (SIGENP). - Lezo, Antonella; Capriati, Teresa; Spagnuolo, Maria Immacolata; Lacitignola, Laura; Goreva, Irina; Di Leo, Grazia; Cecchi, Nicola; Gandullia, Paolo; Amarri, Sergio; Forchielli, Maria Luisa; Dipasquale, Valeria; Parma, Barbara; et al. (Nutrients, 2018)
Home Artificial Nutrition (HAN) is a safe and efficacious technique that insures children's reintegration into the family, society and school. Epidemiological data on paediatric HAN in Italy are not available. AIM: to detect the prevalence and incidence of Home Parenteral Nutrition (HPN) and Home Enteral Nutrition (HEN), either via tube or mouth, in Italy in 2016. MATERIALS AND METHODS: a specific form was sent to all registered SIGENP members and investigators of local HAN centres, inviting them to provide the requested centre's data and demographics, underlying diseases and HAN characteristics of the patients. RESULTS: we recorded 3403 Italian patients on HAN aged 0 to 19 years from 22 centres: 2277 HEN, 950 Oral Nutritional Supplements (ONS) and 179 HPN programs. The prevalence of HEN (205 pts/million inhabitants) and HPN (16 pts/million inhabitants) has dramatically increased in Italy in the last 9 years. Neurodisabling conditions were the first indication for HEN by tube or mouth while HPN is mainly requested in digestive disorders. CONCLUSIONS: HAN is a widespread and rapidly growing treatment in Italy, as well as in other European countries. Awareness of its extent and characteristics helps improving HAN service and patients' quality of life.
Keywords: Adolescent; Age Factors; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Enteral Nutrition; Female; Health Care Surveys; Home Care Services; Humans; Infant; Infant, Newborn; Italy; Male; Nutritional Status; Parenteral Nutrition, Home; Pediatrics; Time Factors; Young Adult

Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.

Pancreatic ductal adenocarcinoma can be detected by analysis of volatile organic compounds (VOCs) in alveolar air. - Princivalle, Andrea; Monasta, Lorenzo; Butturini, Giovanni; Bassi, Claudio; Perbellini, Luigi (BMC Cancer, 2018)
BACKGROUND: In the last decade many studies showed that the exhaled breath of subjects suffering from several pathological conditions has a peculiar volatile organic compound (VOC) profile. The objective of the present work was to analyse the VOCs in alveolar air to build a diagnostic tool able to identify the presence of pancreatic ductal adenocarcinoma in patients with histologically confirmed disease. METHODS: The concentration of 92 compounds was measured in the end-tidal breath of 65 cases and 102 controls. VOCs were measured with an ion-molecule reaction mass spectrometry. To distinguish between subjects with pancreatic adenocarcinomas and controls, an iterated Least Absolute Shrinkage and Selection Operator multivariate Logistic Regression model was elaborated. RESULTS: The final predictive model, based on 10 VOCs, significantly and independently associated with the outcome had a sensitivity and specificity of 100 and 84% respectively, and an area under the ROC curve of 0.99. For further validation, the model was run on 50 other subjects: 24 cases and 26 controls; 23 patients with histological diagnosis of pancreatic adenocarcinomas and 25 controls were correctly identified by the model. CONCLUSIONS: Pancreatic cancer is able to alter the concentration of some molecules in the blood and hence of VOCs in the alveolar air in equilibrium. The detection and statistical rendering of alveolar VOC composition can be useful for the clinical diagnostic approach of pancreatic neoplasms with excellent sensitivity and specificity.

Pathological Significance and Prognostic Value of Surfactant Protein D in Cancer. - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Ricci, Giuseppe; Gulino, Alessandro; Ferrara, Ines; Zanconati, Fabrizio; Tripodo, Claudio; Romano, Federico; Kishore, Uday; Bulla, Roberta (Front Immunol, 2018)
Surfactant protein D (SP-D) is a pattern recognition molecule belonging to the Collectin (collagen-containing C-type lectin) family that has pulmonary as well as extra-pulmonary existence. In the lungs, it is a well-established opsonin that can agglutinate a range of microbes, and enhance their clearance phagocytosis and super-oxidative burst. It can interfere with allergen-IgE interaction and suppress basophil and mast cell activation. However, it is now becoming evident that SP-D is likely to be an innate immune surveillance molecule against tumor development. SP-D has been shown to induce apoptosis in sensitized eosinophils derived from allergic patients and a leukemic cell line p53 pathway. Recently, SP-D has been shown to suppress lung cancer progression interference with the epidermal growth factor signaling. In addition, a truncated form of recombinant human SP-D has been reported to induce apoptosis in pancreatic adenocarcinoma Fas-mediated pathway in a p53-independent manner. To further establish a correlation between SP-D presence/levels and normal and cancer tissues, we performed a bioinformatics analysis, using Oncomine dataset and the survival analysis platforms Kaplan-Meier plotter, to assess if SP-D can serve as a potential prognostic marker for human lung cancer, in addition to human gastric, breast, and ovarian cancers. We also analyzed immunohistochemically the presence of SP-D in normal and tumor human tissues. We conclude that (1) in the lung, gastric, and breast cancers, there is a lower expression of SP-D than normal tissues; (2) in ovarian cancer, there is a higher expression of SP-D than normal tissue; and (3) in lung cancer, the presence of SP-D could be associated with a favorable prognosis. On the contrary, at non-pulmonary sites such as gastric, breast, and ovarian cancers, the presence of SP-D could be associated with unfavorable prognosis. Correlation between the levels of SP-D and overall survival requires further investigation. Our analysis involves a large number of dataset; therefore, any trend observed is reliable. Despite apparent complexity within the results, it is evident that cancer tissues that produce less levels of SP-D compared to their normal tissue counterparts are probably less susceptible to SP-D-mediated immune surveillance mechanisms infiltrating immune cells.

Photobiomodulation at Multiple Wavelengths Differentially Modulates Oxidative Stress and . - Rupel, Katia; Zupin, Luisa; Colliva, Andrea; Kamada, Anselmo; Poropat, Augusto; Ottaviani, Giulia; Gobbo, Margherita; Fanfoni, Lidia; Gratton, Rossella; Santoro, Massimo; Di Lenarda, Roberto; Biasotto, Matteo; et al. (Oxid Med Cell Longev, 2018)
Photobiomodulation (PBM) is emerging as an effective strategy for the management of multiple inflammatory conditions, including oral mucositis (OM) in cancer patients who receive chemotherapy or radiotherapy. Still, the poor understanding of the mechanisms by which the light interacts with biological tissues and the heterogeneity of light sources and protocols employed worldwide significantly limits its applicability. Reactive oxygen species (ROS) are massively generated during the early phases of OM and play a major role in the pathogenesis of inflammation in general. Here, we report the results of a clinical and experimental study, aimed at evaluating the effect of laser light at different wavelengths on oxidative stress in oncologic patients suffering from OM and in two cell types abundantly present within the inflamed oral mucosa, neutrophil polymorphonuclear (PMN) granulocytes, and keratinocytes. In addition to standard ROS detection methods, we exploited a roGFP2-Orp1 genetically encoded sensor, allowing specific, quantitative, and dynamic imaging of redox events in living cells in response to oxidative stress and PBM. We found that the various wavelengths differentially modulate ROS production. In particular, the 660 nm laser light increases ROS production when applied either before or after an oxidative stimulus. In contrast, the 970 nm laser light exerted a moderate antioxidant activity both in the saliva of OM patients and in both cell types. The most marked reduction in the levels of ROS was detected in cells exposed either to the 800 nm laser light or to the combination of the three wavelengths. Overall, our study demonstrates that PBM exerts different effects on the redox state of both PMNs and keratinocytes depending on the used wavelength and prompts the validation of a multiwavelength protocol in the clinical settings.
Keywords: Adult; Aged; Aged, 80 and over; Female; Humans; Keratinocytes; Lasers, Semiconductor; Low-Level Light Therapy; Male; Middle Aged; Neutrophils; Oxidation-Reduction; Oxidative Stress; Stomatitis

Potential use of MCR-ALS for the identification of coeliac-related biochemical changes in hyperspectral Raman maps from pediatric intestinal biopsies. - Fornasaro, Stefano; Vicario, Annalisa; De Leo, Luigina; Bonifacio, Alois; Not, Tarcisio; Sergo, Valter (Integr Biol (Camb), 2018)
Raman hyperspectral imaging is an emerging practice in biological and biomedical research for label free analysis of tissues and cells. Using this method, both spatial distribution and spectral information of analyzed samples can be obtained. The current study reports the first Raman microspectroscopic characterisation of colon tissues from patients with Coeliac Disease (CD). The aim was to assess if Raman imaging coupled with hyperspectral multivariate image analysis is capable of detecting the alterations in the biochemical composition of intestinal tissues associated with CD. The analytical approach was based on a multi-step methodology: duodenal biopsies from healthy and coeliac patients were measured and processed with Multivariate Curve Resolution Alternating Least Squares (MCR-ALS). Based on the distribution maps and the pure spectra of the image constituents obtained from MCR-ALS, interesting biochemical differences between healthy and coeliac patients has been derived. Noticeably, a reduced distribution of complex lipids in the pericryptic space, and a different distribution and abundance of proteins rich in beta-sheet structures was found in CD patients. The output of the MCR-ALS analysis was then used as a starting point for two clustering algorithms (k-means clustering and hierarchical clustering methods). Both methods converged with similar results providing precise segmentation over multiple Raman images of studied tissues.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Predictive value of the number of adverse reaction episodes for the IgE-mediated food allergy diagnosis. - Miceli Sopo, S; Gurnari, G; Monaco, S; Romano, A; Liotti, L; Cuomo, B; Dello Iacono, I; Badina, L; Longo, G; Calvani, M; Giannone, A; Calabrò, C; et al. (Allergol Immunopathol (Madr), 2018)
INTRODUCTION AND OBJECTIVES: The reproducibility of the adverse reaction increases the suggestiveness of a history of food allergy. However, the positive predictive value (PPV) of multiple adverse reaction episodes for the diagnosis of IgE-mediated food allergy is not known. This evaluation was the objective of our study. PATIENTS AND METHODS: We retrospectively studied 180 children with a history of non-anaphylactic adverse reactions after the ingestion of a food. All children had the prick test positive for the offending food and performed the oral food challenge (OFC) within 12 months after the last adverse reaction episode (ARE). We have evaluated whether increasing the number of ARE increased the probability that the OFC would be positive (failed). RESULTS: 93 patients (52%) presented one ARE, 49 (27%) presented two ARE, 24 (13%) presented three ARE, 14 (8%) patients presented≥four ARE. The OFC was positive in 94/180 (52%). The outcome of the OFC was found to be positively correlated with the number of ARE (OR=1.56; 95% CI=1.16-2.09; p=0.003). A PPV=100% was observed with a number of ARE≥five. CONCLUSIONS: The number of ARE is an important predictor of the diagnosis of food allergy, although less than we would have imagined. The number of ARE could be used to increase the predictability of the diagnostic tests currently in use, to define clinical prediction rules alternative to OFC and easy to use in clinical practice.

Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult

Red Flags in Torticollis: A Historical Cohort Study. - Starc, Meta; Norbedo, Stefania; Tubaro, Martina; Ronfani, Luca; Bassanese, Giulia; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: This study aimed to assess the spectrum of pathologies responsible for torticollis in children presenting to the emergency department and to evaluate the associated symptoms to determine clinical red flags for hospitalization. METHODS: This was a historical retrospective cohort study. Medical records of children evaluated in our emergency department for torticollis from 2008 to 2013 were reviewed. RESULTS: Among 392 identified patients, 61% had postural torticollis,19.4% infection related, 16.3% traumatic, and 3.5% other. Twenty-five patients (6.4%) were hospitalized. Four variables were strongly and independently related to the severe outcome: fever, sore throat, headache, and age. CONCLUSIONS: The association of 2 or 3 of these 4 features carried a risk of 32% and 58%, respectively, of having a severe illness.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Emergency Service, Hospital; Female; Hospitalization; Humans; Male; Retrospective Studies; Torticollis

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future. - Cattaneo, Adriano; Amani, Adidja; Charpak, Nathalie; De Leon-Mendoza, Socorro; Moxon, Sarah; Nimbalkar, Somashekhar; Tamburlini, Giorgio; Villegas, Julieta; Bergh, Anne-Marie (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Globally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and high-income settings. Nevertheless, KMC is not as widely used as it should be. The International Network on KMC runs biennial workshops and congresses to help improve the coverage and quality of KMC worldwide. This paper reports the results of the two-day workshop held in November 2016, where 92 participants from 33 countries shared experiences in a series of round tables, group work sessions and plenaries. FINDINGS: Barriers to and enablers of KMC are discussed with regard to parents, health workers and the health system. Key factors for effective implementation and uptake relate to appropriate training for health staff, adherence to protocols and the creation of a welcoming environment for families. Recommendations for planning for national programmes are made according to a six-stage change model. Resources and the cost of making progress are discussed in terms of investment, maintenance, and acceleration and scaling-up costs. KMC training requirements are presented according to three levels of care. To ensure quality KMC, key requisites are proposed for the different KMC components and for sensitive communication with caregivers. The group attending to the monitoring and evaluation of KMC at a national and subnational level highlight the lack of standard indicator definitions. Key priorities for investment include health services research, harmonisation of indicators, development of a costing tool, programming and scaling up, and the follow-up of preterm infants. CONCLUSION: It is hoped that this report will help to further scale-up and sustain KMC through a systematic approach that includes raising commitment, identifying key strategies to address the main barriers and using existing facilitators, ensuring training and quality, agreeing on indicators for monitoring and evaluation, and advancing implementation research.
Keywords: Education; Education, Nonprofessional; Female; Government Programs; Health Plan Implementation; Humans; Infant; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; International Cooperation; Kangaroo-Mother Care Method; Male

Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Teaching pain recognition through art: the Ramsay-Caravaggio sedation scale. - Poropat, Federico; Cozzi, Giorgio; Magnolato, Andrea; Monasta, Lorenzo; Borrometi, Fabio; Krauss, Baruch; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: Clinical observation is a key component of medical ability, enabling immediate evaluation of the patient's emotional state and contributing to a clinical clue that leads to final decision making. In medical schools, the art of learning to look can be taught using medical humanities and especially visual arts. By presenting a Ramsay sedation score (RSS) integrated with Caravaggio's paintings during a procedural sedation conference for pediatric residents, we want to test the effectiveness of this approach to improve the quality of learning. METHODS: In this preliminary study, we presented videos showing sedated pediatric patients in the setting of a procedural sedation lesson to two randomized groups of residents, one attending a lesson on RSS explained through the masterpieces of Caravaggio, the other without artistic support. A week later we tested their learning with ten multi-choice questions focused on theoretical questions about sedation monitoring and ten more questions focused on recognizing the appropriate RSS viewing the videos. The primary outcome was the comparison of the total number of RSS layers properly recognized in both groups. We also evaluated the appreciation of the residents of the use of works of art integrated with the lesson. RESULTS: Eleven students were randomized to each group. Two residents in the standard lesson did not attend the test. The percentage of correct answers on the theoretical part was similar, 82% in the art group and 89% in the other (p > 0.05). No difference was found in the video recognition part of the RSS recognition test. Residents exposed to paintings shown great appreciation for the integration of the lesson with the Caravaggio's masterpieces. CONCLUSIONS: Adding artwork to a standard medical conference does not improve the performance of student tests, although this approach has been greatly appreciated by residents.
Keywords: Clinical Competence; Conscious Sedation; Deep Sedation; Education, Medical, Graduate; Female; Hospitals, University; Humans; Internship and Residency; Italy; Male; Medicine in the Arts; Monitoring, Physiologic; Pain Measurement; Paintings; Pediatrics; Video Recording

Total body irradiation and iron chelation treatment are associated with pancreatic injury following pediatric hematopoietic stem cell transplantation. - Maximova, Natalia; Gregori, Massimo; Simeone, Roberto; Sonzogni, Aurelio; Zanon, Davide; Boz, Giulia; D'Antiga, Lorenzo (Oncotarget, 2018)
Whereas many studies have addressed the risk of organ dysfunction following hematopoietic stem cell transplantation (HSCT), little is known about pancreatic susceptibility in this setting. We aimed to investigate the effect of iron overload (IO) and total body irradiation (TBI) on pancreatic function of children undergoing HSCT. We retrospectively evaluated children admitted between 2012-2016 fulfilling the following criteria: normal pancreatic iron concentration (PIC), regular pancreatic function before HSCT, availability of abdominal magnetic resonance imaging with gradient-recalled-echo sequences and a full set of biochemical markers of IO and pancreatic function performed before HSCT and at discharge. We divided the patients according to the use of TBI or myeloablative chemotherapy (MCHT) in the conditioning regimen. All patients with severe IO or moderate IO with a high risk of engraftment delay or transplantation-related complications underwent chelation therapy with deferoxamine (DFO) from the first day of conditioning to discharge. 63 patients had a HSCT in the study period, 13 did not fulfill the inclusion criteria; 50 (25 in each group) are included in the analysis, and did not show differences at baseline evaluation. At follow up testing the TBI group showed a significantly higher PIC (107,8±100,3 μmol/g vs 28,4±37,9 in MCHT group, p<0,0001). In the TBI group the patients who had DFO treatment had higher PIC (223,2±48,8 μmol/g vs 55,7±10,5 without DFO treatment, p<0,0001), and all patients having PIC >100 μmol/g at follow up had DFO-based chelation therapy, versus 26% of those with lower PIC (p<0,0001). The number of patients presenting exocrine pancreatic dysfunctions one month after transplantation was significantly higher in the TBI group (48% vs 4%; p<0.0001). The mean pancreatic volume reduction was significantly greater in the TBI group (39,1% vs 0,9% in the MCHT group; p<0,05), and was significantly worse on those who received DFO therapy. Based on our data, we suggest that TBI is detrimental for pancreatic functions, and speculate that DFO may contribute to the rapid pancreatic IO observed in these patients.

A transcriptomics study of hereditary angioedema attacks. - Castellano, Giuseppe; Divella, Chiara; Sallustio, Fabio; Montinaro, Vincenzo; Curci, Claudia; Zanichelli, Andrea; Bonanni, Erika; Suffritti, Chiara; Caccia, Sonia; Bossi, Fleur; Gallone, Anna; Schena, Francesco Paolo; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Hereditary angioedema (HAE) caused by C1-inhibitor deficiency is a lifelong illness characterized by recurrent acute attacks of localized skin or mucosal edema. Activation of the kallikrein/bradykinin pathway at the endothelial cell level has a relevant pathogenetic role in acute HAE attacks. Moreover, other pathways are involved given the variable clinical expression of the disease in different patients. OBJECTIVE: We sought to explore the involvement of other putative genes in edema formation. METHODS: We performed a PBMC microarray gene expression analysis on RNA isolated from patients with HAE during an acute attack and compared them with the transcriptomic profile of the same patients in the remission phase. RESULTS: Gene expression analysis identified 23 genes significantly modulated during acute attacks that are involved primarily in the natural killer cell signaling and leukocyte extravasation signaling pathways. Gene set enrichment analysis showed a significant activation of relevant biological processes, such as response to external stimuli and protein processing (q < 0.05), suggesting involvement of PBMCs during acute HAE attacks. Upregulation of 2 genes, those encoding adrenomedullin and cellular receptor for urokinase plasminogen activator (uPAR), which occurs during an acute attack, was confirmed in PBMCs of 20 additional patients with HAE by using real-time PCR. Finally, in vitro studies demonstrated the involvement of uPAR in the generation of bradykinin and endothelial leakage. CONCLUSIONS: Our study demonstrates the increase in levels of adrenomedullin and uPAR in PBMCs during an acute HAE attack. Activation of these genes usually involved in regulation of vascular tone and in inflammatory response might have a pathogenic role by amplifying bradykinin production and edema formation in patients with HAE.

What is the quality of the maternal near-miss case reviews in WHO European Region? Cross-sectional study in Armenia, Georgia, Latvia, Republic of Moldova and Uzbekistan. - Bacci, Alberta; Hodorogea, Stelian; Khachatryan, Henrik; Babojonova, Shohida; Irsa, Signe; Jansone, Maira; Dondiuc, Iurie; Matarazde, George; Lazdane, Gunta; Lazzerini, Marzia (BMJ Open, 2018)
OBJECTIVES: The maternal near-miss case review (NMCR) cycle is a type of clinical audit aiming at improving quality of maternal healthcare by discussing near-miss cases. In several countries this approach has been introduced and supported by WHO and partners since 2004, but information on the quality of its implementation is missing. This study aimed at evaluating the quality of the NMCR implementation in selected countries within WHO European Region. DESIGN: Cross-sectional study. SETTINGS: Twenty-three maternity units in Armenia, Georgia, Latvia, Moldova and Uzbekistan. ASSESSMENT TOOLS: A predefined checklist including 50 items, according to WHO methodology. Quality in the NMCR implementation was defined by summary scores ranging from 0 (totally inappropriate) to 3 (appropriate). RESULTS: Quality of the NMCR implementation was heterogeneous among different countries, and within the same country. Overall, the first part of the audit cycle (from case identification to case analysis) was fairly well performed (mean score 2.00, 95% CI 1.94 to 2.06), with the exception of the 'inclusion of users' views' (mean score 0.66, 95% CI 0.11 to 1.22), while the second part (developing recommendations, implementing them and ensuring quality) was poorly performed (mean score 0.66, 95% CI 0.11 to 1.22). Each country had at least one champion facility, where quality of the NMCR cycle was acceptable. Quality of the implementation was not associated with its duration. Gaps in implementation were of technical, organisational and attitudinal nature. CONCLUSIONS: Ensuring quality in the NMCR may be difficult but achievable. The high heterogeneity in results within the same country suggests that quality of the NMCR implementation depends, to a large extent, from hospital factors, including staff's commitment, managerial support and local coordination. Efforts should be put in preventing and mitigating common barriers that hamper successful NMCR implementation.
Keywords: Armenia; Checklist; Cross-Sectional Studies; Female; Georgia; Humans; Latvia; Maternal Mortality; Medical Audit; Moldova; Near Miss, Healthcare; Pregnancy; Pregnancy Complications; Quality Improvement; Uzbekistan

Young Child in Respiratory Distress. - Cozzi, Giorgio; Conversano, Ester; Cattaruzzi, Elisabetta; Barbi, Egidio (Ann Emerg Med, 2018)
Keywords: Acute Disease; Child, Preschool; Female; Humans; Pulmonary Atelectasis; Radiography, Thoracic; Respiratory Insufficiency

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

Acute Abdominal Pain: Recognition and Management of Constipation in the Emergency Department. - Norbedo, Stefania; Bassanese, Giulia; Barbieri, Francesca; Barbi, Egidio (Pediatr Emerg Care, 2017)
OBJECTIVE: The main aim of the study was to investigate the incidence and the clinically relevant features of functional constipation in patients evaluated for acute abdominal pain in a tertiary care pediatric emergency department. METHODS: This is a retrospective study. We analyzed 4394 medical records and recorded the information (demographics, triage code, symptoms, medical history, physical evaluation, laboratory tests, radiological studies, procedures, and treatments) of all patients admitted for acute abdominal pain to the emergency department of the IRCCS Burlo Garofolo, Trieste, during 2010 to 2013. RESULTS: In this study, a quarter of patients (1020) presenting in the emergency department with acute abdominal pain were affected by functional constipation. Acute pain associated with functional constipation is generally rated from moderate to severe, and the location of the pain on physical evaluation was not a sufficient criterion to guide diagnosis. Isolated vomiting may be present in a minority of cases. Digital rectal exploration was never performed; the majority of patients were treated by means of an enema with prompt relief. Six percent of patients with constipation underwent radiological studies. CONCLUSIONS: This study confirms that the medical history provides a pivotal role in the diagnosis of functional constipation. Digital rectal exploration and x-rays should be avoided in this setting, whereas an enema plays a useful diagnostic and therapeutic role in our study patients.
Keywords: Abdominal Pain; Acute Pain; Adolescent; Child; Child, Preschool; Constipation; Emergency Service, Hospital; Enema; Female; Humans; Incidence; Infant; Male; Retrospective Studies

Adolescent Admissions to Emergency Departments for Self-Injurious Thoughts and Behaviors. - Zanus, Caterina; Battistutta, Sara; Aliverti, Renata; Montico, Marcella; Cremaschi, Silvana; Ronfani, Luca; Monasta, Lorenzo; Carrozzi, Marco (PLoS One, 2017)
The objective of the present study was to describe the incidence and the characteristics of Self-Injurious Thoughts and Behaviors (SITBs), among adolescents aged 11-18 admitted, over a two year period, to all the Emergency Departments of a Region of North-eastern Italy through a comprehensive analysis of medical records. A two-step search was performed in the regional ED electronic database. First, we identified the cases that had been clearly diagnosed as SITBs by an Emergency Department physician. Secondly, suspect cases were detected through a keyword search of the database, and the medical records of these cases were hand screened to identify SITBs. The mean annual incidence rate of SITBs was 90 per 100,000 adolescents aged 11-18 years. Events were more frequent in females. Drug poisoning was the most frequently adopted method (54%). In 42% of cases a diagnosis of SITB was not explicitly reported by the physician. In 65% of cases adolescents were discharged within hours of admission. Only 9% of patients started a psychiatric assessment and treatment program during hospital stay. This research confirms the high incidence of SITBs among adolescents and highlights the difficulty in their proper diagnosis and management. Such difficulty is confirmed by the fact that only a few patients, even among those with a clear diagnosis, were sent for psychiatric assessment. Correct identification and management of SITB patients needs to be improved, since SITBs are an important public health problem in adolescence and one of the main risk factors for suicide.
Keywords: Adolescent; Child; Female; Humans; Incidence; Italy; Male; Medical Records; Patient Admission; Retrospective Studies; Self-Injurious Behavior; Sex Factors; Suicidal Ideation; Suicide, Attempted

Alternative functions of the complement protein C1q at embryo implantation site. - Agostinis, Chiara; Tedesco, Francesco; Bulla, Roberta (J Reprod Immunol, 2017)
Complement component C1q is one of the recognition molecules of the complement system which can serve several functions unrelated to complement activation. This molecule is produced at foeto-maternal interface by macrophages as wells as by decidual endothelial cells and invading trophoblast. Foetal trophoblast cells migrating through the decidua in the early stages of pregnancy synthesize and express C1q on their surface, which is actively involved in promoting trophoblast endovascular and interstitial invasion of the decidua. These functions are mediated by two cell surface receptors, gC1qR and α4β1 integrin, which promote trophoblast adhesion and migration through the activation of ERK1/2 MAPKs. C1q mice manifest increased frequency of foetal resorption, reduced foetal weight, and smaller litter size when compared to their wild-type counterparts, suggesting that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia. C1q acts also as a strong angiogenic factor and promotes neovascularization. These studies suggest novel and unexpected roles of this complement component in physiological and pathological pregnancies.
Keywords: Animals; Complement C1q; Decidua; Embryo Implantation; Extracellular Signal-Regulated MAP Kinases; Female; Humans; Integrin alpha4beta1; Mice; Mice, Knockout; Neovascularization, Physiologic; Pre-Eclampsia; Pregnancy; Trophoblasts; Vascular Remodeling

ANCA-associated vasculitis in childhood: recent advances. - Calatroni, Marta; Oliva, Elena; Gianfreda, Davide; Gregorini, Gina; Allinovi, Marco; Ramirez, Giuseppe A; Bozzolo, Enrica P; Monti, Sara; Bracaglia, Claudia; Marucci, Giulia; Bodria, Monica; Sinico, Renato A; et al. (Ital J Pediatr, 2017)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides are rare systemic diseases that usually occur in adulthood. They comprise granulomatosis with polyangiitis (GPA, Wegener's), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA, Churg-Strauss syndrome). Their clinical presentation is often heterogeneous, with frequent involvement of the respiratory tract, the kidney, the skin and the joints. ANCA-associated vasculitis is rare in childhood but North-American and European cohort studies performed during the last decade have clarified their phenotype, patterns of renal involvement and their prognostic implications, and outcome. Herein, we review the main clinical and therapeutic aspects of childhood-onset ANCA-associated vasculitis, and provide preliminary data on demographic characteristics and organ manifestations of an Italian multicentre cohort.
Keywords: Age Distribution; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Child; Child, Preschool; Churg-Strauss Syndrome; Female; Granulomatosis with Polyangiitis; Humans; Incidence; Male; Microscopic Polyangiitis; Rare Diseases; Risk Assessment; Severity of Illness Index; Sex Distribution; Survival Rate

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Authors' Reply to M.S. Raghuraman: "Intranasal Dexmedetomidine for Procedural Sedation in Children, a Suitable Alternative to Chloral Hydrate". - Cozzi, Giorgio; Norbedo, Stefania; Barbi, Egidio (Paediatr Drugs, 2017)
Keywords: Administration, Intranasal; Child; Chloral Hydrate; Dexmedetomidine; Humans; Hypnotics and Sedatives; Infant

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Bipolar Disorder With Psychotic Features and Ocular Toxoplasmosis: A Possible Pathogenetic Role of the Parasite? - Del Grande, Claudia; Contini, Carlo; Schiavi, Elisa; Rutigliano, Grazia; Maritati, Martina; Seraceni, Silva; Pinto, Barbara; Dell'Osso, Liliana; Bruschi, Fabrizio (J Nerv Ment Dis, 2017)
Recent evidence suggests the involvement of Toxoplasma gondii infection in the emergence of psychotic and affective disorders. In this report, we describe the case of a young Brazilian woman affected by recurrent ocular toxoplasmosis and presenting with a manic episode with psychotic features in the context of a diagnosis of Bipolar Disorder (BD), type I. We observed a relationship between ocular manifestations and the clinical course of bipolar illness, confirmed by molecular analyses (nested-PCR), as well as by the high level of T. gondii specific IgG. This case report is the first showing the presence of circulating parasite DNA at the time of occurrence of psychiatric symptoms, thus providing further support for a possible role of the parasite in the pathogenesis of some cases of BD.
Keywords: Adult; Bipolar Disorder; Brazil; Female; Humans; Toxoplasmosis, Ocular; Young Adult

Bolus feeding has no effect on cerebral hemodynamics, irrespective of gestational age. - Bembich, Stefano; Cont, Gabriele; Bua, Jenny; Orlando, Chiara; Di Benedetto, Donatella; Demarini, Sergio (J Matern Fetal Neonatal Med, 2017)
OBJECTIVE: By multichannel near-infrared spectroscopy, we studied if gestational age has any influence on preterm cerebral hemodynamics, during bolus feeding. METHODS: Oxy-haemoglobin (HbO), as cerebral blood flow estimate, and the ratio between HbO and total haemoglobin (HbO/HbTot), as cerebral oxygenation estimate, were assessed in 40 stable premature infants, during a 10 min bolus feeding. RESULTS: We found no effect of any of the gestational ages studied (25-34 weeks) either on cerebral blood flow or on oxygenation, during a bolus feeding procedure. CONCLUSIONS: Bolus feeding appears not to affect cerebral hemodynamics of uncritically preterm infants, irrespective of gestational age.
Keywords: Cerebrovascular Circulation; Enteral Nutrition; Female; Gestational Age; Heart Rate; Humans; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Male; Oxygen; Oxyhemoglobins; Spectroscopy, Near-Infrared

A boy with fever and arthralgia. - Poropat, Federico; Pastore, Serena; Gesuete, Valentina; Barbi, Egidio (BMJ, 2017)
Keywords: Anti-Bacterial Agents; Anti-Inflammatory Agents, Non-Steroidal; Antibodies, Bacterial; Aortic Valve Insufficiency; Arthralgia; Child; Echocardiography; Echocardiography, Doppler, Color; Fever; Humans; Male; Mitral Valve Insufficiency; Rheumatic Fever; Rheumatic Heart Disease; Streptolysins

CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Children with cancer: a survey on the experience of Italian primary care pediatricians. - Minute, Marta; Cozzi, Giorgio; Plotti, Chiara; Montanari, Giuseppe; Pecile, Paolo; Zanazzo, Giulio Andrea; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2017)
BACKGROUND: Cancer is the second cause of death in children and its diagnosis can be difficult, due to the presence of vague and non-specific symptoms. The primary care pediatrician is often involved in the diagnostic process, but no longer in child care once the treatment started. Care models involving both primary care pediatricians and oncologic referral centre highlighted a higher family satisfaction when they worked together. We conducted a survey on primary care pediatricians involved in childhood cancer in order to describe the actual situation. METHODS: We conducted a retrospective survey enrolling primary care pediatricians from a north-eastern area of Italy. They received a questionnaire that consisted in two parts: the first one aimed to assess the physician's seniority and experience and the second one pertained to each case of cancer and explored the relationship between the pediatrician, the family and the referral centre, and pediatricians degree of satisfaction and emotional impact. RESULTS: We obtained data from 79 pediatricians who described 150 cancer cases. In 99 cases the primary care pediatrician had visited the child at the onset of symptoms and had referred him to the hospital. In 89 cases, he understood the severity of the disease. In 53.3% of cases the pediatrician was informed by the referral centre. The relationship between the pediatrician and child's family improved in 38% of cases and this was related with their participation to the multidisciplinary meetings on child health. CONCLUSIONS: Primary pediatricians' sharing in the management of their patients with cancer was not satisfactory. Development of specific protocols targeted to an integrated care is needed to increase primary pediatricians' involvement and families' satisfactions.
Keywords: Child; Child, Preschool; Cross-Sectional Studies; Disease-Free Survival; Female; Humans; Italy; Male; Needs Assessment; Neoplasms; Outcome Assessment (Health Care); Pediatricians; Practice Patterns, Physicians'; Prevalence; Primary Health Care; Retrospective Studies; Risk Assessment; Survival Analysis

Circulating osteoprotegerin is associated with chronic kidney disease in hypertensive patients. - Bernardi, Stella; Toffoli, Barbara; Bossi, Fleur; Candido, Riccardo; Stenner, Elisabetta; Carretta, Renzo; Barbone, Fabio; Fabris, Bruno (BMC Nephrol, 2017)
BACKGROUND: Osteoprotegerin (OPG) is a glycoprotein that plays an important regulatory role in the skeletal, vascular, and immune system. It has been shown that OPG predicts chronic kidney disease (CKD) in diabetic patients. We hypothesized that OPG could be a risk marker of CKD development also in non-diabetic hypertensive patients. METHODS: A case-control study was carried out to measure circulating OPG levels in 42 hypertensive patients with CKD and in 141 hypertensive patients without CKD. A potential relationship between OPG and the presence of CKD was investigated and a receiver-operating characteristic (ROC) curve was designed thereafter to identify a cut-off value of OPG that best explained the presence of CKD. Secondly, to evaluate whether OPG increase could affect the kidney, 18 C57BL/6J mice were randomized to be treated with saline or recombinant OPG every 3 weeks for 12 weeks. RESULTS: Circulating OPG levels were significantly higher in hypertensive patients with CKD, and there was a significant inverse association between OPG and renal function, that was independent from other variables. ROC analysis showed that OPG levels had a high statistically predictive value on CKD in hypertensive patients, which was greater than that of hypertension. The OPG best cut-off value associated with CKD was 1109.19 ng/L. In the experimental study, OPG delivery significantly increased the gene expression of pro-inflammatory and pro-fibrotic mediators, as well as the glomerular nitrosylation of proteins. CONCLUSIONS: This study shows that OPG is associated with CKD in hypertensive patients, where it might have a higher predictive value than that of hypertension for CKD development. Secondly, we found that OPG delivery significantly increased the expression of molecular pathways involved in kidney damage. Further longitudinal studies are needed not only to evaluate whether OPG predicts CKD development but also to clarify whether OPG should be considered a risk factor for CKD.
Keywords: Aged; Animals; Biomarkers; Case-Control Studies; Female; Follow-Up Studies; Humans; Hypertension; Male; Mice; Mice, Inbred C57BL; Middle Aged; Osteoprotegerin; Random Allocation; Renal Insufficiency, Chronic

[Clinical and molecular study in a family with autosomal dominant hypohidrotic ectodermal dysplasia]. - Callea, Michele; Cammarata-Scalisi, Francisco; Willoughby, Colin E; Giglio, Sabrina R; Sani, Ilaria; Bargiacchi, Sara; Traficante, Giovanna; Bellacchio, Emanuele; Tadini, Gianluca; Yavuz, Izzet; Galeotti, Angela; Clarich, Gabriella (Arch Argent Pediatr, 2017)
Hypohidrotic ectodermal dysplasia (HED) is a rare disease characterized by deficiency in development of structure derived from the ectoderm and is caused by mutations in the genes EDA, EDAR, or EDARADD. Phenotypes caused by mutations in these three may exhibit similar clinical features, explained by a common signaling pathway. Mutations in EDA gene cause X linked HED, which is the most common form. Mutations in EDAR and EDARADD genes cause autosomal dominant and recessive form of HED. The most striking clinical findings in HED are hypodontia, hypotrichosis and hypohidrosis that can lead to episodes of hyperthermia. We report on clinical findings in a child with HED with autosomal dominant inheritance pattern with a heterozygous mutation c.1072C>T (p.Arg358X) in the EDAR gene. A review of the literature with regard to other cases presenting the same mutation has been carried out and discussed.
Keywords: Child, Preschool; Ectodermal Dysplasia 1, Anhidrotic; Edar Receptor; Humans; Male; Mutation; Pedigree

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth. - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Front Immunol, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts toward the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, and has been shown to be involved in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumor by encouraging their adhesion, migration, and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of human C1q in the microenvironment of malignant pleural mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid (HA) its globular domain. C1q bound to HA was able to induce adhesion and proliferation of mesothelioma cells (MES) enhancement of ERK1/2, SAPK/JNK, and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organization of the globular domain, we demonstrated that C1q may bind to HA through ghA module, whereas it may interact with human MES through the ghC. In conclusion, C1q highly expressed in MPM binds to HA and enhances the tumor growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.

A complete duplication of X chromosome resulting in a tricentric isochromosome originated by centromere repositioning. - Villa, N; Conconi, D; Benussi, D Gambel; Tornese, G; Crosti, F; Sala, E; Dalprà, L; Pecile, V (Mol Cytogenet, 2017)
BACKGROUND: Neocentromeres are rare and considered chromosomal aberrations, because a non-centromeric region evolves in an active centromere by mutation. The literature reported several structural anomalies of X chromosome and they influence the female reproductive capacity or are associated to Turner syndrome in the presence of monosomy X cell line. CASE PRESENTATION: We report a case of chromosome X complex rearrangement found in a prenatal diagnosis. The fetal karyotype showed a mosaicism with a 45,X cell line and a 46 chromosomes second line with a big marker, instead of a sex chromosome. The marker morphology and fluorescence in situ hybridization (FISH) characterization allowed us to identify a tricentric X chromosome constituted by two complete X chromosome fused at the p arms telomere and an active neocentromere in the middle, at the union of the two Xp arms, where usually are the telomeric regions. FISH also showed the presence of a paracentric inversion of both Xp arms. Furthermore, fragility figures were found in 56% of metaphases from peripheral blood lymphocytes culture at birth: a shorter marker chromosome and an apparently acentric fragment frequently lost. CONCLUSIONS: At our knowledge, this is the first isochromosome of an entire non-acrocentric chromosome. The neocentromere is constituted by canonical sequences but localized in an unusual position and the original centromeres are inactivated. We speculated that marker chromosome was the result of a double rearrangement: firstly, a paracentric inversion which involved the Xp arm, shifting a part of the centromere at the p end and subsequently a duplication of the entire X chromosome, which gave rise to an isochromosome. It is possible to suppose that the first event could be a result of a non-allelic homologous recombination mediated by inverted low-copy repeats. As expected, our case shows a Turner phenotype with mild facial features and no major skeletal deformity, normal psychomotor development and a spontaneous development of puberty and menarche, although with irregular menses since the last follow-up.

A congenital purplish tumour. - Matarazzo, L; Delise, A; Zennaro, F; Bussani, R; Demarini, S; Berti, I; Ventura, A (Arch Dis Child Educ Pract Ed, 2017)
Keywords: Congenital Abnormalities; Humans; India; Infant; Infant, Newborn; Knee; Male; Neonatology; Neoplasms; Treatment Outcome

Cubosomes for in vivo fluorescence lifetime imaging. - Biffi, Stefania; Andolfi, Laura; Caltagirone, Claudia; Garrovo, Chiara; Falchi, Angela M; Lippolis, Vito; Lorenzon, Andrea; Macor, Paolo; Meli, Valeria; Monduzzi, Maura; Obiols-Rabasa, Marc; Petrizza, Luca; et al. (Nanotechnology, 2017)
Herein we provided the first proof of principle for in vivo fluorescence optical imaging application using monoolein-based cubosomes in a healthy mouse animal model. This formulation, administered at a non-cytotoxic concentration, was capable of providing both exogenous contrast for NIR fluorescence imaging with very high efficiency and chemospecific information upon lifetime analysis. Time-resolved measurements of fluorescence after the intravenous injection of cubosomes revealed that the dye rapidly accumulated mainly in the liver, while lifetimes profiles obtained in vivo allowed for discriminating between free dye or dye embedded within the cubosome nanostructure after injection.
Keywords: Animals; Carbocyanines; Cell Survival; Drug Compounding; Erythrocytes; Female; Fluorescent Dyes; Glycerides; Humans; Injections, Intravenous; Liposomes; Liver; Mice; Mice, Inbred BALB C; Nanoparticles; NIH 3T3 Cells; Optical Imaging; Particle Size; Spectroscopy, Near-Infrared; Time-Lapse Imaging

Curcumin Anti-Apoptotic Action in a Model of Intestinal Epithelial Inflammatory Damage. - Loganes, Claudia; Lega, Sara; Bramuzzo, Matteo; Vecchi Brumatti, Liza; Piscianz, Elisa; Valencic, Erica; Tommasini, Alberto; Marcuzzi, Annalisa (Nutrients, 2017)
The purpose of this study is to determine if a preventive treatment with curcumin can protect intestinal epithelial cells from inflammatory damage induced by IFNγ. To achieve this goal we have used a human intestinal epithelial cell line (HT29) treated with IFNγ to undergo apoptotic changes that can reproduce the damage of intestinal epithelia exposed to inflammatory cytokines. In this model, we measured the effect of curcumin (curcuminoid from ) added as a pre-treatment at different time intervals before stimulation with IFNγ. Curcumin administration to HT29 culture before the inflammatory stimulus IFNγ reduced the cell apoptosis rate. This effect gradually declined with the reduction of the curcumin pre-incubation time. This anti-apoptotic action by curcumin pre-treatment was paralleled by a reduction of secreted IL7 in the HT29 culture media, while there was no relevant change in the other cytokine levels. Even though curcumin pre-administration did not impact the activation of the NF-κB pathway, a slight effect on the phosphorylation of proteins in this inflammatory signaling pathway was observed. In conclusion, curcumin pre-treatment can protect intestinal cells from inflammatory damage. These results can be the basis for studying the preventive role of curcumin in inflammatory bowel diseases.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Apoptosis; Cell Survival; Curcuma; Curcumin; Cytokines; Epithelial Cells; HT29 Cells; Humans; Inflammation; Interferon-gamma; Interleukin-7; Intestinal Mucosa; NF-kappa B; Phosphorylation; Signal Transduction

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

DEFB1 polymorphisms and salivary hBD-1 concentration in Oral Lichen Planus patients and healthy subjects. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Pozzato, Gabriele; Ottaviani, Giulia; Gobbo, Margherita; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2017)
OBJECTIVES: The aetiology of Oral Lichen Planus (OLP), a chronic inflammatory disease of oral mucosa, is not yet well understood. Since innate immunity may be hypothesized as involved in the susceptibility to OLP, we studied human beta defensin 1 (hBD-1) an antimicrobial peptide constitutively expressed in the saliva, looking at functional genetic variants possibly able to diminish hBD-1 production an consequently conferring major susceptibility to OLP. DESIGN: We analysed three DEFB1 polymorphisms at 5' UTR, -52G>A (rs1799946), -44C>G (rs1800972), -20G>A (rs11362) and two DEFB1 polymorphisms at 3'UTR, c*5G>A (rs1047031), c*87A>G (rs1800971), with the aim of correlating these genetic variants and hBD-1 salivary level in a group of OLP patients and in healthy subjects. We also evaluated hBD-1 salivary concentrations, using ELISA, in OLP and healthy controls. RESULTS: We compared hBD-1 concentrations in OLP and healthy subjects: hBD-1 concentration was significantly higher in OLP patients respect to control. When considering the correlation between DEFB1 polymorphisms genotypes and hBD-1 expression levels, significant results were obtained for SNPs -52G>A (p=0.03 both in OLP patients and healthy individuals) and -44C>G (p=0.02 in OLP patients). CONCLUSIONS: hBD-1 production was different between OLP and healthy subjects (not age-matched with OLP). DEFB1 gene polymorphisms, -52G>A and -44C>G, correlated with hBD-1 salivary concentrations.
Keywords: 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; beta-Defensins; Female; Genetic Predisposition to Disease; Genotype; Humans; Lichen Planus, Oral; Male; Middle Aged; Polymorphism, Single Nucleotide; Saliva; Sequence Analysis, DNA

Defects in mitochondrial energetic function compels Fanconi Anaemia cells to glycolytic metabolism. - Cappelli, Enrico; Cuccarolo, Paola; Stroppiana, Giorgia; Miano, Maurizio; Bottega, Roberta; Cossu, Vanessa; Degan, Paolo; Ravera, Silvia (Biochim Biophys Acta Mol Basis Dis, 2017)
Energetic metabolism plays an essential role in the differentiation of haematopoietic stem cells (HSC). In Fanconi Anaemia (FA), DNA damage is accumulated during HSC differentiation, an event that is likely associated with bone marrow failure (BMF). One of the sources of the DNA damage is altered mitochondrial metabolism and an associated increment of oxidative stress. Recently, altered mitochondrial morphology and a deficit in the energetic activity in FA cells have been reported. Considering that mitochondria are the principal site of aerobic ATP production, we investigated FA metabolism in order to understand what pathways are able to compensate for this energy deficiency. In this work, we report that the impairment in mitochondrial oxidative phosphorylation (OXPHOS) in FA cells is countered by an increase in glycolytic flux. By contrast, glutaminolysis appears lower with respect to controls. Therefore, it is possible to conclude that in FA cells glycolysis represents the main pathway for producing energy, balancing the NADH/NAD ratio by the conversion of pyruvate to lactate. Finally, we show that a forced switch from glycolytic to OXPHOS metabolism increases FA cell oxidative stress. This could be the cause of the impoverishment in bone marrow HSC during exit from the homeostatic quiescent state. This is the first work that systematically explores FA energy metabolism, highlighting its flaws, and discusses the possible relationships between these defects and BMF.
Keywords: Cell Line; Fanconi Anemia; Glycolysis; Humans; Mitochondria; Oxidative Phosphorylation; Oxidative Stress

Describing Kawasaki shock syndrome: results from a retrospective study and literature review. - Taddio, Andrea; Rossi, Eleonora Dei; Monasta, Lorenzo; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Bronzetti, Gabriele; Marrani, Edoardo; Mottolese, Biancamaria D'Agata; Simonini, Gabriele; Cimaz, Rolando; Ventura, Alessandro (Clin Rheumatol, 2017)
Kawasaki shock syndrome (KSS) is a rare manifestation of Kawasaki disease (KD) characterized by systolic hypotension or clinical signs of poor perfusion. The objectives of the study are to describe the main clinical presentation, echocardiographic, and laboratory findings, as well as the treatment options and clinical outcomes of KSS patients when compared with KD patients. This is a retrospective study. All children referred to two pediatric rheumatology units from January 1, 2012, to December 31, 2014, were enrolled. Patients were divided into patients with or without KSS. We compared the two groups according to the following variables: sex, age, type of KD (classic, with less frequent manifestations, or incomplete), clinical manifestations, cardiac involvement, laboratory findings, therapy administered, response to treatment, and outcome. Eighty-four patients with KD were enrolled. Of these, five (6 %) met the criteria for KSS. Patients with KSS had higher values of C-reactive protein (p = 0.005), lower hemoglobin levels (p = 0.003); more frequent hyponatremia (p = 0.004), hypoalbuminemia (p = 0.004), and coagulopathy (p = 0.003); and increase in cardiac troponins (p = 0.000). Among the KSS patients, three had a coronary artery involvement, but none developed a permanent aneurysm. Intravenous immunoglobulin resistance was more frequent in the KSS group, although not significantly so (3/5, 60 % vs. 23/79, 30 %, P = NS). None of the five cases was fatal, and all recovered without sequelae. KSS patients are more likely to have higher rates of cardiac involvement. However, most cardiovascular abnormalities resolved promptly with therapy.
Keywords: C-Reactive Protein; Child; Child, Preschool; Echocardiography; Female; Heart Failure; Hemoglobins; Humans; Immunoglobulins, Intravenous; Male; Mucocutaneous Lymph Node Syndrome; Retrospective Studies; Shock; Syndrome

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Early-life nutritional exposures and lifelong health: immediate and long-lasting impacts of probiotics, vitamin D, and breastfeeding. - Berti, Cristiana; Agostoni, Carlo; Davanzo, Riccardo; Hyppönen, Elina; Isolauri, Erika; Meltzer, Helle M; Steegers-Theunissen, Régine P M; Cetin, Irene (Nutr Rev, 2017)
Pregnancy and infancy comprise the most critical stages for conditioning an individual's health, with a number of implications for subsequent risks of morbidity, mortality, and reproductive health. Nutrition may influence both the overall pregnancy outcome and the growth trajectory and immune system of the fetus and infant, with short- and long-term effects on the health of the offspring. Within this context, leading experts at Expo Milano 2015 in Milan, Italy, discussed up-to-date knowledge while providing suggestions and challenges before, during, and after pregnancy. This narrative review summarizes the key issues raised by the experts concerning the interplay between the nutritional environment from conception to early infancy and the offspring's immediate and lifelong health, with a particular focus on epigenetic mechanisms, probiotics, vitamin D, and breastfeeding. Taken together, the findings strengthen the awareness that nutritional exposures occurring from preconception to the postnatal period may be strong determinants of the offspring's health and may provide supportive evidence for current nutritional recommendations and guidelines for pregnant women and infants. Critical topics to be addressed in future research and translated into recommendations of public health relevance are also highlighted.
Keywords: Breast Feeding; Diet; Female; Humans; Infant; Infant Nutritional Physiological Phenomena; Meta-Analysis as Topic; Nutritional Status; Pregnancy; Pregnancy Outcome; Probiotics; Vitamin D

Essure Permanent Birth Control, Effectiveness and Safety: An Italian 11-Year Survey. - Franchini, Mario; Zizolfi, Brunella; Coppola, Carmela; Bergamini, Valentino; Bonin, Cecilia; Borsellino, Giovanni; Busato, Enrico; Calabrese, Stefania; Calzolari, Stefano; Fantin, Gian Piero; Giarrè, Giovanna; Litta, Piero; et al. (J Minim Invasive Gynecol, 2017)
STUDY OBJECTIVE: To describe safety, tolerability, and effectiveness results through a minimum 2-year follow-up of patients who underwent permanent sterilization with the Essure insert. DESIGN: A retrospective multicenter study (Canadian Task Force classification II2). SETTING: Seven general hospitals and 4 clinical teaching centers in Italy. PATIENTS: A total of 1968 women, mean age 39.5 years (range, 23-48 years) who underwent office hysteroscopic sterilization using the Essure insert between April 1, 2003, and December 30, 2014. INTERVENTION: The women underwent office hysteroscopic bilateral Essure insert placement, with satisfactory device location and tube occlusion based on hysterosalpingography or hysterosalpingo-contrast sonography (HyCoSy). MEASUREMENTS AND MAIN RESULTS: Placement rate, successful bilateral tubal occlusion, perioperative adverse events, early postoperative (during the first 3 months of follow-up), and late complications were evaluated. Satisfactory insertion was accomplished in 97.2% of women and, in 4, perforation and 1 expulsion were detected during hysterosalpingography. Three unintended pregnancies occurred before the 3-month confirmation test. Two pregnancies were reported among women relying on the Essure inserts. Postprocedure pain was minimal and brief; in 9 women, pelvic pain became intractable, necessitating removal of the devices via laparoscopy. On telephone interviews, overall satisfaction was rated as "very satisfied" by the majority of women (97.6%), and no long-term adverse events were reported. CONCLUSION: The findings from this extended Italian survey further support the effectiveness, tolerability, and satisfaction of Essure hysteroscopic sterilization when motivated women are selected and well informed of the potential risks of the device. Moreover, the results do not demonstrate an increased incidence of complications and pregnancies associated with long-term Essure use. Patients with a known hypersensitivity to nickel may be less suitable candidates for the Essure insert.
Keywords: Adult; Fallopian Tubes; Female; Follow-Up Studies; Humans; Hypersensitivity; Hysterosalpingography; Hysteroscopy; Italy; Laparoscopy; Middle Aged; Nickel; Pain; Pregnancy; Pregnancy, Unplanned; Retrospective Studies; Sterilization, Reproductive; Sterilization, Tubal; Surveys and Questionnaires; Young Adult

Factors Influencing the Phenotypic Characterization of the Oral Marker, PROP. - Tepper, Beverly J; Melis, Melania; Koelliker, Yvonne; Gasparini, Paolo; Ahijevych, Karen L; Tomassini Barbarossa, Iole (Nutrients, 2017)
In the last several decades, the genetic ability to taste the bitter compound, 6--propyltiouracil (PROP) has attracted considerable attention as a model for understanding individual differences in taste perception, and as an oral marker for food preferences and eating behavior that ultimately impacts nutritional status and health. However, some studies do not support this role. This review describes common factors that can influence the characterization of this phenotype including: (1) changes in taste sensitivity with increasing age; (2) gender differences in taste perception; and (3) effects of smoking and obesity. We suggest that attention to these factors during PROP screening could strengthen the associations between this phenotype and a variety of health outcomes ranging from variation in body composition to oral health and cancer risk.
Keywords: Food Preferences; Genetic Variation; Humans; Propylthiouracil; Taste Perception; Taste Threshold

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

First-time success with needle procedures was higher with a warm lidocaine and tetracaine patch than an eutectic mixture of lidocaine and prilocaine cream. - Cozzi, Giorgio; Borrometi, Fabio; Benini, Franca; Neri, Elena; Rusalen, Francesca; Celentano, Loredana; Zanon, Davide; Schreiber, Silvana; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2017)
AIM: More than 50% of children report apian during venepuncture or intravenous cannulation and using local anaesthetics before needle procedures can lead to different success rates. This study examined how many needle procedures were successful at the first attempt when children received either a warm lidocaine and tetracaine patch or an eutectic mixture of lidocaine and prilocaine (EMLA) cream. METHODS: We conducted this multicentre randomised controlled trial at three tertiary-level children's hospitals in Italy in 2015. Children aged three to 10 years were enrolled in an emergency department, paediatric day hospital and paediatric ward and randomly allocated to receive a warm lidocaine and tetracaine patch or EMLA cream. The primary outcome was the success rate at the first attempt. RESULTS: The analysis included 172 children who received a warm lidocaine and tetracaine patch and 167 who received an EMLA cream. The needle procedure was successful at the first attempt in 158 children (92.4%) who received the warm patch and in 142 children (85.0%) who received the cream (p = 0.03). The pain scores were similar in both groups. CONCLUSION: This study showed that the first-time needle procedure success was 7.4% higher in children receiving a warm lidocaine and tetracaine patch than EMLA cream.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Phlebotomy; Prilocaine; Tetracaine

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Gray platelet syndrome: Novel mutations of the NBEAL2 gene. - Bottega, Roberta; Nicchia, Elena; Alfano, Caterina; Glembotsky, Ana C; Pastore, Annalisa; Bertaggia-Calderara, Debora; Bisig, Bettina; Duchosal, Michel A; Arbesú, Guillermo; Alberio, Lorenzo; Heller, Paula G; Savoia, Anna (Am J Hematol, 2017)
Keywords: Adult; Alleles; Blood Proteins; Child; Female; Gene Expression; Gene Frequency; Genotype; Gray Platelet Syndrome; Humans; Male; Mutation; Phenotype; Platelet Aggregation; Platelet Count; Platelet Membrane Glycoproteins

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the esophageal atresia. - Chiarenza, Salvatore Fabio; Conighi, Maria Luisa; Conforti, Andrea; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Esophageal Atresia; Humans; Infant; Minimally Invasive Surgical Procedures; Video-Assisted Surgery

Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the ureteropelvic-junction obstruction. - Chiarenza, Salvatore Fabio; Bleve, Cosimo; Esposito, Ciro; Escolino, Maria; Beretta, Fabio; Cheli, Maurizio; Di Benedetto, Vincenzo; Scuderi, Maria Grazia; Casadio, Giovanni; Marzaro, Maurizio; Fascetti, Leon Francesco; Bagolan, Pietro; et al. (Pediatr Med Chir, 2017)
Not available.
Keywords: Humans; Infant; Kidney Pelvis; Minimally Invasive Surgical Procedures; Ureteral Obstruction; Video-Assisted Surgery

Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

Histoproteomic Characterization of Localized Cutaneous Amyloidosis in X-Linked Reticulate Pigmentary Disorder. - L'Imperio, Vincenzo; Bruno, Irene; Rabach, Ingrid; Smith, Andrew; Chinello, Clizia; Stella, Martina; Magni, Fulvio; Pagni, Fabio (Skin Pharmacol Physiol, 2017)
Keywords: Amyloidosis; Genetic Diseases, X-Linked; Humans; Pigmentation Disorders; Proteomics; Skin Diseases

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Clinical and Hypoxemic Childhood Pneumonia over Three Years in Central Malawi: An Observational Study. - McCollum, Eric D; Nambiar, Bejoy; Deula, Rashid; Zadutsa, Beatiwel; Bondo, Austin; King, Carina; Beard, James; Liyaya, Harry; Mankhambo, Limangeni; Lazzerini, Marzia; Makwenda, Charles; Masache, Gibson; et al. (PLoS One, 2017)
BACKGROUND: The pneumococcal conjugate vaccine's (PCV) impact on childhood pneumonia during programmatic conditions in Africa is poorly understood. Following PCV13 introduction in Malawi in November 2011, we evaluated the case burden and rates of childhood pneumonia. METHODS AND FINDINGS: Between January 1, 2012-June 30, 2014 we conducted active pneumonia surveillance in children <5 years at seven hospitals, 18 health centres, and with 38 community health workers in two districts, central Malawi. Eligible children had clinical pneumonia per Malawi guidelines, defined as fast breathing only, chest indrawing +/- fast breathing, or, ≥1 clinical danger sign. Since pulse oximetry was not in the Malawi guidelines, oxygenation <90% defined hypoxemic pneumonia, a distinct category from clinical pneumonia. We quantified the pneumonia case burden and rates in two ways. We compared the period immediately following vaccine introduction (early) to the period with >75% three-dose PCV13 coverage (post). We also used multivariable time-series regression, adjusting for autocorrelation and exploring seasonal variation and alternative model specifications in sensitivity analyses. The early versus post analysis showed an increase in cases and rates of total, fast breathing, and indrawing pneumonia and a decrease in danger sign and hypoxemic pneumonia, and pneumonia mortality. At 76% three-dose PCV13 coverage, versus 0%, the time-series model showed a non-significant increase in total cases (+47%, 95% CI: -13%, +149%, p = 0.154); fast breathing cases increased 135% (+39%, +297%, p = 0.001), however, hypoxemia fell 47% (-5%, -70%, p = 0.031) and hospital deaths decreased 36% (-1%, -58%, p = 0.047) in children <5 years. We observed a shift towards disease without danger signs, as the proportion of cases with danger signs decreased by 65% (-46%, -77%, p<0.0001). These results were generally robust to plausible alternative model specifications. CONCLUSIONS: Thirty months after PCV13 introduction in Malawi, the health system burden and rates of the severest forms of childhood pneumonia, including hypoxemia and death, have markedly decreased.
Keywords: Child; Child Mortality; Cost of Illness; Dose-Response Relationship, Immunologic; Geography; Humans; Hypoxia; Malawi; Pneumococcal Vaccines; Pneumonia, Pneumococcal; Time Factors; Vaccines, Conjugate

Impaired fasting glucose and impaired glucose tolerance in children and adolescents with overweight/obesity. - Di Bonito, P; Pacifico, L; Chiesa, C; Valerio, G; Miraglia Del Giudice, E; Maffeis, C; Morandi, A; Invitti, C; Licenziati, M R; Loche, S; Tornese, G; Franco, F; et al. (J Endocrinol Invest, 2017)
OBJECTIVE: To investigate in a large sample of overweight/obese (OW/OB) children and adolescents the prevalence of prediabetic phenotypes such as impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and to assess their association with cardiometabolic risk (CMR) factors including hepatic steatosis (HS). METHODS: Population data were obtained from the CARdiometabolic risk factors in children and adolescents in ITALY study. Between 2003 and 2013, 3088 youths (972 children and 2116 adolescents) received oral glucose tolerance test (OGTT) and were included in the study. In 798 individuals, abdominal ultrasound for identification of HS was available. RESULTS: The prevalence of IFG (3.2 vs. 3.3%) and IGT (4.6 vs. 5.0%) was similar between children and adolescents. Children with isolated IGT had a 2-11 fold increased risk of high LDL-C, non-HDL-C, Tg/HDL-C ratio, and low insulin sensitivity, when compared to those with normal glucose tolerance (NGT). No significant association of IFG with any CMR factor was found in children. Among adolescents, IGT subjects, and to a lesser extent those with IFG, showed a worse CMR profile compared to NGT subgroup. In the overall sample, IGT phenotype showed a twofold increased risk of HS compared to NGT subgroup. CONCLUSIONS: Our study shows an unexpected similar prevalence of IFG and IGT between children and adolescents with overweight/obesity. The IGT phenotype was associated with a worse CMR profile in both children and adolescents. Phenotyping prediabetes conditions by OGTT should be done as part of prediction and prevention of cardiometabolic diseases in OW/OB youth since early childhood.
Keywords: Adolescent; Blood Glucose; Case-Control Studies; Child; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin; Insulin Resistance; Italy; Male; Obesity; Overweight; Prediabetic State; Prevalence

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Intra-articular corticosteroids versus intra-articular corticosteroids plus methotrexate in oligoarticular juvenile idiopathic arthritis: a multicentre, prospective, randomised, open-label trial. - Ravelli, Angelo; Davì, Sergio; Bracciolini, Giulia; Pistorio, Angela; Consolaro, Alessandro; van Dijkhuizen, Evert Hendrik Pieter; Lattanzi, Bianca; Filocamo, Giovanni; Verazza, Sara; Gerloni, Valeria; Gattinara, Maurizio; Pontikaki, Irene; et al. (Lancet, 2017)
BACKGROUND: Little evidence-based information is available to guide the treatment of oligoarticular juvenile idiopathic arthritis. We aimed to investigate whether oral methotrexate increases the efficacy of intra-articular corticosteroid therapy. METHODS: We did this prospective, open-label, randomised trial at ten hospitals in Italy. Using a concealed computer-generated list, children younger than 18 years with oligoarticular-onset disease were randomly assigned (1:1) to intra-articular corticosteroids alone or in combination with oral methotrexate (15 mg/m; maximum 20 mg). Corticosteroids used were triamcinolone hexacetonide (shoulder, elbow, wrist, knee, and tibiotalar joints) or methylprednisolone acetate (ie, subtalar and tarsal joints). We did not mask patients or investigators to treatment assignments. Our primary outcome was the proportion of patients in the intention-to-treat population who had remission of arthritis in all injected joints at 12 months. This trial is registered with European Union Clinical Trials Register, EudraCT number 2008-006741-70. FINDINGS: Between July 7, 2009, and March 31, 2013, we screened 226 participants and randomly assigned 102 to intra-articular corticosteroids alone and 105 to intra-articular corticosteroids plus methotrexate. 33 (32%) patients assigned to intra-articular corticosteroids alone and 39 (37%) assigned to intra-articular corticosteroids and methotrexate therapy had remission of arthritis in all injected joints (p=0·48). Adverse events were recorded for 20 (17%) patients who received methotrexate, which led to permanent treatment discontinuation in two patients (one due to increased liver transaminases and one due to gastrointestinal discomfort). No patient had a serious adverse event. INTERPRETATION: Concomitant administration of methotrexate did not augment the effectiveness of intra-articular corticosteroid therapy. Future studies are needed to define the optimal therapeutic strategies for oligoarticular juvenile idiopathic arthritis. FUNDING: Italian Agency of Drug Evaluation.
Keywords: Adrenal Cortex Hormones; Arthritis, Juvenile; Humans; Injections, Intra-Articular; Italy; Methotrexate; Prospective Studies; Treatment Outcome

Intranasal Dexmedetomidine for Procedural Sedation in Children, a Suitable Alternative to Chloral Hydrate. - Cozzi, Giorgio; Norbedo, Stefania; Barbi, Egidio (Paediatr Drugs, 2017)
Sedation is often required for children undergoing diagnostic procedures. Chloral hydrate has been one of the sedative drugs most used in children over the last 3 decades, with supporting evidence for its efficacy and safety. Recently, chloral hydrate was banned in Italy and France, in consideration of evidence of its carcinogenicity and genotoxicity. Dexmedetomidine is a sedative with unique properties that has been increasingly used for procedural sedation in children. Several studies demonstrated its efficacy and safety for sedation in non-painful diagnostic procedures. Dexmedetomidine's impact on respiratory drive and airway patency and tone is much less when compared to the majority of other sedative agents. Administration via the intranasal route allows satisfactory procedural success rates. Studies that specifically compared intranasal dexmedetomidine and chloral hydrate for children undergoing non-painful procedures showed that dexmedetomidine was as effective as and safer than chloral hydrate. For these reasons, we suggest that intranasal dexmedetomidine could be a suitable alternative to chloral hydrate.
Keywords: Administration, Intranasal; Child; Chloral Hydrate; Dexmedetomidine; Humans; Hypnotics and Sedatives

Intranasal Dexmedetomidine Sedation as Adjuvant Therapy in Acute Asthma Exacerbation With Marked Anxiety and Agitation. - Cozzi, Giorgio; Lega, Sara; Giorgi, Rita; Barbi, Egidio (Ann Emerg Med, 2017)
We describe 2 patients with acute asthma exacerbation who were admitted to the emergency department (ED) with severe agitation and restlessness as a prominent finding, for which bedside asthma treatment sedation with intranasal dexmedetomidine was performed. In both cases, dexmedetomidine allowed the patients to rest and improved tolerance to treatment. Dexmedetomidine is a unique sedative with an excellent safety profile and minimal effect on respiratory function. These properties render it particularly promising for the management of severe agitation in children admitted to the ED with acute asthma exacerbation.
Keywords: Acute Disease; Administration, Intranasal; Anxiety; Asthma; Child, Preschool; Dexmedetomidine; Emergency Service, Hospital; Female; Humans; Hypnotics and Sedatives; Infant; Psychomotor Agitation

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

The Italian Society for Pediatric Nephrology (SINePe) consensus document on the management of nephrotic syndrome in children: Part I - Diagnosis and treatment of the first episode and the first relapse. - Pasini, Andrea; Benetti, Elisa; Conti, Giovanni; Ghio, Luciana; Lepore, Marta; Massella, Laura; Molino, Daniela; Peruzzi, Licia; Emma, Francesco; Fede, Carmelo; Trivelli, Antonella; Maringhini, Silvio; et al. (Ital J Pediatr, 2017)
This consensus document is aimed at providing an updated, multidisciplinary overview on the diagnosis and treatment of pediatric nephrotic syndrome (NS) at first presentation. It is the first consensus document of its kind to be produced by all the pediatric nephrology centres in Italy, in line with what is already present in other countries such as France, Germany and the USA. It is based on the current knowledge surrounding the symptomatic and steroid treatment of NS, with a view to providing the basis for a separate consensus document on the treatment of relapses. NS is one of the most common pediatric glomerular diseases, with an incidence of around 2-7 cases per 100000 children per year. Corticosteroids are the mainstay of treatment, but the optimal therapeutic regimen for managing childhood idiopathic NS is still under debate. In Italy, shared treatment guidelines were lacking and, consequently, the choice of steroid regimen was based on the clinical expertise of each individual unit. On the basis of the 2015 Cochrane systematic review, KDIGO Guidelines and more recent data from the literature, this working group, with the contribution of all the pediatric nephrology centres in Italy and on the behalf of the Italian Society of Pediatric Nephrology, has produced a shared steroid protocol that will be useful for National Health System hospitals and pediatricians. Investigations at initial presentation and the principal causes of NS to be screened are suggested. In the early phase of the disease, symptomatic treatment is also important as many severe complications can occur which are either directly related to the pathophysiology of the underlying NS or to the steroid treatment itself. To date, very few studies have been published on the prophylaxis and treatment of these early complications, while recommendations are either lacking or conflicting. This consensus provides indications for the prevention, early recognition and treatment of these complications (management of edema and hypovolemia, therapy and prophylaxis of infections and thromboembolic events). Finally, recommendations about the clinical definition of steroid resistance and its initial diagnostic management, as well as indications for renal biopsy are provided.
Keywords: Adrenal Cortex Hormones; Child; Child, Preschool; Consensus; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Humans; Italy; Male; Nephrotic Syndrome; Practice Guidelines as Topic; Prognosis; Recurrence; Retreatment; Societies, Medical; Survival Rate; Treatment Outcome

Longitudinal Responses to Weighing and Bathing Procedures in Preterm Infants. - Bembich, Stefano; Fiani, Giulia; Strajn, Tamara; Sanesi, Cecilia; Demarini, Sergio; Sanson, Gianfranco (J Perinat Neonatal Nurs, 2017)
Knowledge of the effects of nursing-induced stress on short-term outcomes in preterm infants is limited. Effects of 2 standard nursing procedures-weighing and bathing-on autonomic and motor stability of preterm infants were studied during their hospitalization. Outcomes were evaluated during and after the procedures. Eleven preterm infants were observed between 32 and 35 weeks' postmenstrual age (PMA) (postnatal days range: 4-63). Neonatal responses were assessed according to the Synactive Theory of Development and nursing was performed taking into account Newborn Individualized Developmental Care and Assessment Program (NIDCAP) principles. Effects of the studied nursing procedures on infants' stability during and after their execution were evaluated by nonparametric statistics. During monitored procedures, stress responses in autonomic and motor systems were observed at all PMAs. However, after 32 weeks' PMA, preterm infants also showed an autonomic and motor stability recovery 5 minutes after procedure completion. Contrary to our hypothesis, preterm infants showed to be stressed by weighing and bathing procedures up to 35 weeks' PMA. However, if facilitated and supported after nursing conclusion by interventions such as swaddling and nesting, according to NIDCAP principles, they recovered autonomic and motor stability by 5 minutes after ending procedures.
Keywords: Baths; Body Weight; Female; Humans; Infant Behavior; Infant Care; Infant, Newborn; Infant, Premature; Male; Neonatal Nursing

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

Long-Term Survival After Hematopoietic Stem Cell Transplantation for Complete STAT1 Deficiency. - Naviglio, Samuele; Soncini, Elena; Vairo, Donatella; Lanfranchi, Arnalda; Badolato, Raffaele; Porta, Fulvio (J Clin Immunol, 2017)
PURPOSE: Complete signal transducer and activator of transcription 1 (STAT1) deficiency is a rare autosomal recessive condition characterized by impairment of intracellular signaling from both type I and type II interferons (IFN). Affected patients are prone to early severe mycobacterial and viral infections, which usually result in death before 18 months of age. We previously reported a patient affected by complete STAT1 deficiency who underwent hematopoietic stem cell transplantation (HSCT). Here, we describe the transplantation procedures and long-term outcomes. METHODS: The patient, who had suffered multiple life-threatening mycobacterial and viral infections in the first years of life, underwent HSCT at 4 years of age from a partially matched (HLA compatibility 8/10) unrelated donor after a myeloablative conditioning regimen consisting of busulfan, cyclophosphamide, and anti-thymocyte globulin. RESULTS: Hematological reconstitution was detected at d+15, with full donor engraftment demonstrated by molecular analysis of leukocytes. Several complications occurred in the post-transplantation phase, including acute graft versus host disease, posterior reversible encephalopathy, thrombotic thrombocytopenic purpura, bilateral keratoconjunctivitis with complete loss of vision, and chronic lower limb lymphedema. Analysis of STAT1 in CD3 cells at 90 and 120 days after HSCT by flow cytometry showed normal STAT1 phosphorylation levels in response to IFN-α. CONCLUSIONS: Notably, no severe infections occurred after discharge (day + 90) during a 9-year follow-up, suggesting that normal response to IFNs in hematopoietic cells is sufficient to provide protection in humans.
Keywords: Child, Preschool; Hematopoietic Stem Cell Transplantation; Humans; Immunologic Deficiency Syndromes; Male; STAT1 Transcription Factor; Treatment Outcome

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

MCM8 and MCM9 Nucleotide Variants in Women With Primary Ovarian Insufficiency. - Desai, Swapna; Wood-Trageser, Michelle; Matic, Jelena; Chipkin, Jaqueline; Jiang, Huaiyang; Bachelot, Anne; Dulon, Jerome; Sala, Cinzia; Barbieri, Caterina; Cocca, Massimiliano; Toniolo, Daniela; Touraine, Philippe; et al. (J Clin Endocrinol Metab, 2017)
Objective: To assess the frequency of variants, including biallelic pathogenic variants, in minichromosome maintenance 8 (MCM8) and minichromosome maintenance 9 (MCM9), other genes related to MCM8-MCM9, and DNA damage repair (DDR) pathway in participants with primary ovarian insufficiency (POI). Design: MCM8, MCM9, and genes encoding DDR proteins that have been implicated in reproductive aging were sequenced among POI participants. Setting: Academic research institution. Participants: All were diagnosed with POI prior to age 40 years and presented with elevated follicle-stimulating hormone levels. Interventions: None. Main Outcome Measures: We identified nucleotide variants in MCM8, MCM9, and genes thought to be involved in the DNA damage response pathway and/or implicated in reproductive aging. Results: MCM8 was sequenced in 155 POI participants, whereas MCM9 was sequenced in 151 participants. Three of 155 (2%) participants carried possibly damaging heterozygous variants in MCM8, whereas 7 of 151 (5%) individuals carried possibly damaging heterozygous variants in MCM9. One participant carried a novel homozygous variant, c.1651C>T, p.Gln551*, in MCM9, which is predicted to introduce a premature stop codon in exon 9. Biallelic damaging heterozygous variants in both MCM8 and MCM9 were identified in 1 participant. Of a total of 10 participants carrying damaging heterozygous variants in either MCM8 or MCM9, 2 individuals carried heterozygous damaging variants in genes associated with either MCM8 or MCM9 or the DDR pathway. Conclusions: We identified a significant number of potentially damaging and novel variants in MCM8 and MCM9 among participants with POI and examined multiallelic association with variants in DDR and MCM8-MCM9 interactome genes.
Keywords: Adult; Aging; DNA Damage; DNA Repair; Female; Humans; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency; Sequence Analysis, DNA

Mental Health Problems in Children and Adolescents in the Emergency Department: "The Times They Are A-Changin'". - Cozzi, Giorgio; Minute, Marta; Ventura, Giovanna; Barbi, Egidio (Pediatr Emerg Care, 2017)
Keywords: Adolescent; Child; Emergency Service, Hospital; Humans; Mental Disorders; Mental Health Services; Patient Admission

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Is middle cerebral artery Doppler related to neonatal and 2-year infant outcome in early fetal growth restriction? - Stampalija, Tamara; Arabin, Birgit; Wolf, Hans; Bilardo, Caterina M; Lees, Christoph (Am J Obstet Gynecol, 2017)
BACKGROUND: Reduced fetal middle cerebral artery Doppler impedance is associated with hypoxemia in fetal growth restriction. It remains unclear as to whether this finding could be useful in timing delivery, especially in the third trimester. In this regard there is a paucity of evidence from prospective studies. OBJECTIVES: The aim of this study was to determine whether there is an association between middle cerebral artery Doppler impedance and its ratio with the umbilical artery in relation to neonatal and 2 year infant outcome in early fetal growth restriction (26-31 weeks of gestation). Additionally we sought to explore which ratio is more informative for clinical use. STUDY DESIGN: This is a secondary analysis from the Trial of Randomized Umbilical and Fetal Flow in Europe, a prospective, multicenter, randomized management study on different antenatal monitoring strategies (ductus venosus Doppler changes and computerized cardiotocography short-term variation) in fetal growth restriction diagnosed between 26 and 31 weeks. We analyzed women with middle cerebral artery Doppler measurement at study entry and within 1 week before delivery and with complete postnatal follow-up (374 of 503). The primary outcome was survival without neurodevelopmental impairment at 2 years corrected for prematurity. Neonatal outcome was defined as survival until first discharge home without severe neonatal morbidity. Z-scores were calculated for middle cerebral artery pulsatility index and both umbilicocerebral and cerebroplacental ratios. Odds ratios of Doppler parameter Z-scores for neonatal and 2 year infant outcome were calculated by multivariable logistic regression analysis adjusted for gestational age and birthweight p50 ratio. RESULTS: Higher middle cerebral artery pulsatility index at inclusion but not within 1 week before delivery was associated with neonatal survival without severe morbidity (odds ratio, 1.24; 95% confidence interval, 1.02-1.52). Middle cerebral artery pulsatility index Z-score and umbilicocerebral ratio Z-score at inclusion were associated with 2 year survival with normal neurodevelopmental outcome (odds ratio, 1.33; 95% confidence interval, 1.03-1.72, and odds ratio, 0.88; 95% confidence interval, 0.78-0.99, respectively) as were gestation at delivery and birthweight p50 ratio (odds ratio, 1.41; 95% confidence interval, 1.20-1.66, and odds ratio, 1.86; 95% confidence interval, 1.33-2.60, respectively). When comparing cerebroplacental ratio against umbilicocerebral ratio, the incremental range of the cerebroplacental ratio tended toward zero, whereas the umbilicocerebral ratio tended toward infinity as the values became more abnormal. CONCLUSION: In a monitoring protocol based on ductus venosus and cardiotocography in early fetal growth restriction (26-31 weeks of gestation), the impact of middle cerebral artery Doppler and its ratios on outcome is modest and less marked than birthweight and delivery gestation. It is unlikely that middle cerebral artery Doppler and its ratios are informative in optimizing the timing of delivery in fetal growth restriction before 32 weeks of gestation. The umbilicocerebral ratio allows for a better differentiation in the abnormal range than the cerebroplacental ratio.
Keywords: Birth Weight; Child Development; Child, Preschool; Delivery, Obstetric; Female; Fetal Growth Retardation; Gestational Age; Humans; Middle Cerebral Artery; Pregnancy; Prospective Studies; Pulsatile Flow; Ultrasonography, Doppler; Ultrasonography, Prenatal; Umbilical Arteries

Multicentric Case-Control Study on Azathioprine Dose and Pharmacokinetics in Early-onset Pediatric Inflammatory Bowel Disease. - Stocco, Gabriele; Martelossi, Stefano; Arrigo, Serena; Barabino, Arrigo; Aloi, Marina; Martinelli, Massimo; Miele, Erasmo; Knafelz, Daniela; Romano, Claudio; Naviglio, Samuele; Favretto, Diego; Cuzzoni, Eva; et al. (Inflamm Bowel Dis, 2017)
BACKGROUND: Early-onset inflammatory bowel disease (IBD) is generally aggressive, with a high probability of complications and need of surgery. Despite the introduction of highly effective biological drugs, treatment with azathioprine continues to be important even for early-onset IBD; however, in these patients azathioprine response seems to be reduced. This study evaluated azathioprine doses, metabolite concentrations, and their associations with patients' age in children with IBD treated at 6 tertiary pediatric referral centers. METHODS: Azathioprine doses, metabolites, and clinical effects were assessed after at least 3 months of therapy in 17 early-onset (age < 6 yr, cases) and 51 nonearly-onset (aged > 12 and <18 yrs, controls) patients with IBD. Azathioprine dose was titrated on therapeutic efficacy (response and adverse effects). Azathioprine metabolites and thiopurine methyltransferase activity were determined by high-performance liquid chromatography with ultra violet-vis detection (HPLC-UV) methods. RESULTS: Frequency of patients in remission was similar among early-onset and control groups, respectively (82% and 84%, P value = 0.72). Early-onset patients required higher doses of azathioprine (median 2.7 versus 2.0 mg·kg·d, P value = 1.1 × 10). Different doses resulted in comparable azathioprine active thioguanine nucleotide metabolite concentrations (median 263 versus 366 pmol/8 × 10 erythrocytes, P value = 0.41) and methylmercaptopurine nucleotide concentrations (median 1455 versus 1532 pmol/8 × 10 erythrocytes, P value = 0.60). Lower ratios between thioguanine nucleotide metabolites and azathioprine doses were found in early-onset patients (median 98 versus 184 pmol/8 × 10 erythrocytes·mg·kg·d, P value = 0.017). Interestingly, early-onset patients presented also higher thiopurine methyltransferase activity (median 476 versus 350 nmol methylmercaptopurine/mg hemoglobin/h, P-value = 0.046). CONCLUSIONS: This study demonstrated that patients with early-onset IBD present increased inactivating azathioprine metabolism, likely because of elevated activity of the enzyme thiopurine methyltransferase.
Keywords: Adolescent; Age of Onset; Antimetabolites; Azathioprine; Case-Control Studies; Child; Child, Preschool; Chromatography, High Pressure Liquid; Dose-Response Relationship, Drug; Erythrocytes; Female; Guanine Nucleotides; Humans; Inflammatory Bowel Diseases; Male; Mercaptopurine; Methyltransferases; Thioguanine

Mutations of RUNX1 in families with inherited thrombocytopenia. - De Rocco, Daniela; Melazzini, Federica; Marconi, Caterina; Pecci, Alessandro; Bottega, Roberta; Gnan, Chiara; Palombo, Flavia; Giordano, Paola; Coccioli, Maria Susanna; Glembotsky, Ana C; Heller, Paula G; Seri, Marco; et al. (Am J Hematol, 2017)
Keywords: Adult; Blood Platelets; Cell Size; Child; Child, Preschool; Core Binding Factor Alpha 2 Subunit; Female; Frameshift Mutation; Genes, Dominant; Heterozygote; Humans; Introns; Leukemia, Myeloid, Acute; Male; Middle Aged; Mutation, Missense; Protein Domains; RNA Splice Sites; Sequence Deletion; Thrombocythemia, Essential; Thrombopoietin; Transcriptional Activation; Young Adult

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

A Novel Panel of Serum Biomarkers for MPM Diagnosis. - Bonotti, A; Foddis, R; Landi, S; Melaiu, O; De Santi, C; Giusti, L; Donadio, E; Ciregia, F; Mazzoni, M R; Lucacchini, A; Bovenzi, M; Comar, M; et al. (Dis Markers, 2017)
Exposure to asbestos is the main cause of malignant pleural mesothelioma (MPM), a highly aggressive cancer of the pleura. Since the only tools for early detection are based on radiological tests, some authors focused on serum markers (i.e., mesothelin). The aim of this study was the evaluation of new serum biomarkers to be used individually or in combination, in order to improve the outcome of patients whose disease would be diagnosed at an earlier stage. Serum and plasma were available from 43 subjects previously exposed to asbestos and 27 MPM patients, all being epithelioid type. All the new markers found differentially expressed in MPM and healthy subjects, by proteomic and genomic approaches, have been validated in the serum by the use of specific ELISA. The combined approach, using tools of genomics and proteomics, is found to be highly innovative for this type of disease and led to the identification of new serum markers in the diagnosis of MPM. These results, if confirmed in a larger series, may have a strong impact in this area, because early detection of this cancer in people at high risk could significantly improve the course of the disease and the clinical approach to an individualized therapy.
Keywords: Aged; Biomarkers, Tumor; Blood Proteins; Case-Control Studies; Female; Humans; Lung Neoplasms; Male; Mesothelioma; Middle Aged; Proteome

Outcome of childhood-onset full-house nephropathy. - Ruggiero, Barbara; Vivarelli, Marina; Gianviti, Alessandra; Pecoraro, Carmine; Peruzzi, Licia; Benetti, Elisa; Ventura, Giovanna; Pennesi, Marco; Murer, Luisa; Coppo, Rosanna; Emma, Francesco (Nephrol Dial Transplant, 2017)
Background: Patients with full-house nephropathy (FHN) present renal lesions that are indistinguishable from those of lupus nephritis (LN) but lack the systemic features necessary to meet diagnostic criteria for systemic lupus erithematosus (SLE). Some have been reported to develop a delayed SLE with time. The clinical outcome of children having FHN without SLE has never been reported. Methods: Children with biopsy-proven FHN were selected after excluding SLE cases by the absence of America College of Rheumatology criteria. The proportion of patients with complete (proteinuria <0.5 g/day) or partial remission (proteinuria ≤50% from baseline), relapse (estimated glomerular filtration rate <25% and/or proteinuria ≥50% from baseline) and progression to Stage III chronic kidney disease (CKD) was described according to age and gender groups with the Kaplan-Meier curve and compared with the Log-rank test. Entity of treatment was summarized by a score at induction (0-6 months) and maintenance (6-18 months). Cox-regression model was performed to test predictors of remission, relapse and progression to CKD. Results: Among 42 patients (28 pre-pubertal) who met the inclusion criteria, 39 (92.9%) achieved partial and 32 (76.2%) complete remission of nephropathy over 2.78 and 7.51 months of follow-up. At 10 years, the probability of progressing to CKD was 4.8%. Of those achieving remission, 18% had a renal flare mainly within 4 years after remission. Pre-pubertal males achieved complete remission more frequently than other patients but often relapsed; pre-pubertal females were treated more aggressively. Cox-regression analysis did not find independent predictors of remission or relapse. Conclusions: The outcome of the patients with FHN we investigated was encouraging. Recurrences are limited to the first 4 years following diagnosis, allowing progressive withdrawal of immunosuppression in patients achieving remission. Evaluation of risk factors for adverse outcome is necessary especially in pre-pubertal children.
Keywords: Adolescent; Age of Onset; Child; Disease Progression; Female; Glomerular Filtration Rate; Glomerulonephritis; Humans; Kidney Diseases; Lupus Erythematosus, Systemic; Lupus Nephritis; Male; Proteinuria; Recurrence; Remission Induction; Retrospective Studies; Risk Factors; Survival Rate

Pediatric Ovarian Torsion and its Recurrence: A Multicenter Study. - Bertozzi, Mirko; Esposito, Ciro; Vella, Claudio; Briganti, Vito; Zampieri, Nicola; Codrich, Daniela; Ubertazzi, Michele; Trucchi, Alessandro; Magrini, Elisa; Battaglia, Sonia; Bini, Vittorio; Conighi, Maria Luisa; et al. (J Pediatr Adolesc Gynecol, 2017)
STUDY OBJECTIVE: To report results of a retrospective multicentric Italian survey concerning the management of pediatric ovarian torsion (OT) and its recurrence. DESIGN: Multicenter retrospective cohort study. SETTING: Italian Units of Pediatric Surgery. PARTICIPANTS: Participants were female aged 1-14 years of age with surgically diagnosed OT between 2004 and 2014. INTERVENTIONS: Adnexal detorsion, adnexectomy, mass excision using laparoscopy or laparotomy. Different kinds of oophoropexy (OPY) for OT or recurrence, respectively. MAIN OUTCOME MEASURES: A total of 124 questionnaires were returned and analyzed to understand the current management of pediatric OT and its recurrence. The questionnaires concerned patient age, presence of menarche, OT site, presence and type of mass, performed procedure, OPY technique adopted, intra- and postoperative complications, recurrence and site, procedure performed for recurrence, OPY technique for recurrence, and 1 year follow-up of detorsed ovaries. RESULTS: Mean age at surgery was 9.79 ± 3.54 years. Performed procedures were open adnexectomy (52 of 125; 41.6%), laparoscopic adnexectomy (25 of 125; 20%), open detorsion (10 of 125; 8%), and laparoscopic detorsion (38 of 125; 30.4%). Recurrence occurred in 15 of 125 cases (12%) and resulted as significant (P = .012) if associated with a normal ovary at the first episode of torsion. Recurrence occurred only in 1 of 19 cases after OPY (5.2%). Ultrasonographic results of detorsed ovaries were not significant whether an OPY was performed or not (P = 1.00). CONCLUSION: Unfortunately, oophorectomy and open technique are still widely adopted even if not advised. Recurrence is not rare and the risk is greater in patients without ovarian masses. OPY does not adversely affect ultrasonographic results at 1 year. When possible OPY should be performed at the first episode of OT.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Humans; Infant; Italy; Laparoscopy; Laparotomy; Menarche; Ovarian Diseases; Ovariectomy; Postoperative Complications; Recurrence; Retrospective Studies; Surveys and Questionnaires; Torsion Abnormality

Polymorphisms in key bone modulator cytokines genes influence bisphosphonates therapy in postmenopausal women. - Lima, C A D; Javorski, N R; Souza, A P O; Barbosa, A D; Valença, A P M C; Crovella, S; Souza, P R E; de Azevêdo Silva, J; Sandrin-Garcia, P (Inflammopharmacology, 2017)
Osteoporosis is a multifactorial and debilitating disease resulting from decreased bone mineral density (BMD) and loss of tissue microarchitecture. Ineffective therapies may lead to bone fractures and subsequent death. Single nucleotide polymorphisms (SNPs) in key immune regulator genes have been associated with therapeutic response to bisphosphonates, which are the first therapeutic line of choice for osteoporosis. However, cytokine pathways and their relation with therapeutic adhesion remain to be fully elucidated. Aimed at better understanding these processes, we investigated the response to bisphosphonate therapy in postmenopausal women and four SNPs in key proinflammatory cytokines genes: IL23R +2284 (C>A) (rs10889677), IL17A +672 (G>A) (rs7747909), IL12B +1188 (T>G) (rs3212227) and INF-γ -1616 (G>A) (rs2069705). A total of 69 patients treated with bisphosphonate were followed for a period of 1 up to 4 years, genotyped and compared according to their changes in bone mineral density (BMD) and level of biochemical markers during their treatment. The INF-γ -1616 G/G associated with increased BMD values in femoral neck (GG/AA, p = 0.016) and decreased BMD values in total hip (GG/GA, p = 0.019; GG/AA, p = 0.011). In relation to biochemical markers, INF-γ -1616 SNP associated with increased alkaline phosphatase (GG/AA; p < 0.0001) and parathyroid hormone levels (AA/GA; p = 0.017). Vitamin D values changes were related to IL17A +672 (GG/GA, p = 0.034) and to IL12B +1188 (TT/TG, p = 0.046) SNPs. Besides, significant differences in changes of calcium levels correlated with IL23R +2284 (CC/CA, p = 0.016) genotypes. Altogether, we suggest that these polymorphisms may play an important role for therapeutic decisions in osteoporosis treatment.
Keywords: Aged; Bone Density; Bone Remodeling; Cytokines; Diphosphonates; Female; Humans; Middle Aged; Osteoporosis, Postmenopausal; Polymorphism, Single Nucleotide; Postmenopause

Predictors of Relapse after Discontinuing Systemic Treatment in Childhood Autoimmune Chronic Uveitis. - Simonini, Gabriele; Bracaglia, Claudia; Cattalini, Marco; Taddio, Andrea; Brambilla, Alice; de Libero, Cinzia; Pires Marafon, Denise; Caputo, Roberto; Cimaz, Rolando (J Rheumatol, 2017)
OBJECTIVE: To identify clinical predictors of relapse in childhood autoimmune chronic uveitis after stopping systemic treatment. METHODS: A retrospective, multicenter, cohort study. RESULTS: Ninety-four children in remission, receiving no treatments and with at least a 6-month followup, were enrolled. A higher probability of maintaining remission after discontinuing treatment was shown in idiopathic compared with juvenile idiopathic arthritis uveitis (Mantel-Cox chi-square = 23.21) if inactivity had been obtained within 6 months from starting systemic treatment (Mantel-Cox chi-square = 24.17) and by antitumor necrosis factor-α treatment (Mantel-Cox chi-square = 6.43). CONCLUSION: Type of disease, time, and type of systemic therapy to achieve inactivity predict different duration of uveitis remission after treatment withdrawal.
Keywords: Adolescent; Antirheumatic Agents; Autoimmune Diseases; Child; Child, Preschool; Female; Humans; Male; Predictive Value of Tests; Recurrence; Retrospective Studies; Treatment Outcome; Uveitis; Withholding Treatment

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

Preputial reconstruction in hypospadias repair. - Castagnetti, Marco; Bagnara, Vincenzo; Rigamonti, Waifro; Cimador, Marcello; Esposito, Ciro (J Pediatr Urol, 2017)
OBJECTIVE: In principle, the prepuce can be reconstructed during hypospadias repair, but the procedure has not gained wide acceptance and preputial reconstruction (PR) is surrounded by several controversies. MATERIAL AND METHODS: A review is provided of the technique for PR, how PR combines with the other steps of hypospadias repair, the risks of complications related to the urethroplasty and specific to PR, and the results of PR with particular regard to the relevance for the patient and his family. RESULTS: PR can be important for patients requiring hypospadias repair and their parents. It can be performed in almost all patients with distal hypospadias except perhaps those with the most asymmetrical prepuces or severe ventral skin deficiency. PR does not seem to increase urethroplasty complications, but combination of PR with tubularisation of the urethral plate urethroplasty seems to offer the best chance of success. Specific complications occur in around 8% of patients and include partial or complete dehiscence of the prepuce and secondary phimosis. To prevent the latter, the reconstructed prepuce should be easily retractile at the end of surgery. Technical modifications can help to achieve this goal. Cosmetically, reconstructed prepuces are not fully normal, but the abnormality could be less important for a patient and his parents that the complete absence of the prepuce. CONCLUSION: On the basis of the evidence summarised above, an algorithm for PR in patients with distal hypospadias is proposed. PR can be offered to the vast majority of distal hypospadias patients, although some modification of the technique for hypospadias repair can be required. Retractility of the reconstructed prepuce at the end of surgery seems paramount for final success.

Presentation of acute suppurative parotitis in a newborn with incessant crying. - Velkoski, Angelika; Amoroso, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Trappan, Antonella; Travan, Laura (Arch Dis Child Fetal Neonatal Ed, 2017)
Keywords: Acute Disease; Anti-Bacterial Agents; Crying; Female; Humans; Infant, Newborn; Parotitis; Staphylococcal Infections; Staphylococcus aureus

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Retrospective study on the incidence and outcome of proven and probable invasive fungal infections in high-risk pediatric onco-hematological patients. - Cesaro, Simone; Tridello, Gloria; Castagnola, Elio; Calore, Elisabetta; Carraro, Francesca; Mariotti, Ilaria; Colombini, Antonella; Perruccio, Katia; Decembrino, Nunzia; Russo, Giovanna; Maximova, Natalia; Baretta, Valentina; et al. (Eur J Haematol, 2017)
BACKGROUND: Invasive fungal infection (IFI) is a cause of morbidity, mortality and increased health costs in children undergoing chemotherapy or hematopoietic stem cell transplant (HSCT). METHODS: Multicenter, retrospective study to assess the incidence, outcome of proven and probable IFI (PP-IFI) in children treated for acute leukemia, non-Hodgkin lymphoma or who underwent HSCT from 2006 to 2012. RESULTS: Over the 7-year period, 127 PP-IFI were diagnosed in 123 patients, median age of 9.7 years. The 1-year cumulative incidence was 2.5% (CI 1.8-3.7) after frontline chemotherapy, 9.4% (CI 5.8-15.0) after relapse, and 5.3% (CI 3.9-7.1) after HSCT. Severe neutropenia was present in 98 (77%) patients. Culture-proven agents were Candida spp., mostly non-albicans, 28, mold 23, whereas three proven IFI were identified by histopathology. Favorable response to treatment within 3 months from diagnosis was observed in 77 (89%). The overall ninety-day probability of survival was 68% (CI 59-76). CONCLUSIONS: About two-thirds of pediatric patients with PP-IFI survived, regardless of whether the infection occurred after frontline chemotherapy, reinduction chemotherapy for disease relapse, or after HSCT. Further prospective studies are needed to define the impact of antifungal prophylaxis and early combination therapy on short-term overall survival.
Keywords: Adolescent; Antifungal Agents; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Drug Therapy, Combination; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Incidence; Male; Mycoses; Patient Outcome Assessment; Retrospective Studies; Survival Analysis; Treatment Outcome

Risk of hospitalisation after early-revisit in the emergency department. - Cozzi, Giorgio; Ghirardo, Sergio; Fiorese, Ilaria; Proietti, Ilaria; Monasta, Lorenzo; Minute, Marta; Barbi, Egidio; Calligaris, Lorenzo (J Paediatr Child Health, 2017)
AIM: Early-revisits are frequent in the paediatric emergency department (ED) setting, but few data are available about early-revisited patients. The aim of this study was to investigate the hospitalisation rate of a population of early-revisited patients and to detect if an early-revisited patient was at risk of a more severe disease. METHODS: Between June 2014 and January 2015, we conducted a retrospective cohort study, considering all patients presented to the ED of a tertiary level children's hospital in Italy. We selected all patients who were revisited within 72 h from the initial visit (study cohort), while all other patients accessed in the same period were considered the control cohort. The two cohorts were compared for age, gender, triage category, hospitalisation rate, diagnosis at admission and hospital length of stay. RESULTS: In the study period, we reviewed 10 750 visits, of which 430 (4%) were unplanned revisits for the same chief complaint within 72 h from the initial visit. Hospitalisation rate of early-revisited patients was significantly higher compared to control patients (8.4 vs. 2.9%). Hospitalisation rate increases in parallel with the number of revisits, but in many cases, it was not directly related to a worst triage category, neither to a longer hospital length of stay. CONCLUSION: Early revisited patients in the ED had a significantly higher risk of hospitalisation, but this risk was only partially related to their clinical conditions.
Keywords: Adolescent; Child; Child, Preschool; Emergency Service, Hospital; Female; Hospitalization; Humans; Infant; Italy; Male; Retrospective Studies; Risk Assessment; Tertiary Care Centers; Time Factors

Safety and effectiveness of oral propranolol for infantile hemangiomas started before 5 weeks and after 5 months of age: an Italian multicenter experience. - El Hachem, Maya; Gesualdo, Francesco; Diociaiuti, Andrea; Berti, Irene; Vercellino, Nadia; Boccaletti, Valeria; Neri, Iria; Porcedda, Giulio; Greco, Antonella; Carnevale, Claudia; Oranges, Teresa; Cutrone, Mario; et al. (Ital J Pediatr, 2017)
BACKGROUND: Despite not being licensed for the treatment of infantile hemangiomas (IH) in infants younger than 5 weeks or older than 5 months, propranolol is often used in these age groups to prevent or to treat potentially severe complications. The objective of the present study was to review the experience of 8 Italian pediatric and dermatologic centers regarding propranolol treatment for IH started before 5 weeks or after 5 months of age. METHODS: We retrospectively reviewed the records of patients followed up for IH, on propranolol treatment started before 5 weeks or after 5 months of age, and collected information on sociodemographic data, treatment indications, IH involution, IH relapse, and treatment side effects. RESULTS: A total of 343 patients were enrolled; 15 were started on propranolol before 5 weeks (group 1), 328 were started after 5 months of age (group 2). The most frequent indications were permanent aesthetical disfigurement (91.8%) and function threatening complications (42.6%). In most cases, the treatment was effective. The involution was partial in 67.7% of patients. In 11.8% of cases a relapse was observed. No relapse was observed in group 1. Treatment complications were reported in 15.8% of children, most frequently sleep disorders (6.6%), followed by irritability (5.1%) and diarrhea (2.2%). Only a case of mild constipation was observed in group 1. CONCLUSION: The safety and effectiveness profile of propranolol in infants younger than 5 weeks or older than 5 months may be acceptable. Taking in account propranolol's potential in preventing severe complications, further studies should assess the acceptability of propranolol treatment, especially in the <5-week age group .
Keywords: Administration, Oral; Age Factors; Cohort Studies; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Hemangioma; Humans; Infant; Infant, Newborn; Italy; Male; Patient Safety; Propranolol; Retrospective Studies; Skin Neoplasms; Treatment Outcome

Shifts of subgingival bacterial population after nonsurgical and pharmacological therapy of localized aggressive periodontitis, followed for 1 year by Ion Torrent PGM platform. - Campisciano, Giuseppina; Toschetti, Annamaria; Comar, Manola; Taranto, Rosanna Di; Berton, Federico; Stacchi, Claudio (Eur J Dent, 2017)
The possibility of targeting the hypervariable region V3 of the 16S rRNA gene using Ion Torrent Personal Genome Machine (PGM) could provide a complete analysis of subgingival plaque samples, potentially able to identify microbiological species missed by culture-based methods. A 16-year-old female smoker patient, affected by localized aggressive periodontitis, underwent a full-mouth disinfection protocol and was inserted in a 3-month recall program. Microbiological samples were collected at baseline and at 30, 100, 365 days follow-up and analyzed by Ion Torrent PGM. , , , and were the most represented pathogens at baseline. Nonsurgical treatment and systemic antibiotics drastically lowered the anaerobic species, and their presence remained limited after 100 days, while a consistent recolonization by anaerobic bacteria was detected at 365 days. The patient showed a general improvement of periodontal conditions. Differently from polymerase chain reaction and other microarray techniques, Ion Torrent performs a quantitative analysis of the microbiota, irrespective of the searched species. An accurate definition of the shifts of the bacterial community might help periodontal researchers for a better understanding of the impact of different treatment approaches or in intercepting nonresponsive conditions.

Somatic symptom disorder was common in children and adolescents attending an emergency department complaining of pain. - Cozzi, Giorgio; Minute, Marta; Skabar, Aldo; Pirrone, Angela; Jaber, Mohamad; Neri, Elena; Montico, Marcella; Ventura, Alessandro; Barbi, Egidio (Acta Paediatr, 2017)
AIM: The aim of this study was to quantify the prevalence of somatic pain in a paediatric emergency department (ED). METHODS: We conducted a prospective observational study using patients admitted to the ED of an Italian children's hospital between December 2014 and February 2015. We enrolled children aged 7-17 who turned up at the ED complaining of pain. Patients and parents were asked to fill in a questionnaire to allow the analysis of the patients' medical history and provide contact details for follow-up. We divided the enrolled patients into four groups: post-traumatic pain, organic pain, functional pain and somatic pain. The questionnaire was used to define pain characteristics and to generate an impairment score. RESULTS: Of the 713 patients who met inclusion criteria, 306 (42.9%) were enrolled in the study. Of these, 135 (44.0%) suffered from post-traumatic pain, 104 (34.0%) from organic pain, 41 (13.4%) from functional pain and 26 (8.6%) from somatic pain. Somatic pain patients had endured pain longer, had missed more school days and had suffered severe functional impairment. CONCLUSION: This study highlighted that somatic pain was a significant contributor to paediatric emergency room visits and should be suspected and diagnosed in children reporting pain.
Keywords: Adolescent; Child; Emergency Service, Hospital; Female; Humans; Italy; Male; Medically Unexplained Symptoms; Pain; Prospective Studies

Subcutaneous Granuloma Annulare: A Diagnostic Conundrum-Learning From Mistakes. - Pederiva, Federica; Paloni, Giulia; Berti, Irene (Pediatr Emerg Care, 2017)
Subcutaneous granuloma annulare is an inflammatory lesion occurring in otherwise healthy children. We present 3 pediatric patients with different diagnostic-therapeutic paths depending on the ward they were referred to. The lesions regress spontaneously, and medical or surgical treatments are generally not necessary.
Keywords: Arm; Child, Preschool; Connective Tissue Diseases; Diagnosis, Differential; Female; Granuloma Annulare; Humans; Infant; Leg; Male; Ultrasonography, Doppler, Color

SV40 Infection of Mesenchymal Stromal Cells From Wharton's Jelly Drives the Production of Inflammatory and Tumoral Mediators. - Cason, Carolina; Campisciano, Giuseppina; Zanotta, Nunzia; Valencic, Erica; Delbue, Serena; Bella, Ramona; Comar, Manola (J Cell Physiol, 2017)
The Mesenchymal Stromal Cells from umbilical cord Wharton's jelly (WJSCs) are a source of cells with high potentiality for the treatment of human immunological disorders. Footprints of the oncogenic viruses Simian Virus 40 (SV40) and JC Virus (JCPyV) have been recently detected in human WJSCs specimens. The aim of this study is to evaluate if WJSCs can be efficiently infected by these Polyomaviruses and if they can potentially exert tumoral activity. Cell culture experiments indicated that WJSCs could sustain both SV40 and JCPyV infections. A transient and lytic replication was observed for JCPyV, while SV40 persistently infected WJSCs over a long period of time, releasing a viral progeny at low titer without evident cytopathic effect (CPE). Considering the association between SV40 and human tumors and the reported ability of the oncogenic viruses to drive the host innate immune response to cell transformation, the expression profile of a large panel of immune mediators was evaluated in supernatants by the Bioplex platform. RANTES, IL-3, MIG, and IL-12p40, involved in chronic inflammation, cells differentiation, and transformation, were constantly measured at high concentration comparing to control. These findings represent a new aspect of SV40 biological activity in the humans, highlighting its interaction with specific host cellular pathways. In view of these results, it seems to be increasingly urgent to consider Polyomaviruses in the management of WJSCs for their safely use as promising therapeutic source. J. Cell. Physiol. 232: 3060-3066, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: Cell Line, Transformed; Cell Separation; Cell Transformation, Viral; Chemokine CCL5; Chemokine CXCL9; Cytopathogenic Effect, Viral; DNA, Viral; Host-Pathogen Interactions; Humans; Inflammation Mediators; Interleukin-12 Subunit p40; Interleukin-3; JC Virus; Mesenchymal Stem Cells; Real-Time Polymerase Chain Reaction; Simian virus 40; Time Factors; Up-Regulation; Viral Load; Virus Replication; Wharton Jelly

Synthesis of Lipophilic Core-Shell FeO@SiO@Au Nanoparticles and Polymeric Entrapment into Nanomicelles: A Novel Nanosystem for in Vivo Active Targeting and Magnetic Resonance-Photoacoustic Dual Imaging. - Monaco, Ilaria; Arena, Francesca; Biffi, Stefania; Locatelli, Erica; Bortot, Barbara; La Cava, Francesca; Marini, Giada Maria; Severini, Giovanni Maria; Terreno, Enzo; Comes Franchini, Mauro (Bioconjug Chem, 2017)
In this work, iron/silica/gold core-shell nanoparticles (FeO@SiO@Au NPs) characterized by magnetic and optical properties have been synthesized to obtain a promising theranostic platform. To improve their biocompatibility, the obtained multilayer nanoparticles have been entrapped in polymeric micelles, decorated with folic acid moieties, and tested in vivo for photoacoustic and magnetic resonance imaging detection of ovarian cancer.
Keywords: Animals; Cell Proliferation; Female; Ferric Compounds; Folic Acid; Gold; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Magnetite Nanoparticles; Mice; Mice, Inbred BALB C; Mice, Nude; Micelles; Multimodal Imaging; Ovarian Neoplasms; Photoacoustic Techniques; Polymers; Silicon Dioxide; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

Targeted sequencing identifies novel variants involved in autosomal recessive hereditary hearing loss in Qatari families. - Alkowari, Moza K; Vozzi, Diego; Bhagat, Shruti; Krishnamoorthy, Navaneethakrishnan; Morgan, Anna; Hayder, Yousra; Logendra, Barathy; Najjar, Nehal; Gandin, Ilaria; Gasparini, Paolo; Badii, Ramin; Girotto, Giorgia; et al. (Mutat Res, 2017)
Hereditary hearing loss is characterized by a very high genetic heterogeneity. In the Qatari population the role of GJB2, the worldwide HHL major player, seems to be quite limited compared to Caucasian populations. In this study we analysed 18 Qatari families affected by non-syndromic hearing loss using a targeted sequencing approach that allowed us to analyse 81 genes simultaneously. Thanks to this approach, 50% of these families (9 out of 18) resulted positive for the presence of likely causative alleles in 6 different genes: CDH23, MYO6, GJB6, OTOF, TMC1 and OTOA. In particular, 4 novel alleles were detected while the remaining ones were already described to be associated to HHL in other ethnic groups. Molecular modelling has been used to further investigate the role of novel alleles identified in CDH23 and TMC1 genes demonstrating their crucial role in Ca2+ binding and therefore possible functional role in proteins. Present study showed that an accurate molecular diagnosis based on next generation sequencing technologies might largely improve molecular diagnostics outcome leading to benefits for both genetic counseling and definition of recurrence risk.
Keywords: Adolescent; Alleles; Cadherins; Child; Child, Preschool; Connexins; Female; GPI-Linked Proteins; Hearing Loss, Sensorineural; Humans; Infant; Male; Membrane Proteins; Models, Molecular; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Qatar; Sequence Analysis, DNA

A Teenager with Sudden Unilateral Breast Enlargement. - Pellegrin, Maria Chiara; Naviglio, Samuele; Cattaruzzi, Elisabetta; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2017)
Keywords: Bullying; Child; Gynecomastia; Hematoma; Humans; Male; Wounds, Nonpenetrating

Theophylline increases diaphragmatic contractility in mechanically ventilated newborns. - De Cunto, Angela; Paviotti, Giulia; Bua, Jenny; Demarini, Sergio (J Crit Care, 2017)
Keywords: Diaphragm; Humans; Infant, Newborn; Muscle Contraction; Theophylline

Thrombogenesis in Thrombophilic Pregnancy: Evaluation of Low-Molecular-Weight Heparin Prophylaxis. - Simeone, Roberto; Giacomello, Roberta; Bruno, Germano; Parco, Sergio; Maximova, Natalia; Martinelli, Monica; Zito, Gabriella; Luppi, Stefania; Cervi, Gina; Ricci, Giuseppe (Acta Haematol, 2017)
The aim of this study is to investigate thrombogenesis and the hypercoagulable changes in pregnant women affected by thrombophilia who received low-molecular-weight heparin (LWMH) prophylaxis. We included 21 pregnant women affected by thrombophilia treated with LWMH and 20 nontreated normal pregnant women as the control group. The sample group of thrombophilic pregnant women included different conditions (factor V Leiden mutation, protein C deficiency, protein S deficiency, antiphospholipid antibodies syndrome, and combined defects). Three blood samples were collected during pregnancy (i.e., at 16, 20, and 24 weeks) and tested for activated partial thromboplastin time and prothrombin fragment F1 + 2 (F1 + 2); anti-FXa activity was tested only in treated thrombophilic pregnant women. F1 + 2 levels progressively increased during pregnancy in both study groups. However, the F1 + 2 increase in women exposed to heparin prophylaxis was significantly lower than that in normal pregnant women in all 3 measurements carried out during gestation (p < 0.05); a statistically significant inverse correlation between F1 + 2 levels and anti-Xa activity (R = -0.8575, p < 0.05) was observed in treated women during pregnancy. Our findings suggest that F1 + 2 in addition to anti-Xa measurement could be used to adjust LWMH prophylaxis, at least in high-risk pregnant women.
Keywords: Adult; Anticoagulants; Case-Control Studies; Factor Xa Inhibitors; Female; Heparin, Low-Molecular-Weight; Humans; Nadroparin; Partial Thromboplastin Time; Peptide Fragments; Pilot Projects; Pregnancy; Pregnancy Complications, Hematologic; Prothrombin; Thrombophilia; Thrombosis

Towards measles elimination in Italy: Virological surveillance and genotypes trend (2013-2015). - Magurano, Fabio; Baggieri, Melissa; Filia, Antonietta; Del Manso, Martina; Lazzarotto, Tiziana; Amendola, Antonella; D'Agaro, Pierlanfranco; Chironna, Maria; Ansaldi, Filippo; Iannazzo, Stefania; Bucci, Paola; Marchi, Antonella; et al. (Virus Res, 2017)
In accordance with the goal of the World Health Organization Regional Office for Europe, the Italian National Measles and Rubella Elimination Plan aimed to interrupt indigenous measles transmission in Italy by the end of 2015. However, from 2013 to 2015, Italy experienced high measles burden with 4902 measles cases (49.3% laboratory-confirmed) reported to the enhanced measles surveillance system (cumulative incidence in the triennium reference period: 2.4/100,000 population). The measles elimination goal was not reached. Laboratory surveillance of measles circulating genotypes is performed by the Measles and Rubella National Reference Laboratory (NRL) at the Italian National Institute of Health (Istituto Superiore di Sanità - ISS), in Rome. Samples received from 1 January 2013-31 December 2015 were analysed. Those positive for measles genome by molecular tests were sequenced and phylogenetically analysed. Phylogenetic analysis performed by NRL identified that genotypes D4 and D8 were endemic and co-circulated in 2011-2013: study results show that genotype D4 disappeared during 2013. Sporadic cases were associated to genotype B3 during 2011-2013, which became endemic in Italy during 2014 and co-circulated with D8 until 2015. Sporadic cases were found belonging to genotypes D9 and H1 all over the period in exam. Similar trend has been observed in European WHO Region.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; Disease Outbreaks; Female; Genotype; Humans; Infant; Italy; Male; Measles; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny; RNA, Viral; Sentinel Surveillance; Young Adult

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Withdrawal Assessment Tool-1 Monitoring in PICU: A Multicenter Study on Iatrogenic Withdrawal Syndrome. - Amigoni, Angela; Mondardini, Maria Cristina; Vittadello, Ilaria; Zaglia, Federico; Rossetti, Emanuele; Vitale, Francesca; Ferrario, Stefania; Savron, Fabio; Coffaro, Giancarlo; Brugnaro, Luca; Amato, Roberta; Wolfler, Andrea; et al. (Pediatr Crit Care Med, 2017)
OBJECTIVES: Withdrawal syndrome is an adverse reaction of analgesic and sedative therapy, with a reported occurrence rate between 17% and 57% in critically ill children. Although some factors related to the development of withdrawal syndrome have been identified, there is weak evidence for the effectiveness of preventive and therapeutic strategies. The main aim of this study was to evaluate the frequency of withdrawal syndrome in Italian PICUs, using a validated instrument. We also analyzed differences in patient characteristics, analgesic and sedative treatment, and patients' outcome between patients with and without withdrawal syndrome. DESIGN: Observational multicenter prospective study. SETTING: Eight Italian PICUs belonging to the national PICU network Italian PICU network. PATIENTS: One hundred thirteen patients, less than 18 years old, mechanically ventilated and treated with analgesic and sedative therapy for five or more days. They were admitted in PICU from November 2012 to May 2014. INTERVENTIONS: Symptoms of withdrawal syndrome were monitored with Withdrawal Assessment Tool-1 scale. MEASUREMENTS AND MAIN RESULTS: The occurrence rate of withdrawal syndrome was 64.6%. The following variables were significantly different between the patients who developed withdrawal syndrome and those who did not: type, duration, and cumulative dose of analgesic therapy; duration and cumulative dose of sedative therapy; clinical team judgment about analgesia and sedation's difficulty; and duration of analgesic weaning, mechanical ventilation, and PICU stay. Multivariate logistic regression analysis revealed that patients receiving morphine as their primary analgesic were 83% less likely to develop withdrawal syndrome than those receiving fentanyl or remifentanil. CONCLUSIONS: Withdrawal syndrome was frequent in PICU patients, and patients with withdrawal syndrome had prolonged hospital treatment. We suggest adopting the lowest effective dose of analgesic and sedative drugs and frequent reevaluation of the need for continued use. Further studies are necessary to define common preventive and therapeutic strategies.
Keywords: Adolescent; Analgesics; Child; Child, Preschool; Critical Care; Female; Humans; Hypnotics and Sedatives; Iatrogenic Disease; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Italy; Logistic Models; Male; Prospective Studies; Respiration, Artificial; Substance Withdrawal Syndrome

Achieving early functional auditory access in paediatric cochlear implantation. - Orzan, E; Muzzi, E; Marchi, R; Falzone, C; Battelino, S; Ciciriello, E (Acta Otorhinolaryngol Ital, 2016)
Cochlear implantation (CI) is a viable option for providing access to auditory stimulation in severe-to-profound hearing loss/impairment of cochlear origin. It has been demonstrated that CI is safe and effective for deaf children. Younger age at activation after CI is linked with better outcomes. It is important to study variables and issues that can interfere with an early fitting and access to sound after CI. They range from patient characteristics, family compliance and support, to technical, medical or organisational problems. A SWOT analysis and a subsequent TOWS matrix was conducted to discuss issues and propose recommendations to be considered when operating an early switch on of the CI.

Achieving effective hearing aid fitting within one month after identification of childhood permanent hearing impairment. - Bastanza, G; Gallus, R; De Carlini, M; Picciotti, P M; Muzzi, E; Ciciriello, E; Orzan, E; Conti, G (Acta Otorhinolaryngol Ital, 2016)
Diagnosis of child permanent hearing impairment (PHI) can be made with extreme timeliness compared to the past thanks to improvements in PHI identification through newborn hearing screening programmes. It now becomes essential to provide an effective amplification as quickly as possible in order to restore auditory function and favour speech and language development. The early fitting of hearing aids and possible later cochlear implantation indeed prompts the development of central auditory pathways, connections with secondary sensory brain areas, as well as with motor and articulatory cortex. The aim of this paper is to report the results of a strategic analysis that involves identification of strengths, weaknesses, opportunities and threats regarding the process of achieving early amplification in all cases of significant childhood PHI. The analysis is focused on the Italian situation and is part of the Italian Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children".

Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

An Animal Model for the Juvenile Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis. - Marin, Veronica; Rosso, Natalia; Dal Ben, Matteo; Raseni, Alan; Boschelle, Manuela; Degrassi, Cristina; Nemeckova, Ivana; Nachtigal, Petr; Avellini, Claudio; Tiribelli, Claudio; Gazzin, Silvia (PLoS One, 2016)
Non Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH) are the hepatic manifestations of the metabolic syndrome; worrisome is the booming increase in pediatric age. To recreate the full spectrum of juvenile liver pathology and investigate the gender impact, male and female C57Bl/6 mice were fed with high fat diet plus fructose in the drinking water (HFHC) immediately after weaning (equal to 3-years old human), and disease progression followed for 16 weeks, until adults (equal to 30-years old human). 100% of subjects of both genders on HFHC diet developed steatosis in 4weeks, and some degree of fibrosis in 8weeks, with the 86% of males and 15% of females presenting a stage 2 fibrosis at 16weeks. Despite a similar final liver damage both groups, a sex difference in the pathology progression was observed. Alterations in glucose homeostasis, dyslipidemia, hepatomegaly and obese phenotype were evident from the very beginning in males with an increased hepatic inflammatory activity. Conversely, such alterations were present in females only at the end of the HFHC diet (with the exception of insulin resistance and the hepatic inflammatory state). Interestingly, only females showed an altered hepatic redox state. This juvenile model appears a good platform to unravel the underlying gender dependent mechanisms in the progression from NAFLD to NASH, and to characterize novel therapeutic approaches.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

Candidate Soluble Immune Mediators in Young Women with High-Risk Human Papillomavirus Infection: High Expression of Chemokines Promoting Angiogenesis and Cell Proliferation. - Zanotta, Nunzia; Tornesello, Maria Lina; Annunziata, Clorinda; Stellato, Giovanni; Buonaguro, Franco Maria; Comar, Manola (PLoS One, 2016)
BACKGROUND: The causal interpretation of cervical immune response to Human Papillomavirus (HPV) infection is complex and poorly characterized mainly due to the delicate balance that exists between viral infection, increase of inflammatory cytokines and host risk factors. This study aims to explore the significance of cervical immune mediators associated to cell survival, angiogenesis and interaction with immune response, in predicting the risk to develop HPV-related intraepithelial lesions. METHODS: A panel of 48 cytokines and growth factors were explored in a selected cohort of 168 immunocompetent women including 88 diagnosed with low (LSIL) or high (HSIL) squamous intraepithelial lesions of the cervix and 80 with normal cervical cytology (NIL). HPV genotyping was performed by Linear Array HPV test and the soluble concentration of 48 immune molecules was analyzed using the Bio-Plex platform. RESULTS: The prevalence of single HR-HPV infection was 30% in NIL and 100% in LSIL and HSIL women. The expression of 13 cytokines, including interleukins IL-6, IL-3, IL-12p40, IL-12p70, IL-16, IL-18, LIF, of chemokines CCL7 (MCP-3), CXCL9 (MIG), CXCL12 (SDF-1α) and of the tropic factors VEGF, G-CSF, M-CSF were significantly associated with the presence of infection, with levels being higher in women with precancerous lesions compared to NIL HPV negative women. Only the growth factor GM-CSF was positively associated with the cytological abnormalities. CONCLUSIONS: The ability of HR-HPV to escape from innate immune recognition and to orchestrate the production of specific inflammatory and growth factors, involved in early inflammatory response and in the cell-proliferating phase of intraepithelial damage, was documented in women before the development of cervical lesions.
Keywords: Adult; Cell Survival; Cervix Uteri; Chemokines; Cohort Studies; Female; Humans; Neovascularization, Pathologic; Papillomaviridae; Papillomavirus Infections

A Case of Prenatal Neurocytoma Associated With ATR-16 Syndrome. - Quadrifoglio, Mariachiara; Faletra, Flavio; Bussani, Rossana; Pecile, Vanna; Zennaro, Floriana; Grasso, Alessandra; Zandonà, Lorenzo; Alberico, Salvatore; Stampalija, Tamara (J Ultrasound Med, 2016)

Chemokines involved in the early inflammatory response and in pro-tumoral activity in asbestos-exposed workers from an Italian coastal area with territorial clusters of pleural malignant mesothelioma. - Comar, M; Zanotta, N; Zanconati, F; Cortale, M; Bonotti, A; Cristaudo, A; Bovenzi, M (Lung Cancer, 2016)
OBJECTIVES: Immune mediators are likely to be relevant for the biological response to asbestos exposure. The aim of this study was to investigate the association between immune mediators involved in inflammation, cell survival and angiogenesis, and asbestos-related diseases in workers from a coastal area of North-East Italy with a high incidence of pleural malignant mesothelioma (PMM). MATERIALS AND METHODS: A selected custom set of 12 soluble mediators was evaluated with a Luminex platform in sera, pleural fluid and mesothelioma biopsies from 123 asbestos-exposed workers (38 free from pleural-pulmonary disorders, 46 with non-malignant asbestos diseases, 39 with PMM) and in sera from 33 healthy controls from the same territorial area. RESULTS: Increased immune mediator concentrations were observed in the sera of the asbestos-exposed workers compared to controls for human fibroblast growth factor (FGF-b), vascular endothelial growth factor (VEGF), CCL5 (RANTES), CXCL10 (IP-10), CLEC11A (SCGF-b), CCL27 (CTACK), CCL11 (EOTAXIN), IL-5 and IL-6 (p<0.001). The chemokines IP-10 and RANTES were associated with the severity of asbestos-related diseases. In the workers with PMM, the immune proteins secreted by mesothelioma biopsies showed detectable levels of RANTES, VEGF, and IP-10. In the same workers with PMM, a significant relationship between serum and pleural fluid concentrations was found for RANTES alone. CONCLUSIONS: Occupational exposure to asbestos seems to drive the production of specific growth factors dually involved in the early inflammatory response and in pro-tumoral activity before clinical evidence of related disorders, suggesting that their over-expression may precede the onset of asbestos-related diseases. These findings suggest that some chemokines may have a prognostic role in the progression of asbestos-related diseases and could be used for the health surveillance of either workers with an occupational history of asbestos exposure or patients affected by non-malignant asbestos-related diseases.

Chemokines SNPs in HIV-1+ Patients and Healthy Controls from Northeast Brazil: Association with Protection against HIV-1 Infection. - Celerino da Silva, Ronaldo; Victor Campos Coelho, Antonio; Cláudio Arraes, Luiz; André Cavalcanti Brandão, Lucas; Lima Guimarães, Rafael; Crovella, Sergio (Curr HIV Res, 2016)
BACKGROUND: HIV-1 virus is known to infect the host mainly through CD4+ T-lymphocyte cells, by interactions among the viral envelope proteins, CD4 receptor and HIV-1 coreceptors, such as chemokines receptors. Variations in the genes encoding HIV-1 coreceptors and their natural ligands have been shown to modify HIV-1 infection susceptibility and disease progression. METHODS AND RESULTS: We analysed the distribution of SNPs in chemokines (CCL3, CCL4, CCL5, CXCL12) and chemokine receptor (CXCR6) genes, in 268 HIV-1 infected patients (HIV-1+) and 221 healthy controls from Northeast Brazil, and their possible connection with susceptibility to HIV-1 infection. The genotyping were performed through allele specific fluorogenic probes using real time PCR. We observed that the T alleles and AT genotype of rs1719153 CCL4 SNP were more frequent in healthy controls (19.8% and 35.0%, respectively) than in HIV-1+ patients (T allele: 14.1%; OR=0.67; 95%CI=0.47-0.95; p-value=0.020; and AT genotype: 24.4%; OR=0.61; 95%CI=0.40- 0.93; p-value=0.021) after correcting for age and sex. The rs1719134 (CCL3) and rs1719153 (CCL4) SNPs presented linkage disequilibrium (D'=0.83). The AT haplotype frequency was increased in healthy controls (17.3%) in relation to HIV-1+ patients (11.0%; OR=0.62; 95%CI=0.42-0.93; p-value=0.020). CONCLUSION: Since our results revealed an increased frequency of alleles and genotypes of CCL3/CCL4 SNPs and haplotype (CCL3-CCL4) among healthy controls, we suggest that these variations might have a potential protective role against HIV-1 infection.

Childhood hearing surveillance activity in Italy: preliminary recommendations. - Orzan, E; Ruta, F; Bolzonello, P; Marchi, R; Ceschin, F; Ciciriello, E (Acta Otorhinolaryngol Ital, 2016)
Following the positive outcomes of the newborn hearing screening programmes already underway in several Italian regions, it is now necessary to address the identification of childhood hearing impairments that missed the neonatal screening programme or have delayed onset. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for early Identification, Intervention and Care of Hearing Impaired Children", a group of professionals identified three main recommendations that can be useful to improve hearing surveillance activity within the regional and state Italian Health System. The family paediatrician is recognised as having a key role in ongoing monitoring of hearing capacity and development of the growing child.

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

Clinical and pathogenetic features of ETV6 related thrombocytopenia with predisposition to acute lymphoblastic leukemia. - Melazzini, Federica; Palombo, Flavia; Balduini, Alessandra; De Rocco, Daniela; Marconi, Caterina; Noris, Patrizia; Gnan, Chiara; Pippucci, Tommaso; Bozzi, Valeria; Faleschini, Michela; Barozzi, Serena; Doubek, Michael; et al. (Haematologica, 2016)
ETV6-related thrombocytopenia (ETV6-RT) is an autosomal dominant thrombocytopenia that has been recently identified in a few families and has been suspected to predispose to hematological malignancies. To gain further information on this disorder, we searched for ETV6 mutations in the 130 families with inherited thrombocytopenia of unknown origin from our cohort of 274 consecutive pedigrees with familial thrombocytopenia. We identified 20 ETV6-RT patients from 7 pedigrees. They have 5 different ETV6 variants, including three novel mutations affecting the highly conserved E26 transformation-specific domain. The relative frequency of ETV6-RT resulted 2.6% in the whole case series and 4.6% among the families with known forms of inherited thrombocytopenia. The degree of thrombocytopenia and bleeding tendency of ETV6-RT patients were mild, but 4 subjects developed B-cell acute lymphoblastic leukemia during childhood, resulting in a significantly increased incidence compared to the general population. Clinical and laboratory findings did not identify any peculiar defects that can be used to suspect this disorder by routine diagnostic workup. However, at variance with most inherited thrombocytopenias, platelet size was not enlarged. In vitro studies revealed that patients megakaryocytes have defective maturation and impaired proplatelet formation. Moreover, ETV6-RT platelets have reduced ability to spread on fibrinogen. Since also the dominant thrombocytopenias due to mutations in RUNX1 and ANKRD26 are characterized by normal platelet size and predispose to hematological malignancies, we suggest that mutation screening of ETV6, RUNX1 and ANKRD26 should be performed in all the subjects with autosomal dominant thrombocytopenia and normal platelet size.

Clinical Spectrum of PRKAG2 Syndrome. - Porto, Andrea Giuseppe; Brun, Francesca; Severini, Giovanni Maria; Losurdo, Pasquale; Fabris, Enrico; Taylor, Matthew R G; Mestroni, Luisa; Sinagra, Gianfranco (Circ Arrhythm Electrophysiol, 2016)
Keywords: AMP-Activated Protein Kinases; DNA; Heart Conduction System; Humans; Mutation; Wolff-Parkinson-White Syndrome

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Consensus Conference on Clinical Management of pediatric Atopic Dermatitis. - Galli, Elena; Neri, Iria; Ricci, Giampaolo; Baldo, Ermanno; Barone, Maurizio; Belloni Fortina, Anna; Bernardini, Roberto; Berti, Irene; Caffarelli, Carlo; Calamelli, Elisabetta; Capra, Lucetta; Carello, Rossella; et al. (Ital J Pediatr, 2016)
The Italian Consensus Conference on clinical management of atopic dermatitis in children reflects the best and most recent scientific evidence, with the aim to provide specialists with a useful tool for managing this common, but complex clinical condition. Thanks to the contribution of experts in the field and members of the Italian Society of Pediatric Allergology and Immunology (SIAIP) and the Italian Society of Pediatric Dermatology (SIDerP), this Consensus statement integrates the basic principles of the most recent guidelines for the management of atopic dermatitis to facilitate a practical approach to the disease. The therapeutical approach should be adapted to the clinical severity and requires a tailored strategy to ensure good compliance by children and their parents. In this Consensus, levels and models of intervention are also enriched by the Italian experience to facilitate a practical approach to the disease.

The cortical response to a noxious procedure changes over time in preterm infants. - Bembich, Stefano; Marrazzo, Francesca; Barini, Alice; Ravalico, Paola; Cont, Gabriele; Demarini, Sergio (Pain, 2016)
The aim of the study was to investigate whether cortical response to a repeated noxious procedure may change over time in preterm infants. Possible reasons for change are: (1) advancing maturation of central nervous system; and (2) increasing experience with noxious procedures during hospital stay. Sixteen preterm infants were recruited, with a postmenstrual age (PMA) ranging between 29 and 36 weeks. Newborns were assessed during a heel-prick procedure, once a week for at least 3 consecutive times. Multichannel near-infrared spectroscopy was used to detect cortical activation, by measuring increase in cortical oxy-haemoglobin (HbO2). Parietal, temporal, and posterior frontal areas were monitored bilaterally. By regression analysis, we studied the effect of (1) increasing PMA and (2) increasing number of heel pricks, on the magnitude of cortical activation. We observed a bilateral nociceptive event-related activation of the posterior frontal cortex, mainly contralateral to the side pricked. Additionally, we found a significant positive effect of PMA, as HbO2 progressively increased in the posterior frontal cortex (P < 0.001), bilaterally, over time. Conversely, the degree of cortical activation decreased as the number of noxious events increased (P < 0.002). We conclude the following: (1) Preterm newborns showed a significant activation of the posterior frontal cortex in association with noxious stimuli; (2) Cortical activation was progressively greater with increasing PMA; (3) There was an inverse relationship between cortical activation and the number of heel pricks. We speculate that such findings may be due to both endogenous cortical maturation and experience-dependent neuroplasticity of the developing brain (eg, synaptogenesis, synaptic pruning).

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

Current concepts in management of pain in children in the emergency department. - Krauss, Baruch S; Calligaris, Lorenzo; Green, Steven M; Barbi, Egidio (Lancet, 2016)
Pain is common in children presenting to emergency departments with episodic illnesses, acute injuries, and exacerbation of chronic disorders. We review recognition and assessment of pain in infants and children and discuss the manifestations of pain in children with chronic illness, recurrent pain syndromes, and cognitive impairment, including the difficulties of pain management in these patients. Non-pharmacological interventions, as adjuncts to pharmacological management for acute anxiety and pain, are described by age and development. We discuss the pharmacological management of acute pain and anxiety, reviewing invasive and non-invasive routes of administration, pharmacology, and adverse effects.
Keywords: Acute Pain; Analgesics, Opioid; Anesthetics, Local; Anti-Inflammatory Agents, Non-Steroidal; Anxiety; Child; Emergency Medicine; Emergency Service, Hospital; Humans; Pain Management; Pediatrics; Stress, Psychological

Decline in Lung Function in Childhood Asthma. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (N Engl J Med, 2016)
Keywords: Anti-Inflammatory Agents; Asthma; Female; Humans; Lung; Male

DEFB1 gene polymorphisms and tuberculosis in a Northeastern Brazilian population. - Celerino da Silva, Ronaldo; da Cruz, Heidi Lacerda Alves; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Montenegro, Lilian Maria Lapa; Schindler, Haiana Charifker; Segat, Ludovica; Crovella, Sergio (Braz J Microbiol, 2016)
β-Defensin-1, an antimicrobial peptide encoded by the DEFB1 gene, is known to play an important role in lung mucosal immunity. In our association study we analyzed three DEFB1 functional polymorphisms -52G>A (rs1799946), -44C>G (rs1800972) and -20G>A (rs11362) in 92 tuberculosis patients and 286 healthy controls, both from Northeast Brazil: no association was found between the studied DEFB1 polymorphisms and the disease. However we cannot exclude that this lack of association could be due to the low number of subjects analyzed, as suggested by the low statistical power achieved for the three analyzed SNPs (values between 0.16 and 0.50).

Differential expression of GAS5 in rapamycin-induced reversion of glucocorticoid resistance. - Lucafò, Marianna; Bravin, Vanessa; Tommasini, Alberto; Martelossi, Stefano; Rabach, Ingrid; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Clin Exp Pharmacol Physiol, 2016)
This study evaluates the association between the long noncoding RNA GAS5 levels and the anti-proliferative effect of the glucocorticoid (GC) methylprednisolone (MP) alone and in combination with rapamycin in peripheral blood mononuclear cells (PBMCs) obtained from healthy donors. The effect of MP, rapamycin, and MP plus rapamycin was determined in 17 healthy donors by labelling metabolically active cells with [methyl-3H] thymidine and the expression levels of GAS5 gene were evaluated by real-time RT-PCR TaqMan analysis. We confirmed a role for GAS5 in modulating GC response: poor responders presented higher levels of GAS5 in comparison with good responders. Interestingly, when PBMCs were treated with the combination of rapamycin plus MP, the high levels of GAS5 observed for each drug in the MP poor responders group decreased in comparison with rapamycin (P value = 0.0134) or MP alone (P value = 0.0193). GAS5 is involved in GC resistance and co-treatment of rapamycin with GCs restores GC effectiveness in poor responders through the downregulation of the long noncoding RNA. GAS5 could be considered a biomarker to personalize therapy and a novel therapeutic target useful for the development of new pharmacological approaches to restore GC sensitivity.

Does Preputial Reconstruction Increase Complication Rate of Hypospadias Repair? 20-Year Systematic Review and Meta-Analysis. - Castagnetti, Marco; Gnech, Michele; Angelini, Lorenzo; Rigamonti, Waifro; Bagnara, Vincenzo; Esposito, Ciro (Front Pediatr, 2016)
INTRODUCTION: We performed a systematic review of the literature on preputial reconstruction (PR) during hypospadias repair to determine the cumulative risk of preputial skin complications and the influence of PR on urethroplasty complications, namely, fistula formation and overall reoperation rate of the repair. MATERIALS AND METHODS: A systematic search of the literature published after 06/1995 was performed in 06/2015 using the keyword "hypospadias." Only studies on the outcome of PR in children, defined as dehiscence of the reconstructed prepuce or secondary phimosis needing circumcision, were selected. A meta-analysis of studies comparing PR vs. circumcision was performed for the outcomes "hypospadias fistula formation" and "reoperation rate." RESULTS: Twenty studies were identified. Nineteen reported the outcome of PR in 2115 patients. Overall, 95% (2016/2115) of patients undergoing PR had distal hypospadias. The cumulative rate of PR complications was 7.7% (163/2115 patients), including 5.7% (121/2115 patients) preputial dehiscences and 1.5% (35/2117 reported patients) secondary phimoses needing circumcision. A meta-analysis of seven studies comparing patients undergoing PR vs. circumcision showed no increased risk of urethral fistula formation associated with PR, odds ratio (OR) (Mantel-Haenszel, Fixed effect, 95% CI), 1.25 (0.80-1.97). Likewise, two studies comparing the overall reoperation rate did not show an increased risk of reoperation associated with PR, OR (Mantel-Haenszel, Random effect, 95% CI), 1.27 (0.45-3.58). CONCLUSION: PR carries an 8% risk of specific complications (dehiscence of reconstructed prepuce or secondary phimosis needing circumcision), but does not seem to increase the risk of urethroplasty complications, and the overall reoperation rate of hypospadias repair.

Early diagnosis and Early Start Denver Model intervention in autism spectrum disorders delivered in an Italian Public Health System service. - Devescovi, Raffaella; Monasta, Lorenzo; Mancini, Alice; Bin, Maura; Vellante, Valerio; Carrozzi, Marco; Colombi, Costanza (Neuropsychiatr Dis Treat, 2016)
BACKGROUND: Early diagnosis combined with an early intervention program, such as the Early Start Denver Model (ESDM), can positively influence the early natural history of autism spectrum disorders. This study evaluated the effectiveness of an early ESDM-inspired intervention, in a small group of toddlers, delivered at low intensity by the Italian Public Health System. METHODS: Twenty-one toddlers at risk for autism spectrum disorders, aged 20-36 months, received 3 hours/wk of one-to-one ESDM-inspired intervention by trained therapists, combined with parents' and teachers' active engagement in ecological implementation of treatment. The mean duration of treatment was 15 months. Cognitive and communication skills, as well as severity of autism symptoms, were assessed by using standardized measures at pre-intervention (Time 0 [T0]; mean age =27 months) and post-intervention (Time 1 [T1]; mean age =42 months). RESULTS: Children made statistically significant improvements in the language and cognitive domains, as demonstrated by a series of nonparametric Wilcoxon tests for paired data. Regarding severity of autism symptoms, younger age at diagnosis was positively associated with greater improvement at post-assessment. CONCLUSION: Our results are consistent with the literature that underlines the importance of early diagnosis and early intervention, since prompt diagnosis can reduce the severity of autism symptoms and improve cognitive and language skills in younger children. Particularly in toddlers, it seems that an intervention model based on the ESDM principles, involving the active engagement of parents and nursery school teachers, may be effective even when the individual treatment is delivered at low intensity. Furthermore, our study supports the adaptation and the positive impact of the ESDM entirely sustained by the Italian Public Health System.

Effect of Early Versus Late Azathioprine Therapy in Pediatric Ulcerative Colitis. - Aloi, Marina; DʼArcangelo, Giulia; Bramuzzo, Matteo; Gasparetto, Marco; Martinelli, Massimo; Alvisi, Patrizia; Illiceto, Maria Teresa; Valenti, Simona; Distante, Manuela; Pellegrino, Salvatore; Gatti, Simona; Arrigo, Serena; et al. (Inflamm Bowel Dis, 2016)
BACKGROUND: We aimed at describing the efficacy of azathioprine (AZA) in pediatric ulcerative colitis, comparing the outcomes of early (0-6 months) versus late (6-24 months) initiation of therapy. METHODS: Children with ulcerative colitis treated with AZA within 24 months of diagnosis were included. Corticosteroid (CS)-free remission and mucosal healing (MH), assessed by endoscopy or fecal calprotectin, at 12 months were the primary outcomes. Patients were also compared for CS-free remission and MH, need for treatment escalation or surgery, number of hospitalizations, and adverse events during a 24-month follow-up. RESULTS: A total of 121 children entered the study (median age 10.5 ± 4.0 years, 59% girls). Seventy-six (63%) started AZA between 0 and 6 months (early group) and 45 (37%) started between 6 and 24 months (late group). Seventy-five percent and 53% of patients in the early and late group, respectively, received CS at the diagnosis (P = 0.01). CS-free remission at 1 year was achieved by 30 (50%) of the early and 23 (57%) of the late patients (P = 0.54). MH occurred in 37 (37%) patients at 1 year, with no difference between the 2 groups (33% early, 42% late; P = 0.56). No difference was found for the other outcomes. CONCLUSIONS: Introduction of AZA within 6 months of diagnosis seems not more effective than later treatment to achieve CS-free remission in pediatric ulcerative colitis. MH does not depend on the timing of AZA initiation; however, because of the incomplete comparability of the 2 groups at the diagnosis and the use of fecal calprotectin as a surrogate marker of MH, our results should be further confirmed by prospective studies.

Effectiveness of the Baby Friendly Community Initiative in Italy: a non-randomised controlled study. - Cattaneo, Adriano; Bettinelli, Maria Enrica; Chapin, Elise; Macaluso, Anna; Córdova do Espírito Santo, Lílian; Murante, Anna Maria; Montico, Marcella (BMJ Open, 2016)
OBJECTIVE: To assess the effectiveness of the Baby Friendly Community Initiative (BFCI) on exclusive breast feeding at 6 months. DESIGN: Controlled, non-randomised trial. SETTING: 18 Local Health Authorities in 9 regions of Italy. PARTICIPANTS: 5094 mother/infant dyads in 3 cohorts were followed up to 12 months after birth in 3 rounds of data collection: at baseline, after implementation of the intervention in the early intervention group and after implementation in the late intervention group. 689 (14%) dyads did not complete the study. INTERVENTION: Implementation of the 7 steps of the BFCI. MAIN OUTCOME MEASURES: The rate of exclusive breast feeding at 6 months was the primary outcome; breast feeding at discharge, 3 and 12 months was also measured. RESULTS: The crude rates of exclusive breast feeding at discharge, 3 and 6 months, and of any breast feeding at 6 and 12 months increased at each round of data collection after baseline in the early and late intervention groups. At the end of the project, 10% of infants were exclusively breast fed at 6 months and 38% were continuing to breast feed at 12 months. However, the comparison by adjusted rates and logistic regression failed to show statistically significant differences between groups and rounds of data collection in the intention-to-treat analysis, as well as when compliance with the intervention and training coverage was taken into account. CONCLUSIONS: The study failed to demonstrate an effect of the BFCI on the rates of breast feeding. This may be due, among other factors, to the time needed to observe an effect on breast feeding following this complex intervention.

Efficacy of ketamine in refractory convulsive status epilepticus in children: a protocol for a sequential design, multicentre, randomised, controlled, open-label, non-profit trial (KETASER01). - Rosati, Anna; Ilvento, Lucrezia; L'Erario, Manuela; De Masi, Salvatore; Biggeri, Annibale; Fabbro, Giancarlo; Bianchi, Roberto; Stoppa, Francesca; Fusco, Lucia; Pulitanò, Silvia; Battaglia, Domenica; Pettenazzo, Andrea; et al. (BMJ Open, 2016)
INTRODUCTION: Status epilepticus (SE) is a life-threatening neurological emergency. SE lasting longer than 120 min and not responding to first-line and second-line antiepileptic drugs is defined as 'refractory' (RCSE) and requires intensive care unit treatment. There is currently neither evidence nor consensus to guide either the optimal choice of therapy or treatment goals for RCSE, which is generally treated with coma induction using conventional anaesthetics (high dose midazolam, thiopental and/or propofol). Increasing evidence indicates that ketamine (KE), a strong N-methyl-d-aspartate glutamate receptor antagonist, may be effective in treating RCSE. We hypothesised that intravenous KE is more efficacious and safer than conventional anaesthetics in treating RCSE. METHODS AND ANALYSIS: A multicentre, randomised, controlled, open-label, non-profit, sequentially designed study will be conducted to assess the efficacy of KE compared with conventional anaesthetics in the treatment of RCSE in children. 10 Italian centres/hospitals are involved in enrolling 57 patients aged 1 month to 18 years with RCSE. Primary outcome is the resolution of SE up to 24 hours after withdrawal of therapy and is updated for each patient treated according to the sequential method. ETHICS AND DISSEMINATION: The study received ethical approval from the Tuscan Paediatric Ethics Committee (12/2015). The results of this study will be published in peer-reviewed journals and presented at international conferences. TRIAL REGISTRATION NUMBER: NCT02431663; Pre-results.

Empowering the family during the first months after identification of permanent hearing impairment in children. - Ciciriello, E; Bolzonello, P; Marchi, R; Falzone, C; Muzzi, E; Orzan, E (Acta Otorhinolaryngol Ital, 2016)
The latest international guidelines highlight the importance of involving the family in the diagnostic and rehabilitation process of children affected by permanent hearing impairment. This emphasises how meaningful this approach is for the development of the deaf child. So far, there is very little evidence about this approach in Italy, and there are still some barriers to its practical management. The aim of this paper is to report the results of a strategic analysis, which identifies the strengths, weaknesses, opportunities and threats of the family empowerment process during early auditory diagnosis and rehabilitation. The audiology programme should have the goal to offer information and support to families in order to achieve a conscious decision about the use and type of auditory prosthesis and rehabilitation choice within three months after audiologic diagnosis. Within the framework of the Ministry of Health project CCM 2013 "Preventing Communication Disorders: a Regional Program for Early Identification, Intervention and Care of Hearing Impaired Children", a group of professionals identified three main recommendations that can be useful to foster the natural communicative development of the child by strengthening the therapeutic alliance and empowerment of the family. The recommendations obtained with this analysis can help to develop new Italian guidelines with the aim to foster natural communicative development of the child by strengthening the therapeutic alliance and empowerment of the family.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Epigenetic Signals on Plant Adaptation: A Biotic Stress Perspective. - Neto, José Ribamar Costa Ferreira; da Silva, Manassés Daniel; Pandolfi, Valesca; Crovella, Sergio; Benko-Iseppon, Ana Maria; Kido, Éderson Akio (Curr Protein Pept Sci, 2016)
For sessile organisms such as plants, regulatory mechanisms of gene expression are vital, since they remain exposed to climatic and biological threats. Thus, they have to face hazards with instantaneous reorganization of their internal environment. For this purpose, besides the use of transcription factors, the participation of chromatin as an active factor in the regulation of transcription is crucial. Chemical changes in chromatin structure affect the accessibility of the transcriptional machinery and acting in signaling, engaging/inhibiting factors that participate in the transcription processes. Mechanisms in which gene expression undergoes changes without the occurrence of DNA gene mutations in the monomers that make up DNA, are understood as epigenetic phenomena. These include (1) post-translational modifications of histones, which results in stimulation or repression of gene activity and (2) cytosine methylation in the promoter region of individual genes, both preventing access of transcriptional activators as well as signaling the recruitment of repressors. There is evidence that such modifications can pass on to subsequent generations of daughter cells and even generations of individuals. However, reports indicate that they persist only in the presence of a stressor factor (or an inductor of the above-mentioned modifications). In its absence, these modifications weaken or lose heritability, being eliminated in the next few generations. In this review, it is argued how epigenetic signals influence gene regulation, the mechanisms involved and their participation in processes of resistance to biotic stresses, controlling processes of the plant immune system.

Evaluation of energy metabolism and calcium homeostasis in cells affected by Shwachman-Diamond syndrome. - Ravera, Silvia; Dufour, Carlo; Cesaro, Simone; Bottega, Roberta; Faleschini, Michela; Cuccarolo, Paola; Corsolini, Fabio; Usai, Cesare; Columbaro, Marta; Cipolli, Marco; Savoia, Anna; Degan, Paolo; et al. (Sci Rep, 2016)
Isomorphic mutation of the SBDS gene causes Shwachman-Diamond syndrome (SDS). SDS is a rare genetic bone marrow failure and cancer predisposition syndrome. SDS cells have ribosome biogenesis and their protein synthesis altered, which are two high-energy consuming cellular processes. The reported changes in reactive oxygen species production, endoplasmic reticulum stress response and reduced mitochondrial functionality suggest an energy production defect in SDS cells. In our work, we have demonstrated that SDS cells display a Complex IV activity impairment, which causes an oxidative phosphorylation metabolism defect, with a consequent decrease in ATP production. These data were confirmed by an increased glycolytic rate, which compensated for the energetic stress. Moreover, the signalling pathways involved in glycolysis activation also appeared more activated; i.e. we reported AMP-activated protein kinase hyper-phosphorylation. Notably, we also observed an increase in a mammalian target of rapamycin phosphorylation and high intracellular calcium concentration levels ([Ca(2+)]i), which probably represent new biochemical equilibrium modulation in SDS cells. Finally, the SDS cell response to leucine (Leu) was investigated, suggesting its possible use as a therapeutic adjuvant to be tested in clinical trials.

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

The Great Pretender: Pediatric Wandering Spleen: Two Case Reports and Review of the Literature. - Radillo, Lucia; Taddio, Andrea; Ghirardo, Sergio; Bramuzzo, Matteo; Pederiva, Federica; Maschio, Massimo; Barbi, Egidio (Pediatr Emerg Care, 2016)
Wandering spleen is a rare condition, typically not only due to embryological defects of the splenic ligaments, but also secondary to trauma and splenomegaly. The most common presentation is acute abdomen with a mobile abdominal mass or recurrent abdominal pain. However, the spleen may be temporary in its normal position, and patients could be asymptomatic. A familiarity, if present, strengthens the diagnostic suspect.Abdominal ultrasonography and computed tomography are the examination of choice, and the management is surgical.

Hand-held computers can help to distract children undergoing painful venipuncture procedures. - Crevatin, Franca; Cozzi, Giorgio; Braido, Elena; Bertossa, Gabriella; Rizzitelli, Patrizia; Lionetti, Daniela; Matassi, Daniela; Calusa, Dorotea; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2016)
AIM: Needle-related procedures can be painful for children, and distraction provides ideal pain relief in blood-drawing centres. This study assessed the effectiveness of playing a computer game during venipuncture, compared with low-tech distraction by a nurse. METHODS: We conducted this prospective, randomised controlled trial at the blood-drawing centre of a tertiary-level children's hospital in Italy. Half of the 200 children played Angry Birds on a hand-held computer while the other half were distracted by a second, specifically trained nurse who sang to them, read a book, blew bubbles or played with puppets. Pain was measured using a faces pain scale for children aged 4-7 years and a numeric scale for children aged 8-13 years. RESULTS: The 200 children had a median age of eight years. Children reported significant pain in 16 cases (16%) in the hand-held computer distraction group and in 15 cases (15%) in the nurse-led low-tech distraction group (p = 0.85). The procedural success rate at the first attempt was not different in the two groups. CONCLUSION: Playing a game on a hand-held computer meant that only one in six children reported pain during venipuncture, but it was not superior to being distracted by nurses.

Heterologous Expression Systems for Plant Defensin Expression: Examples of Success and Pitfalls. - Gazzaneo, Luis Rs; Pandolfi, Valesca; Jesus, André Ls; Crovella, Sergio; Benko-Iseppon, Ana M; Freitas, Antonio Carlos (Curr Protein Pept Sci, 2016)
Defensins are a superfamily of antimicrobial peptides, present in vertebrates, invertebrates, fungi and plants, suggesting that they appeared prior to the divergence in eukaryotes. The destitution of toxicity to mammalian cells of plant defensins has led to a new research ground, i.e., their potential medical use against human infectious diseases. Isolating defensins from natural sources, like plant tissues, can be time-consuming, labor intensive and usually present low yields. Strategies for large-scale production of purified active defensins have been employed using heterologous expression systems (HES) for defensin production, usually based in E. coli system. Like any other technology, HES present limitations and drawbacks demanding a careful experimental design prior the system selection. This review is proposed to discuss some of the major concerns when choosing to heterologously express plant defensins, with special attention on bacterial expression system.

Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.

Incidence and Estimated Prevalence of Endometriosis and Adenomyosis in Northeast Italy: A Data Linkage Study. - Morassutto, Caterina; Monasta, Lorenzo; Ricci, Giuseppe; Barbone, Fabio; Ronfani, Luca (PLoS One, 2016)
Despite being quite frequent and having serious implications in terms of symptomatology and fertility, data on incidence and prevalence of endometriosis and adenomyosis following gold standard definitions are dramatically lacking. The average time from onset of symptoms to diagnosis in industrialized countries still ranges from five to ten years. Using the regional centralized data linkage system, we calculated incidence and prevalence of endometriosis and adenomyosis in the female population of Friuli Venezia Giulia region, Italy, for the years 2011-2013. Cases were defined as new diagnoses from hospital discharge records, following procedures allowing direct visualization for endometriosis and hysterectomy for adenomyosis, with or without histological confirmation. Diagnoses were considered "new" after verifying women had not been diagnosed in the previous ten years. Incidence of endometriosis and adenomyosis in women aged 15-50 years is 0.14%. Prevalence, estimated from incidence, is 2.00%. Adenomyosis, representing 28% of all diagnoses, becomes increasingly prevalent after the age of 50 years. Our results shows how the study of both endometriosis and adenomyosis should not be limited to women of premenopausal age. Further efforts are needed to sensitize women and health professional, and to find new data linkage possibilities to identify undiagnosed cases.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

Isolation of the left innominate artery: a question of connection. - Gesuete, Valentina; Sanabor, Daniela; Benettoni, Alessandra; Bobbo, Marco; Ventura, Alessandro (J Cardiovasc Med (Hagerstown), 2016)

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Macrocephaly and palmoplantar pitting. - Rabach, Ingrid; Salis, Simona; Bruno, Irene; Ventura, Alessandro (Arch Dis Child, 2016)

Mortality and its risk factors in Malawian children admitted to hospital with clinical pneumonia, 2001-12: a retrospective observational study. - Lazzerini, Marzia; Seward, Nadine; Lufesi, Norman; Banda, Rosina; Sinyeka, Sophie; Masache, Gibson; Nambiar, Bejoy; Makwenda, Charles; Costello, Anthony; McCollum, Eric D; Colbourn, Tim (Lancet Glob Health, 2016)
BACKGROUND: Few studies have reported long-term data on mortality rates for children admitted to hospital with pneumonia in Africa. We examined trends in case fatality rates for all-cause clinical pneumonia and its risk factors in Malawian children between 2001 and 2012. METHODS: Individual patient data for children (<5 years) with clinical pneumonia who were admitted to hospitals participating in Malawi's Child Lung Health Programme between 2001 and 2012 were recorded prospectively on a standardised medical form. We analysed trends in pneumonia mortality and children's clinical characteristics, and we estimated the association of risk factors with case fatality for children younger than 2 months, 2-11 months of age, and 12-59 months of age using separate multivariable mixed effects logistic regression models. FINDINGS: Between November, 2012, and May, 2013, we retrospectively collected all available hard copies of yellow forms from 40 of 41 participating hospitals. We examined 113 154 pneumonia cases, 104 932 (92·7%) of whom had mortality data and 6903 of whom died, and calculated an overall case fatality rate of 6·6% (95% CI 6·4-6·7). The case fatality rate significantly decreased between 2001 (15·2% [13·4-17·1]) and 2012 (4·5% [4·1-4·9]; ptrend<0·0001). Univariable analyses indicated that the decrease in case fatality rate was consistent across most subgroups. In multivariable analyses, the risk factors significantly associated with increased odds of mortality were female sex, young age, very severe pneumonia, clinically suspected Pneumocystis jirovecii infection, moderate or severe underweight, severe acute malnutrition, disease duration of more than 21 days, and referral from a health centre. Increasing year between 2001 and 2012 and increasing age (in months) were associated with reduced odds of mortality. Fast breathing was associated with reduced odds of mortality in children 2-11 months of age. However, case fatality rate in 2012 remained high for children with very severe pneumonia (11·8%), severe undernutrition (15·4%), severe acute malnutrition (34·8%), and symptom duration of more than 21 days (9·0%). INTERPRETATION: Pneumonia mortality and its risk factors have steadily improved in the past decade in Malawi; however, mortality remains high in specific subgroups. Improvements in hospital care may have reduced case fatality rates though a lack of sufficient data on quality of care indicators and the potential of socioeconomic and other improvements outside the hospital precludes adequate assessment of why case-fatality rates fell. Results from this study emphasise the importance of effective national systems for data collection. Further work combining this with data on trends in the incidence of pneumonia in the community are needed to estimate trends in the overall risk of mortality from pneumonia in children in Malawi. FUNDING: Bill & Melinda Gates Foundation.

Nationwide study of headache pain in Italy shows that pain assessment is still inadequate in paediatric emergency care. - Benini, Franca; Piga, Simone; Zangardi, Tiziana; Messi, Gianni; Tomasello, Caterina; Pirozzi, Nicola; Cuttini, Marina (Acta Paediatr, 2016)
AIM: Italian national guidelines on pain management were published in 2010, but there is little information on how effective pain management is in paediatric emergency care, with other countries reporting poor levels. Using headache as an indicator, we described pain assessment in Italian emergency departments and identified predictors of algometric scale use. METHODS: All Italian paediatric and maternal and child hospitals participated, plus four general hospitals. Data on all children aged 4-14 years admitted during a one-month period with headache as their chief complaint were abstracted from clinical records. Multivariable analyses identified predictors of algometric assessment, taking into account the cluster study design. RESULTS: We studied 470 admissions. During triage, pain was assessed using a standardised scale (41.5%), informally (15.5%) or was not recorded (42.9%). Only 32.1% of the children received analgesia in the emergency department. The odds ratios for predictors of algometric assessment were non-Italian nationality (3.6), prehospital medication (1.8), admission to a research hospital (7.3) and a more favourable nurses-to-admissions ratio of 10.8 for the highest versus lowest tertile. CONCLUSION: Despite national guidelines, paediatric pain assessment in Italian emergency care was suboptimal. Hospital variables appeared to be stronger predictors of adequate assessment than patient characteristics.

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

The one-step synthesis and surface functionalization of dumbbell-like gold-iron oxide nanoparticles: a chitosan-based nanotheranostic system. - Kostevsek, Nina; Locatelli, Erica; Garrovo, Chiara; Arena, Francesca; Monaco, Ilaria; Nikolov, Ivaylo Petrov; Sturm, Saso; Zuzek Rozman, Kristina; Lorusso, Vito; Giustetto, Pierangela; Bardini, Paola; Biffi, Stefania; et al. (Chem Commun (Camb), 2016)
The first one-step synthesis of dumbbell-like gold-iron oxide nanoparticles has been reported here. Surface functionalization with a biocompatible chitosan matrix allowed us to obtain a novel targetable diagnostic and therapeutic tool.

Pharmacogenetics driving personalized medicine: analysis of genetic polymorphisms related to breast cancer medications in Italian isolated populations. - Cocca, Massimiliano; Bedognetti, Davide; La Bianca, Martina; Gasparini, Paolo; Girotto, Giorgia (J Transl Med, 2016)
BACKGROUND: Breast cancer is the most common cancer in women characterized by a high variable clinical outcome among individuals treated with equivalent regimens and novel targeted therapies. In this study, we performed a population based approach intersecting high-throughput genotype data from Friuli Venezia Giulia (FVG) isolated populations with publically available pharmacogenomics information to estimate the frequency of genotypes correlated with responsiveness to breast cancer treatment thus improving the clinical management of this disease in an efficient and cost effective way. METHODS: A list of 80 variants reported to be related to the efficacy or toxicity of breast cancer drugs was obtained from PharmGKB database. Fourty-one were present in FVG, 1000G European (EUR) and ExAC (Non Finnish European) databases. Their frequency was extracted using PLINK software and the differences tested by Fisher's exact test. RESULTS: Statistical analyses revealed that 13 out of the 41 (32 %) variants were significantly different in frequency in our sample as compared to the EUR/ExAC cohorts. For nine variants the available level of evidence (LOE) included polymorphisms related to cyclophosphamide, tamoxifen, doxorubicin, fluorpyrimidine and paclitaxel. In particular, for trastuzumab two variants were detected: (1) rs1801274-G within FCGR2A and associated with decreased efficacy (LOE 2B); (2) rs1136201-G located within ERBB2 and associated with increased toxicity (LOE 3). Both these two variants were underrepresented in the FVG population compared to EUR/ExAC population thus suggesting a high therapeutic index of this drug in our population. Moreover, as regards fluoropyrimidines, the frequency of two polymorphisms within the DPYD gene associated with drug toxicity (e.g., rs2297595-C allele and rs3918290-T allele, LOE 2A and 1, respectively) was extremely low in FVG population thus suggesting that a larger number of FVG patients could benefit from full dosage of fluoropyrimidine therapy. CONCLUSIONS: All these findings increase the overall knowledge on the prevalence of specific variants related with breast cancer treatment responsiveness in FVG population and highlight the importance of assessing gene polymorphisms related with cancer medications in isolated communities.

Pitfalls and promises in FTIR spectromicroscopy analyses to monitor iron-mediated DNA damage in sperm. - Pascolo, Lorella; Bedolla, Diana E; Vaccari, Lisa; Venturin, Irene; Cammisuli, Francesca; Gianoncelli, Alessandra; Mitri, Elisa; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Zweyer, Marina; Ricci, Giuseppe (Reprod Toxicol, 2016)
Many drugs, chemicals, and environmental factors can impair sperm functionality by inducing DNA damage, one of the important causes of reduced fertility potential. The use of vibrational spectromicroscopy represents a promising approach for monitoring DNA integrity in sperm, although some limitations exist, depending from the experimental conditions. Here, we report that when using FTIR spectromicroscopy to reveal oxidative stress mediated by Fenton's reaction on hydrated sperm samples, DNA damage interpretation is partially compromised by unexpected cell surface precipitates. The precipitates give a broad band in the 1150-1000cm(-1) infrared region, which partially covers one of the signatures of DNA (phosphate stretching bands), and are detected as iron and oxygen containing material when using XRF spectroscopy. On the other hand, the analyses further support the potential of FTIR spectromicroscopy to reveal cellular oxidative damage events such as lipid peroxidation, protein misfolding and aggregations, as well as DNA strain breaks.

Plant Elite Squad: First Defense Line and Resistance Genes - Identification, Diversity and Functional Roles. - Wanderley-Nogueira, Ana Carolina; Bezerra-Neto, João Pacífico; Kido, Éderson Akio; de Araújo, Flávia Tadeu; Amorim, Lidiane Lindinalva Barbosa; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Plants exhibit sensitive mechanisms to respond to environmental stresses, presenting some specific and non-specific reactions when attacked by pathogens, including organisms from different classes and complexity, as viroids, viruses, bacteria, fungi and nematodes. A crucial step to define the fate of the plant facing an invading pathogen is the activation of a compatible Resistance (R) gene, the focus of the present review. Different aspects regarding R-genes and their products are discussed, including pathogen recognition mechanisms, signaling and effects on induced and constitutive defense processes, splicing and post transcriptional mechanisms involved. There are still countless challenges to the complete understanding of the mechanisms involving R-genes in plants, in particular those related to the interactions with other genes of the pathogen and of the host itself, their regulation, acting mechanisms at transcriptional and post-transcriptional levels, as well as the influence of other types of stress over their regulation. A magnification of knowledge is expected when considering the novel information from the omics and systems biology.

Plants Defense-related Cyclic Peptides: Diversity, Structure and Applications. - Maria, Ana Carolina Wanderley-Nogueira; Bezerra-Neto, João Pacífico; Kido, Éderson Akio; de Araújo, Flávia Tadeu; Amorim, Lidiane Lindinalva Barbosa; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Plant growth is prone to several unfavorable factors that may compromise or impair development and survival, including abiotic or biotic stressors. Aiming at defending themselves, plants have developed several strategies to survive and adapt to such adversities. Cyclotides are a family of plant-derived proteins that exhibit a diverse range of biological activities including antimicrobial and insecticidal activities that actively participate in plant defense processes. Three main categories of peptides have been described: (i) Cyclotides (ii) Sunflower Trypsin Inhibitor (SFTI) and (iii) peptides MCoTI-I and II, from Momordica cochinchinensis. They comprise proteins of approximately 30 amino acids, containing a head-to-tail cyclized backbone, with three disulfide bonds configured in a cystine knot topology, therefore bearing greater peptide stability. Given their features and multifunctionality, cyclotides stand out as promising sources for the discovery of new antimicrobial agents. The present review describes cyclotide occurrence, abundance and action in plants, also their diversity and evolution. Considerations regarding their use in the context of biomedical and agronomical sciences uses are also presented.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Protective Role of BST2 Polymorphisms in Mother-to-Child Transmission of HIV-1 and Adult AIDS Progression. - Kamada, Anselmo J; Bianco, Anna M; Zupin, Luisa; Girardelli, Martina; Matte, Maria C C; Medeiros, Rúbia Marília de; Almeida, Sabrina Esteves de Matos; Rocha, Marineide M; Segat, Ludovica; Chies, José A B; Kuhn, Louise; Crovella, Sergio (J Acquir Immune Defic Syndr, 2016)
Bone marrow stromal cell antigen-2 (BST-2)/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (rs919266, rs9192677, and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 single nucleotide polymorphism analyses were performed in 2 cohorts with acquired immunodeficiency syndrome (AIDS) progression: an adult Brazilian cohort (37 rapid, 30 chronic and 21 long-term non-progressors) and an Italian pediatric cohort (21 rapid and 67 slow progressors). The rs9576A allele was nominally associated with protection during breastfeeding (P = 0.019) and individuals carrying rs919266 GA showed slower progression to AIDS (P = 0.033). Despite the influence of rs919266 and rs9576 on BST2 expression being still undetermined, a preventive role by BST2 polymorphisms was found during HIV-1 infection.

Putative modifier genes in mevalonate kinase deficiency. - Marcuzzi, Annalisa; Vozzi, Diego; Girardelli, Martina; Tricarico, Paola Maura; Knowles, Alessandra; Crovella, Sergio; Vuch, Josef; Tommasini, Alberto; Piscianz, Elisa; Bianco, Anna Monica (Mol Med Rep, 2016)
Mevalonate kinase deficiency (MKD) is an autosomal recessive auto‑inflammatory disease, caused by impairment of the mevalonate pathway. Although the molecular mechanism remains to be elucidated, there is clinical evidence suggesting that other regulatory genes may be involved in determining the phenotype. The identification of novel target genes may explain non‑homogeneous genotype‑phenotype correlations, and provide evidence in support of the hypothesis that novel regulatory genes predispose or amplify deregulation of the mevalonate pathway in this orphan disease. In the present study, DNA samples were obtained from five patients with MKD, which were then analyzed using whole exome sequencing. A missense variation in the PEX11γ gene was observed in homozygosis in P2, possibly correlating with visual blurring. The UNG rare gene variant was detected in homozygosis in P5, without correlating with a specific clinical phenotype. A number of other variants were found in the five analyzed DNA samples from the MKD patients, however no correlation with the phenotype was established. The results of the presents study suggested that further analysis, using next generation sequencing approaches, is required on a larger sample size of patients with MKD, who share the same MVK mutations and exhibit 'extreme' clinical phenotypes. As MVK mutations may be associated with MKD, the identification of specific modifier genes may assist in providing an earlier diagnosis.

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children's anxiety and pain levels in emergency department. - Felluga, Margherita; Rabach, Ingrid; Minute, Marta; Montico, Marcella; Giorgi, Rita; Lonciari, Isabella; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2016)
UNLABELLED: The aim of the study is to investigate if the presence of medical clowns during painful procedures in the emergency department (ED) affects children's anxiety and pain. Forty children (4-11 years) admitted to the ED with the need of painful procedures were prospectively enrolled. They were randomly assigned to the clown group, where children interacted with clowns or to the control group in which they were entertained by parents and ED nurses. The children's anxiety was assessed by the Children's Anxiety and Pain Scales; pain was evaluated with the Numerical Rating Scale and Wong-Backer Scale, according to the children's age. Staff and clown's opinions were evaluated by means of dedicated questionnaires. Children's anxiety levels in the clown group were significantly lower than those compared with the control group, while children's pain levels did not change between the two groups. CONCLUSION: The presence of clowns in the ED before and during painful procedures was effective in reducing children's anxiety. WHAT IS KNOWN: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Role of inflammasome genetics in susceptibility to HPV infection and cervical cancer development. - Pontillo, A; Bricher, P; Leal, V N C; Lima, S; Souza, P R E; Crovella, S (J Med Virol, 2016)
PROBLEM: Only a small proportion of HPV+ women develop virus-associated lesions and cervical cancer, suggesting that other factors are involved in HPV+ keratinocyte transformation. Immune response plays an important role in clearing HPV infection, and host genetic variants resulting in defective immune response have been associated with virus persistence and/or cervical cancer. Considering that genetic variations in inflammasome genes were previously associated with viral infection and cancer development, the present study investigates selected single nucleotide polymorphisms (SNPs) in inflammasome genes as a possible risk factor for HPV infection susceptibility and/or for progression to cervical cancer. PATIENTS AND METHODS: 12 SNPs in seven inflammasome-related genes (NLRP1, NLRP3, NLRP6, CARD8, IL1B, IL18, TNFAIP3) were genotyped in a Brazilian HPV+ case/control cohort (n = 246/310). Multivariate analysis was performed in case/control as well as in HPV+ women stratified by the presence or severity of histologic lesion, HPV persistence, and type of virus. RESULTS: IL1B rs1143643 was associated with protection against HPV infection in case/control analysis. NLRP1 rs11651270 plays a protection role against HPV persistence and/or oncogenesis. NLRP3 rs10754558 and IL18 rs1834481 exert a beneficial role against HPV persistence. NLRP3 rs10754558 variant resulted significantly associated with a lower risk to be infected with a high-risk HPV. CONCLUSION: Our findings for the first time demonstrated that inflammasome genetics could affect HPV/host interaction in terms of virus susceptibility as well as of virus/persistence and cervical cancer progression. J. Med. Virol. 88:1646-1651, 2016. © 2016 Wiley Periodicals, Inc.

"Safety and utility of percutaneous liver biopsy in hematopoietic stem cell transplant pediatric recipients: a retrospective study". - Maximova, Natalia; Gregori, Massimo; Barbieri, Francesca; Pizzol, Antonio; Sonzogni, Aurelio (BMC Cancer, 2016)
BACKGROUND: Liver biopsies in pediatric hematopoietic stem cell transplantation (HSCT) patients are as and effective when performed at bedside in the Bone Marrow Transplant Unit (BMTU) than in the Day Surgery Unit (DSU), with better patient compliance and lower emotional distress for these children. METHODS: The study group consisted of 45 children who underwent allogeneic HSCT. We reviewed 68 liver biopsies performed between April 2006 and September 2015. 12 (17.6 %) biopsies were performed in the DSU and 56 (82.3 %) in the BMTU; nine (13.2 %) prior to HSCT and 59 (86.7 %) after HSCT. Pre-procedural behavioral status (subjective score) was evaluated by pediatric transplant physicians by filling in a questionnaire employing a three-point scale: "calm and cooperative", "agitated and non-cooperative" or "frightened and suffering". Objective score was obtained measuring patient's heart rate before the procedure and comparing it with mean heart rate. RESULTS: Patients who underwent the procedure at the BMTU experienced less emotional distress than those who underwent it in the DSU: 58.3 % of patients treated at the DSU were agitated as compared with 16.1 % of those treated at the BMTU (p < 0.01). Among the 59 biopsies performed after HSCT, 41 (69.5 %) were taken from symptomatic patients for a diagnostic purpose and 18 (30.5 %) in asymptomatic ones in order to rule out hepatic GVHD. Among these 18 procedures, GVHD was diagnosed in 16 (88.9 %) cases. Minor complications occurred in about 17 % of procedures (12 biopsies), at a rate of 25 % for the DSU location compared with 16 % for the BMTU location. Only two major complications were reported, one in the DSU and one in the BMTU. CONCLUSION: Liver biopsy performed at bedside in HSCT patients does not carry a higher risk of adverse events than the same procedure performed in the DSU and has lower emotional distress associated with better patient compliance, thus contributing significantly to a higher standard of care.

Snakin: Structure, Roles and Applications of a Plant Antimicrobial Peptide. - Oliveira-Lima, Marx; Benko-Iseppon, Ana Maria; Neto, José Ribamar Costa Ferreira; Rodríguez-Decuadro, Susana; Kido, Éderson Akio; Crovella, Sergio; Pandolfi, Valesca (Curr Protein Pept Sci, 2016)
Snakins are plant antimicrobial peptides (AMPs) of the Snakin/GASA family, formed by three distinct regions: an N-terminal signal peptide; a variable site; and the GASA domain in the C-terminal region composed by twelve conserved cysteine residues that contribute to the biochemical stability of the molecule. These peptides are known to play different roles in response to a variety of biotic (i.e. induced by bacteria, fungi and nematode pathogens) and abiotic (salinity, drought and ROS) stressors, as well as in crosstalk promoted by plant hormones, with emphasis on abscisic and salicylic acid (ABA and SA, respectively). Such properties make snakin/GASA members promising biotechnological sources for potential therapeutic and agricultural applications. However, information regarding their tertiary structure, mode of action and function are not yet completely elucidated. The present review presents aspects of snakin structure, expression, functional studies and perspectives about the potential applications for agricultural and medical purposes.

Somatic, hematologic phenotype, long-term outcome, and effect of hematopoietic stem cell transplantation. An analysis of 97 Fanconi anemia patients from the Italian national database on behalf of the Marrow Failure Study Group of the AIEOP (Italian Associ - Svahn, Johanna; Bagnasco, Francesca; Cappelli, Enrico; Onofrillo, Daniela; Caruso, Silvia; Corsolini, Fabio; De Rocco, Daniela; Savoia, Anna; Longoni, Daniela; Pillon, Marta; Marra, Nicoletta; Ramenghi, Ugo; et al. (Am J Hematol, 2016)
We analyzed 97 Fanconi anemia patients from a clinic/biological database for genotype, somatic, and hematologic phenotype, adverse hematological events, solid tumors, and treatment. Seventy-two patients belonged to complementation group A. Eighty percent of patients presented with mild/moderate somatic phenotype and most with cytopenia. No correlation was seen between somatic/hematologic phenotype and number of missense mutations of FANCA alleles. Over follow-up, 33% of patients improved or maintained mild/moderate cytopenia or normal blood count, whereas remaining worsened cytopenia. Eleven patients developed a hematological adverse event (MDS, AML, pathological cytogenetics) and three developed solid tumors. 10 years cumulative risk of death of the whole cohort was 25.6% with median follow-up 5.8 years. In patients eligible to hematopoietic stem cell transplantation because of moderate cytopenia, mortality was significantly higher in subjects transplanted from matched unrelated donor over nontransplanted subjects, whereas there was no significant difference between matched sibling donor transplants and nontransplanted patients. In patients eligible to transplant because of severe cytopenia and clonal disease, mortality risk was not significantly different in transplanted from matched unrelated versus matched sibling donor versus nontransplanted subjects. The decision to transplant should rely on various elements including, type of donor, HLA matching, patient comorbidities, impairment, and clonal evolution of hematopoiesis. Am. J. Hematol. 91:666-671, 2016. © 2016 Wiley Periodicals, Inc.

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

Thalidomide for inflammatory bowel disease: Systematic review. - Bramuzzo, Matteo; Ventura, Alessandro; Martelossi, Stefano; Lazzerini, Marzia (Medicine (Baltimore), 2016)
BACKGROUND: Thalidomide is an immunomodulatory drug used in the experimental treatment of refractory Crohn disease and ulcerative colitis. We aimed to review the existing evidence on the efficacy and safety of thalidomide in the treatment of inflammatory bowel diseases. METHODS: CENTRAL, MEDLINE, LILACS, POPLINE, CINHAL, and Web of Science were searched in March 2016. Manual search included conference and reference lists. All types of studies, except single case reports, were included. Outcomes evaluated were: induction of remission; maintenance of remission; steroid reduction; effect on penetrating Crohn disease; endoscopic remission; adverse events. RESULTS: The research strategies retrieved 722 papers. Two randomized controlled trials and 29 uncontrolled studies for a total of 489 patients matched the inclusion criteria. Thalidomide induced a clinical response in 296/427 (69.3%) patients. Clinical remission was achieved in 220/427 (51.5%) cases. Maintenance of remission was reported in 128/160 (80.0%) patients at 6 months and in 96/133 (72.2%) at 12 months. Reduction in steroid dosage was reported in 109/152 (71.7%) patients. Fistulas improved in 49/81 (60.5%) cases and closed in 28/81 (34.6%). Endoscopic improvement was observed in 46/66 (69.7%) and complete mucosal healing in 35/66 (53.0%) patients. Cumulative incidence of total adverse events and of those leading to drug suspension was 75.6 and 19.7/1000 patient-months, respectively. Neurological disturbances accounted for 341/530 (64.3%) adverse events and were the most frequent cause of drug withdrawal. CONCLUSION: Existing evidence suggests that thalidomide may be a valid treatment option for patients with inflammatory bowel diseases refractory to other first- and second-line treatments.

Torticollis as the Presenting Sign of Cervical Spondylodiscitis. - Pizzol, Antonio; Bramuzzo, Matteo; Pillon, Roberto; Taddio, Andrea; Barbi, Egidio (Pediatr Emerg Care, 2016)
Acquired torticollis is a common clinical finding in children evaluated in the pediatric emergency department. It may be the presentation symptom of different illnesses, such as trauma, muscle contraction, infections, or malignancies, and an accurate differential diagnosis is required to correctly identify the cause and choose the right treatment. Spondylodiscitis is a low-grade bacterial infection that involves intervertebral disks and the adjacent vertebral bodies. Spondylodiscitis of the cervical spine is unusual and may be a rare cause of torticollis. We report the case of a 4-year-old male patient admitted to the emergency department for a 5-day history of painful torticollis. Blood tests showed an elevated erythrocyte sedimentation rate. The radiograph of the cervical spine showed a thin fifth cervical soma. The magnetic resonance imaging of cervical spine showed the alteration of cervical vertebral bodies and intervertebral disks, suggesting the diagnosis of cervical spondylodiscitis. The patient recovered after endovenous antibiotic treatment. We suggest that cervical spondylodiscitis should be suspected and investigated by means of an magnetic resonance imaging in every case of unexplained torticollis with persisting symptoms.

Toward SERS-based point-of-care approaches for therapeutic drug monitoring: the case of methotrexate. - Fornasaro, Stefano; Marta, Silvia Dalla; Rabusin, Marco; Bonifacio, Alois; Sergo, Valter (Faraday Discuss, 2016)
To date, in spite of their toxicity, the plasmatic concentration of most chemotherapeutic drugs is difficult to monitor in oncological patients, because their quantitative determination is expensive and time consuming. This contribution reports a first attempt for the direct quantitative determination of a chemotherapeutic drug in human serum samples by means of Surface Enhanced Raman Spectroscopy (SERS). In this study, SERS substrates constituted by Au nanoparticles deposited on paper by a simple dipping method have been used for rapid (few minutes) analysis of diluted human serum spiked with different concentrations of methotrexate, MTX. The drug concentrations were chosen in a range designed to cover typical therapeutic plasmatic values (from nanomolar to millimolar) in oncological patients, and the pertinent calibration was obtained by Partial Least-Squares Regression (PLSR). Stability selection was employed to evaluate the capability of the PLSR model to accurately predict and extract spectral variations correlated to MTX concentration. Such a quantitative determination is crucial for frequent, and hence adherent, therapeutic drug monitoring, TDM, of chemiotherapic drugs, given their heavy side effects. Its low cost, rapid response and the possibility of obtaining spectra with simple and compact instruments, make SERS particularly apt for implementing effective TDM. The promising results obtained in the analytical validation indicate which steps are to be taken on the way toward a clinical validation with real samples from oncological patients, for MTX as well as for other chemotherapeutic drugs.

Tracking of the origin of recurrent mutations of the BRCA1 and BRCA2 genes in the North-East of Italy and improved mutation analysis strategy. - Cini, Giulia; Mezzavilla, Massimo; Della Puppa, Lara; Cupelli, Elisa; Fornasin, Alessio; D'Elia, Angela Valentina; Dolcetti, Riccardo; Damante, Giuseppe; Bertok, Sara; Miolo, Gianmaria; Maestro, Roberta; de Paoli, Paolo; et al. (BMC Med Genet, 2016)
BACKGROUND: About 20 % of hereditary breast cancers are caused by mutations in BRCA1 and BRCA2 genes. Since BRCA1 and BRCA2 mutations may be spread throughout the gene, genetic testing is usually performed by direct sequencing of entire coding regions. In some populations, especially if relatively isolated, a few number of recurrent mutations is reported, sometimes caused by founder effect. METHODS: BRCA1 and BRCA2 screening for mutations was carried out on 1114 breast and/or ovarian cancer patients complying with the eligibility criteria for BRCA testing. Haplotype analysis was performed on the probands carrying recurrent mutations and their relatives, using two sets of microsatellite markers covering the BRCA1 (D17S588, D17S806, D17S902, D17S1325, D17S855, D17S1328, D17S800, and D17S250) and BRCA2 (D13S220, D13S267, D13S171, D13S1701, D13S1698, D13S260, D13S290, D13S1246) loci. The DMLE + 2.2 software was used to estimate the age of BRCA1 c.676delT and BRCA2 c.7806-2A > G. A multiplex PCR and two different primer extension assays were optimized and used for genotyping the recurrent mutations of the two genes. RESULTS: In the time frame of almost 20 years of genetic testing, we have found that five BRCA1 and three BRCA2 mutations are recurrent in a substantial subset of carriers from North-East Italy and neighboring Istria, where they represent more than 50 % of all mutations. Microsatellite analyses identified a common haplotype of different length for each mutation. Age estimation of BRCA1 c.676delT and BRCA2 c.7806-2A > G mutations revealed that they arose in the Friuli Venezia Giulia area about 86 and 94 generations ago, respectively. Suggestion of an association between BRCA2 c.7806-2A > G and risk of breast cancer in males has emerged. Finally, we developed a simple and efficient pre-screening test, performing an in-house primer extension SNaPshot® assay for the rapid identification of the eight recurrent mutations. CONCLUSIONS: Proofs of common ancestry has been obtained for the eight recurrent mutations. The observed genotype-phenotype correlation and the proposed rapid mutation detection strategy could improve the clinical management of breast and ovarian patients in North-East of Italy and neighboring geographic areas.
Keywords: Adult; Aged; Alleles; BRCA1 Protein; BRCA2 Protein; Breast Neoplasms; Case-Control Studies; DNA Mutational Analysis; Female; Founder Effect; Genetic Testing; Genome-Wide Association Study; Genotyping Techniques; Haplotypes; Humans; Italy; Male; Microsatellite Repeats; Middle Aged; Mutation; Ovarian Neoplasms; Young Adult

Transcription factors involved in plant resistance to pathogens. - Amorim, Lidiane L B; da Fonseca-Dos-Santos, Romulo; Guida-Santos, Mauro; Crovella, Sergio; Benko-Iseppon, Ana Maria (Curr Protein Pept Sci, 2016)
Phytopathogenic microorganisms have a significant influence on survival and productivity of several crop plants. Transcription factors (TFs) are important players in the response to biotic stresses, as insect attack and pathogen infection. In face of such adversities many TF families have been previously reported as differentially expressed in plants as a reaction to bacterial, fungal and viral infection. This review highlights recent progresses in understanding the structure, function, signal regulation and interaction of transcription factors with other proteins in response to pathogens. Hence, we focus on three families of transcription factors: ERF, bZIP and WRKY, due to their abundance, importance and the availability of functionally well-characterized members in response to pathogen attack. Their roles and the possibilities related to the use of this knowledge for engineering pathogen resistance in crop plants are also discussed.

TRIM5 gene polymorphisms in HIV-1-infected patients and healthy controls from Northeastern Brazil. - Celerino da Silva, Ronaldo; Coelho, Antônio Victor Campos; Arraes, Luiz Claudio; Brandão, Lucas André Cavalcanti; Crovella, Sergio; Guimarães, Rafael Lima (Immunol Res, 2016)
Humans show heterogeneity in vulnerability to HIV-1 infection, partially under control of genes involved in host immunity and virus replication. TRIM5α protein has restriction activity against replication of many retroviruses. Human TRIM5 gene single nucleotide polymorphisms have been reported as involved in susceptibility to HIV-1 infection. We recruited 213 HIV-1-positive patients and 234 healthy uninfected controls from Northeast Brazil; two non-synonymous variants at exon 2, rs3740996 (H43Y) and rs10838525 (R136Q), and one regulatory polymorphism (rs16934386) at 5'UTR region of TRIM5 were analyzed. The R136Q variation presented significant differences between HIV-1-positive patients and healthy controls. The 136Q allele and the 136QQ genotype were more frequent in healthy controls (32.7 and 10.2 %, respectively) than in HIV-1-positive patients (136Q allele: 24.4 %; OR 0.66; CI 95 % 0.49-0.90; p value = 0.008/136QQ genotype: 4.2 %; OR 0.33; CI 95 % 0.13-0.79, p = 0.008) also after adjusting for age and sex. We also stratified our findings according to the presence of CCR5Δ32 variation, but the results remained the same. We observed that rs10838525 (R136Q) and rs3740996 (H43Y) were in linkage disequilibrium (D' = 0.71), forming four possible haplotypes. The H43-136Q haplotype was significantly more frequent in healthy controls (28.2 %) than in HIV-positive patients (21.4 %; OR 0.69; CI 95 % 0.50-0.96; p = 0.022). An increased frequency of allele (136Q) and genotype (136QQ) of the non-synonymous rs10838525 (R136Q) variant and the haplotype (43H-136Q) was observed among healthy controls individuals. Being aware of the limitation of this study (unavailability of exposed but uninfected individuals), we hypothesize a potential role for TRIM5 variations in the protection against HIV-1 infection.

When a lymphatic malformation determines a bowel volvulus: Are clinical status and images always reliable? - Guida, Edoardo; Di Grazia, Massimo; Cattaruzzi, Elisabetta; Bussani, Rossana; Rigamonti, Waifro; Lembo, Maria Antonietta (Int J Surg Case Rep, 2016)
INTRODUCTION: An acute abdomen in the form of small-bowel volvulus could be a presentation of a lymphatic malformation in childhood. CASE PRESENTATION: A 5year old male was admitted to our Institute for an acute abdomen. Clinical aspects and radiological images were not specific for a certain diagnosis. Laparotomy revealed a big soft mass, with a milky content, completely involving about 50cm of ileus with a partial volvulus of the intestinal loop. A complete mass excision and also a bowel involved resection were performed. After a histological examination, a lymphatic malformation was diagnosed. DISCUSSION: The diagnosis of a mesenteric lymphatic malformation could be intraoperative and a complete resection should be the treatment of choice. Sometimes it could be necessary to perform an involved bowel tract resection in the case of volvolus with ischemia. CONCLUSIONS: Paediatricians and surgeons should bare in mind that an intrabdominal lymphatic malformation may present as a nonspecific an acute abdomen caused by a bowel volvolus and diagnosis may not be so simple preoperatively.

ACTN1-related thrombocytopenia: identification of novel families for phenotypic characterization. - Bottega, Roberta; Marconi, Caterina; Faleschini, Michela; Baj, Gabriele; Cagioni, Claudia; Pecci, Alessandro; Pippucci, Tommaso; Ramenghi, Ugo; Pardini, Simonetta; Ngu, Loretta; Baronci, Carlo; Kunishima, Shinji; et al. (Blood, 2015)
Inherited thrombocytopenias (ITs) are a heterogeneous group of syndromic and nonsyndromic diseases caused by mutations affecting different genes. Alterations of ACTN1, the gene encoding for α-actinin 1, have recently been identified in a few families as being responsible for a mild form of IT (ACTN1-related thrombocytopenia; ACTN1-RT). To better characterize this disease, we screened ACTN1 in 128 probands and found 10 (8 novel) missense heterozygous variants in 11 families. Combining bioinformatics, segregation, and functional studies, we demonstrated that all but 1 amino acid substitution had deleterious effects. The clinical and laboratory findings of 31 affected individuals confirmed that ACTN1-RT is a mild macrothrombocytopenia with low risk for bleeding. Low reticulated platelet counts and only slightly increased serum thrombopoietin levels indicated that the latest phases of megakaryopoiesis were affected. Given its relatively high frequency in our cohort (4.2%), ACTN1-RT has to be taken into consideration in the differential diagnosis of ITs.
Keywords: Actinin; Adolescent; Adult; Aged; Aged, 80 and over; Blood Platelets; Case-Control Studies; Child; Child, Preschool; Female; Gene Expression; Genotype; Heterozygote; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Platelet Count; Severity of Illness Index; Thrombocytopenia; Thrombopoiesis; Thrombopoietin

Acute myeloid leukemia in a 3 years old child with cleidocranial dysplasia. - Callea, Michele; Bellacchio, Emanuele; Fattori, Fabiana; Bertini, Enrico; Callea, Francesco; Cammarata-Scalisi, Francisco (Leuk Lymphoma, 2015)

Acute pseudotumoral hemicerebellitis in a child: a rare and distinct entity? - Alberini, Elena; Vellante, Valerio; Zennaro, Floriana; Calligaris, Lorenzo; Barbi, Egidio; Carrozzi, Marco; Devescovi, Raffaella (J Child Neurol, 2015)
A pseudotumoral presentation of acute hemicerebellitis is rare in pediatric age. The authors report a new single case study of a 7-year-old child with pseudotumoral unilateral cerebellitis mimicking an intracranial tumor, which clinically presented itself with signs of intracranial hypertension and mild contralateral hemiparesis, completely recovered after anti-inflammatory therapy. Brain magnetic resonance imaging (MRI) was essential for the differential diagnosis between inflammatory and neoplastic processes. The literature highlighting specific clues about pseudotumoral hemicerebellitis as a distinct clinical and radiological entity is reviewed.
Keywords: Brain; Cerebellar Diseases; Child; Diagnosis, Differential; Encephalitis; Humans; Magnetic Resonance Imaging; Male

Advising Mothers on the Use of Medications during Breastfeeding: A Need for a Positive Attitude. - Davanzo, Riccardo; Bua, Jenny; De Cunto, Angela; Farina, Maria Luisa; De Ponti, Fabrizio; Clavenna, Antonio; Mandrella, Stefania; Sagone, Antonella; Clementi, Maurizio (J Hum Lact, 2015)
The use of medications by the nursing mother is a common reason for interrupting breastfeeding. Few drugs have been demonstrated to be absolutely contraindicated during breastfeeding. Excessive caution may lead health professionals to unnecessarily advise to interrupt breastfeeding, without assessing the latest evidence or considering the risk-benefit ratio of taking a medication versus terminating breastfeeding. To foster an appropriate approach toward the use of medications in breastfeeding women, the Italian Society of Perinatal Medicine created the following policy statement.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Analgesia by cooling vibration during venipuncture in children with cognitive impairment. - Schreiber, Silvana; Cozzi, Giorgio; Rutigliano, Rosaria; Assandro, Paola; Tubaro, Martina; Cortellazzo Wiel, Luisa; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Children with cognitive impairment experience pain more frequently than healthy children and are more likely to require venipuncture or intravenous cannulation for various procedures. They are frequently unable to report pain and often receive poor pain assessment and management. This study assessed the effectiveness of physical analgesia during vascular access in children with cognitive impairments. METHODS: We conducted a prospective randomised controlled study at a tertiary-level children's hospital in Italy from April to May 2015 to assess whether a cooling vibration device called Buzzy decreased pain during venipuncture and intravenous cannulation in children with cognitive impairment. None of the children had verbal skills and the main cognitive impairments were cerebral palsy, epileptic encephalopathy and genetic syndromes. RESULTS: We tested 70 children with a median age of nine years: 34 in the Buzzy group and 36 in the no-intervention group. Parents were trained in the use of the Noncommunicating Children's Pain Checklist - postoperative version scale, and they reported no or mild procedural pain in 32 cases (91.4%) in the Buzzy group and in 22 cases (61.1%) in the no-intervention group (p = 0.003). CONCLUSION: Cooling vibration analgesia during vascular access reduced pain in children with cognitive impairment.

The anti-leukemic activity of sodium dichloroacetate in p53mutated/null cells is mediated by a p53-independent ILF3/p21 pathway. - Agnoletto, Chiara; Brunelli, Laura; Melloni, Elisabetta; Pastorelli, Roberta; Casciano, Fabio; Rimondi, Erika; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2015)
B-chronic lymphocytic leukemia (B-CLL) patients harboring p53 mutations are invariably refractory to therapies based on purine analogues and have limited treatment options and poor survival. Having recently demonstrated that the mitochondria-targeting small molecule sodium dichloroacetate (DCA) exhibits anti-leukemic activity in p53wild-type B-CLL cells, the aim of this study was to evaluate the effect of DCA in p53mutated B-CLL cells and in p53mutated/null leukemic cell lines. DCA exhibited comparable cytotoxicity in p53wild-type and p53mutated B-CLL patient cell cultures, as well as in p53mutated B leukemic cell lines (MAVER, MEC-1, MEC-2). At the molecular level, DCA promoted the transcriptional induction of p21 in all leukemic cell types investigated, including p53null HL-60. By using a proteomic approach, we demonstrated that DCA up-regulated the ILF3 transcription factor, which is a known regulator of p21 expression. The role of the ILF3/p21 axis in mediating the DCA anti-leukemic activity was underscored by knocking-down experiments. Indeed, transfection with ILF3 and p21 siRNAs significantly decreased both the DCA-induced p21 expression and the DCA-mediated cytotoxicity. Taken together, our results emphasize that DCA is a small molecule that merits further evaluation as a therapeutic agent also for p53mutated leukemic cells, by acting through the induction of a p53-independent pathway.

Appendicitis in children less than five years old: A challenge for the general practitioner. - Marzuillo, Pierluigi; Germani, Claudio; Krauss, Baruch S; Barbi, Egidio (World J Clin Pediatr, 2015)
Acute appendicitis is one of the most common indications for abdominal surgery in pediatrics with peak incidence in the second decade of life. Acute appendicitis in the first years of life is an uncommon event. The clinical presentation is often varied and the diagnosis may be overshadowed by other medical conditions. Gastroenteritis is the most common misdiagnosis, with a history of diarrhea present in 33% to 41% of patients. Pain is the most common presenting symptom in children less than 5 years old, followed by vomiting, fever, anorexia and diarrhea. The most common physical sign is focal tenderness (61% of the patients) followed by guarding (55%), diffuse tenderness (39%), rebound (32%), and mass (6%). Neonatal appendicitis is a very rare disease with high mortality; presenting symptoms are nonspecific with abdominal distension representing the main clinical presentation. The younger the patient, the earlier perforation occurs: 70% of patients less than 3 years develop a perforation within 48 h of onset of symptoms. A timely diagnosis reduces the risk of complications. We highlight the epidemiology, pathophysiology, clinical signs and laboratory clues of appendicitis in young children and suggest an algorithm for early diagnosis.

Applications of nanoparticles in cancer medicine and beyond: optical and multimodal in vivo imaging, tissue targeting and drug delivery. - Biffi, Stefania; Voltan, Rebecca; Rampazzo, Enrico; Prodi, Luca; Zauli, Giorgio; Secchiero, Paola (Expert Opin Drug Deliv, 2015)
INTRODUCTION: Nanotechnology has opened up the way to the engineering of new organized materials endowed with improved performances. In the past decade, engineered nanoparticles (NPs) have been progressively implemented by exploiting synthetic strategies that yield complex materials capable of performing functions with applications also in medicine. Indeed, in the field of 'nanomedicine' it has been explored the possibility to design multifunctional nanosystems, characterized by high analytical performances and stability, low toxicity and specificity towards a given cell target. Area covered: In this review article, we summarize the advances in the engineering of NPs for biomedical applications, from optical imaging (OI) to multimodal OI and targeted drug delivery. For this purpose, we will provide some examples of how investigations in nanomedicine can support preclinical and clinical research generating innovative diagnostic and therapeutic strategies in oncology. Expert opinion: The progressive breakthroughs in nanomedicine have supported the development of multifunctional and multimodal NPs. In particular, NPs are significantly impacting the diagnostic and therapeutic strategies since they allow the development of: NP-based OI probes containing more than one modality-specific contrast agent; surface functionalized NPs for specific 'molecular recognition'. Therefore, the design and characterization of innovative NP-based systems/devices have great applicative potential into the medical field.

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

"Blaschkoid dyspigmentation" in a child: don't forget fibroblast chromosomal analysis. - Gortani, Giulia; Faletra, Flavio; Bruno, Irene; Berti, Irene; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Abnormalities, Multiple; Child, Preschool; Chromosomes; DNA; Female; Fibroblasts; Humans; Phenotype; Pigmentation Disorders

A brain and heart connection: X-linked periventricular heterotopia. - Naviglio, Samuele; Bruno, Irene; Zanus, Caterina; Faletra, Flavio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Adolescent; Brain; Diagnosis, Differential; DNA Mutational Analysis; Epilepsy; Female; Filamins; Humans; Magnetic Resonance Imaging; Mutation; Periventricular Nodular Heterotopia

Brain sparing effect in growth-restricted fetuses is associated with decreased cardiac acceleration and deceleration capacities: a case-control study. - Stampalija, T; Casati, D; Monasta, L; Sassi, R; Rivolta, M W; Muggiasca, M L; Bauer, A; Ferrazzi, E (BJOG, 2015)
OBJECTIVE: Phase rectified signal averaging (PRSA) is a new method of fetal heart rate variability (fHRV) analysis that quantifies the average acceleration (AC) and deceleration capacity (DC) of the heart. The aim of this study was to evaluate AC and DC of fHR [recorded by trans-abdominal fetal electrocardiogram (ta-fECG)] in relation to Doppler velocimetry characteristics of intrauterine growth restriction (IUGR). DESIGN: Prospective case-control study. SETTING: Single third referral centre. POPULATION: IUGR (n = 66) between 25 and 40 gestational weeks and uncomplicated pregnancies (n = 79). METHODS: In IUGR the nearest ta-fECG monitoring to delivery was used for PRSA analysis and Doppler velocimetry parameters obtained within 48 hours. AC and DC were computed at s = T = 9. The relation was evaluated between either AC or DC and Doppler velocimetry parameters adjusting for gestational age at monitoring, as well as the association between either AC or DC and IUGR with or without brain sparing. RESULTS: In IUGRs there was a significant association between either AC and DC and middle cerebral artery pulsatility index (PI; P = 0.01; P = 0.005), but the same was not true for uterine or umbilical artery PI (P > 0.05). Both IUGR fetuses with and without brain sparing had lower AC and DC than controls, but this association was stronger for IUGRs with brain sparing. CONCLUSIONS: Our study observed for the first time that AC and DC at PRSA analysis are associated with middle cerebral artery PI, but not with uterine or umbilical artery PI, and that there is a significant decrease of AC and DC in association with brain sparing in IUGR fetuses from 25 weeks of gestation to term. TWEETABLE ABSTRACT: Brain sparing in IUGR fetuses is associated with decreased acceleration and deceleration capacities of the heart.

Brain-derived neurotrophic factor serum levels in genetically isolated populations: gender-specific association with anxiety disorder subtypes but not with anxiety levels or Val66Met polymorphism. - Carlino, Davide; Francavilla, Ruggiero; Baj, Gabriele; Kulak, Karolina; d'Adamo, Pio; Ulivi, Sheila; Cappellani, Stefania; Gasparini, Paolo; Tongiorgi, Enrico (PeerJ, 2015)
Anxiety disorders (ADs) are disabling chronic disorders with exaggerated behavioral response to threats. This study was aimed at testing the hypothesis that ADs may be associated with reduced neurotrophic activity, particularly of Brain-derived neurotrophic factor (BDNF), and determining possible effects of genetics on serum BDNF concentrations. In 672 adult subjects from six isolated villages in North-Eastern Italy with high inbreeding, we determined serum BDNF levels and identified subjects with different ADs subtypes such as Social and Specific Phobias (PHSOC, PHSP), Generalized Anxiety Disorder (GAD), and Panic Disorder (PAD). Analysis of the population as a whole or individual village showed no significant correlation between serum BDNF levels and Val66Met polymorphism and no association with anxiety levels. Stratification of subjects highlighted a significant decrease in serum BDNF in females with GAD and males with PHSP. This study indicates low heritability and absence of any impact of the Val66Met polymorphism on circulating concentrations of BDNF. Our results show that BDNF is not a general biomarker of anxiety but serum BDNF levels correlate in a gender-specific manner with ADs subtypes.

Central venous access devices in pediatric malignancies: a position paper of Italian Association of Pediatric Hematology and Oncology. - Crocoli, Alessandro; Tornesello, Assunta; Pittiruti, Mauro; Barone, Angelica; Muggeo, Paola; Inserra, Alessandro; Molinari, Angelo Claudio; Grillenzoni, Valeria; Durante, Viviana; Cicalese, Maria Pia; Zanazzo, Giulio Andrea; Cesaro, Simone (J Vasc Access, 2015)
INTRODUCTION: Treatment of pediatric malignancies is becoming progressively more complex, implying the adoption of multimodal therapies. A reliable, long-lasting venous access represents one of the critical requirements for the success of those treatments. Recent technical innovations-such as minimally invasive procedures for placement, new devices and novel materials-have rapidly spread for clinical use in adult patients, but are still not consistently used in the pediatric population. METHODS: The Supportive Therapy Working Group of Italian Association of Hematology and Oncology (AIEOP) reviewed medical literature focusing on new aspects of central venous access devices (VADs) in pediatric patients affected by oncohematological diseases. RESULTS: Appropriate recommendations for clinical use in these patients have been discussed and formulated. CONCLUSIONS: The importance of the correct choice, management and use of VADs in pediatric oncohematological patients is a necessary prerequisite for an adequate standard of care, also considering the increased chances of cure and the longer life expectancy of those patients with modern therapies.

Cerebral oxygenation with different nasal continuous positive airway pressure levels in preterm infants. - Bembich, Stefano; Travan, Laura; Cont, Gabriele; Bua, Jenny; Strajn, Tamara; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2015)
OBJECTIVES: This study evaluates the effect of varying nasal continuous positive airway pressure (NCPAP) level on cerebral blood flow (CBF) and oxygenation in preterm infants. METHODS: Oxy-haemoglobin (HbO2) and total haemoglobin (HbTot), as CBF estimates, and the ratio between HbO2 and HbTot (HbO2/HbTot), as cerebral oxygenation estimate, were assessed by near-infrared spectroscopy in 26 stable preterm newborns at a postmenstrual age between 26 and 33 weeks. Baseline HbO2, HbTot and HbO2/HbTot values were initially collected with NCPAP at 5 cm H2O and then compared with values obtained with NCPAP levels at both 3 and 8 cm H2O. RESULTS: Compared with 5 cm H2O, cerebral HbO2, HbTot and HbO2/HbTot remained unchanged both after increasing (to 8 cm H2O) and decreasing (to 3 cm H2O) the NCPAP level. This result was observed both in regional areas (24 sites) and in the overall monitored area (frontal and parietal cortex). Compared with 8 cm H2O, peripheral oxygen saturation significantly decreased at 3 cm H2O (p=0.021). Heart rate did not change. CONCLUSIONS: No differences in CBF and cerebral oxygenation were observed with NCPAP levels in the range 3-8 cm H2O despite a decrease in peripheral oxygenation with 3 cm H2O.
Keywords: Cerebrovascular Circulation; Continuous Positive Airway Pressure; Female; Hemoglobins; Humans; Infant, Newborn; Infant, Premature; Intensive Care, Neonatal; Male; Nasal Cavity; Oxygen; Oxygen Consumption; Oxyhemoglobins; Spectroscopy, Near-Infrared

Characterization of 14 novel deletions underlying Rubinstein-Taybi syndrome: an update of the CREBBP deletion repertoire. - Rusconi, Daniela; Negri, Gloria; Colapietro, Patrizia; Picinelli, Chiara; Milani, Donatella; Spena, Silvia; Magnani, Cinzia; Silengo, Margherita Cirillo; Sorasio, Lorena; Curtisova, Vaclava; Cavaliere, Maria Luigia; Prontera, Paolo; et al. (Hum Genet, 2015)
Rubinstein-Taybi syndrome (RSTS) is a rare, clinically heterogeneous disorder characterized by cognitive impairment and several multiple congenital anomalies. The syndrome is caused by almost private point mutations in the CREBBP (~55% of cases) and EP300 (~8%) genes. The CREBBP mutational spectrum is variegated and characterized by point mutations (30-50 %) and deletions (~10%). The latter are diverse in size and genomic position and remove either the whole CREBBP gene and its flanking regions or only an intragenic portion. Here, we report 14 novel CREBBP deletions ranging from single exons to the whole gene and flanking regions which were identified by applying complementary cytomolecular techniques: fluorescence in situ hybridization, multiplex ligation-dependent probe amplification and array comparative genome hybridization, to a large cohort of RSTS patients. Deletions involving CREBBP account for 23% of our detected CREBBP mutations, making an important contribution to the mutational spectrum. Genotype-phenotype correlations revealed that patients with CREBBP deletions extending beyond this gene did not always have a more severe phenotype than patients harboring CREBBP point mutations, suggesting that neighboring genes play only a limited role in the etiopathogenesis of CREBBP-centerd contiguous gene syndrome. Accordingly, the extent of the deletion is not predictive of the severity of the clinical phenotype.
Keywords: Adolescent; Adult; Base Sequence; Child; Child, Preschool; Cohort Studies; CREB-Binding Protein; Female; Humans; Infant; Infant, Newborn; Male; Middle Aged; Point Mutation; Rubinstein-Taybi Syndrome; Sequence Deletion

Clinical aspects of Fanconi anemia individuals with the same mutation of FANCF identified by next generation sequencing. - Nicchia, Elena; Benedicenti, Francesco; Rocco, Daniela De; Greco, Chiara; Bottega, Roberta; Inzana, Francesca; Faleschini, Michela; Bonin, Serena; Cappelli, Enrico; Mogni, Massimo; Stanzial, Franco; Svahn, Johanna; et al. (Birth Defects Res A Clin Mol Teratol, 2015)
BACKGROUND: Fanconi anemia (FA) is a rare genetic disease characterized by congenital malformations, aplastic anemia and increased risk of developing malignancies. FA is genetically heterogeneous as it is caused by at least 17 different genes. Among these, FANCA, FANCC, and FANCG account for approximately 85% of the patients whereas the remaining genes are mutated in only a small percentage of cases. For this reason, the molecular diagnostic process is complex and not always extended to all the FA genes, preventing the characterization of individuals belonging to rare groups. METHODS: The FA genes were analyzed using a next generation sequencing approach in two unrelated families. RESULTS: The analysis identified the same, c.484_485del, homozygous mutation of FANCF in both families. A careful examination of three electively aborted fetuses in one family and one affected girl in the other indicated an association of the FANCF loss-of-function mutation with a severe phenotype characterized by multiple malformations. CONCLUSION: The systematic use of next generation sequencing will allow the recognition of individuals from rare complementation groups, a better definition of their clinical phenotypes, and consequently, an appropriate genetic counseling. Birth Defects Research (Part A) 103:1003-1010, 2015. © 2015 Wiley Periodicals, Inc.

Coeliac disease in the ERA of the new ESPGHAN and BSPGHAN guidelines: a prospective cohort study. - Benelli, Elisa; Carrato, Valentina; Martelossi, Stefano; Ronfani, Luca; Not, Tarcisio; Ventura, Alessandro (Arch Dis Child, 2015)
OBJECTIVE: To evaluate the consequences of the last European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) and British Society of Paediatric Gastroenterology, Hepatology and Nutrition (BSPGHAN) guidelines for the diagnosis of coeliac disease (CD) by means of a prospective study. DESIGN: Prospective cohort study. SETTING: Institute for Maternal and Child Health IRCCS Burlo Garofolo (Trieste, Italy). PATIENTS: Children diagnosed with CD without a duodenal biopsy (group 1), following the last ESPGHAN and BSPGHAN guidelines, and children diagnosed with a duodenal biopsy, matched for sex, age and year of diagnosis (group 2), were prospectively enrolled over a 3-year period. All patients were put on a gluten-free diet (GFD) and were followed up for clinical conditions and laboratory testing at 6 months every year since diagnosis (median follow up: 1.9 years). OUTCOME MEASURES: Resolution of symptoms, body mass index, laboratory testing (haemoglobin, anti-transglutaminase IgA), adherence to a GFD, quality of life, and supplementary post-diagnosis medical consultations. RESULTS: 51 out of 468 (11%) patients were diagnosed without a duodenal biopsy (group 1; median age 2.1 years) and matched to 92 patients diagnosed with a biopsy (group 2; median age 2.4 years). At the end of follow-up the two groups were statistically comparable in terms of clinical and nutritional status, anti-transglutaminase IgA antibody titres, quality of life, adherence to a GFD, and number of supplementary medical consultations. CONCLUSIONS: On the basis of this prospective study, diagnosis of CD can be reliably performed without a duodenal biopsy in approximately 11% of cases. At least during a medium-term follow-up, this approach has no negative consequences relating to clinical remission, adherence to diet, and quality of life of children with CD.

The combination of N-acetyl cysteine, alpha-lipoic acid, and bromelain shows high anti-inflammatory properties in novel in vivo and in vitro models of endometriosis. - Agostinis, C; Zorzet, S; De Leo, R; Zauli, G; De Seta, F; Bulla, R (Mediators Inflamm, 2015)
To evaluate the efficacy of an association of N-acetyl cystein, alpha-lipoic acid, and bromelain (NAC/LA/Br) in the treatment of endometriosis we set up a new in vivo murine model. We explored the anti-inflammatory and proapoptotic effect of this combination on human endometriotic endothelial cells (EECs) and on endothelial cells isolated from normal uterus (UtMECs). We implanted fragments of human endometriotic cysts intraperitoneally into SCID mice to evaluate the efficacy of NAC/LA/Br treatment. UtMECs and EECs, untreated or treated with NAC/LA/Br, were activated with the proinflammatory stimulus TNF-α and their response in terms of VCAM1 expression was evaluated. The proapoptotic effect of higher doses of NAC/LA/Br on UtMECs and EECs was measured with a fluorogenic substrate for activated caspases 3 and 7. The preincubation of EECs with NAC/LA/Br prior to cell stimulation with TNF-α prevents the upregulation of the expression of the inflammatory "marker" VCAM1. Furthermore NAC/LA/Br were able to induce EEC, but not UtMEC, apoptosis. Finally, the novel mouse model allowed us to demonstrate that mice treated with NAC/LA/Br presented a lower number of cysts, smaller in size, compared to untreated mice. Our findings suggest that these dietary supplements may have potential therapeutic uses in the treatment of chronic inflammatory diseases like endometriosis.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

The diagnostic challenge of very early-onset enterocolitis in an infant with XIAP deficiency. - Girardelli, Martina; Arrigo, Serena; Barabino, Arrigo; Loganes, Claudia; Morreale, Giuseppe; Crovella, Sergio; Tommasini, Alberto; Bianco, Anna Monica (BMC Pediatr, 2015)
BACKGROUND: Aggressive course and resistance to treatments usually characterize very early onset inflammatory bowel disease (VEO-IBD). Some VEO-IBD cases are due to monogenic immune defects and can benefit from hematopoietic stem cell transplantation (HSCT). CASE PRESENTATION: We describe a Caucasian male baby who presented in the first months of life macrophage activation syndrome, followed by intractable colitis, recurrent episodes of fever and mild splenomegaly. After several immunological, genetic and clinical investigations, subsequently a therapeutic attempt with colectomy, analysis of VEO-IBD-associated genes, revealed a causative mutation in XIAP. The genetic diagnosis of a primary immune deficiency allowed curing the boy with hematopoietic stem cell transplantation. CONCLUSION: Our report, together with novel findings from recent literature, should contribute to increase awareness of monogenic immune defects as a cause of VEO-IBD. Comprehensive genetic analysis can allow a prompt diagnosis, resulting in the choice of effective treatments and sparing useless and damaging procedures.

Diagnostic criteria currently proposed for "ictal epileptic headache": Perspectives on strengths, weaknesses and pitfalls. - Parisi, Pasquale; Verrotti, Alberto; Costa, Paola; Striano, Pasquale; Zanus, Caterina; Carrozzi, Marco; Raucci, Umberto; Villa, Maria Pia; Belcastro, Vincenzo (Seizure, 2015)
PURPOSE: When we published the diagnostic criteria for "ictal epileptic headache" in 2012, we deliberately and consciously chose to adopt restrictive criteria that probably underestimate the phenomenon, rather than spread panic among patients and physicians who are reluctant to accept this entity. METHODS: Here we discuss four intriguing clinical cases to highlight why we believe, to this day, that it is necessary to follow these restrictive diagnostic criteria. CONCLUSIONS: EEG is not recommended as a routine examination for children diagnosed with headache, but it is mandatory and must be carried out promptly in cases of prolonged headache that does not respond to antimigraine drugs, if epilepsy is suspected or has been diagnosed previously. This is not a marginal or irrelevant question because possible isolated, non-motor, ictal manifestations should be taken into account before declaring that an epileptic patient is "seizure free" so as to ensure that any decision taken to suspend anticonvulsant therapy is safe.

Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Effect of seminal leukocytes on in vitro fertilization and intracytoplasmic sperm injection outcomes. - Ricci, Giuseppe; Granzotto, Marilena; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Zito, Gabriella; Borelli, Massimo (Fertil Steril, 2015)
OBJECTIVE: To investigate the influence of seminal leukocytes on conventional IVF and intracytoplasmic sperm injection (ICSI) outcomes, using a flow cytometry method. DESIGN: Prospective study. SETTING: Tertiary infertility center and research institute. PATIENT(S): One hundred sixty-four couples undergoing conventional IVF or ICSI. INTERVENTION(S): Seminal leukocytes were counted by flow cytometry. MAIN OUTCOME MEASURE(S): Correlation between seminal leukocytes concentration and reproductive outcomes in IVF and ICSI cycles. RESULT(S): The median number of oocytes retrieved, the fertilization and cleavage rate, the median number and grade of embryos transferred, the median number of good-quality embryos transferred, and the median percentage of good-quality embryos from total embryos transferred, in leukocytospermic and non-leukocytospermic patients were not statistically different after either IVF or ICSI. Similarly, there were no significant differences between the two groups for implantation rate and clinical pregnancy rate. Multivariate logistic regression analysis showed that the reproductive outcomes were not influenced by adjustment for female age, infertility diagnosis, number of previous attempts, treatment protocol (GnRH agonist or antagonist), assisted reproduction procedure (IVF or ICSI), and leukocytospermia. By profiling the proper Poisson regression models, no leukocytospermia cut-off value was able to identify the subjects at risk for oocyte fertilization or embryo cleavage failure. CONCLUSION(S): Using a flow cytometry method, we demonstrated that leukocytospermia does not significantly influence IVF or ICSI outcomes. The same results were obtained by using lower or higher cut-off values for leukocytospermia (from 0.2 to 2 × 10(6)/mL).
Keywords: Adult; Female; Fertilization in Vitro; Flow Cytometry; Humans; Leukocytes; Male; Pregnancy; Pregnancy Rate; Prospective Studies; Semen; Sperm Injections, Intracytoplasmic

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Fainting Starting Parenteral Nutrition. - Pederiva, Federica; Barbi, Egidio; Zennaro, Floriana; Neri, Elena (Pediatr Emerg Care, 2015)
Complications such as mechanical accidents, infections, and thrombosis are commonly described in the presence of a central venous catheter. We present a case of a boy who had fainting episodes due to dislocation of a central venous catheter.

Fever tree revisited: From malaria to autoinflammatory diseases. - Pastore, Serena; Vuch, Josef; Bianco, Anna Monica; Taddio, Andrea; Tommasini, Alberto (World J Clin Pediatr, 2015)
Over the centuries the idea of recurrent fevers has mainly been associated with malaria, but many other fevers, such as typhoid and diphtheria were cause for concern. It is only in recent times, with the more severe forms of fever from infectious origin becoming less frequent or a cause for worry that we started noticing recurrent fevers without any clear infectious cause, being described as having a pathogenesis of autoinflammatory nature. The use of molecular examinations in many cases can allow a diagnosis where the cause is monogenic. In other cases, however the pathogenesis is likely to be multifactorial and the diagnostic-therapeutic approach is strictly clinical. The old fever tree paradigm developed to describe fevers caused by malaria has been revisited here to describe today's periodic fevers from the periodic fever adenitis pharyngitis aphthae syndrome to the more rare autoinflammatory diseases. This model may allow us to place cases that are yet to be identified which are likely to be of multifactorial origin.

Ficolin Gene Polymorphisms in Systemic Lupus Erythematosus and Rheumatoid Arthritis. - Addobbati, Catarina; De Azevêdo Silva, Jaqueline; A C Tavares, Nathália; Monticielo, Odirlei; M Xavier, Ricardo; T Brenol, João Carlos; Crovella, Sergio; B Chies, José Artur; Sandrin-Garcia, Paula (Ann Hum Genet, 2015)
Systemic lupus erythemathosus (SLE) and rheumatoid arthritis (RA) are complex autoimmune diseases characterized by an immune balance breakdown and by chronic inflammation. Several findings link SLE and RA development with the complement system and ficolin components have emerged as candidates for disease development. Since genetic association studies with ficolin genes in SLE and RA have not yet been conducted in a Brazilian population, the aim of this study was to determine whether polymorphisms of ficolin-1(FCN1) and ficolin-2 (FCN2) genes are associated with SLE and RA susceptibility as well as disease manifestation. Two SNPs within FCN1 (rs2989727 and 1071583) and three in FCN2 (rs17514136, rs3124954, and rs7851696) were studied in 208 SLE and184 RA patients as well as 264 healthy individuals in a Southeast Brazilian population. For SLE patients, the FCN2 rs17514136 SNP was associated with a more severe disease (SLICC) (p = 0.0067). Furthermore, an association between the occurrence of nephritis and the T/T genotype for FCN2 rs3124954 SNP (p = 0.047, OR = 3.17, 95%CI = 1.34-7.5) was observed. No association was observed between the studied polymorphisms and RA development. Thus, our data support involvement of the FCN2 gene in the SLE phenotype.

Food protein-induced enterocolitis syndrome caused by fish and/or shellfish in Italy. - Miceli Sopo, Stefano; Monaco, Serena; Badina, Laura; Barni, Simona; Longo, Giorgio; Novembre, Elio; Viola, Serena; Monti, Giovanna (Pediatr Allergy Immunol, 2015)
BACKGROUND: The study describes the demographic features, culprit foods, clinical features and outcomes for children presenting with acute fish and/or shellfish food protein-induced enterocolitis syndrome (FPIES) in four Italian paediatric allergy centres. METHODS: A retrospective/prospective study was undertaken. All children diagnosed with fish or shellfish FPIES were enrolled. The diagnosis of FPIES was based on Sicherer's or Miceli Sopo clinical criteria. Skin prick tests (SPT) were performed in all patients, at the time of diagnosis and prior to OFC. RESULTS: Seventy children were enrolled. Mean age at first episode was 14 months (range 6-46 months); mean age at diagnosis was 34 months (range 6-164 months). Sole and cod were the fish most commonly implicated. Fifty-seven of 70 (81%) children had FPIES exclusively to fish, 37 of 57 (65%) children had single-fish FPIES, 20 of 57 (35%) multiple-fish FPIES, nine of 70 (13%) presented adverse reactions exclusively to shellfish, and four of 70 (6%) presented adverse reactions to both fish and shellfish. Only four (5.7%) children presented episodes of acute FPIES with different foods (2 to cow's milk, 1 to egg, 1 to beef); in all cases, onset was prior to that of fish or shellfish FPIES. Fifteen of 70 (21%) children tolerated fish other than the offending fish. Twenty-four of 70 (34%) children achieved tolerance (age range 24-102 months). CONCLUSIONS: The chief peculiarities of acute fish and shellfish FPIES, compared to more frequent cow's milk or soy FPIES, are (i) later age of onset, (ii) longer persistence and (iii) possibility of tolerating fish other than the offending fish. Adverse reactions with shellfish are possible.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genetic testing and genomic analysis: a debate on ethical, social and legal issues in the Arab world with a focus on Qatar. - El Shanti, Hatem; Chouchane, Lotfi; Badii, Ramin; Gallouzi, Imed Eddine; Gasparini, Paolo (J Transl Med, 2015)
In 2013 both Saudi Arabia and Qatar launched genome projects with the aim of providing information for better diagnosis, treatment and prevention of diseases and, ultimately to realize personalized medicine by sequencing hundred thousands samples. These population based genome activities raise a series of relevant ethical, legal and social issues general, related to the specific population structure as well as to the Islamic perspective on genomic analysis and genetic testing. To contribute to the debate, the Authors after reviewing the existing literature and taking advantage of their professional experience in the field and in the geographic area, discuss and provide their opinions. In particular, the Authors focus on the impact of consanguinity on population structure and disease frequency in the Arab world, on genetic testing and genomic analysis (i.e. technical aspects, impact, etc.) and on their regulations. A comparison between the Islamic perspective and the ethical, social and legal issues raised in other population contexts is also carried. In conclusion, this opinion article with an up-to-date contribution to the discussion on the relevance and impact of genomic analysis and genetic testing in the Arab world, might help in producing specific national guidelines on genetic testing and genomic analysis and help accelerate the implementation and roll out of genome projects in Muslim countries and more specifically in Qatar, and other countries of the Gulf.

Genetics of inflammatory bowel disease from multifactorial to monogenic forms. - Bianco, Anna Monica; Girardelli, Martina; Tommasini, Alberto (World J Gastroenterol, 2015)
Inflammatory bowel disease (IBD) is a group of chronic multifactorial disorders. According to a recent study, the number of IBD association loci is increased to 201, of which 37 and 27 loci contribute specifically to the development of Crohn's disease and ulcerative colitis respectively. Some IBD associated genes are involved in innate immunity, in the autophagy and in the inflammatory response such as NOD2, ATG16L1 and IL23R, while other are implicated in immune mediated disease (STAT3) and in susceptibility to mycobacterium infection (IL12B). In case of early onset of IBD (VEO-IBD) within the 6(th) year of age, the disease may be caused by mutations in genes responsible for severe monogenic disorders such as the primary immunodeficiency diseases. In this review we discuss how these monogenic disorders through different immune mechanisms can similarly be responsible of VEO-IBD phenotype. Moreover we would highlight how the identification of pathogenic genes by Next Generation Sequencing technologies can allow to obtain a rapid diagnosis and to apply specific therapies.

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on normal hearing function identifies PCDH20 and SLC28A3 as candidates for hearing function and loss. - Vuckovic, Dragana; Dawson, Sally; Scheffer, Deborah I; Rantanen, Taina; Morgan, Anna; Di Stazio, Mariateresa; Vozzi, Diego; Nutile, Teresa; Concas, Maria P; Biino, Ginevra; Nolan, Lisa; Bahl, Aileen; et al. (Hum Mol Genet, 2015)
Hearing loss and individual differences in normal hearing both have a substantial genetic basis. Although many new genes contributing to deafness have been identified, very little is known about genes/variants modulating the normal range of hearing ability. To fill this gap, we performed a two-stage meta-analysis on hearing thresholds (tested at 0.25, 0.5, 1, 2, 4, 8 kHz) and on pure-tone averages (low-, medium- and high-frequency thresholds grouped) in several isolated populations from Italy and Central Asia (total N = 2636). Here, we detected two genome-wide significant loci close to PCDH20 and SLC28A3 (top hits: rs78043697, P = 4.71E-10 and rs7032430, P = 2.39E-09, respectively). For both loci, we sought replication in two independent cohorts: B58C from the UK (N = 5892) and FITSA from Finland (N = 270). Both loci were successfully replicated at a nominal level of significance (P < 0.05). In order to confirm our quantitative findings, we carried out RT-PCR and reported RNA-Seq data, which showed that both genes are expressed in mouse inner ear, especially in hair cells, further suggesting them as good candidates for modulatory genes in the auditory system. Sequencing data revealed no functional variants in the coding region of PCDH20 or SLC28A3, suggesting that variation in regulatory sequences may affect expression. Overall, these results contribute to a better understanding of the complex mechanisms underlying human hearing function.

Germline mutations in ETV6 are associated with thrombocytopenia, red cell macrocytosis and predisposition to lymphoblastic leukemia. - Noetzli, Leila; Lo, Richard W; Lee-Sherick, Alisa B; Callaghan, Michael; Noris, Patrizia; Savoia, Anna; Rajpurkar, Madhvi; Jones, Kenneth; Gowan, Katherine; Balduini, Carlo L; Pecci, Alessandro; Gnan, Chiara; et al. (Nat Genet, 2015)
Some familial platelet disorders are associated with predisposition to leukemia, myelodysplastic syndrome (MDS) or dyserythropoietic anemia. We identified a family with autosomal dominant thrombocytopenia, high erythrocyte mean corpuscular volume (MCV) and two occurrences of B cell-precursor acute lymphoblastic leukemia (ALL). Whole-exome sequencing identified a heterozygous single-nucleotide change in ETV6 (ets variant 6), c.641C>T, encoding a p.Pro214Leu substitution in the central domain, segregating with thrombocytopenia and elevated MCV. A screen of 23 families with similar phenotypes identified 2 with ETV6 mutations. One family also had a mutation encoding p.Pro214Leu and one individual with ALL. The other family had a c.1252A>G transition producing a p.Arg418Gly substitution in the DNA-binding domain, with alternative splicing and exon skipping. Functional characterization of these mutations showed aberrant cellular localization of mutant and endogenous ETV6, decreased transcriptional repression and altered megakaryocyte maturation. Our findings underscore a key role for ETV6 in platelet formation and leukemia predisposition.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Erythrocytes, Abnormal; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; Germ-Line Mutation; HEK293 Cells; Hematologic Diseases; Humans; Male; Mutation, Missense; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Proto-Oncogene Proteins c-ets; Repressor Proteins; Thrombocytopenia

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

An IBCLC in the Maternity Ward of a Mother and Child Hospital: A Pre- and Post-Intervention Study. - Chiurco, Antonella; Montico, Marcella; Brovedani, Pierpaolo; Monasta, Lorenzo; Davanzo, Riccardo (Int J Environ Res Public Health, 2015)
Published evidence on the impact of the integration of International Board Certified Lactation Consultants (IBCLCs) for breastfeeding promotion is growing, but still relatively limited. Our study aims at evaluating the effects of adding an IBCLC for breastfeeding support in a mother and child hospital environment. We conducted a prospective study in the maternity ward of our maternal and child health Institute, recruiting 402 mothers of healthy term newborns soon after birth. The 18-month intervention of the IBCLC (Phase II) was preceded (Phase I) by data collection on breastfeeding rates and factors related to breastfeeding, both at hospital discharge and two weeks later. Data collection was replicated just before the end of the intervention (Phase III). In Phase III, a significantly higher percentage of mothers: (a) received help to breastfeed, and also received correct information on breastfeeding and community support, (b) started breastfeeding within two hours from delivery, (c) reported a good experience with the hospital staff. Moreover, the frequency of sore and/or cracked nipples was significantly lower in Phase III. However, no difference was found in exclusive breastfeeding rates at hospital discharge or at two weeks after birth.

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Immunologic evidence of a strong association between non-Hodgkin lymphoma and simian virus 40. - Tognon, Mauro; Luppi, Mario; Corallini, Alfredo; Taronna, Angelo; Barozzi, Patrizia; Rotondo, John Charles; Comar, Manola; Casali, Maria Vittoria; Bovenzi, Massimo; D'Agostino, Antonio; Vinante, Fabrizio; Rigo, Antonella; et al. (Cancer, 2015)
BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed to detect specific antibodies against SV40. Serum samples were taken from 2 distinct cohorts of NHL-affected patients (NHL1 [n = 89] and NHL2 [n = 61]) along with controls represented by oncologic patients affected by breast cancer (BC; n = 78) and undifferentiated nasopharyngeal carcinoma (UNPC; n = 64) and 3 different cohorts of healthy subjects (HSs; HS1 [n = 130], HS2 [n = 83], and HS3 [n = 87]). RESULTS: Immunologic data indicated that in serum samples from NHL patients, antibodies against SV40 mimotopes were detectable with a prevalence of 40% in NHL1 patients and with a prevalence of 43% in NHL2 patients. In HSs of the same median age as NHL patients, the prevalence was 16% for the HS1 group (57 years) and 14% for the HS2 group (65 years). The difference was statistically significant (P < .0001 and P < .001). Interestingly, the difference between NHL1/NHL2 patients and BC patients (40%/43% vs 15%, P < .001) and between NHL1/NHL2 patients and UNPC patients (40%/43% vs 25%, P < .05) was significant. CONCLUSIONS: Our data indicate a strong association between NHL and SV40 and thus a need for innovative therapeutic approaches for this hematologic malignancy.
Keywords: Adult; Aged; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lymphoma, Non-Hodgkin; Male; Middle Aged; Polyomavirus Infections; Seroepidemiologic Studies; Simian virus 40; Tumor Virus Infections

Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2015)
OBJECTIVES: Human β-defensin 1 (hBD-1) is an antimicrobial peptide involved in epithelial defence of various tissues, also present in the saliva. Individual genetic variations within the DEFB1 gene, encoding for hBD-1, could influence gene expression and protein production. DESIGN: Three DEFB1 polymorphisms at 5' untranslated region (UTR), -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362), and two polymorphisms at DEFB1 3' UTR, c*5G > A (rs1047031) and c*87A > G (rs1800971), were analysed by direct sequencing and correlated with hDB-1 salivary concentration (tested with enzyme-linked immunosorbent assay (ELISA)) in 40 healthy subjects. RESULTS: Significant associations were found between individuals presenting different DEFB1 polymorphisms at positions -52 and -44 of the gene and hBD-1 salivary concentrations: -52 G/G carriers had higher levels of protein than G/A and A/A; -44C/G subjects showed a higher protein concentration than homozygous wild-type C/C. For the -20G > A, c*5G > A and c*87A > G polymorphisms, no statistically significant differences were found. Combined haplotype analysis confirmed the results obtained considering the single-nucleotide polymorphisms (SNPs) singularly. CONCLUSION: Polymorphisms in the DEFB1 gene influence hBD-1 production and, therefore, could modify the innate immune system responses and, consequently, the oral health.

Impact of Surgery for Neonatal Gastrointestinal Diseases on Weight and Fat Mass. - De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (J Pediatr, 2015)
OBJECTIVE: To compare growth, fat mass (FM), and fat-free mass in surgical infants vs matched controls at similar postconceptional age (PCA). STUDY DESIGN: Anthropometric and body composition measurements by air-displacement plethysmography (PeaPod-Infant Body Composition System; LMI, Concord, California) were performed at the same PCA in 21 infants who received gastrointestinal surgery and in 21 controls matched for gestational age, birth weight, and sex. RESULTS: Despite similar anthropometry at birth, postsurgical infants were shorter (50.4 [4.7] cm vs 53.2 [4.1] cm, P = .001), lighter (3516 [743] g vs 3946 [874] g, P < .001), and had lower FM content (%FM 14.8 [4.7]% vs 20.2 [5.8]%, P < .0001) than their peers at similar PCA (43 [4] weeks). All surgical infants but 1 (20/21) received parenteral nutrition (PN). Mean PN duration was 40 (30) days. Five infants in the control group received PN because of prematurity for 15 (9-30) days. Nine infants in the surgical group and 1 in the control group had PN-associated cholestasis. CONCLUSIONS: Neonates having surgery for gastrointestinal diseases were shorter, had lower weight, and lower FM content than their peers, despite receiving more PN. Body composition evaluation and monitoring may help optimize growth in these newborns.

Increased rate of deleterious variants in long runs of homozygosity of an inbred population from Qatar. - Mezzavilla, Massimo; Vozzi, Diego; Badii, Ramin; Alkowari, Moza Khalifa; Abdulhadi, Khalid; Girotto, Giorgia; Gasparini, Paolo (Hum Hered, 2015)
OBJECTIVE: The aim of this study is to evaluate the fraction of putatively deleterious variants within genomic runs of homozygosity (ROH) regions in an inbred and selected cohort of Qatari individuals. METHODS: High-density SNP array analysis was performed in 36 individuals, and for 14 of them whole-exome sequencing (WES) was also carried out. RESULTS: In all individuals, regions characterized by a high (hotspot) or low (coldspot) degree of homozygosity in all the analysed individuals were mapped, and the most frequent hotspot regions were selected. WES data were exploited to identify the single nucleotide variations (SNVs) harboured by genes located within both regions in each individual. Evolutionary conservation-based algorithms were employed to predict the potential deleteriousness of SNVs. The amount of in silico predicted deleterious SNVs was significantly different (p < 0.05) between homozygosity hotspot and coldspot regions. CONCLUSION: Genes located within ROH hotspot regions contain a significant burden of predicted putatively deleterious variants compared to genes located outside these regions, suggesting inbreeding as a possible mechanism allowing an enrichment of putatively deleterious variants at the homozygous state.
Keywords: Cohort Studies; Consanguinity; Homozygote; Humans; Mutation; Polymorphism, Single Nucleotide; Qatar

Insights from Cardiac Mechanics after Three Decades from Successfully Repaired Aortic Coarctation. - Faganello, Giorgio; Fisicaro, Maurizio; Russo, Giulia; Iorio, Anita; Mazzone, Carmine; Grande, Eliana; Humar, Franco; Cherubini, Antonella; Pandullo, Claudio; Barbati, Giulia; Tarantini, Luigi; Benettoni, Alessandra; et al. (Congenit Heart Dis, 2015)
BACKGROUND AND AIMS: Patients who underwent a successful repair of the aortic coarctation show chronic hyperdynamic state and normal left ventricular (LV) geometry; however, there are few data regarding the LV systolic function in the long term. Accordingly, we assessed LV systolic mechanics and factors associated with LV systolic dysfunction (LVSD) in patients with repaired CoA. METHODS: Clinical and echocardiographic data from 19 repaired CoA were analyzed 28 ± 13 years after surgery. Stress-corrected midwall shortening (sc-MS) and mitral annular peak systolic velocity (S') were analyzed as indexes of LV circumferential and longitudinal systolic function, respectively. Echocardiographic data of CoA patients were compared with 19 patients matched for age and hypertension and 38 healthy controls. Sc-MS was considered impaired if <89%, S' if <8.5 cm/s (10th percentiles of healthy controls, respectively). RESULTS: There were no statistical differences between study groups in LV volumes, mass and geometry. LV ejection fraction and Sc-MS were similar in all groups, however, CoA group had a significantly lower peak S' in comparison with matched and healthy controls (7.1 ± 1.3, 10.3 ± 1.9, and 11.1 ± 1.5, respectively; all P < 0.001). Prevalence of longitudinal LVSD defined as low S' was 84% in CoA, 13% in matched, and 5% in healthy control group (all P<0.05). Multivariate logistic regression analysis revealed that low peak S' was independently related to higher E/E' ratio and the presence of CoA. CONCLUSIONS: Patients who underwent a successful repair of CoA commonly show asymptomatic longitudinal LVSD associated with worse LV diastolic function in the long-term follow-up.

Intranasal adminsitration of oxytocin in postnatal depression: implications for psychodynamic psychotherapy from a randomized double-blind pilot study. - Clarici, Andrea; Pellizzoni, Sandra; Guaschino, Secondo; Alberico, Salvatore; Bembich, Stefano; Giuliani, Rosella; Short, Antonia; Guarino, Giuseppina; Panksepp, Jaak (Front Psychol, 2015)
Oxytocin is a neuropeptide that is active in the central nervous system and is generally considered to be involved in prosocial behaviors and feelings. In light of its documented positive effect on maternal behavior, we designed a study to ascertain whether oxytocin exerts any therapeutic effects on depressive symptoms in women affected by maternal postnatal depression. A group of 16 mothers were recruited in a randomized double-blind study: the women agreed to take part in a brief course of psychoanalytic psychotherapy (12 sessions, once a week) while also being administered, during the 12-weeks period, a daily dose of intranasal oxytocin (or a placebo). The pre-treatment evaluation also included a personality assessment of the major primary-process emotional command systems described by Panksepp () and a semi-quantitative assessment by the therapist of the mother's depressive symptoms and of her personality. No significant effect on depressive symptomatology was found following the administration of oxytocin (as compared to a placebo) during the period of psychotherapy. Nevertheless, a personality trait evaluation of the mothers, conducted in our overall sample group, showed a decrease in the narcissistic trait only within the group who took oxytocin. The depressive (dysphoric) trait was in fact significantly affected by psychotherapy (this effect was only present in the placebo group so it may reflect a positive placebo effect enhancing the favorable influence of psychotherapy on depressive symptoms) but not in the presence of oxytocin. Therefore, the neuropeptide would appear to play some role in the modulation of cerebral functions involved in the self-centered (narcissistic) dimension of the suffering that can occur with postnatal depression. Based on these results, there was support for our hypothesis that what is generally defined as postnatal depression may include disturbances of narcissistic affective balance, and oxytocin supplementation can counteract that type of affective disturbance. The resulting improvements in well-being, reflected in better self-centering in post-partuent mothers, may in turn facilitate better interpersonal acceptance of (and interactions with) the child and thereby, improved recognition of the child's needs.

Intrapartum fetal heart rate monitoring interpretation in labour: a critical appraisal. - Maso, G; Piccoli, M; De Seta, F; Parolin, S; Banco, R; Camacho Mattos, L; Bogatti, P; Alberico, S (Minerva Ginecol, 2015)
Electronic fetal monitoring (EFM) has been introduced in the obstetrics practice as a test to identify the first signs of fetal deterioration, allowing a prompt intervention to reduce neonatal morbidity and mortality. However, results from clinical trials fail to demonstrate a clear benefit with the use of EFM. No decrease in the incidence of cerebral palsy due to intrapartum asphyxia has been achieved and a significant increase in the rate of operative deliveries and in medico-legal litigations has been observed instead. Despite the lack of evidence supporting its safety and effectiveness, this method is routinely used in the clinical practice and periodical updated guidelines to standardize the method of interpretation and proper actions are proposed. However, limitations still exist and the unavoidable consequences are the increasing rate of caesarean delivery, partly due to a defensive attitude in medical choices, and medico-legal litigations for presumed inappropriate evaluation in case of perinatal adverse event. While Obstetrics Societies are trying to "fight" the rise in caesarean section rates, intrapartum EFM tracings are taken in the court proceedings as one of the main evidences in case of adverse event. The aim of this review is to discuss the limitations of guidelines dealing with intrapartum EFM and the pathophysiological basis to assess the suspicious tracings which represent the most observed and critical issue of EFM interpretation.

Lactotransferrin gene functional polymorphisms do not influence susceptibility to human immunodeficiency virus-1 mother-to-child transmission in different ethnic groups. - Zupin, Luisa; Polesello, Vania; Coelho, Antônio Victor Campos; Boniotto, Michele; Arraes, Luiz Claudio; Segat, Ludovica; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2015)
Lactotransferrin, also known as lactoferrin, is an iron binding glycoprotein that displays antiviral activity against many different infectious agents, including human immunodeficiency virus (HIV)-1. Lactotransferrin is present in the breast milk and in the female genitourinary mucosa and it has been hypothesised as a possible candidate to prevent mother-to-child HIV-1 transmission. To verify if two functional polymorphisms, Thr29Ala and Arg47Lys, in the lactotransferrin encoding gene (LTF) could affect HIV-1 infection and vertical transmission, a preliminary association study was performed in 238 HIV-1 positive and 99 HIV-1 negative children from Brazil, Italy, Africa and India. No statistically significant association for the Thr29Ala and Arg47Lys LTF polymorphisms and HIV-1 susceptibility in the studied populations was found. Additionally LTF polymorphisms frequencies were compared between the four different ethnic groups.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Brazil; Child; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; HIV-1; Humans; India; Infant, Newborn; Infectious Disease Transmission, Vertical; Italy; Lactoferrin; Male; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction; Retrospective Studies; Zimbabwe

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Legius syndrome: case report and review of literature. - Benelli, Elisa; Bruno, Irene; Belcaro, Chiara; Ventura, Alessandro; Berti, Irene (Ital J Pediatr, 2015)
A 8-month-old child was referred to our Dermatologic Unit for suspected Neurofibromatosis type 1 (NF 1), because of the appearance, since few days after birth, of numerous café-au-lait spots (seven larger than 5 mm); no other sign evocative of NF 1 was found. Her family history was remarkable for the presence of multiple café-au-lait spots in the mother, the grandfather and two aunts. The family had been already examined for NF 1, but no sign evocative of the disease was found. We then suspected Legius syndrome, a dominant disease characterized by a mild neurofibromatosis 1 phenotype. The diagnosis was confirmed by the finding of a mutation in SPRED1 gene, a feedback regulator of RAS/MAPK signaling. Here, we discuss the differential diagnosis of cafè-au-lait spots and we briefly review the existing literature about Legius syndrome.

Leptin/adiponectin ratio predicts poststroke neurological outcome. - Carbone, Federico; Burger, Fabienne; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; Bertolotto, Maria; Dallegri, Franco; Mach, François; Fainardi, Enrico; et al. (Eur J Clin Invest, 2015)
BACKGROUND AND AIMS: Different adipokines have been associated with atherosclerotic plaque rupture and cardiovascular events, such as acute ischaemic stroke (AIS). However, the potential role of these molecules in postischaemic brain injury remains largely unknown. METHODS AND METHODS: We performed a substudy analysis on nonobese patients with first atherothrombotic stroke (n = 35) from a recently published prospective cohort. Primary endpoint was to investigate the predictive value of serum leptin/adiponectin ratio on neurological recovery at 90 days after AIS. The secondary endpoint was the predictive value of serum adipokine levels of clinical and radiological outcomes at a shorter follow-up (at days 1 and 7 after AIS). The radiological evaluation included ischaemic lesion volume and haemorrhagic transformation (HT). The clinical examination was based on National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). RESULTS: At day 1 after AIS, serum leptin and leptin/adiponectin ratio were increased and inversely correlated with both radiological and clinical parameters at all follow-up time points. Once identified the best cut-off points by receiver operating characteristic (ROC) analysis, risk analysis showed that higher circulating leptin improved neurological recovery at day 90. In addition, leptin/adiponectin ratio maintained statistical significance after adjustment for age, gender and thrombolysis, also predicting the occurrence of HT in the first 7 days after AIS (adjusted OR 0·15 [95% CI 0·03-0·83); P = 0·030]). CONCLUSIONS: Higher leptin/adiponectin ratio at day 1 predicted better neurological outcomes in patients with atherothrombotic AIS and might be potentially useful as a prognostic biomarker of the disease.

Life-threatening unilateral hearing impairments. Review of the literature on the association between inner ear malformations and meningitis. - Muzzi, E; Battelino, S; Gregori, M; Pellegrin, A; Orzan, E (Int J Pediatr Otorhinolaryngol, 2015)
BACKGROUND: Bacterial meningitis is a life threatening disease that can be triggered by a CSF leak through an inner ear malformation. Early identification of the specific type of cochleovestibular dysplasia and the associated risk of meningitis is of vital importance. OBJECTIVES: The objective of this review is to collect and discuss available data on the association between inner ear malformations and meningitis in children. METHODS: Electronic databases were crosschecked for obtaining relevant papers published in the last 20 years, and further cases were identified by hand searching through the references. Demographic data were extracted from full texts, together with information on the severity of hearing impairment, the type of inner ear anomaly, the site of cerebrospinal fluid leak, the number of recurrent meningitis episodes. RESULTS: Sixty-seven cases of meningitis related to inner ear malformation have been identified among 45 papers. Mean age at presentation is 3.60±3.00 (range 0.1-14) years. Average diagnostic delay from the first episode of meningitis is 3.44±3.41 (range 0.00-10.00) years. The number of meningitis episodes that occurred before the correct diagnosis and definitive surgical treatment is 3.27±1.81 (range 1.00-10.00). Unilateral hearing impairment affects 70% of patients. Six patients had normal hearing at presentation. Two children are dead from inner-ear-malformation-related meningitis among reviewed reports. CONCLUSION: A high number of paediatric patients carrying inner ear malformations, especially when associated with unilateral hearing impairment, could be at risk to develop recurrent bacterial meningitis. Universal newborn hearing screening programs should prompt a diagnostic work-up even in the case of unilateral hearing impairment, in order to prevent inner ear malformation-related meningitis.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

Maternal holding vs oral glucose administration as nonpharmacologic analgesia in newborns: a functional neuroimaging study. - Bembich, Stefano; Cont, Gabriele; Baldassi, Giulio; Bua, Jenny; Demarini, Sergio (JAMA Pediatr, 2015)
Keywords: Administration, Oral; Analgesia; Blood Specimen Collection; Female; Functional Neuroimaging; Glucose; Humans; Infant, Newborn; Mother-Child Relations; Pain; Pain Management; Spectroscopy, Near-Infrared

Mature and immature teratoma: A report from the second Italian pediatric study. - Terenziani, Monica; D'Angelo, Paolo; Inserra, Alessandro; Boldrini, Renata; Bisogno, Gianni; Babbo, Gian Luca; Conte, Massimo; Dall' Igna, Patrizia; De Pasquale, Maria Debora; Indolfi, Paolo; Piva, Luigi; Riccipetitoni, Giovanna; et al. (Pediatr Blood Cancer, 2015)
BACKGROUND: Teratomas demonstrate a benign clinical behavior, however they may recur with malignant components or as teratoma, and in a small group of patients prognosis could be fatal. After the first Italian study, we collected cases of teratoma, alongside the protocol for malignant germ cell tumors. PROCEDURE: Patients with teratoma were collected from 2004 to 2014. Teratomas were classified according to the WHO classifications, as mature and immature. Patients with pathological aFP and/or bHCG, and those with a malignant germ cell component were not included. RESULTS: The study enrolled 219 patients (150 mature, 69 immature teratomas) with a median age at diagnosis of 42 months. The primary sites involved were: 118 gonadal and 101 extragonadal teratomas. Two females with ovarian teratoma had a positive family history. Complete and incomplete surgeries were performed in 85% and 9% of cases. Seventeen events occurred: six females had a second metachronous tumor (5 contralateral ovarian teratoma, 1 adrenal neuroblastoma) and 11 teratomas relapsed/progressed (3 mature, 8 immature teratomas). Two patients died, one of progressive immature teratoma and one of surgical complications. At a median follow up of 68 months, the event-free, relapse-free, and overall survival rates were 90.6%, 94.3%, 98.6%, respectively. CONCLUSIONS: Teratomas show a good prognosis, especially the mature ones: surgery and follow-up remain the standard approach. Incomplete surgery in immature teratoma is the group at greatest risk of relapse. Bilateral ovarian tumors are a possibility, and the rare family predisposition to ovarian mature teratoma warrants further analyses.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasm Grading; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Second Primary; Neuroblastoma; Ovarian Neoplasms; Prognosis; Prospective Studies; Survival Rate; Teratoma; Testicular Neoplasms; Young Adult

The mediating role of interpersonal conflict at work in the relationship between negative affectivity and biomarkers of stress. - Girardi, Damiano; Falco, Alessandra; De Carlo, Alessandro; Benevene, Paula; Comar, Manola; Tongiorgi, Enrico; Bartolucci, Giovanni Battista (J Behav Med, 2015)
This study examined the association between interpersonal conflict at work (ICW) and serum levels of three possible biomarkers of stress, namely the pro-inflammatory cytokines Interleukin 1 beta (IL-1β), Interleukin 12 (IL-12), and Interleukin 17 (IL-17). Additionally, this study investigated the role of negative affectivity (NA) in the relationship between ICW and the pro-inflammatory cytokines. Data from 121 employees in an Italian healthcare organization were analyzed using structural equation modeling. Results showed that ICW was positively associated with IL-1β, IL-12, and IL-17, after controlling for the effect of gender. Moreover, ICW completely mediated the relationship between NA and the pro-inflammatory cytokines IL-1β, IL-12, and IL-17. This mediating effect was significant after controlling for the effect of gender. Overall, this study suggests that work-related stress may be associated with biomarkers of inflammation, and that negative affectivity may influence the stress process affecting the exposure to psychosocial stressors.

Meta-analysis and time series modeling allow a systematic review of primary HIV-1 drug-resistant prevalence in Latin America and Caribbean. - Coelho, Antônio Victor Campos; De Moura, Ronald Rodrigues; da Silva, Ronaldo Celerino; Kamada, Anselmo Jiro; Guimarães, Rafael Lima; Brandão, Lucas André Cavalcanti; Coelho, Hemílio Fernandes Campos; Crovella, Sergio (Curr HIV Res, 2015)
Here we review the prevalence of HIV-1 primary drug resistance in Latin America and Caribbean using meta-analysis as well as time-series modeling. We also discuss whether there could be a drawback to HIV/AIDS programs due to drug resistance in Latin America and Caribbean in the next years. We observed that, although some studies report low or moderate primary drug resistance prevalence in Caribbean countries, this evidence needs to be updated. In other countries, such as Brazil and Argentina, the prevalence of drug resistance appears to be rising. Mutations conferring resistance against reverse transcriptase inhibitors were the most frequent in the analyzed populations (70% of all mutational events). HIV-1 subtype B was the most prevalent in Latin America and the Caribbean, although subtype C and B/F recombinants have significant contributions in Argentina and Brazil. Thus, we suggest that primary drug resistance in Latin America and the Caribbean could have been underestimated. Clinical monitoring should be improved to offer better therapy, reducing the risk for HIV-1 resistance emergence and spread, principally in vulnerable populations, such as men who have sex with men transmission group, sex workers and intravenous drug users.

Meta-analysis of Brazilian genetic admixture and comparison with other Latin America countries. - Moura, Ronald Rodrigues de; Coelho, Antônio Victor Campos; Balbino, Valdir de Queiroz; Crovella, Sergio; Brandão, Lucas André Cavalcanti (Am J Hum Biol, 2015)
OBJECTIVES: This study aims at performing a systematic review and meta-analysis with the studies of genetic admixture inference of Brazilian population and to compare these results with the genetic admixture levels in other Latin American countries. METHODS: We searched for articles regarding the estimation of Brazilian genetic admixture published between 1980 and 2014 that used autosomal markers. Then, conducted meta-analyses at the whole-country and regional level. Finally, we compared the results of Brazil with other estimates from other South, Central and North American countries. RESULTS: We analyzed data from 25 studies in 38 different Brazilian populations. European (EUR) ancestry is the major contributor to the genetic background of Brazilians, followed by African (AFR), and Amerindian (AMR) ancestries. The pooled ancestry contributions were 0.62 EUR, 0.21 AFR, and 0.17AMR. The Southern region had a greater EUR contribution (0.77) than other regions. Individuals from the Northeast (NE) region had the highest AFR contribution (0.27) whereas individuals from the North regions had more AMR contribution (0.32). In the Latin America context, Brazil has the 5th high EUR contribution, the 12th for the AFR component and the 10th for the AMR ancestry. CONCLUSIONS: Admixture proportions vary greatly among Brazilian populations and also through Latin America. More studies in the Center-West, North and NE regions are needed to capture a more complete picture of the genomic ancestry of Brazil.

MID2 can substitute for MID1 and control exocytosis of lytic granules in cytotoxic T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Levring, Trine B; Woetmann, Anders; Ødum, Niels; Bonefeld, Charlotte M; Geisler, Carsten (APMIS, 2015)
We have recently shown that the E3 ubiquitin ligase midline 1 (MID1) is upregulated in murine cytotoxic lymphocytes (CTL), where it controls exocytosis of lytic granules and the killing capacity. Accordingly, CTL from MID1 knock-out (MID1(-/-)) mice have a 25-30% reduction in exocytosis of lytic granules and cytotoxicity compared to CTL from wild-type (WT) mice. We wondered why the MID1 gene knock-out did not affect exocytosis and cytotoxicity more severely and speculated whether MID2, a close homologue of MID1, might partially compensate for the loss of MID1 in MID1(-/-) CTL. Here, we showed that MID2, like MID1, is upregulated in activated murine T cells. Furthermore, MID1(-/-) CTL upregulated MID2 two-twenty-fold stronger than CTL from WT mice, suggesting that MID2 might compensate for MID1. In agreement, transfection of MID2 into MID1(-/-) CTL completely rescued exocytosis of lytic granules in MID1(-/-) CTL, and vice versa, knock-down of MID2 inhibited exocytosis of lytic granules in both WT and MID1(-/-) CTL, demonstrating that both MID1 and MID2 play a central role in the regulation of granule exocytosis and that functional redundancy exists between MID1 and MID2 in CTL.
Keywords: Animals; Cytoplasmic Granules; Exocytosis; Interferon-gamma; Mice; Mice, Inbred C57BL; Mice, Knockout; Microtubule-Associated Proteins; Proteins; T-Lymphocytes, Cytotoxic; Transcription Factors; Up-Regulation

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

Nasal irrigation with saline solution significantly improves oxygen saturation in infants with bronchiolitis. - Schreiber, Silvana; Ronfani, Luca; Ghirardo, Sergio; Minen, Federico; Taddio, Andrea; Jaber, Mohamad; Rizzello, Elisa; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Published guidelines do not recommend nasal irrigation in bronchiolitis, but it is common practice in Italy, despite a lack of data on its benefits or adverse effects. This single-blind, multicentre, randomised controlled trial compared nasal irrigation using either isotonic 0.9% sodium chloride or hypertonic 3% sodium chloride with simple supportive care in infants with bronchiolitis. METHOD: We randomly assigned 133 Infants up one year of age, who were admitted to the emergency department with bronchiolitis and an oxygen saturation (SpO2) of between 88-94%, to the isotonic (n=47), hypertonic (n=44) or standard care (n=42) groups. Variations in SpO2 and the wheeze, air exchange, respiratory rate, muscle use (WARM) respiratory distress score were recorded at zero, five, 15, 20 and 50 minutes. RESULTS: Five minutes after the intervention, the median SpO2 value (95%) in the isotonic group was higher than both the hypertonic (94%) and the standard care (93%) groups. The differences between the isotonic and standard treatment groups were statistically significant at each time point, while the hypertonic group only reached significantly higher values after 50 minutes. However, the WARM score did not improve. CONCLUSION: A single nasal irrigation with saline solution significantly improved oxygen saturation in infants with bronchiolitis. This article is protected by copyright. All rights reserved.

A nationwide survey of PMM2-CDG in Italy: high frequency of a mild neurological variant associated with the L32R mutation. - Barone, Rita; Carrozzi, M; Parini, R; Battini, R; Martinelli, D; Elia, M; Spada, M; Lilliu, F; Ciana, G; Burlina, A; Leuzzi, V; Leoni, M; et al. (J Neurol, 2015)
PMM2-CDG (PMM2 gene mutations) is the most common congenital disorder of N-glycosylation. We conducted a nationwide survey to characterize the frequency, clinical features, glycosylation and genetic correlates in Italian patients with PMM2-CDG. Clinical information was obtained through a questionnaire filled in by the referral physicians including demographics, neurological and systemic features, neuroimaging data and genotype. Glycosylation analyses of serum transferrin were complemented by MALDI-Mass Spectrometry (MALDI-MS). Between 1996 and 2012, data on 37 Italian patients with PMM2-CDG were collected. All the patients with a severe phenotype were unable to walk unaided, 84 % had severe intellectual disability and 81 % microcephaly. Conversely, among 17 mildly affected patients 82 % had independent ambulation, 64 % had borderline to mild intellectual disability and 35 % microcephaly. Epilepsy and stroke-like events did not occur among patients with the mild phenotype. The rate and extent of systemic involvement were more pronounced in severely affected patients. The L32R misfolding mutation of the PMM2 gene occurred in 70 % of the patients with the mild phenotype and was associated with a less severe underglycosylation of serum Tf at MALDI-MS analyses. Despite their different disease severity, all patients had progressive (olivo)ponto-cerebellar atrophy that was the hallmark clinical feature for the diagnosis. A mild neurological phenotype of PMM2-CDG marked by preserved ambulatory ability and autonomy and associated with L32R mutation is particularly frequent in Italy. PMM2-CDG should be considered in patients with even mild developmental disability and/or unexplained progressive cerebellar atrophy.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Next-generation sequencing and its initial applications for molecular diagnosis of systemic auto-inflammatory diseases. - Rusmini, Marta; Federici, Silvia; Caroli, Francesco; Grossi, Alice; Baldi, Maurizia; Obici, Laura; Insalaco, Antonella; Tommasini, Alberto; Caorsi, Roberta; Gallo, Eleonora; Olivieri, Alma Nunzia; Marzano, AngeloValerio; et al. (Ann Rheum Dis, 2015)
OBJECTIVES: Systemic auto-inflammatory disorders (SAIDs) are a heterogeneous group of monogenic diseases sharing a primary dysfunction of the innate immune system. More than 50% of patients with SAID does not show any mutation at gene(s) tested because of lack of precise clinical classification criteria and/or incomplete gene screening. To improve the molecular diagnosis and genotype interpretation of SAIDs, we undertook the development of a next-generation sequencing (NGS)-based protocol designed to simultaneous screening of 10 genes. METHODS: Fifty patients with SAID, already genotyped for the respective causative gene(s), were massively sequenced for the coding portions of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12, NOD2, PSTPIP1, IL1RN, LPIN2 and PSMB8. Three different bioinformatic pipelines (Ion Reporter, CLC Bio Genomics Workbench, GATK-based in-house workflow) were compared. RESULTS: Once resulting variants were compared with the expected mutation list, no workflow turned out to be able to detect all the 79 variants known in the 50 DNAs. Additional variants were also detected, validated by Sanger sequencing and compared to assess true and false positive detection rates of the three workflows. Finally, the overall clinical picture of 34 patients was re-evaluated in the light of the new mutations found. CONCLUSIONS: The present gene panel has resulted suitable for molecular diagnosis of SAIDs. Moreover, genotype-phenotype correlation has confirmed that the interpretation of NGS data in patients with an undefined inflammatory phenotype is remarkably difficult, thus supporting the need of evidence-based and validated clinical criteria to be used concurrently with the genetic analysis for the final diagnosis and classification of patients with SAIDs.

NLRP1 and NLRP3 polymorphisms in mesothelioma patients and asbestos exposed individuals a population-based autopsy study from North East Italy. - Borelli, Violetta; Moura, Ronal R; Trevisan, Elisa; Crovella, Sergio (Infect Agent Cancer, 2015)
NRLP1 (rs12150220, rs9889625, rs9900356, rs6502867, rs2670660) and NLRP3 (rs35829419, rs10754558) polymorphisms have been analyzed in 69 subjects with documented asbestos exposure and death for malignant pleural mesothelioma and 59 patients with documented asbestos exposure but death for other causes, all from a North East Italy. No association was found between NLRP1 and NLRP3 polymorphisms and susceptibility to develop mesothelioma using the general, dominant or recessive models. Also haplotype analysis did not reveal any significant association with mesothelioma. Our findings, being controversial with respect to another study on Italian patients, do suggest the need of further studies to unravel the contribution of NLRP1 and NLRP3 in susceptibility to mesothelioma.

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

Ondasetron Is More Likely Than Ketamine to Cause Ventricular Tachycardia. - Marzuillo, Pierluigi; Rabach, Ingrid; Barbi, Egidio (Pediatr Emerg Care, 2015)
Keywords: Anesthetics, Dissociative; Female; Humans; Ketamine; Tachycardia, Ventricular

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

Pain activates a defined area of the somatosensory and motor cortex in newborn infants. - Bembich, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Travan, Laura; Grassi, Veronica; Demarini, Sergio (Acta Paediatr, 2015)

The p.Cys169Tyr variant of connexin 26 is not a polymorphism. - Zonta, Francesco; Girotto, Giorgia; Buratto, Damiano; Crispino, Giulia; Morgan, Anna; Abdulhadi, Khalid; Alkowari, Moza; Badii, Ramin; Gasparini, Paolo; Mammano, Fabio (Hum Mol Genet, 2015)
Mutations in the GJB2 gene, which encodes the gap junction protein connexin 26 (Cx26), are the primary cause of hereditary prelingual hearing impairment. Here, the p.Cys169Tyr missense mutation of Cx26 (Cx26C169Y), previously classified as a polymorphism, has been identified as causative of severe hearing loss in two Qatari families. We have analyzed the effect of this mutation using a combination of confocal immunofluorescence microscopy and molecular dynamics simulations. At the cellular level, our results show that the mutant protein fails to form junctional channels in HeLa transfectants despite being correctly targeted to the plasma membrane. At the molecular level, this effect can be accounted for by disruption of the disulfide bridge that Cys169 forms with Cys64 in the wild-type structure (Cx26WT). The lack of the disulfide bridge in the Cx26C169Y protein causes a spatial rearrangement of two important residues, Asn176 and Thr177. In the Cx26WT protein, these residues play a crucial role in the intra-molecular interactions that permit the formation of an intercellular channel by the head-to-head docking of two opposing hemichannels resident in the plasma membrane of adjacent cells. Our results elucidate the molecular pathogenesis of hereditary hearing loss due to the connexin mutation and facilitate the understanding of its role in both healthy and affected individuals.
Keywords: Alleles; Amino Acid Substitution; Cell Line; Connexins; Female; Gap Junctions; Gene Expression; Genotype; Hearing Loss; Humans; Immunohistochemistry; Male; Models, Molecular; Mutation, Missense; Pedigree; Polymorphism, Genetic; Protein Conformation; Protein Interaction Domains and Motifs; Transfection

Persistent viremia and urine shedding of tick-borne encephalitis virus in an infected immunosuppressed patient from a new epidemic cluster in North-Eastern Italy. - Caracciolo, Ilaria; Bassetti, Matteo; Paladini, Giorgio; Luzzati, Roberto; Santon, Daniela; Merelli, Maria; Sabbata, Giovanni De; Carletti, Tea; Marcello, Alessandro; D'Agaro, Pierlanfranco (J Clin Virol, 2015)
A persistent tick-borne encephalitis virus infection in an immune-suppressed patient is presented. Such an unusual clinical case offers the unique chance of detecting persistent viremia associated to the erythrocyte fraction and shedding of the virus in the urine for more than six weeks. The infection occurred in a new area of the Friuli Venezia-Giulia region (North Eastern Italy) where two additional cases are also being reported.

Phenotypic and genetic characterization of a family carrying two Xq21.1-21.3 interstitial deletions associated with syndromic hearing loss. - Iossa, Sandra; Costa, Valerio; Corvino, Virginia; Auletta, Gennaro; Barruffo, Luigi; Cappellani, Stefania; Ceglia, Carlo; Cennamo, Giovanni; d'Adamo, Adamo Pio; D'Amico, Alessandra; Di Paolo, Nilde; Forte, Raimondo; et al. (Mol Cytogenet, 2015)
BACKGROUND: Sensorineural hearing impairment is a common pathological manifestation in patients affected by X-linked intellectual disability. A few cases of interstitial deletions at Xq21 with several different phenotypic characteristics have been described, but to date, a complete molecular characterization of the deletions harboring disease-causing genes is still missing. Thus, the aim of this study is to realize a detailed clinical and molecular analysis of a family affected by syndromic X-linked hearing loss with intellectual disability. RESULTS: Clinical analyses revealed a very complex phenotype that included inner ear malformations, vestibular problems, choroideremia and hypotonia with a peculiar pattern of phenotypic variability. Genomic analysis revealed, for the first time, the presence of two close interstitial deletions in the Xq21.1-21.3, harboring 11 protein coding, 9 non-coding genes and 19 pseudogenes. Among these, 3 protein coding genes have already been associated with X-linked hearing loss, intellectual disability and choroideremia. CONCLUSIONS: In this study we highlighted the presence of peculiar genotypic and phenotypic details in a family affected by syndromic X-linked hearing loss with intellectual disability. We identified two, previously unreported, Xq21.1-21.3 interstitial deletions. The two rearrangements, containing several genes, segregate with the clinical features, suggesting their role in the pathogenicity. However, not all the observed phenotypic features can be clearly associated with the known genes thus, further study is necessary to determine regions involved.

Phleboliths as a marker of slow-flow venous malformation. - Calligaris, Lorenzo; Berti, Irene; Barbi, Egidio (Arch Dis Child, 2015)

Polymorphisms in sweet taste genes (TAS1R2 and GLUT2), sweet liking, and dental caries prevalence in an adult Italian population. - Robino, Antonietta; Bevilacqua, Lorenzo; Pirastu, Nicola; Situlin, Roberta; Di Lenarda, Roberto; Gasparini, Paolo; Navarra, Chiara Ottavia (Genes Nutr, 2015)
The aim of the study was to assess the relationship between sweet taste genes and dental caries prevalence in a large sample of adults. In addition, the association between sweet liking and sugar intake with dental caries was investigated. Caries was measured by the decayed, missing, filled teeth (DMFT) index in 647 Caucasian subjects (285 males and 362 females, aged 18-65 years), coming from six villages in northeastern Italy. Sweet liking was assessed using a 9-point scale, and the mean of the liking given by each individual to specific sweet food and beverages was used to create a sweet liking score. Simple sugar consumption was estimated by a dietary history interview, considering both added sugars and sugar present naturally in foods. Our study confirmed that polymorphisms in TAS1R2 and GLUT2 genes are related to DMFT index. In particular, GG homozygous individuals for rs3935570 in TAS1R2 gene (p value = 0.0117) and GG homozygous individuals for rs1499821 in GLUT2 gene (p value = 0.0273) showed higher DMFT levels compared to both heterozygous and homozygous for the alternative allele. Furthermore, while the relationship sugar intake-DMFT did not achieve statistical significance (p value = 0.075), a significant association was identified between sweet liking and DMFT (p value = 0.004), independent of other variables. Our study showed that sweet taste genetic factors contribute to caries prevalence and highlighted the role of sweet liking as a predictor of caries risk. Therefore, these results may open new perspectives for individual risk identification and implementation of target preventive strategies, such as identifying high-risk patients before caries development.

Population genetic differentiation of height and body mass index across Europe. - Robinson, Matthew R; Hemani, Gibran; Medina-Gomez, Carolina; Mezzavilla, Massimo; Esko, Tõnu; Shakhbazov, Konstantin; Powell, Joseph E; Vinkhuyzen, Anna; Berndt, Sonja I; Gustafsson, Stefan; Justice, Anne E; Kahali, Bratati; et al. (Nat Genet, 2015)
Across-nation differences in the mean values for complex traits are common, but the reasons for these differences are unknown. Here we find that many independent loci contribute to population genetic differences in height and body mass index (BMI) in 9,416 individuals across 14 European countries. Using discovery data on over 250,000 individuals and unbiased effect size estimates from 17,500 sibling pairs, we estimate that 24% (95% credible interval (CI) = 9%, 41%) and 8% (95% CI = 4%, 16%) of the captured additive genetic variance for height and BMI, respectively, reflect population genetic differences. Population genetic divergence differed significantly from that in a null model (height, P < 3.94 × 10(-8); BMI, P < 5.95 × 10(-4)), and we find an among-population genetic correlation for tall and slender individuals (r = -0.80, 95% CI = -0.95, -0.60), consistent with correlated selection for both phenotypes. Observed differences in height among populations reflected the predicted genetic means (r = 0.51; P < 0.001), but environmental differences across Europe masked genetic differentiation for BMI (P < 0.58).

PRE- AND POSTNATAL MODIFICATIONS IN PARENTAL MENTAL REPRESENTATIONS IN THREE CASES OF FETAL GASTROSCHISIS DIAGNOSED DURING PREGNANCY. - Tripani, Antonella; Pellizzoni, Sandra; Giuliani, Rosella; Bembich, Stefano; Clarici, Andrea; Lonciari, Isabella; Ammaniti, Massimo (Infant Ment Health J, 2015)
The aim of this study was to identify possible effects of gastroschisis on parents' intrapsychic dynamics by applying an observational clinical approach. More specifically, we intend to (a) evaluate the representational style of parents informed about the diagnosis of fetal gastroschisis during pregnancy using the Interview of Maternal Representations During Pregnancy and the Interview of Paternal Representations During Pregnancy (M. Ammaniti, C. Candelori, M. Pola, & R. Tambelli, ) and (b) observe whether the baby's birth influences the parents' representational styles through the application of the same tools (the Interview of Maternal Representations After the Birth, M. Ammaniti & R. Tambelli, , and the Interview of Paternal Representations After the Birth, M. Ammaniti & R. Tambelli, ), adapted to the postnatal period. During the prenatal period, all parents showed a restricted/disinvested style. Three parents-one mother and two fathers-changed their styles from restricted/disinvested to integrated between pregnancy and Month 6 after the birth of their child. Clinical data from the interviews and observations are discussed in an attempt at better defining intrapsychic dynamics of parents after a diagnosis of gastroschisis.

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

R705H mutation of MYH9 is associated with MYH9-related disease and not only with non-syndromic deafness DFNA17. - Verver, E; Pecci, A; De Rocco, D; Ryhänen, S; Barozzi, S; Kunst, H; Topsakal, V; Savoia, A (Clin Genet, 2015)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disease caused by mutation of MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (NMMHC-IIA). MYH9-RD patients have macrothrombocytopenia and granulocyte inclusions (pathognomonic sign of the disease) containing wild-type and mutant NMMHC-IIA. During life they might develop sensorineural hearing loss, cataract, glomerulonephritis, and elevation of liver enzymes. One of the MYH9 mutations, p.R705H, was previously reported to be associated with DFNA17, an autosomal dominant non-syndromic sensorineural hearing loss without any other features associated. We identified the same mutation in two unrelated families, whose four affected individuals had not only hearing impairment but also thrombocytopenia, giant platelets, leukocyte inclusions, as well as mild to moderate elevation of some liver enzymes. Our data suggest that DFNA17 should not be a separate genetic entity but part of the wide phenotypic spectrum of MYH9-RD characterized by congenital hematological manifestations and variable penetrance and expressivity of the extra-hematological features.

A rapid screening of ancestry for genetic association studies in an admixed population from Pernambuco, Brazil. - Coelho, A V C; Moura, R R; Cavalcanti, C A J; Guimarães, R L; Sandrin-Garcia, P; Crovella, S; Brandão, L A C (Genet Mol Res, 2015)
Genetic association studies determine how genes influence traits. However, non-detected population substructure may bias the analysis, resulting in spurious results. One method to detect substructure is to genotype ancestry informative markers (AIMs) besides the candidate variants, quantifying how much ancestral populations contribute to the samples' genetic background. The present study aimed to use a minimum quantity of markers, while retaining full potential to estimate ancestries. We tested the feasibility of a subset of the 12 most informative markers from a previously established study to estimate influence from three ancestral populations: European, African and Amerindian. The results showed that in a sample with a diverse ethnicity (N = 822) derived from 1000 Genomes database, the 12 AIMs had the same capacity to estimate ancestries when compared to the original set of 128 AIMs, since estimates from the two panels were closely correlated. Thus, these 12 SNPs were used to estimate ancestry in a new sample (N = 192) from an admixed population in Recife, Northeast Brazil. The ancestry estimates from Recife subjects were in accordance with previous studies, showing that Northeastern Brazilian populations show great influence from European ancestry (59.7%), followed by African (23.0%) and Amerindian (17.3%) ancestries. Ethnicity self-classification according to skin-color was confirmed to be a poor indicator of population substructure in Brazilians, since ancestry estimates overlapped between classifications. Thus, our streamlined panel of 12 markers may substitute panels with more markers, while retaining the capacity to control for population substructure and admixture, thereby reducing sample processing time.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

RelB activation in anti-inflammatory decidual endothelial cells: a master plan to avoid pregnancy failure? - Masat, Elisa; Gasparini, Chiara; Agostinis, Chiara; Bossi, Fleur; Radillo, Oriano; De Seta, Francesco; Tamassia, Nicola; Cassatella, Marco A; Bulla, Roberta (Sci Rep, 2015)
It is known that excessive inflammation at fetal-maternal interface is a key contributor in a compromised pregnancy. Female genital tract is constantly in contact with microorganisms and several strategies must be adopted to avoid pregnancy failure. Decidual endothelial cells (DECs) lining decidual microvascular vessels are the first cells that interact with pro-inflammatory stimuli released into the environment by microorganisms derived from gestational tissues or systemic circulation. Here, we show that DECs are hypo-responsive to LPS stimulation in terms of IL-6, CXCL8 and CCL2 production. Our results demonstrate that DECs express low levels of TLR4 and are characterized by a strong constitutive activation of the non-canonical NF-κB pathway and a low responsiveness of the canonical pathway to LPS. In conclusion, DECs show a unique hypo-responsive phenotype to the pro-inflammatory stimulus LPS in order to control the inflammatory response at feto-maternal interface.

Risk factors for mortality from acute lower respiratory infections (ALRI) in children under five years of age in low and middle-income countries: a systematic review and meta-analysis of observational studies. - Sonego, Michela; Pellegrin, Maria Chiara; Becker, Genevieve; Lazzerini, Marzia (PLoS One, 2015)
OBJECTIVE: To evaluate risk factors for death from acute lower respiratory infections (ALRI) in children in low- and middle-income countries. DESIGN: Systematic review and meta-analysis. STUDY SELECTION: Observational studies reporting on risk factors for death from ALRI in children below five years in low- and middle income countries. DATA SOURCES: Medline, Embase, Global Health Library, Lilacs, and Web of Science to January 2014. RISK OF BIAS ASSESSMENT: Quality In Prognosis Studies tool with minor adaptations to assess the risk of bias; funnel plots and Egger's test to evaluate publication bias. RESULTS: Out of 10,655 papers retrieved, 77 studies from 39 countries (198,359 children) met the inclusion criteria. Host and disease characteristics more strongly associated with ALRI mortality were: diagnosis of very severe pneumonia as per WHO definition (odds ratio 9.42, 95% confidence interval 6.37‒13.92); age below two months (5.22, 1.70‒16.03); diagnosis of Pneumocystis Carinii (4.79, 2.67‒8.61), chronic underlying diseases (4.76, 3.27‒6.93); HIV/AIDS (4.68, 3.72‒5.90); and severe malnutrition (OR 4.27, 3.47‒5.25). Socio-economic and environmental factors significantly associated with increased odds of death from ALRI were: young maternal age (1.84, 1.03‒3.31); low maternal education (1.43, 1.13‒1.82); low socio-economic status (1.62, 1.32‒2.00); second-hand smoke exposure (1.52, 1.20 to 1.93); indoor air pollution (3.02, 2.11‒4.31). Immunisation (0.46, 0.36‒0.58) and good antenatal practices (0.50, 0.31‒0.81) were associated with decreased odds of death. CONCLUSIONS: Host and disease characteristics as well as socio-economic and environmental determinants affect the risk of death from ALRI in children. Together with the prevention and treatment of chronic diseases, interventions to modify underlying risk factors such as poverty, lack of female education, and poor environmental conditions, should be considered among the strategies to reduce ALRI mortality in children in low- and middle-income countries.
Keywords: Child, Preschool; Developing Countries; Environmental Exposure; Humans; Infant; Infant, Newborn; Observational Studies as Topic; Poverty; Respiratory Tract Infections; Risk Factors; Survival Analysis

Risk-adjusted operative delivery rates and maternal-neonatal outcomes as measures of quality assessment in obstetric care: a multicenter prospective study. - Maso, Gianpaolo; Monasta, Lorenzo; Piccoli, Monica; Ronfani, Luca; Montico, Marcella; De Seta, Francesco; Parolin, Sara; Businelli, Caterina; Travan, Laura; Alberico, Salvatore (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Although the evaluation of caesarean delivery rates has been suggested as one of the most important indicators of quality in obstetrics, it has been criticized because of its controversial ability to capture maternal and neonatal outcomes. In an "ideal" process of labor and delivery auditing, both caesarean (CD) and assisted vaginal delivery (AVD) rates should be considered because both of them may be associated with an increased risk of complications. The aim of our study was to evaluate maternal and neonatal outcomes according to the outlier status for case-mix adjusted CD and AVD rates in the same obstetric population. METHODS: Standardized data on 15,189 deliveries from 11 centers were prospectively collected. Multiple logistic regression was used to estimate the risk-adjusted probability of a woman in each center having an AVD or a CD. Centers were classified as "above", "below", or "within" the expected rates by considering the observed-to-expected rates and the 95% confidence interval around the ratio. Adjusted maternal and neonatal outcomes were compared among the three groupings. RESULTS: Centers classified as "above" or "below" the expected CD rates had, in both cases, higher adjusted incidence of composite maternal (2.97%, 4.69%, 3.90% for "within", "above" and "below", respectively; p = 0.000) and neonatal complications (3.85%, 9.66%, 6.29% for "within", "above" and "below", respectively; p = 0.000) than centers "within" CD expected rates. Centers with AVD rates above and below the expected showed poorer and better composite maternal (3.96%, 4.61%, 2.97% for "within", "above" and "below", respectively; p = 0.000) and neonatal (6.52%, 9.77%, 3.52% for "within", "above" and "below", respectively; p = 0.000) outcomes respectively than centers with "within" AVD rates. CONCLUSIONS: Both risk-adjusted CD and AVD delivery rates should be considered to assess the level of obstetric care. In this context, both higher and lower-than-expected rates of CD and "above" AVD rates are significantly associated with increased risk of complications, whereas the "below" status for AVD showed a "protective" effect on maternal and neonatal outcomes.

Serum TRAIL levels increase shortly after insulin therapy and metabolic stabilization in children with type 1 diabetes mellitus. - Tornese, Gianluca; Tisato, Veronica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Zauli, Giorgio; Secchiero, Paola (Acta Diabetol, 2015)

A Shining Scrotal Fountain. - Copertino, Marco; Benelli, Elisa; Gregori, Massimo; Barbi, Egidio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Child; Edema; Humans; Male; Penile Diseases; Scrotum

Short Communication FYB polymorphisms in Brazilian patients with type I diabetes mellitus and autoimmune polyglandular syndrome type III. - Addobbati, C J C; de Azevêdo Silva, J; Tavares, N A C; Araujo, J; Guimarães, R L; Brandão, L; Crovella, S; Sandrin-Garcia, P (Genet Mol Res, 2015)
The aim of this study was to perform an association study between seven Fyn-binding protein gene (FYB)-tag single nucleotide polymorphisms (SNPs) and type I diabetes mellitus (T1DM), as well as with disease age of onset. We also assessed the role of FYB SNPs in the insurgence of autoimmune polyglandular syndrome type III (APSIII), characterized by the simultaneous presence of autoimmune thyroid disease and celiac disease, in patients with T1DM from a Northeastern Brazilian population. One hundred and seventy-seven patients with T1DM and 190 healthy individuals were genotyped for seven tag SNPs, covering most of the FYB locus, using real-time polymerase chain reaction amplification. There was no significant difference in the distribution of allele and genotype frequencies among patients and healthy individuals. Moreover, none of the tag SNPs were associated either to T1DM age of onset or to the insurgence of APSIII. However, since the FYB protein is a key component in T cell response, its gene variants might play a role in protein function, which might be testable in a population with different genetic backgrounds or by using functional assays.

Target sequencing approach intended to discover new mutations in non-syndromic intellectual disability. - Morgan, Anna; Gandin, Ilaria; Belcaro, Chiara; Palumbo, Pietro; Palumbo, Orazio; Biamino, Elisa; Dal Col, Valentina; Laurini, Erik; Pricl, Sabrina; Bosco, Paolo; Carella, Massimo; Ferrero, Giovanni Battista; et al. (Mutat Res, 2015)
The technological improvements over the last years made considerable progresses in the knowledge of the etiology of intellectual Disability (ID). However, at present very little is known about the genetic heterogeneity underlying the non-syndromic form of ID (NS-ID). To investigate the genetic basis of NS-ID we analyzed 43 trios and 22 isolated NS-ID patients using a targeted sequencing (TS) approach. 71 NS-ID genes have been selected and sequenced in all subjects. We found putative pathogenic mutations in 7 out of 65 patients. The pathogenic role of mutations was evaluated through sequence comparison and structural analysis was performed to predict the effect of alterations in a 3D computational model through molecular dynamics simulations. Additionally, a deep patient clinical re-evaluation has been performed after the molecular results. This approach allowed us to find novel pathogenic mutations with a detection rate close to 11% in our cohort of patients. This result supports the hypothesis that many NS-ID related genes still remain to be discovered and that NS-ID is a more complex phenotype compared to syndromic form, likely caused by a complex and broad interaction between genes alterations and environment factors.

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

Tinea Incognito. - Paloni, Giulia; Valerio, Enrico; Berti, Irene; Cutrone, Mario (J Pediatr, 2015)

To Extinguish the Fire from Outside the Cell or to Shutdown the Gas Valve Inside? Novel Trends in Anti-Inflammatory Therapies. - Marcuzzi, Annalisa; Piscianz, Elisa; Valencic, Erica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Tommasini, Alberto (Int J Mol Sci, 2015)
Cytokines are the most important soluble mediators of inflammation. Rare pediatric diseases provided exemplar conditions to study the anti-inflammatory efficacy of new generation therapies (biologics/biopharmaceuticals) selectively targeting single cytokines. Monoclonal antibodies and recombinant proteins have revolutionized anti-inflammatory therapies in the last two decades, allowing the specific targeting of single cytokines. They are very effective in extinguishing inflammation from outside the cell, even with the risk of an excessive and prolonged immunosuppression. Small molecules can enter the cell and shutdown the valve of inflammation by directly targeting signal proteins involved in cytokine release or in response to cytokines. They are orally-administrable drugs whose dosage can be easily adjusted to obtain the desired anti-inflammatory effect. This could make these drugs more suitable for a wide range of diseases as stroke, gout, or neurological impairment, where inflammatory activation plays a pivotal role as trigger. Autoinflammatory diseases, which have previously put anti-cytokine proteins in the limelight, can again provide a valuable model to measure the real potential of small inhibitors as anti-inflammatory agents.

TRAIL modulates the immune system and protects against the development of diabetes. - Bossi, Fleur; Bernardi, Stella; Zauli, Giorgio; Secchiero, Paola; Fabris, Bruno (J Immunol Res, 2015)
TRAIL or tumor necrosis factor (TNF) related apoptosis-inducing ligand is a member of the TNF superfamily of proteins, whose best characterized function is the induction of apoptosis in tumor, infected, or transformed cells through activation of specific receptors. In nontransformed cells, however, the actions of TRAIL are less well characterized. Recent studies suggest that TRAIL may be implicated in the development and progression of diabetes. Here we review TRAIL biological actions, its effects on the immune system, and how and to what extent it has been shown to protect against diabetes.
Keywords: Animals; Diabetes Mellitus; Humans; Immune System; Receptors, TNF-Related Apoptosis-Inducing Ligand; Signal Transduction

Treatment of asthma based on symptoms. - Bibalo, Cristina; Longo, Giorgio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Asthma; Female; Humans; Male; Spirometry

Two-dimensional gel electrophoresis analysis of the leiomyoma interstitial fluid reveals altered protein expression with a possible involvement in pathogenesis. - Ura, Blendi; Scrimin, Federica; Zanconati, Fabrizio; Arrigoni, Giorgio; Monasta, Lorenzo; Romano, Andrea; Banco, Rubina; Zweyer, Marina; Milani, Daniela; Ricci, Giuseppe (Oncol Rep, 2015)
Uterine leiomyoma is the most common smooth benign neoplasm. In the present study, we analyzed the global interstitial fluid (IF) profile of leiomyoma vs. normal myometrium to identify protein dysregulation involved in leiomyoma pathogenesis. Two-dimensional gel electrophoresis and mass spectrometry were used to generate and compare the global interstitial fluid profiles of the leiomyoma and of the normal tissue. Two proteins were validated by immunohistochemistry. By comparing the interstitial fluid profile of the leiomyoma with that of the normal myometrium, the levels of seven proteins were found to be significantly different: four structural organization proteins (desmin, prelamin-A/C, transgelin and α-actinin-1), an inflammatory response (α1-antitrypsin), a response to oxidative stress (peroxiredoxin-2), and a folding protein (heat shock 70 kDa protein 1A/1B). Desmin, α1-antitrypsin and peroxiredoxin-2 were upregulated in the leiomyoma, whereas heat shock 70 kDa protein 1A/1B, α-actinin-1, prelamin-A/C and transgelin were downregulated. Desmin and α1-antitrypsin were further validated by immunohistochemistry. By identifying proteins with altered expression levels compared to the myometrium from several pathways of the leiomyoma pathogenesis, we found the leiomyoma interstitial fluid to have a characteristic proteomic profile. A better appreciation of the pathophysiology of the disease can be useful in the development of conservative treatments that serve as viable alternatives to hysterectomy.

Two‑gene mutation in a single patient: Biochemical and functional analysis for a correct interpretation of exome results. - Bianco, Anna Monica; Faletra, Flavio; Vozzi, Diego; Girardelli, Martina; Knowles, Alessandra; Tommasini, Alberto; Zauli, Giorgio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Next-generation sequencing (NGS) has generated a large amount of sequence data with the requirement of frequent critical revisions of reported mutations. This innovative tool has proved to be effective in detecting pathogenic mutations; however, it requires a certain degree of experience to identify incidental findings. In the present study, whole exome sequencing analysis was performed for the molecular diagnosis and correct genotype/phenotype correlation between parents and a patient presenting with an atypical phenotype. In addition, mevalonic acid quantification and frequency analysis of detected variants in public databases and X‑chromosome inactivation (XCI) studies on the patient's mother were performed. V377I as well as the S135L mutations were identified on the mevalonate kinase deficiency gene and the levels of mevalonic acid in the patient were 5,496 µg/ml. A D59G variation, reported in ESP6500 in two healthy individuals, was found on the Martin Probst syndrome gene (RAB40AL). Based on XCI studies on the patient's mother, it is likely that RAB40AL escapes XCI, while still remaining balanced. In conclusion, the results of the present study indicated that the Martin Probst syndrome is an X‑linked condition, which is probably not caused by RAB40AL mutations. Although NGS is a powerful tool to identify pathogenic mutations, the analysis of genetic data requires expert critical revision of all detected variants.

Ultrastructural Morphology of Sperm from Human Globozoospermia. - Ricci, Giuseppe; Andolfi, Laura; Zabucchi, Giuliano; Luppi, Stefania; Boscolo, Rita; Martinelli, Monica; Zweyer, Marina; Trevisan, Elisa (Biomed Res Int, 2015)
Globozoospermia is a rare disorder characterized by the presence of sperm with round head, lacking acrosome. Coiling tail around the nucleus has been reported since early human studies, but no specific significance has conferred it. By contrast, studies on animal models suggest that coiling tail around the nucleus could represent a crucial step of defective spermatogenesis, resulting in round-headed sperm. No observations, so far, support the transfer of this hypothesis to human globozoospermia. The purpose of this work was to compare ultrastructural morphology of human and mouse model globozoospermic sperm. Sperm have been investigated by using scanning and transmission electron microscopy. The images that we obtained show significant similarities to those described in GOPC knockout mice, an animal model of globozoospermia. By using this model as reference, we were able to identify the probable steps of the tail coiling process in human globozoospermia. Although we have no evidence that there is the same pathophysiology in man and knocked-out mouse, the similarities between these ultrastructural observations in human and those in the experimental model are very suggestive. This is the first demonstration of the existence of relevant morphological homologies between the tail coiling in animal model and human globozoospermia.

Unusual onset of a case of chronic recurrent multifocal osteomyelitis. - Barrani, M; Massei, F; Scaglione, M; Paolicchi, A; Vitali, S; Ciancia, E M; Crovella, S; Caparello, M C; Consolini, R (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare condition that commonly affects the clavicle and pelvis. CASE PRESENTATION: We report here a case a 12 years old girl with CRMO arising with recurrent episodes of left supraorbital headache, followed by the appearance of a periorbital dyschromia. Magnetic resonance imaging (MRI) of the skull and orbits revealed an important subacute inflammatory process. Few months after, the child presented a painful swelling of the left clavicle; the histological examination of the related biopsy allowed to establish the diagnosis of CRMO. CONCLUSION: CRMO presenting as acute headache involving neurocranium is rare; to our knowledge this is the first recognized case in the world literature. This pathological condition is frequently misdiagnosed as infection or neoplasm and needs a deep investigation for the differential diagnosis. The physical, laboratoristic and instrumental diagnostic investigations of the patient and the treatment employed are described in detail.

On the use of Chinese population as a proxy of Amerindian ancestors in genetic admixture studies with Latin American populations. - de Moura, Ronald R; de Queiroz Balbino, Valdir; Crovella, Sergio; Brandão, Lucas A C (Eur J Hum Genet, 2015)

Validation of the Italian translation of the affective neuroscience personality scales. - Pascazio, Lorenzo; Bembich, Stefano; Nardone, Ilaria B; Vecchiet, Cristina; Guarino, Giuseppina; Clarici, Andrea (Psychol Rep, 2015)
The theoretical perspective on affective neuroscience advanced by Panksepp, identified six basic innate affective systems: the SEEK, FEAR, ANGER, SADNESS, PLAY, and CARE systems. (3) It has been proposed that the fundamental elements of human personality and its variants may be based on the different expressions of these basic emotional systems and their combinations. A self-report inventory, the Affective Neuroscience Personality Scales (ANPS), has been devised with the aim of studying and evaluating personality from this perspective. This study reports data on the initial validation of ANPS Italian translation on a sample of 418 adult participants. Descriptive statistics for each scale were calculated, assessing also their internal consistency, as a measure of reliability and factorial validity. Acceptable internal consistency was found in all but one scale (SADNESS), and a second-order factor analysis identified a more general affective feature of personality hinging on relational characteristics, independent of the dimensions of general positive and negative affect.
Keywords: Adolescent; Adult; Affect; Aged; Aged, 80 and over; Female; Humans; Italy; Male; Middle Aged; Neurosciences; Personality; Personality Inventory; Psychometrics; Young Adult

Vitamin D receptor polymorphisms and expression profile in rheumatoid arthritis brazilian patients. - Cavalcanti, Catarina Addobbati Jordão; De Azevêdo Silva, Jaqueline; de Barros Pita, Will; Veit, Tiago Degani; Monticielo, Odirlei Andre; Xavier, Ricardo Machado; Brenol, João Carlos Tavares; Brenol, Cleiton Viegas; Fragoso, Thiago Sotero; Barbosa, Alexandre Domingues; Duarte, Ângela Luiza Branco Pinto; Oliveira, Renê Donizeti Ribeiro; et al. (Mol Biol Rep, 2015)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and important joint commitment, being the most common systemic autoimmune disease worldwide. RA displays important genetic background with a variety of genes contributing to the immune balance breakdown. Recent studies have demonstrated that vitamin D, through its receptor (VDR), is able to regulate the immune balance and suppress the autoimmunity process, being a potential target in autoimmune diseases. In the present genetic association study, we assessed 5 Tag single nucleotide polymorphisms (SNPs) (rs11168268, rs2248098, rs1540339, rs4760648 and rs3890733), which cover most of the VDR gene, in three different Brazilian populations (from Northeast, Southeast and South Brazil). We also evaluated the VDR expression profile in whole blood and monocytes from RA patients. For genotyping study, 428 RA patients and 616 healthy controls were genotyped with fluorogenic allele specific probes on an ABI7500 platform. For gene expression study, VDR mRNA levels of 15 RA patients and 26 healthy individuals were assessed by RT-PCR. Our results showed that SNPs rs4760648 and rs3890733 are associated to RA susceptibility (p value = 0.0026, OR 1.31 and p value = 0.0091, OR 1.28 with statistical power = 0.999 and 0.993, respectively). Regarding RA clinical features, the studied SNPs did not show significant associations. The gene expression assays showed that VDR mRNA levels were down regulated in both whole blood (-3.3 fold) and monocytes (-3.2 fold) of RA patients when compared to healthy controls. Our results, the first reported for distinct Brazilian populations, support a role of the VDR gene in the susceptibility to RA.

When Feeding Difficulties Are due to Genetics: The Case of Familial Partial 9q Duplication. - Travan, Laura; Rocca, Maria Santa; Buonomo, Francesca; Cleva, Lisa; Pecile, Vanna; De Cunto, Angela (J Investig Med High Impact Case Rep, 2015)
Chromosomal abnormalities may cause growth failure before or since birth. 9q duplication is reported as a cause of intrauterine growth restriction, mild dysmporphism, and intellectual disabilities. We report a case of a maternally inherited 9q21.31q21.33 duplication causing prenatal and postnatal growth restriction with feeding refusal and mild facial dysmorphisms, prenatally diagnosed by single-nucleotide polymorphism array analysis. Hypothesis of the possible pathogenic mechanisms are discussed.

A young soccer player with sudden pain after kicking the ball. - Lega, Sara; Rabach, Ingrid; Barbi, Egidio; Ventura, Alessandro (BMJ, 2015)
Keywords: Adolescent; Athletic Injuries; Emergency Medicine; Fractures, Bone; Humans; Ilium; Male; Soccer

Acquired long QT syndrome: a focus for the general pediatrician. - Marzuillo, Pierluigi; Benettoni, Alessandra; Germani, Claudio; Ferrara, Giovanna; D'Agata, Biancamaria; Barbi, Egidio (Pediatr Emerg Care, 2014)
Acquired long QT syndrome (LQTS) is a disorder of cardiac repolarization most often due to specific drugs, hypokalemia, or hypomagnesemia that may precipitate torsade de pointes and cause sudden cardiac death. Common presentations of the LQTS are palpitations, presyncope, syncope, cardiac arrest, and seizures. An abnormal 12-lead electrocardiogram obtained while the patient is at rest is the key to diagnosis. The occurrence of drug-induced LQTS is unpredictable in any given individual, but a common observation is that most patients have at least 1 identifiable risk factor in addition to drug exposure. The cornerstone of the management of acquired LQTS includes the identification and discontinuation of any precipitating drug and the correction of metabolic abnormalities, such as hypokalemia or hypomagnesemia. Most of the episodes of torsade de pointes are short-lived and terminate spontaneously. We propose a management protocol that could be useful for the daily practice in the emergency pediatric department to reduce the risk of acquired QT prolongation.
Keywords: Adolescent; Death, Sudden, Cardiac; Electrocardiography; Female; General Practitioners; Humans; Long QT Syndrome; Ondansetron; Risk Factors; Serotonin Antagonists

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Assessment of coupling between trans-abdominally acquired fetal ECG and uterine activity by bivariate phase-rectified signal averaging analysis. - Casati, Daniela; Stampalija, Tamara; Rizas, Konstantinos; Ferrazzi, Enrico; Mastroianni, Cristina; Rosti, Eleonora; Quadrifoglio, Mariachiara; Bauer, Axel (PLoS One, 2014)
UNLABELLED: Couplings between uterine contractions (UC) and fetal heart rate (fHR) provide important information on fetal condition during labor. At present, couplings between UC and fHR are assessed by visual analysis and interpretation of cardiotocography. The application of computerized approaches is restricted due to the non-stationarity of the signal, missing data and noise, typical for fHR. Herein, we propose a novel approach to assess couplings between UC and fHR, based on a signal-processing algorithm termed bivariate phase-rectified signal averaging (BPRSA). METHODS: Electrohysterogram (EHG) and fetal electrocardiogram (fECG) were recorded non-invasively by a trans-abdominal device in 73 women at term with uneventful singleton pregnancy during the first stage of labor. Coupling between UC and fHR was analyzed by BPRSA and by conventional cross power spectral density analysis (CPSD). For both methods, degree of coupling was assessed by the maximum coefficient of coherence (CPRSA and CRAW, respectively) in the UC frequency domain. Coherence values greater than 0.50 were consider significant. CPRSA and CRAW were compared by Wilcoxon test. RESULTS: At visual inspection BPRSA analysis identified coupled periodicities in 86.3% (63/73) of the cases. 11/73 (15%) cases were excluded from further analysis because no 30 minutes of fECG recording without signal loss was available for spectral analysis. Significant coupling was found in 90.3% (56/62) of the cases analyzed by BPRSA, and in 24.2% (15/62) of the cases analyzed by CPSD, respectively. The difference between median value of CPRSA and CRAW was highly significant (0.79 [IQR 0.69-0.90] and 0.29 [IQR 0.17-0.47], respectively; p<0.0001). CONCLUSION: BPRSA is a novel computer-based approach that can be reliably applied to trans-abdominally acquired EHG-fECG. It allows the assessment of correlations between UC and fHR patterns in the majority of labors, overcoming the limitations of non-stationarity and artifacts. Compared to standard techniques of cross-correlations, such as CPSD, BPRSA is significantly superior.
Keywords: Electrocardiography; Female; Heart Rate, Fetal; Humans; Labor, Obstetric; Pregnancy; Uterine Contraction

Association between orofacial granulomatosis and Crohn's disease in children: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Ventura, Alessandro (World J Gastroenterol, 2014)
AIM: To review pediatric cases of orofacial granulomatosis (OFG), report disease characteristics, and explore the association between OFG and Crohn's disease. METHODS: We conducted a systematic review according to the PRISMA guidelines. We searched Medline, LILACS, Virtual Health Library, and Web of Knowledge in September 2013 for cases of OFG in the pediatric age range (< 18 years), with no language limitations. All relevant articles were accessed in full text. The manual search included references of retrieved articles. We extracted data on patients' characteristics, disease characteristics, association with other diseases, and treatment. We analyzed the data and reported the results in tables and text. RESULTS: We retrieved 173 reports of OFG in children. Mean age at onset was 11.1 ± 3.8 years (range: 2.0-18 years). Prevalence in males was significant higher than in females (P < 0.001), with a male:female ratio of 2:1. Gastrointestinal signs or symptoms were present in 26.0% of children at the time of OFG diagnosis. Overall, 70/173 (40.4%) children received a concomitant diagnosis of Crohn's disease. In about half (51.4%) of the cases the onset of OFG anticipated the diagnosis of Crohn's disease, with a mean time between the two diagnoses of 13.1 ± 11.6 mo (range: 3-36 mo). Overall, 21/173 (12.1%) of the children with OFG had perianal disease, while 11/173 (6.4%) had a family history of Crohn's disease. Both perianal disease and a family history of Crohn's disease were significantly associated with a higher risk of Crohn's disease diagnosis in children with OFG [relative risk (RR) = 3.10, 95% confidence interval (CI): 2.46-3.90; RR = 2.74, 95%CI: 2.24-3.36, P < 0.0001 for both). Treatment of OFG included steroids (70.8% of children) and other immunosuppressive drugs (42.7%), such as azathioprine, thalidomide and infliximab. CONCLUSION: High prevalence of Crohn's disease in children with OFG suggests that OFG may be a subtype of Crohn's disease.
Keywords: Adolescent; Age of Onset; Child; Child, Preschool; Crohn Disease; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Prevalence; Risk Factors; Steroids; Treatment Outcome

Association of serum tumor necrosis factor-related apoptosis inducing ligand with body fat distribution as assessed by dual X-rays absorptiometry. - Cervellati, Carlo; Secchiero, Paola; Bonaccorsi, Gloria; Celeghini, Claudio; Zauli, Giorgio (Mediators Inflamm, 2014)
A low chronic inflammation mediated by cytokine release is considered a major pathogenic mechanism accounting for the higher risk of cardiovascular disease in the overweight/obese population. In this context, although the existence of a possible interaction between soluble tumor necrosis factor- (TNF-) related apoptosis inducing ligand (TRAIL) and quantity and localization, of adiposity in the body has been hypothesized, no studies have yet investigated this link by radiologic techniques able to assess directly fat mass (FM) in different body regions. To address this issue, we assessed body fat distribution by dual X-rays absorptiometry (DXA) in a sample of 103 women and investigated the possible association between the derived adiposity measures and serum TRAIL concentration. The level of TRAIL showed a positive and independent correlation with arms FM (P < 0.05), trunk FM (P < 0.001) and trunk FM% (P < 0.05), total FM and total FM% (P < 0.001 for both), and an inverse association with legs FM% (P < 0.05). Only trunk FM retained a significant correlation (P < 0.05) with TRAIL after adjusting for all the other indices of regional adiposity. In conclusion, from our study it emerged a significant and independent association of serum TRAIL levels with overall, and, mainly, central adiposity. Further studies are needed to longitudinally investigate the cause-effect relationship between change in body fat distribution and TRAIL.
Keywords: Absorptiometry, Photon; Adipose Tissue; Adiposity; Adult; Anthropometry; Female; Gene Expression Regulation; Humans; Inflammation; Linear Models; Menopause; Middle Aged; Overweight; TNF-Related Apoptosis-Inducing Ligand

Autosomal recessive Stickler syndrome due to a loss of function mutation in the COL9A3 gene. - Faletra, Flavio; d'Adamo, Adamo P; Bruno, Irene; Athanasakis, Emmanouil; Biskup, Saskia; Esposito, Laura; Gasparini, Paolo (Am J Med Genet A, 2014)
Stickler syndrome (STL) is a clinically variable and genetically heterogeneous syndrome characterized by ophthalmic, articular, orofacial, and auditory manifestations. STL has been described with both autosomal dominant and recessive inheritance. The dominant form is caused by mutations of COL2A1 (STL 1, OMIM 108300), COL11A1 (STL 2, OMIM 604841), and COL11A2 (STL 3, OMIM 184840) genes, while recessive forms have been associated with mutations of COL9A1 (OMIM 120210) and COL9A2 (OMIM 120260) genes. Type IX collagen is a heterotrimeric molecule formed by three genetically distinct chains: α1, α2, and α3 encoded by the COL9A1, COL9A2, and COL9A3 genes. Up to this time, only heterozygous mutations of COL9A3 gene have been reported in human and related to: (1) multiple epiphyseal dysplasia type 3, (2) susceptibility to an intervertebral disc disease, and (3) hearing loss. Here, we describe the first autosomal recessive Stickler family due to loss of function mutations (c.1176_1198del, p.Gln393Cysfs*25) of COL9A3 gene. These findings extend further the role of collagen genes family in the disease pathogenesis.
Keywords: Adolescent; Arthritis; Bone and Bones; Child; Child, Preschool; Collagen Diseases; Collagen Type IX; Connective Tissue Diseases; DNA Mutational Analysis; Facies; Female; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; Male; Mutation; Pedigree; Retinal Detachment

A boy with sudden headache. - Norbedo, Stefania; Naviglio, Samuele; Murru, Flora Maria; Cavallin, Roberta; Giurici, Nagua; Rabusin, Marco; Barbi, Egidio (Pediatr Emerg Care, 2014)
Headache is a common presenting complaint in pediatric emergency departments. The goal of emergent evaluation is to identify those children with potentially life-threatening conditions. We present the case of an adolescent boy presenting with headache and hypertension who was diagnosed with a catecholamine-secreting abdominal paraganglioma. Genetic testing eventually led to the diagnosis of SDHB-related hereditary paraganglioma-pheochromocytoma syndrome. Alarm features ("red flags") in children presenting with headache are reviewed, as well as the main features of paragangliomas and the indications for genetic testing.
Keywords: Abdominal Neoplasms; Adolescent; Emergencies; Headache; Humans; Male; Paraganglioma

Breastfeeding and migraine drugs. - Davanzo, Riccardo; Bua, Jenny; Paloni, Giulia; Facchina, Giulia (Eur J Clin Pharmacol, 2014)
PURPOSE: Breastfeeding women may suffer from migraine. While we have many drugs for its treatment and prophylaxis, the majority are poorly studied in breastfeeding women. We conducted a review of the most common anti-migraine drugs (AMDs) and we determined their lactation risk. METHODS: For each AMD, we collected all retrievable data from Hale's Medications and Mother Milk (2012), from the LactMed database (2014) of the National Library of Medicine, and from a MedLine Search of relevant studies published in the last 10 years. RESULTS: According to our review, AMDs safe during breastfeeding are as follows: low-dose acetylsalicylic acid (ASA), ibuprofen, sumatriptan, metoprolol, propranolol, verapamil, amitriptyline, escitalopram, paroxetine, sertraline, acetaminophen, caffeine, and metoclopramide. AMDs compatible with breastfeeding but warranting caution are as follows: diclofenac, ketoprofen, naproxen, most new triptans, topiramate, valproate, venlafaxine, and cyproheptadine. Finally, high-dose ASA, atenolol, nadolol, cinnarizine, flunarizine, ergotamine, methysergide, and pizotifen are contraindicated. CONCLUSIONS: According to our review, the majority of the revised AMDs were assessed to be compatible with breastfeeding.
Keywords: Adrenergic beta-Antagonists; Analgesics, Non-Narcotic; Animals; Anti-Inflammatory Agents, Non-Steroidal; Anticonvulsants; Antidepressive Agents; Breast Feeding; Calcium Channel Blockers; Female; Humans; Migraine Disorders; Tryptamines

C1q as a unique player in angiogenesis with therapeutic implication in wound healing. - Bossi, Fleur; Tripodo, Claudio; Rizzi, Lucia; Bulla, Roberta; Agostinis, Chiara; Guarnotta, Carla; Munaut, Carine; Baldassarre, Gustavo; Papa, Giovanni; Zorzet, Sonia; Ghebrehiwet, Berhane; Ling, Guang Sheng; et al. (Proc Natl Acad Sci U S A, 2014)
We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound healing we observed that vessel formation was defective in C1qa(-/-) mice and was restored to normal after local application of C1q. The mean vessel density of wound-healing tissue and the healed wound area were significantly increased in C1q-treated rats. On the basis of these results we suggest that C1q may represent a valuable therapeutic agent that can be used to treat chronic ulcers or other pathological conditions in which angiogenesis is impaired, such as myocardial ischemia.
Keywords: Animals; Cell Proliferation; Complement C1q; DNA Primers; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Human Umbilical Vein Endothelial Cells; Humans; Immunoblotting; Immunohistochemistry; In Situ Hybridization; Mice; Mice, Inbred C57BL; Mice, Knockout; Neovascularization, Physiologic; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Wound Healing

Can body mass index accurately predict adiposity in newborns? - De Cunto, Angela; Paviotti, Giulia; Ronfani, Luca; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2014)
Body mass index (BMI) is correlated with body fatness and risk of related diseases in children and adults. Proportionality indexes such as BMI and ponderal index (PI) have been suggested as complementary measures in neonatal growth assessment. Yet, they are still not used in neonates and their correlation with fatness is unknown. The aim of the study was to test the hypothesis that BMI z-score would predict neonatal adiposity. Body composition measurements (ie, fat mass, fat-free mass) by air displacement plethysmography (PEA POD, LMI, Concord-USA), weight and length were obtained in 200 infants ≥36 weeks' gestational age (GA) at birth. Linear regression analysis showed a direct association between BMI z-score and %fat mass (r(2)=0.43, p<0.0001). This association was confirmed independently from sex, GA and maternal prepregnancy BMI. BMI z-score predicted adiposity better than PI. However, both BMI z-score and PI were poor predictors of adiposity at birth.
Keywords: Adiposity; Adult; Anthropometry; Body Composition; Body Mass Index; Cross-Sectional Studies; Female; Gestational Age; Humans; Infant, Newborn; Male; Mothers; Plethysmography; Predictive Value of Tests; Regression Analysis; Reproducibility of Results; Sex Factors

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Class IV laser therapy as treatment for chemotherapy-induced oral mucositis in onco-haematological paediatric patients: a prospective study. - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A; Verzegnassi, Federico; Treister, Nathaniel S; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena (Int J Paediatr Dent, 2014)
BACKGROUND: Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). AIM: This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. DESIGN: Eighteen onco-haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re-evaluated 11 days after the first day of laser therapy. RESULTS: All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11-day follow-up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1-2 days of laser therapy. CONCLUSIONS: Given class IV laser therapy appears to be safe, non-invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.

Clinical features and follow-up in patients with 22q11.2 deletion syndrome. - Cancrini, Caterina; Puliafito, Pamela; Digilio, Maria Cristina; Soresina, Annarosa; Martino, Silvana; Rondelli, Roberto; Consolini, Rita; Ruga, Ezia Maria; Cardinale, Fabio; Finocchi, Andrea; Romiti, Maria Luisa; Martire, Baldassarre; et al. (J Pediatr, 2014)
OBJECTIVE: To investigate the clinical manifestations at diagnosis and during follow-up in patients with 22q11.2 deletion syndrome to better define the natural history of the disease. STUDY DESIGN: A retrospective and prospective multicenter study was conducted with 228 patients in the context of the Italian Network for Primary Immunodeficiencies. Clinical diagnosis was confirmed by cytogenetic or molecular analysis. RESULTS: The cohort consisted of 112 males and 116 females; median age at diagnosis was 4 months (range 0 to 36 years 10 months). The diagnosis was made before 2 years of age in 71% of patients, predominantly related to the presence of heart anomalies and neonatal hypocalcemia. In patients diagnosed after 2 years of age, clinical features such as speech and language impairment, developmental delay, minor cardiac defects, recurrent infections, and facial features were the main elements leading to diagnosis. During follow-up (available for 172 patients), the frequency of autoimmune manifestations (P = .015) and speech disorders (P = .002) increased. After a median follow-up of 43 months, the survival probability was 0.92 at 15 years from diagnosis. CONCLUSIONS: Our data show a delay in the diagnosis of 22q11.2 deletion syndrome with noncardiac symptoms. This study provides guidelines for pediatricians and specialists for early identification of cases that can be confirmed by genetic testing, which would permit the provision of appropriate clinical management.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Age Factors; Child; Child, Preschool; Chromosomes, Human, Pair 22; Delayed Diagnosis; Developmental Disabilities; DiGeorge Syndrome; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; Genetic Testing; Humans; Infant; Infant, Newborn; Male; Monitoring, Physiologic; Prospective Studies; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Time Factors; Young Adult

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

A comparison of three scales for measuring pain in children with cognitive impairment. - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio (Acta Paediatr, 2014)
AIM: Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non-Communicating Children's Pain Checklist Postoperative Version (NCCPC-PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. METHODS: Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter-rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. RESULTS: The correlation between the NCCPC-PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter-rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC-PV was the easiest use and the most appropriate for rating the child's pain. CONCLUSION: The NCCPC-PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.

Consanguinity and hereditary hearing loss in Qatar. - Girotto, Giorgia; Mezzavilla, Massimo; Abdulhadi, Khalid; Vuckovic, Dragana; Vozzi, Diego; Khalifa Alkowari, Moza; Gasparini, Paolo; Badii, Ramin (Hum Hered, 2014)
Qatar is a sovereign state located on the Eastern coast of the Arabian Peninsula in the Persian Gulf. Its native population consists of 3 major subgroups: people of Arabian origin or Bedouins, those from an Eastern or Persian ancestry and individuals with African admixture. Historically, all types of consanguineous marriages have been and still are common in the Qatari population, particularly among first and double-first cousins. Thus, there is a higher risk for most inherited diseases including hereditary hearing loss (HHL). In particular, a hearing loss prevalence of 5.2% has been reported in Qatar, with parental consanguinity being more common among affected individuals as compared with unaffected ones. Our recent molecular results confirm a high homogeneity and level of inbreeding in Qatari HHL patients. Among all HHL genes, GJB2, the major player worldwide, accounts for a minor proportion of cases and at least 3 additional genes have been found to be mutated in Qatari patients. Interestingly, one gene, BDP1, has been described to cause HHL only in this country. These results point towards an unexpected level of genetic heterogeneity despite the high level of inbreeding. This review provides an up-to-date picture of HHL in Qatar and of the impact of consanguinity on this disease.
Keywords: Consanguinity; Hearing Loss; Homozygote; Humans; Inheritance Patterns; Pedigree; Prevalence; Principal Component Analysis; Qatar; Transcription Factor TFIIIB

Cow's milk allergy in children, from avoidance to tolerance. - Calligaris, Lorenzo; Longo, Giorgio; Badina, Laura; Berti, Irene; Barbi, Egidio (Endocr Metab Immune Disord Drug Targets, 2014)
Food allergy is the primary cause of anaphylaxis in paediatric age affecting roughly 4% of children and their families worldwide, and requiring changes in dietary habits. The prognosis for food allergy in children has traditionally been regarded as good for the most frequent allergens, however the prognosis for cow's milk allergy in the pediatric age is currently considered to be worse than previously believed. There is now enough evidence that measures of avoidance for children at risk did not have any preventive effect whatsoever, but they still came to be counterproductive by avoiding the physiological interaction between food allergens and gastrointestinal mucosal immune system. Programs of specific oral tolerance induction (SOTI) have obtained interesting results in the treatment of food allergy supporting the idea that antigen exposure through gastrointestinal section is important to allow the development of tolerance. Nevertheless this approach is not yet considered "ready" for community recommendations. In this paper we describe our experience in the field of SOTI in children with cow's milk allergy.
Keywords: Animals; Cattle; Child; Child, Preschool; Desensitization, Immunologic; Humans; Immune Tolerance; Milk Hypersensitivity; Milk Substitutes; Retrospective Studies

Curcumin and inflammatory bowel disease: potential and limits of innovative treatments. - Vecchi Brumatti, Liza; Marcuzzi, Annalisa; Tricarico, Paola Maura; Zanin, Valentina; Girardelli, Martina; Bianco, Anna Monica (Molecules, 2014)
Curcumin belongs to the family of natural compounds collectively called curcuminoids and it possesses remarkable beneficial anti-oxidant, anti-inflammatory, anti-cancer, and neuroprotective properties. Moreover it is commonly assumed that curcumin has also been suggested as a remedy for digestive diseases such as inflammatory bowel diseases (IBD), a chronic immune disorder affecting the gastrointestinal tract and that can be divided in two major subgroups: Crohn's disease (CD) and Ulcerative Colitis (UC), depending mainly on the intestine tract affected by the inflammatory events. The chronic and intermittent nature of IBD imposes, where applicable, long-term treatments conducted in most of the cases combining different types of drugs. In more severe cases and where there has been no good response to the drugs, a surgery therapy is carried out. Currently, IBD-pharmacological treatments are generally not curative and often present serious side effects; for this reason, being known the relationship between nutrition and IBD, it is worthy of interesting the study and the development of new dietary strategy. The curcumin principal mechanism is the suppression of IBD inflammatory compounds (NF-κB) modulating immune response. This review summarizes literature data of curcumin as anti-inflammatory and anti-oxidant in IBD, trying to understand the different effects in CD e UC.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Chemistry, Pharmaceutical; Clinical Trials as Topic; Curcumin; Humans; Inflammatory Bowel Diseases; Molecular Targeted Therapy; Nanotechnology; Treatment Outcome

DC-SIGN polymorphisms are associated to type 1 diabetes mellitus. - da Silva, Ronaldo Celerino; Cunha Tavares, Nathália de Alencar; Moura, Ronald; Coelho, Antônio; Guimarães, Rafael Lima; Araújo, Jacqueline; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Silva, Jaqueline de Azevêdo (Immunobiology, 2014)
Type I diabetes mellitus (T1DM) is an autoimmune disorder featured by raised glucoses levels. It has been hypothesised that raised glucose levels in T1DM might be recognised as PAMPs, leading to immune response by overloading the cell receptors for pathogens recognition. DC-SIGN is a transmembrane protein, present in dendritic cells (DC) and macrophages: it has an important role in inflammatory response and T cells activation. Notably, DC-SIGN activation and triggering of the immune response depend on the type of ligand, which may lead to a pro or anti-inflammatory pathway. In our association study, we analysed the SNPs rs4804803 (-336 A>G) and rs735239 (-871 A>G), both at DC-SIGN promoter region, in 210 T1DM patients and 157 healthy controls, also looking for a correlation with the age of onset of the disease. We found that the allele G and genotypes G/G and A/G of SNP-871 (rs735239), as well as the alleles G-G (rs735239-rs4804803) and genotypes combined AA-GG (rs735239-rs4804803) were associated with protection of T1DM development. We did not find association between these variations with the age of onset of the disease and the presence of other autoimmune disorders. Our results suggest that SNPs in DC-SIGN promoter region can be associated to protection for T1DM in the Northeast Brazilian population.
Keywords: Adolescent; Alleles; Case-Control Studies; Cell Adhesion Molecules; Child; Child, Preschool; Diabetes Mellitus, Type 1; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Infant; Infant, Newborn; Lectins, C-Type; Male; Odds Ratio; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface

Development of an enzyme-linked immunosorbent assay for Bartonella henselae infection detection. - Ferrara, F; Di Niro, R; D'Angelo, S; Busetti, M; Marzari, R; Not, T; Sblattero, D (Lett Appl Microbiol, 2014)
UNLABELLED: Several serological diagnostics rely on enzyme-linked immunosorbent assay (ELISA) to detect bacterial infections. However, for some pathogens, including Bartonella henselae, diagnosis still depends on manually intensive, time-consuming assays including micro-immunofluorescence, Western blotting or indirect immunofluorescence. For such pathogens, there is obviously still a need to identify antigens to establish a reliable, fast and high-throughput assay (Dupon et al. ). We evaluated two B. henselae proteins to develop a novel serological ELISA: a well-known antigen, the 17-kDa protein, and GroEL, identified during this study by a proteomic approach. When serum IgG were tested, the specificity and sensitivity were 76 and 65·7% for 17-kDa, respectively, and 82 and 42·9% for GroEL, respectively. IgM were found to be more sensitive and specific for both proteins: 17-kDa protein, specificity 86·2% and sensitivity 75%; GroEL, specificity 97·7% and sensitivity 45·3%. IgM antibodies were also measured in lymphoma patients and patients with Mycobacterium tuberculosis infection to assess the usefulness of our ELISA to distinguish them from B. henselae infected patients. The resulting specificities were 89·1 and 93·5% for 17-kDa protein and GroEL, respectively. Combining the results from the two tests, we obtained a sensitivity of 82·8% and a specificity of 83·9%. Our work described and validated a proteomic approach suitable to identify immunogenic proteins useful for developing a serological test of B. henselae infection. SIGNIFICANCE AND IMPACT OF THE STUDY: A reliable serological assay for the diagnosis of Cat Scratch Disease (CSD) - a pathological condition caused by Bartonella henselae infection - has not yet been developed. Such an assay would be extremely useful to discriminate between CSD and other pathologies with similar symptoms but different aetiologies, for example lymphoma or tuberculosis. We investigate the use of two B. henselae proteins - GroEL and 17-kDa - to develop a serological-based ELISA, showing promising results with the potential for further development as an effective tool for the differential diagnosing of B. henselae infection.
Keywords: Adolescent; Adult; Amino Acid Sequence; Antibodies, Bacterial; Antigens, Bacterial; Bacterial Proteins; Bartonella henselae; Case-Control Studies; Cat-Scratch Disease; Chaperonin 60; Child; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; Humans; Immunoglobulin M; Lymphoma; Male; Molecular Sequence Data; ROC Curve; Tuberculosis, Pulmonary; Young Adult

Diagnostic accuracy of ultrasonography for hand bony fractures in paediatric patients. - Neri, Elena; Barbi, Egidio; Rabach, Ingrid; Zanchi, Chiara; Norbedo, Stefania; Ronfani, Luca; Guastalla, Veronica; Ventura, Alessandro; Guastalla, Pierpaolo (Arch Dis Child, 2014)
OBJECTIVE: Hand fractures are common in childhood, and radiography is the standard diagnostic procedure. US has been used to evaluate bone injuries, mainly in adults for long-bone trauma; there are only a few studies about hand fractures in children. The purpose of this study was to evaluate and confirm the safety and applicability of the US diagnostic procedure in comparison to X-ray diagnosis. STUDY DESIGN: This cross-sectional study involved a convenience sample of young patients (between 2 and 17 years old) who were taken to the emergency department due to hand trauma. After clinical assessment, patients with a suspected hand fracture first underwent X-ray, and subsequently US examination by two different operators; a radiologist experienced in US and a trained emergency physician in "double-blind" fashion. US and radiographic findings were then compared, and sensitivity as well as specificity was calculated. RESULTS: A total of 204 patients were enrolled in the study. Seventy-nine fractures of phalanges or metacarpals were detected by standard radiography. When US imaging was performed by an expert radiologist, 72 fractures were detected with sensitivity and a specificity of 91.1% and 97.6%, respectively. Sensitivity and specificity were found to be (respectively) 91.5% and 96.8% when US was performed by the ED physicians. CONCLUSIONS: US imaging showed excellent sensitivity and specificity results in the diagnosis of hand fractures in children. The study also showed a great agreement between the results of the US carried out by the senior radiologist and those carried out by the paediatric emergency physician, suggesting that US can be performed by an ED physician, allowing a rapid and accurate evaluation in ED and could become the first diagnostic approach whenever a hand fracture is suspected.
Keywords: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Double-Blind Method; Emergency Service, Hospital; Female; Fractures, Bone; Hand Bones; Humans; Italy; Male; Sensitivity and Specificity

Differences in time course activation of dorsolateral prefrontal cortex associated with low or high risk choices in a gambling task. - Bembich, Stefano; Clarici, Andrea; Vecchiet, Cristina; Baldassi, Giulio; Cont, Gabriele; Demarini, Sergio (Front Hum Neurosci, 2014)
Prefrontal cortex plays an important role in decision making (DM), supporting choices in the ordinary uncertainty of everyday life. To assess DM in an unpredictable situation, a playing card task, such as the Iowa Gambling Task (IGT), has been proposed. This task is supposed to specifically test emotion-based learning, linked to the integrity of the ventromedial prefrontal cortex (VMPFC). However, the dorsolateral prefrontal cortex (DLPFC) has demonstrated a role in IGT performance too. Our aim was to study, by multichannel near-infrared spectroscopy, the contribution of DLPFC to the IGT execution over time. We tested the hypothesis that low and high risk choices would differentially activate DLPFC, as IGT execution progressed. We enrolled 11 healthy adults. To identify DLPFC activation associated with IGT choices, we compared regional differences in oxy-hemoglobin variation, from baseline to the event. The time course of task execution was divided in four periods, each one consisting of 25 choices, and DLPFC activation was distinctly analyzed for low and high risk choices in each period. We found different time courses in DLPFC activation, associated with low or high risk choices. During the first period, a significant DLPFC activation emerged with low risk choices, whereas, during the second period, we found a cortical activation with high risk choices. Then, DLPFC activation decreased to non-significant levels during the third and fourth period. This study shows that DLPFC involvement in IGT execution is differentiated over time and according to choice risk level. DLPFC is activated only in the first half of the task, earlier by low risk and later by high risk choices. We speculate that DLPFC may sustain initial and more cognitive functions, such as attention shifting and response inhibition. The lack of DLPFC activation, as the task progresses, may be due to VMPFC activation, not detectable by fNIRS, which takes over the IGT execution in its second half.

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Doing without codeine: why and what are the alternatives? - Benini, Franca; Barbi, Egidio (Ital J Pediatr, 2014)
Codeine is a mild opioid widely used as an analgesic in various age groups, including various pediatric settings. It is a prodrug that owes its analgesic effect almost entirely to the principal metabolite: morphine. The genetic polymorphisms can contribute to making the pharmacokinetics of codeine hard to predict and this it is particularly important in the pediatric population because infants and children have greater susceptibility to the side-effects of morphine. In recent years there have been several reports in the literature on the risks relating to the use of codeine. In August 2012, the American Food and Drugs Administration began to revise its recommendations for the safe use of codeine and in February 2013, established that codeine should not be used for postoperative pain control in children undergoing adenoidectomy and/or tonsillectomy and did restrict the use of this drug in the pediatric population. In June 2013, the European Medicine Agency opted the same decision. In July 2013, the Agenzia Italiana del Farmaco prohibit the use of medicines containing codeine for patients under 12 years old and recommended a limited use of the drug, in many other situations. Complying with these recommendations naturally means changing habits and treatment strategies well established in pediatric practice, but other drugs, tools and techniques available enable us to continue to assure an adequate pain control in pediatric patients, irrespective of their age and situation. The article proposes same alternatives of pain control drugs.
Keywords: Acetaminophen; Analgesics, Non-Narcotic; Analgesics, Opioid; Child; Codeine; Humans; Pain Measurement; Pain, Postoperative; Tonsillectomy

Effects of estroprogestins containing natural estrogen on vaginal flora. - De Seta, Francesco; Restaino, Stefano; Banco, Rubina; Conversano, Ester; De Leo, Rossella; Tonon, Maddalena; Maso, Gianpaolo; Barbati, Giulia; Lello, Stefano (Gynecol Endocrinol, 2014)
Estroprogestins with "natural oestrogen" has represented a new option in terms of combined hormonal contraception. So, the aim of this study is to investigate how estroprogestins with natural estrogen may modify the vaginal niche. In literature, very few studies focused on the interaction between hormonal contraception and vaginal milieu. This is a prospective comparative study. We enrolled 60 women from January 2013 to September 2013, 30 of them were administered estradiol valerate dienogest (E2V+DNG - Klaira®) in a quadriphasic regimen, while the other 30 women were administered 17-β estradiol with nomestrol acetate (EV+NOMAC - Zoely®) in a monophasic regimen. After a baseline study of vaginal milieu at recruitment of patients (Gram stain with Nugent score, vaginal pH, vaginal wet mount for the quantification of leukocytes, Lactobacilli and/or presence of Candida), we performed the same follow-up after six months of estroprogestin therapy. Our results showed that the women treated with E2V+DNG had a trend of an improvement of vaginal health in terms of increase of lactobacillar flora and reduction of vaginal pH in place of women treated with EV+NOMAC that showed a reduction of cervical mucus. Finally, our data about the effects on vaginal flora exerted by two estroprogestin pills (EPs) containing a natural estrogen suggest slight, but interesting differences in terms of vaginal ecology. These differences could be related to the type of estrogen, type of progestin, regimen of administration and, after all, to the net balance between estrogenic and progestin component of the EPs.
Keywords: Adolescent; Adult; Drug Combinations; Estradiol; Female; Humans; Megestrol; Middle Aged; Nandrolone; Norpregnadienes; Prospective Studies; Vagina; Young Adult

Expression and replication studies to identify new candidate genes involved in normal hearing function. - Girotto, Giorgia; Vuckovic, Dragana; Buniello, Annalisa; Lorente-Cánovas, Beatriz; Lewis, Morag; Gasparini, Paolo; Steel, Karen P (PLoS One, 2014)
Considerable progress has been made in identifying deafness genes, but still little is known about the genetic basis of normal variation in hearing function. We recently carried out a Genome Wide Association Study (GWAS) of quantitative hearing traits in southern European populations and found several SNPs with suggestive but none with significant association. In the current study, we followed up these SNPs to investigate which of them might show a genuine association with auditory function using alternative approaches. Firstly, we generated a shortlist of 19 genes from the published GWAS results. Secondly, we carried out immunocytochemistry to examine expression of these 19 genes in the mouse inner ear. Twelve of them showed distinctive cochlear expression patterns. Four showed expression restricted to sensory hair cells (Csmd1, Arsg, Slc16a6 and Gabrg3), one only in marginal cells of the stria vascularis (Dclk1) while the others (Ptprd, Grm8, GlyBP, Evi5, Rimbp2, Ank2, Cdh13) in multiple cochlear cell types. In the third step, we tested these 12 genes for replication of association in an independent set of samples from the Caucasus and Central Asia. Nine out of them showed nominally significant association (p<0.05). In particular, 4 were replicated at the same SNP and with the same effect direction while the remaining 5 showed a significant association in a gene-based test. Finally, to look for genotype-phenotype relationship, the audiometric profiles of the three genotypes of the most strongly associated gene variants were analyzed. Seven out of the 9 replicated genes (CDH13, GRM8, ANK2, SLC16A6, ARSG, RIMBP2 and DCLK1) showed an audiometric pattern with differences between different genotypes further supporting their role in hearing function. These data demonstrate the usefulness of this multistep approach in providing new insights into the molecular basis of hearing and may suggest new targets for treatment and prevention of hearing impairment.
Keywords: Adult; Animals; DNA Replication; Gene Expression Profiling; Genome-Wide Association Study; Genotype; Hair Cells, Auditory; Hearing; Humans; Mice; Phenotype; Polymorphism, Single Nucleotide; Stria Vascularis

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation

The first trimester gravid serum regulates procalcitonin expression in human macrophages skewing their phenotype in vitro. - Rami, Damiano; La Bianca, Martina; Agostinis, Chiara; Zauli, Giorgio; Radillo, Oriano; Bulla, Roberta (Mediators Inflamm, 2014)
Procalcitonin (PCT) is one of the best diagnostic and prognostic markers in clinical practice, widely used to evaluate the evolution of bacterial infections. Although it is mainly produced by thyroid, during sepsis almost all the peripheral tissues are involved in PCT production. Parenchymal cells have been suggested as the main source of PCT expression; however the contribution of macrophages is not clear yet. In response to environmental cues, tissue macrophages acquire distinct functional phenotypes, ranging from proinflammatory (M1) to anti-inflammatory (M2) phenotype. Macrophages at the fetal-maternal interface show immunosuppressive M2-like activities required for the maintenance of immunological homeostasis during pregnancy. This study aims to clarify the ability to synthesise PCT of fully differentiated (M0), polarized (M1/M2) macrophages and those cultured either in the presence of first trimester gravid serum (GS) or pregnancy hormones. We found out that M1 macrophages upregulate PCT expression following LPS stimulation compared to M0 and M2. The GS downregulates PCT expression in macrophages, skewing them towards an M2-like phenotype. This effect seems only partially mediated by the hormonal milieu. Our findings strengthen the key role of macrophages in counteracting inflammatory stimuli during pregnancy, suggesting PCT as a possible new marker of M1-like macrophages.
Keywords: Biomarkers; Calcitonin; Cells, Cultured; Chorionic Gonadotropin; Estradiol; Female; Gene Expression Regulation; Homeostasis; Humans; Inflammation; Macrophages; Monocytes; Phenotype; Pregnancy; Pregnancy Trimester, First; Protein Precursors; Serum; Up-Regulation

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Hemophagocytic lymphohistiocytosis in total parenteral nutrition dependent children: description of 5 cases and practical tips for management. - Pastore, Serena; Barbieri, Francesca; Di Leo, Grazia; Valencic, Erica; Tommasini, Alberto; Ventura, Alessandro (J Pediatr Hematol Oncol, 2014)
Although total parenteral nutrition (TPN) is mandatory in children with intestinal failure, this treatment is not risk free. The main complications of TPN include catheter-related sepsis, thrombosis, hepatic cholestasis and cirrhosis, metabolic bone disease, and, rarely, reactive hemophagocytic lymphohistiocytosis (HLH). The pathogenesis of HLH in patients with TPN is not known, although some authors hypothesized that it can result from the activation of macrophages because of "fat overload." We reported 5 cases of HLH that occurred in patients with 4 different underlying disorders, all requiring TPN for a long term. In our series, an underlying immunological defect or a serious infection (sepsis) can have triggered HLH. Therefore, it could be reasonable to hypothesize that besides TPN in itself, minor immune defects and infections may act together by overcoming a threshold of immune stimulation, which ultimately leads to HLH.
Keywords: Child, Preschool; Fatty Acids; Female; Humans; Infant; Intestinal Diseases; Lymphohistiocytosis, Hemophagocytic; Male; Parenteral Nutrition, Total; Steroids; Treatment Outcome

Hereditary hearing loss: a 96 gene targeted sequencing protocol reveals novel alleles in a series of Italian and Qatari patients. - Vozzi, D; Morgan, A; Vuckovic, D; D'Eustacchio, A; Abdulhadi, K; Rubinato, E; Badii, R; Gasparini, P; Girotto, G (Gene, 2014)
Deafness is a really common disorder in humans. It can begin at any age with any degree of severity. Hereditary hearing loss is characterized by a vast genetic heterogeneity with more than 140 loci described in humans but only 65 genes so far identified. Families affected by hearing impairment would have real advantages from an early molecular diagnosis that is of primary relevance in genetic counseling. In this perspective, here we report a family-based approach employing Ion Torrent DNA sequencing technology to analyze coding and UTR regions of 96 genes related to hearing function and loss in a first series of 12 families coming from Italy and Qatar. Using this approach we were able to find the causative gene in 4 out of these 12 families (33%). In particular 5 novel alleles were identified in the following genes LOXHD1, TMPRSS3, TECTA and MYO15A already associated with hearing impairment. Our study confirms the usefulness of a targeted sequencing approach despite larger numbers are required for further validation and for defining a molecular epidemiology picture of hearing loss in these two countries.
Keywords: Alleles; Amino Acid Sequence; Carrier Proteins; Extracellular Matrix Proteins; Female; Genetic Testing; GPI-Linked Proteins; Hearing Loss; Humans; Italy; Male; Membrane Proteins; Molecular Sequence Data; Mutation; Myosins; Neoplasm Proteins; Pedigree; Qatar; Sequence Analysis, DNA; Serine Endopeptidases; Untranslated Regions

High-frequency percussive ventilation as rescue treatment in severe hypoxemic respiratory failure in term neonates. - Paviotti, Giulia; Bua, Jenny; De Cunto, Angela; Travan, Laura; Demarini, Sergio (J Crit Care, 2014)
Keywords: Female; High-Frequency Ventilation; Humans; Male; Oxygen; Pulmonary Gas Exchange; Respiratory Insufficiency

HLA-G gene polymorphisms associated with susceptibility to rheumatoid arthritis disease and its severity in Brazilian patients. - Catamo, E; Addobbati, C; Segat, L; Sotero Fragoso, T; Domingues Barbosa, A; Tavares Dantas, A; de Ataíde Mariz, H; F da Rocha, L; Branco Pinto Duarte, A L; Monasta, L; Sandrin-Garcia, P; Crovella, S (Tissue Antigens, 2014)
We analyzed the possible association between human leukocyte antigen-G (HLA-G) genetic variants, supposed to regulate HLA-G expression, and the susceptibility to develop rheumatoid arthritis (RA) as well as its clinical manifestations. The 5'upstream regulatory region (5'URR) and 3'untranslated region (3'UTR) regions of the HLA-G gene were screened in 127 RA patients and 128 controls: 10 5'URR and 3 3'UTR HLA-G polymorphisms as well as two haplotypes were associated with risk for RA development, while a polymorphism in the 5'URR showed an association with the degree of disease activity. These findings, although the number of cases analyzed is limited and the P-values are modest, indicate a possible association between HLA-G gene polymorphisms and susceptibility to develop RA disease and its severity.
Keywords: 3' Untranslated Regions; 5' Flanking Region; Aged; Arthritis, Rheumatoid; Brazil; Disease Progression; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Haplotypes; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult

Immunomodulation mediated by a herbal syrup containing a standardized Echinacea root extract: a pilot study in healthy human subjects on cytokine gene expression. - Dapas, B; Dall'Acqua, S; Bulla, R; Agostinis, C; Perissutti, B; Invernizzi, S; Grassi, G; Voinovich, D (Phytomedicine, 2014)
In this study, the immunomodulatory effect of a triply standardized Echinacea angustifolia root extract (Polinacea(®)) was evaluated in 10 healthy subjects. Ten ml of syrup containing one hundred mg of extract (corresponding to 4.7 mg of Echinacoside and 8.0mg of a high molecular weight-20,000 Da- polysaccharide) were administered as a herbal syrup once a day for one month. The immunomodulatory effect was evaluated before and after herbal syrup administration evaluating the expression levels of the cytokines IL-2, IL-8, IL-6 and TNF-α. Cytokine expression was studied in lympho-monocytes and in plasma samples measuring the mRNA and protein levels, respectively. The results were analysed by ANOVA and non-parametric Friedman rank sum tests; when possible it was adopted a pair-wise comparisons at different post-treatment times, using the paired t-tests with Holm correction. The correlation between the variations of cytokine plasma levels and the respective mRNA was carried out using a linear regression model. In lympho-monocytes our data indicate the up-regulation of the mRNA levels of IL-2 and IL-8 and the down regulation of the mRNA levels of the pro-inflammatory cytokines TNF-α and IL6. The differential regulation was maximal after 14 days of treatment. IL-2 up-regulation and IL-6 down-regulation were also confirmed at the protein level in plasma. Finally, the up-regulation of the mRNA of IL-2/IL-8 and the down-regulation of IL-6 positively correlated with the protein levels detected in the plasma. In conclusion, this pilot study suggests a relevant role for the standardized Echinacea angustifolia root extract in the control of cytokine expression. This first demonstration of the immuno-modulating activity of Echinacea angustifolia root extract in the healthy subject, supports at least in part the common use of such products as health promoting supplement.
Keywords: Adult; Cytokines; Down-Regulation; Echinacea; Female; Glycosides; Healthy Volunteers; Humans; Immunomodulation; Interleukin-2; Interleukin-6; Interleukin-8; Lymphocytes; Male; Middle Aged; Monocytes; Pilot Projects; Plant Extracts; Plant Roots; Tumor Necrosis Factor-alpha

Increased levels of C-C chemokine RANTES in asbestos exposed workers and in malignant mesothelioma patients from an hyperendemic area. - Comar, Manola; Zanotta, Nunzia; Bonotti, Alessandra; Tognon, Mauro; Negro, Corrado; Cristaudo, Alfonso; Bovenzi, Massimo (PLoS One, 2014)
BACKGROUND: Asbestos-induced mesothelial inflammatory processes are thought to be the basic mechanisms underlying Malignant Mesothelioma (MM) development. Detection of MM often occurs at late stage due to the long and unpredictable latent period and the low incidence in asbestos exposed individuals. The aim of this study was to investigate early immunological biomarkers to characterize the prognostic profile of a possible asbestos-induced disease, in subjects from a MM hyperendemic area. METHODS: The Luminex Multiplex Panel Technology was used for the simultaneous measurement of serum levels of a large panel of 47 analytes, including cytokines and growth factors, from workers previously exposed to asbestos (Asb-workers), asbestos-induced MM patients and healthy subjects. In addition, to explore the influence on serum cytokines profile exerted by SV40 infection, a cofactor in MM development, a quantitative real time PCR was performed for sequences detection in the N-terminal and intronic regions of the SV40 Tag gene. Statistical analysis was done by means of the Mann-Whitney test and the Kruskall-Wallis test for variance analysis. RESULTS: A variety of 25 cytokines linked to pulmonary inflammation and tumor development were found significantly associated with Asb-workers and MM patients compared with healthy controls. A specific pattern of cytokines were found highly expressed in Asb-workers: IFN-alpha (p<0.05), EOTAXIN (p<0.01), RANTES (p<0.001), and in MM patients: IL-12(p40), IL-3, IL-1 alpha, MCP-3, beta-NGF, TNF-beta, RANTES (p<0.001). Notably, the chemokine RANTES measured the highest serum level showing an increased gradient of concentration from healthy subjects to Asb-workers and MM patients (p<0.001), independently of SV40 infection. CONCLUSION: This study shows that, in subjects from an hyperendemic area for MM, the C-C chemokine RANTES is associated with the exposure to asbestos fibres. If validated in larger samples, this factor could have the potential to be a critical biomarker for MM prognosis as recently reported for breast tumor.
Keywords: Aged; Aged, 80 and over; Asbestos; Biomarkers, Tumor; Case-Control Studies; Chemokine CCL5; Cytokines; Endemic Diseases; Gene Expression; Gene Expression Profiling; Humans; Lung Neoplasms; Mesothelioma; Middle Aged; Occupational Exposure; Simian virus 40; Viral Proteins

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

Insight into genetic determinants of resting heart rate. - Mezzavilla, Massimo; Iorio, Annamaria; Bobbo, Marco; D'Eustacchio, Angela; Merlo, Marco; Gasparini, Paolo; Ulivi, Sheila; Sinagra, Gianfranco (Gene, 2014)
BACKGROUND: Recent studies suggested that resting heart rate (RHR) might be an independent predictor of cardiovascular mortality and morbidity. Nonetheless, the interrelation between RHR and cardiovascular diseases is not clear. In order to resolve this puzzle, the importance of genetic determinants of RHR has been recently suggested, but it needs to be further investigated. OBJECTIVE: The aim of this study was to estimate the contribution of common genetic variations on RHR using Genome Wide Association Study. METHODS: We performed a Genome Wide Association Study in an isolated population cohort of 1737 individuals, the Italian Network on Genetic Isolates - Friuli Venezia Giulia (INGI-FVG). Moreover, a haplotype analysis was performed. A regression tree analysis was run to highlight the effect of each haplotype combination on the phenotype. RESULTS: A significant level of association (p<5 × 10(-8)) was detected for Single Nucleotide Polymorphisms (SNPs) in two genes expressed in the heart: MAML1 and CANX. Founding that the three different variants of the haplotype, which encompass both genes, yielded a phenotypic correlation. Indeed, a haplotype in homozygosity is significantly associated with the lower quartile of RHR (RHR ≤ 58 bpm). Moreover no significant association was found between cardiovascular risk factors and the different haplotype combinations. CONCLUSION: Mastermind-like 1 and Calnexin were found to be associated with RHR. We demonstrated a relation between a haplotype and the lower quartile of RHR in our populations. Our findings highlight that genetic determinants of RHR may be implicated in determining cardiovascular diseases and could allow a better risk stratification.
Keywords: Calnexin; Cardiovascular Diseases; DNA-Binding Proteins; Female; Genome-Wide Association Study; Haplotypes; Heart Rate; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Transcription Factors

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Juvenile stroke in combined syndrome of hereditary hemorrhagic telangiectasia and juvenile polyposis. - Mazzucco, Sara; Benini, Luigi; Gallione, Carol; d'Adamo, Pio; Girelli, Domenico (Neurol Sci, 2014)
Keywords: Adult; Arteriovenous Malformations; Brain Ischemia; Chromosomes, Human, Pair 18; Echocardiography, Transesophageal; Embolism, Paradoxical; Embolization, Therapeutic; Epistaxis; Family Health; Humans; Intestinal Polyposis; Intracranial Embolism; Introns; Lod Score; Male; Pulmonary Artery; Smad4 Protein; Telangiectasia, Hereditary Hemorrhagic; Thalamus; Ultrasonography, Doppler, Transcranial

Lactobacillus plantarum P17630 for preventing Candida vaginitis recurrence: a retrospective comparative study. - De Seta, F; Parazzini, F; De Leo, R; Banco, R; Maso, G P; De Santo, D; Sartore, A; Stabile, G; Inglese, S; Tonon, M; Restaino, S (Eur J Obstet Gynecol Reprod Biol, 2014)
BACKGROUND: Recurrence is a frequent complaint of patients with vulvovaginal candidiasis (VVC). Although the pathogenesis of VVC remains a controversial issue, disruption of the balance between the vaginal microbiota may facilitate overgrowth by Candida. Some probiotic bacterial strains can suppress Candida albicans; Lactobacillus plantarum P17630 is able to attach to vaginal epithelial cells and significantly reduce the adhesion of C. albicans. OBJECTIVE: To evaluate the effect of the application of Lactobacillus plantarum P17630 in restoring the vaginal microbiota and prevention of relapses among women with acute VVC undergoing conventional (azole) local and main therapy. METHODS: Retrospective comparative study. We recruited 89 women with a diagnosis of VVC, who were placed into two groups on the basis of reported treatment. The control group was treated with a daily dose of 2% clotrimazole vaginal cream at bedtime for 3 days, followed by vaginal application of a capsule containing lubricant once a day for 6 days and then once a week for another 4 weeks. The probiotic group was treated with the same azole-based protocol but followed by vaginal application of a capsule containing Lactobacillus plantarum P17630 (>10₈ CFU) once a day for 6 days and then once a week for another 4 weeks beginning the day following clotrimazole discontinuation. Clinical and diagnostic patterns were monitored for three months of follow-up. RESULTS: At the end of study the probiotic-treated women showed a statistically significant increase in Lactobacillus values "+++" (80% versus 40%, p<0.001) and a better subjective resolution of symptoms such as vaginal discomfort described as burning or itching (90% versus 67.5%, p<0.03). Among controls there was a non-significant increase at 3 months of recurrence of infection, but a significant increase of women with value of pH=5 or >5. CONCLUSION: Although the results of different studies are controversial, most have suggested use of probiotics in the prevention or treatment of VVC, and no adverse effects have been reported. Our data with L. plantarum P17630 (Gyno-Canesflor - Bayer) confirm the role of this specific strain as a potential empirical preventive agent for reducing vaginal discomfort after conventional treatment of acute VVC and shifting the vaginal milieu toward a predominance of lactobacilli with an improvement of the vaginal pH value.
Keywords: Administration, Intravaginal; Adolescent; Adult; Antifungal Agents; Candidiasis, Vulvovaginal; Clotrimazole; Female; Humans; Lactobacillus plantarum; Microbiota; Middle Aged; Probiotics; Recurrence; Retrospective Studies; Secondary Prevention; Vagina; Vaginal Creams, Foams, and Jellies; Young Adult

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Management of central venous catheters in pediatric onco-hematology using 0.9% sodium chloride and positive-pressure-valve needleless connector. - Buchini, Sara; Scarsini, Sara; Montico, Marcella; Buzzetti, Roberto; Ronfani, Luca; Decorti, Cinzia (Eur J Oncol Nurs, 2014)
PURPOSE: To describe, in a sample of pediatric onco-hematological patients, the rate of occlusions in unused central venous catheters (CVC) flushed once a week with a 0.9% sodium chloride solution through a positive-pressure-valve needleless connector. METHOD: Retrospective cohort study. Subjects aged 0-17 years were identified through a manual search in medical and nursing records and were observed for two years or until the occurrence of one of the following events: start or resume of continuous infusion; CVC removal; death. The primary study outcome was the frequency of CVC occlusion (partial or complete). RESULTS: Fifty-one patients were identified (median age 6 years). The median duration of follow-up was 169 days (IQR 111-305). During the follow up period, 14 patients (27%) had one CVC occlusion, in 2 cases (4%) the occlusion was complete, in 12 (23%) partial. All the occlusions were solved without the need for catheter removal. The lumen diameter ≤ 4.2 vs > 4.2 French showed a statistically significant association with occlusion at multivariate analysis (OR 4.0; 95% CI 1.1-14.7). CONCLUSIONS: Our findings are reassuring with respect to the management of the CVC using the adopted protocol. The study provides useful information for patient care, by verifying the performance of the adopted CVC management protocol and by identifying critical areas for nursing care.
Keywords: Adolescent; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Child, Preschool; Cohort Studies; Equipment Design; Female; Hematology; Humans; Infant; Infant, Newborn; Italy; Male; Oncology Nursing; Pediatric Nursing; Practice Guidelines as Topic; Retrospective Studies; Sodium Chloride

Mevalonate kinase deficiency and IBD: shared genetic background. - Bianco, Anna Monica; Girardelli, Martina; Vozzi, Diego; Crovella, Sergio; Kleiner, Giulio; Marcuzzi, Annalisa (Gut, 2014)
Keywords: Genetic Predisposition to Disease; Humans; Inflammatory Bowel Diseases

Midline 1 directs lytic granule exocytosis and cytotoxicity of mouse killer T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Johansen, Bo B; Braunstein, Thomas H; Bonefeld, Charlotte M; Kongsbak, Martin; Jensen, Benjamin A H; Woetmann, Anders; Thomsen, Allan R; Odum, Niels; von Essen, Marina R; et al. (Eur J Immunol, 2014)
Midline 1 (MID1) is a microtubule-associated ubiquitin ligase that regulates protein phosphatase 2A activity. Loss-of-function mutations in MID1 lead to the X-linked Opitz G/BBB syndrome characterized by defective midline development during embryogenesis. Here, we show that MID1 is strongly upregulated in murine cytotoxic lymphocytes (CTLs), and that it controls TCR signaling, centrosome trafficking, and exocytosis of lytic granules. In accordance, we find that the killing capacity of MID1(-/-) CTLs is impaired. Transfection of MID1 into MID1(-/-) CTLs completely rescued lytic granule exocytosis, and vice versa, knockdown of MID1 inhibited exocytosis of lytic granules in WT CTLs, cementing a central role for MID1 in the regulation of granule exocytosis. Thus, MID1 orchestrates multiple events in CTL responses, adding a novel level of regulation to CTL activation and cytotoxicity.
Keywords: Animals; Blotting, Western; Cytotoxicity, Immunologic; Exocytosis; Flow Cytometry; Mice; Mice, Knockout; Mice, Transgenic; Proteins; Reverse Transcriptase Polymerase Chain Reaction; Secretory Vesicles; T-Lymphocytes, Cytotoxic

Modulation of circulating cytokine-chemokine profile in patients affected by chronic venous insufficiency undergoing surgical hemodynamic correction. - Tisato, Veronica; Zauli, Giorgio; Gianesini, Sergio; Menegatti, Erica; Brunelli, Laura; Manfredini, Roberto; Zamboni, Paolo; Secchiero, Paola (J Immunol Res, 2014)
The expression of proinflammatory cytokines/chemokines has been reported in in vitro/ex vivo settings of chronic venous insufficiency (CVI), but the identification of circulating mediators that might be associated with altered hemodynamic forces or might represent innovative biomarkers is still missing. In this study, the circulating levels of 31 cytokines/chemokines involved in inflammatory/angiogenic processes were analysed in (i) CVI patients at baseline before surgical hemody namic correction, (ii) healthy subjects, and (iii) CVI patients after surgery. In a subgroup of CVI patients, in whom the baseline levels of cytokines/chemokines were analyzed in paired blood samples obtained from varicose vein and forearm vein, EGF, PDGF, and RANTES were increased at the varicose vein site as compared to the general circulation. Moreover, while at baseline, CVI patients showed increased levels of 14 cytokines/chemokines as compared to healthy subjects, 6 months after surgery, 11 cytokines/chemokines levels were significantly reduced in the treated CVI patients as compared to the CVI patients before surgery. Of note, a patient who exhibited recurrence of the disease 6 months after surgery, showed higher levels of EGF, PDGF, and RANTES compared to nonrecurrent patients, highlighting the potential role of the EGF/PDGF/RANTES triad as sensitive biomarkers in the context of CVI.
Keywords: Adult; Aged; Chemokines; Chronic Disease; Cytokines; Female; Hemodynamics; Humans; Male; Middle Aged; Saphenous Vein; Varicose Veins; Venous Insufficiency

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Multiple Ileo-Ileal Intussusceptions Caused by Eosinophilic Enteropathy. - Bramuzzo, Matteo; Martelossi, Stefano; Villanacci, Vincenzo; Maschio, Massimo; Costa, Stefano; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2014)

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

A neonate with a 'milky' blood. What can it be? - Bordugo, Andrea; Carlin, Eva; Demarini, Sergio; Faletra, Flavio; Colonna, Franco (Arch Dis Child Fetal Neonatal Ed, 2014)
Keywords: Female; Humans; Hyperlipoproteinemia Type IV; Infant, Newborn; Lipoprotein Lipase; Milk Proteins; Mutation

Neutralizing and IgG antibodies against simian virus 40 in healthy pregnant women in Italy. - Comar, Manola; Wong, Connie; Tognon, Mauro; Butel, Janet S (PLoS One, 2014)
OBJECTIVE: Polyomavirus simian virus 40 (SV40) sequences have been detected in various human specimens and SV40 antibodies have been found in human sera from both healthy individuals and cancer patients. This study analyzed serum samples from healthy pregnant women as well as cord blood samples to determine the prevalence of SV40 antibodies in pregnancy. METHODS: Serum samples were collected at the time of delivery from two groups of pregnant women as well as cord bloods from one group. The women were born between 1967 and 1993. Samples were assayed by two different serological methods, one group by neutralization of viral infectivity and the other by indirect ELISA employing specific SV40 mimotopes as antigens. Viral DNA assays by real-time polymerase chain reaction were carried out on blood samples. RESULTS: Neutralization and ELISA tests indicated that the pregnant women were SV40 antibody-positive with overall prevalences of 10.6% (13/123) and 12.7% (14/110), respectively. SV40 neutralizing antibodies were detected in a low number of cord blood samples. Antibody titers were generally low. No viral DNA was detected in either maternal or cord bloods. CONCLUSIONS: SV40-specific serum antibodies were detected in pregnant women at the time of delivery and in cord bloods. There was no evidence of transplacental transmission of SV40. These data indicate that SV40 is circulating at a low prevalence in the northern Italian population long after the use of contaminated vaccines.

Next generation sequencing in nonsyndromic intellectual disability: from a negative molecular karyotype to a possible causative mutation detection. - Athanasakis, Emmanouil; Licastro, Danilo; Faletra, Flavio; Fabretto, Antonella; Dipresa, Savina; Vozzi, Diego; Morgan, Anna; d'Adamo, Adamo P; Pecile, Vanna; Biarnés, Xevi; Gasparini, Paolo (Am J Med Genet A, 2014)
The identification of causes underlying intellectual disability (ID) is one of the most demanding challenges for clinical Geneticists and Researchers. Despite molecular diagnostics improvements, the vast majority of patients still remain without genetic diagnosis. Here, we report the results obtained using Whole Exome and Target Sequencing on nine patients affected by isolated ID without pathological copy number variations, which were accurately selected from an initial cohort of 236 patients. Three patterns of inheritance were used to search for: (1) de novo, (2) X-linked, and (3) autosomal recessive variants. In three of the nine proband-parent trios analyzed, we identified and validated two de novo and one X-linked potentially causative mutations located in three ID-related genes. We proposed three genes as ID candidate, carrying one de novo and three X-linked mutations. Overall, this systematic proband-parent trio approach using next generation sequencing could explain a consistent percentage of patients with isolated ID, thus increasing our knowledge on the molecular bases of this disease and opening new perspectives for a better diagnosis, counseling, and treatment.
Keywords: Computational Biology; Exome; Female; Genes, Recessive; Genes, X-Linked; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Intellectual Disability; Karyotype; Male; Mutation; Workflow

NLRP3 polymorphism is associated with protection against human T-lymphotropic virus 1 infection. - Kamada, Anselmo Jiro; Pontillo, Alessandra; Guimarães, Rafael Lima; Loureiro, Paula; Crovella, Sergio; Brandão, Lucas André Cavalcanti (Mem Inst Oswaldo Cruz, 2014)
Inter-individual heterogeneity in the response to human T-lymphotropic virus 1 (HTLV-1) infection has been partially attributed to host genetic background. The antiviral activity of the inflammasome cytoplasmic complex recognises viral molecular patterns and regulates immune responses via the activation of interleukin (IL)-1 family (IL-1, IL-18 and IL-33) members. The association between polymorphisms in the inflammasome receptors NLRP1 and NLRP3 and HTLV-1 infection was evaluated in a northeastern Brazilian population (84 HTLV-1 carriers and 155 healthy controls). NLRP3 rs10754558 G/G was associated with protection against HTLV-1 infection (p = 0.012; odds ratio = 0.37). rs10754558 affects NLRP3 mRNA stability; therefore, our results suggest that higher NLRP3 expression may augment first-line defences, leading to the effective protection against HTLV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Female; Genetic Predisposition to Disease; HTLV-I Infections; Human T-lymphotropic virus 1; Humans; Inflammasomes; Interleukin-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protective Factors

A non-complement-fixing antibody to β2 glycoprotein I as a novel therapy for antiphospholipid syndrome. - Agostinis, Chiara; Durigutto, Paolo; Sblattero, Daniele; Borghi, Maria O; Grossi, Claudia; Guida, Filomena; Bulla, Roberta; Macor, Paolo; Pregnolato, Francesca; Meroni, Pier Luigi; Tedesco, Francesco (Blood, 2014)
A single-chain fragment variable (scFv) recognizing β2-glycoprotein 1 (β2GPI) from humans and other species was isolated from a human phage display library and engineered to contain an IgG1 hinge-CH2-CH3 domain. The scFv-Fc directed against β2GPI domain I-induced thrombosis and fetal loss, thus mimicking the effect of antibodies from patients with antiphospholipid syndrome (APS). Complement is involved in the biological effect of anti-β2GPI scFv-Fc, as demonstrated by its ability to promote in vitro and in vivo complement deposition and the failure to induce vascular thrombosis in C6-deficient rats and fetal loss in C5-depleted mice. A critical role for complement was also supported by the inability of the CH2-deleted scFv-Fc to cause vessel occlusion and pregnancy failure. This antibody prevented the pathological effects of anti-β2GPI antibodies from APS patients and displaced β2GPI-bound patient antibodies. The CH2-deleted antibody represents an innovative approach potentially useful to treat APS patients refractory to standard therapy.
Keywords: Abortion, Spontaneous; Animals; Antibodies, Monoclonal; Antiphospholipid Syndrome; Autoantigens; beta 2-Glycoprotein I; Complement Activation; Complement System Proteins; Human Umbilical Vein Endothelial Cells; Humans; Immunoglobulin G; Male; Mice; Protein Binding; Rats; Recombinant Proteins; Single-Chain Antibodies; Thrombosis; Trophoblasts

Novel missense mutation in the NOD2 gene in a patient with early onset ulcerative colitis: causal or chance association? - Girardelli, Martina; Vuch, Josef; Tommasini, Alberto; Crovella, Sergio; Bianco, Anna Monica (Int J Mol Sci, 2014)
Deregulated immune response to gut microflora in genetically predisposed individuals is typical for inflammatory bowel diseases. It is reasonable to assume that genetic association with the disease will be more pronounced in subjects with early onset than adult onset. The nucleotide-binding oligomerization domain containing-2 gene, commonly involved in multifactorial risk of Crohn's disease, and interleukin 10 receptor genes, associated with rare forms of early onset inflammatory bowel diseases, were sequenced in an early onset patient. We identified a novel variant in the NOD2 gene (c.2857A > G p.K953E) and two already described missense variants in the IL10RA gene (S159G and G351R). The new NOD2 missense variant was examined in silico with two online bioinformatics tools to predict the potentially deleterious effects of the mutation. Although cumulative effect of these variations in the early onset of the disease can be only hypothesized, we demonstrated that family information and in silico studies can be used to predict association with the disease.
Keywords: Age of Onset; Amino Acid Sequence; Base Sequence; Child; Colitis, Ulcerative; Crohn Disease; DNA Mutational Analysis; Genetic Predisposition to Disease; Genotype; Humans; Interleukin-10 Receptor alpha Subunit; Interleukin-10 Receptor beta Subunit; Molecular Sequence Data; Mutation, Missense; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Risk Factors; Sequence Homology, Amino Acid

Osteoprotegerin increases in metabolic syndrome and promotes adipose tissue proinflammatory changes. - Bernardi, Stella; Fabris, Bruno; Thomas, Merlin; Toffoli, Barbara; Tikellis, Christos; Candido, Riccardo; Catena, Cristiana; Mulatero, Paolo; Barbone, Fabio; Radillo, Oriano; Zauli, Giorgio; Secchiero, Paola (Mol Cell Endocrinol, 2014)
BACKGROUND: Inflammation is believed to link obesity to insulin resistance, as in the setting of metabolic syndrome (MetS). Osteoprotegerin (OPG) is a soluble protein that seems to exert proatherogenic and prodiabetogenic effects. This study aims at determining OPG levels in MetS and whether OPG might contribute to MetS development and progression. METHODOLOGY/PRINCIPAL FINDINGS: Circulating OPG was measured in 46 patients with MetS and 63 controls, and was found significantly elevated in those with MetS. In addition, circulating and tissue OPG was significantly increased in high-fat diet (HFD) fed C57BL6 mice, which is one of the animal models for the study of MetS. To evaluate the consequences of OPG elevation, we delivered this protein to C57BL6 mice, finding that it promoted systemic and adipose tissue proinflammatory changes in association with metabolic abnormalities. CONCLUSIONS/SIGNIFICANCE: These data suggest that OPG may trigger adipose tissue proinflammatory changes in MetS/HFD-induced obesity.
Keywords: Adipose Tissue; Adult; Animals; Blood Glucose; Body Mass Index; C-Reactive Protein; Case-Control Studies; Cholesterol, HDL; Cholesterol, LDL; Diet, High-Fat; Female; Humans; Inflammation; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Mice; Mice, Inbred C57BL; Middle Aged; Obesity; Osteoprotegerin; Triglycerides

Paracetamol: a focus for the general pediatrician. - Marzuillo, Pierluigi; Guarino, Stefano; Barbi, Egidio (Eur J Pediatr, 2014)
UNLABELLED: Paracetamol (acetaminophen) is one of the most popular and widely used drugs for the treatment of pain and fever in children. This drug has multiple mechanisms of action, but its pharmacodynamic is still not well known. The central nervous system is the main site of action and it mirrors the paracetamol effect compartment. The recommended dosages and routes of administration should be different whether paracetamol is used for the treatment of pain or fever. For example, the rectal route, while being efficacious for the treatment of fever, should be avoided in pain management. Paracetamol is a safe drug, but some clinical conditions and concomitant drugs, which are frequent in clinical practice, may increase the risk of paracetamol toxicity. Therefore, it is important to optimize its administration to avoid overdoses and maximize its effect. The principal mediator of the paracetamol toxicity is the N-acetyl-p-benzo-quinone imine (NAPQI), a toxic product of the paracetamol metabolism, which could bind cysteine groups on proteins forming paracetamol-protein adduct in the liver. CONCLUSION: Although frequently prescribed, the concept of "effect compartment concentration" and the possible co-factors that could cause toxicity at recommended doses are not familiar to all pediatricians and general practitioners. We reviewed the literature concerning paracetamol mechanisms of action, we highlighted some relevant pharmacodynamic concepts for clinical practice, and we summarized the possible risk factors for toxicity at therapeutic dosages.
Keywords: Acetaminophen; Analgesics, Non-Narcotic; Child; Drug Overdose; Fever; Humans; Pain; Risk Factors

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Platelet diameters in inherited thrombocytopenias: analysis of 376 patients with all known disorders. - Noris, Patrizia; Biino, Ginevra; Pecci, Alessandro; Civaschi, Elisa; Savoia, Anna; Seri, Marco; Melazzini, Federica; Loffredo, Giuseppe; Russo, Giovanna; Bozzi, Valeria; Notarangelo, Lucia Dora; Gresele, Paolo; et al. (Blood, 2014)
Abnormalities of platelet size are one of the distinguishing features of inherited thrombocytopenias (ITs), and evaluation of blood films is recommended as an essential step for differential diagnosis of these disorders. Nevertheless, what we presently know about this subject is derived mainly from anecdotal evidence. To improve knowledge in this field, we evaluated platelet size on blood films obtained from 376 patients with all 19 forms of IT identified so far and found that these conditions differ not only in mean platelet diameter, but also in platelet diameter distribution width and the percentage of platelets with increased or reduced diameters. On the basis of these findings, we propose a new classification of ITs according to platelet size. It distinguishes forms with giant platelets, with large platelets, with normal or slightly increased platelet size, and with normal or slightly decreased platelet size. We also measured platelet diameters in 87 patients with immune thrombocytopenia and identified cutoff values for mean platelet diameter and the percentage of platelets with increased or reduced size that have good diagnostic accuracy in differentiating ITs with giant platelets and with normal or slightly decreased platelet size from immune thrombocytopenia and all other forms of IT.
Keywords: Adolescent; Adult; Blood Platelets; Case-Control Studies; Cell Size; Child; Child, Preschool; Diagnosis, Differential; Female; Hearing Loss, Sensorineural; Humans; Infant; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Purpura, Thrombocytopenic, Idiopathic; Thrombocytopenia; Young Adult

Potential role of circulating microRNAs as early markers of preeclampsia. - Ura, Blendi; Feriotto, Giordana; Monasta, Lorenzo; Bilel, Sabrine; Zweyer, Marina; Celeghini, Claudio (Taiwan J Obstet Gynecol, 2014)
OBJECTIVE: To identify microRNAs (miRNAs) differentially expressed at early stages of gestation (12-14 weeks) in the serum of pregnant women, who later developed severe preeclampsia (sPE) in the third trimester of pregnancy (n = 24) compared to women with normal pregnancy (n = 24). MATERIALS AND METHODS: Sera from 12-14-week-gestation whole blood were subjected to microarray analysis with TaqMan Low Density Array chips (human microRNA panel V3.0), and to quantitative real-time polymerase chain reaction. RESULTS: By using the TaqMan Low Density Array chip technology, 19 mature miRNAs appeared differentially expressed in the group of women who later developed sPE as compared to normal women. The expression of four miRNAs (miR-1233, miR-520, miR-210, miR-144) was validated by quantitative real-time polymerase chain reaction analysis. MiR-1233 was the most overexpressed in the serum of women who later developed sPE. CONCLUSION: Circulating miRNAs deserve further investigation in order to explore their potential role in the pathogenesis of preeclampsia. In particular, miR-1233 might represent a potential marker of early sPE.
Keywords: Adult; Biomarkers; Female; Gestational Age; Humans; MicroRNAs; Oligonucleotide Array Sequence Analysis; Pilot Projects; Pre-Eclampsia; Pregnancy; Retrospective Studies

A precordial rub in a boy with a severe attack of ulcerative colitis. - Badina, Laura; Ferrara, Giovanna; Guastalla, Pierpaolo; Barbi, Egidio (Pediatr Emerg Care, 2014)
A case of a pneumomediastinum mimicking a pericarditis in a boy with an occult perforation due to ulcerative colitis is reported. Pneumomediastinum is a rare complication of severe attacks of ulcerative colitis, with or without the previous development of a toxic megacolon, that should be considered in the differential diagnosis.
Keywords: Adolescent; Colitis, Ulcerative; Diagnosis, Differential; Humans; Intestinal Perforation; Male; Mediastinal Emphysema; Pericarditis; Radiography, Thoracic

Procedural sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis (JIA) should be a standard of care. - Pastore, Serena; Gortani, Giulia; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2014)
Keywords: Arthritis, Juvenile; Conscious Sedation; Female; Glucocorticoids; Humans; Male; Pain; Patient Preference

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

Re: Tramadol can selectively manage moderate pain in children following European advice limiting codeine use. - Calligaris, Lorenzo; Marzuillo, Pierluigi; Barbi, Egidio (Acta Paediatr, 2014)

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Rhythm perception and production predict reading abilities in developmental dyslexia. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Front Hum Neurosci, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia-a learning disability that affects reading acquisition despite normal intelligence and adequate education-have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.

The role of gestational diabetes, pre-pregnancy body mass index and gestational weight gain on the risk of newborn macrosomia: results from a prospective multicentre study. - Alberico, Salvatore; Montico, Marcella; Barresi, Valentina; Monasta, Lorenzo; Businelli, Caterina; Soini, Valentina; Erenbourg, Anna; Ronfani, Luca; Maso, Gianpaolo (BMC Pregnancy Childbirth, 2014)
BACKGROUND: It is crucial to identify in large population samples the most important determinants of excessive fetal growth. The aim of the study was to evaluate the independent role of pre-pregnancy body mass index (BMI), gestational weight gain and gestational diabetes on the risk of macrosomia. METHODS: A prospective study collected data on mode of delivery and maternal/neonatal outcomes in eleven Hospitals in Italy. Multiple pregnancies and preterm deliveries were excluded. The sample included 14109 women with complete records. Associations between exposure variables and newborn macrosomia were analyzed using Pearson's chi squared test. Multiple logistic regression models were built to assess the independent association between potential predictors and macrosomia. RESULTS: Maternal obesity (adjusted OR 1.7, 95% CI 1.4-2.2), excessive gestational weight gain (adjusted OR 1.9, 95% CI 1.6-2.2) and diabetes (adjusted OR 2.1, 95% CI 1.5-3.0 for gestational; adjusted OR 3.0, 95% CI 1.2-7.6 for pre-gestational) resulted to be independent predictors of macrosomia, when adjusted for other recognized risk factors. Since no significant interaction was found between pre-gestational BMI and gestational weight gain, excessive weight gain should be considered an independent risk factor for macrosomia. In the sub-group of women affected by gestational or pre-gestational diabetes, pre-gestational BMI was not significantly associated to macrosomia, while excessive pregnancy weight gain, maternal height and gestational age at delivery were significantly associated. In this sub-population, pregnancy weight gain less than recommended was not significantly associated to a reduction in macrosomia. CONCLUSIONS: Our findings indicate that maternal obesity, gestational weight gain excess and diabetes should be considered as independent risk factors for newborn macrosomia. To adequately evaluate the clinical evolution of pregnancy all three variables need to be carefully assessed and monitored.
Keywords: Adolescent; Adult; Birth Weight; Body Height; Body Mass Index; Diabetes, Gestational; Female; Fetal Macrosomia; Gestational Age; Humans; Infant, Newborn; Italy; Middle Aged; Obesity; Pregnancy; Pregnancy in Diabetics; Prospective Studies; Risk Factors; Weight Gain; Young Adult

Salt-inducible kinase 3, SIK3, is a new gene associated with hearing. - Wolber, Lisa E; Girotto, Giorgia; Buniello, Annalisa; Vuckovic, Dragana; Pirastu, Nicola; Lorente-Cánovas, Beatriz; Rudan, Igor; Hayward, Caroline; Polasek, Ozren; Ciullo, Marina; Mangino, Massimo; Steves, Claire; et al. (Hum Mol Genet, 2014)
Hearing function is known to be heritable, but few significant and reproducible associations of genetic variants have been identified to date in the adult population. In this study, genome-wide association results of hearing function from the G-EAR consortium and TwinsUK were used for meta-analysis. Hearing ability in eight population samples of Northern and Southern European ancestry (n = 4591) and the Silk Road (n = 348) was measured using pure-tone audiometry and summarized using principal component (PC) analysis. Genome-wide association analyses for PC1-3 were conducted separately in each sample assuming an additive model adjusted for age, sex and relatedness of subjects. Meta-analysis was performed using 2.3 million single-nucleotide polymorphisms (SNPs) tested against each of the three PCs of hearing ability in 4939 individuals. A single SNP lying in intron 6 of the salt-inducible kinase 3 (SIK3) gene was found to be associated with hearing PC2 (P = 3.7×10(-8)) and further supported by whole-genome sequence in a subset. To determine the relevance of this gene in the ear, expression of the Sik3 protein was studied in mouse cochlea of different ages. Sik3 was expressed in murine hair cells during early development and in cells of the spiral ganglion during early development and adulthood. Our results suggest a developmental role of Sik3 in hearing and may be required for the maintenance of adult auditory function.
Keywords: Age Factors; Animals; Cochlea; European Continental Ancestry Group; Genome-Wide Association Study; Hearing; Humans; Mice, Inbred C57BL; Polymorphism, Single Nucleotide; Protein Kinases

The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection. - Calitri, Carmelina; Gabiano, Clara; Galli, Luisa; Chiappini, Elena; Giaquinto, Carlo; Buffolano, Wilma; Genovese, Orazio; Esposito, Susanna; Bernardi, Stefania; de Martino, Maurizio; Tovo, Pier-Angelo (BMC Infect Dis, 2014)
BACKGROUND: In the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing. METHODS: A description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children. RESULTS: Twenty-three women had 29 pregnancies. They had started an antiretroviral therapy at a median of 7.7 years (interquartile range, IQR 2.3 - 11.4), and had experienced a median of 4 therapeutic regimens (IQR 2-6). Twenty women (87%) had taken zidovudine (AZT) before pregnancy, in 14 cases as a starting monotherapy. In 21 pregnancies a protease inhibitor-based regimen was used. At delivery, the median of CD4+ T lymphocytes was 450/μL (IQR 275-522), and no viral load was detectable in 15 cases (reported in 21 pregnancies). Twenty-eight children were delivered through caesarean section (median gestational age: 38 weeks, IQR 36-38, median birth weight: 2550 grams, IQR 2270 - 3000). Intravenous AZT was administered during delivery in 26 cases. All children received oral AZT (median: 42 days, IQR 31 - 42), with no adverse events reported. No child acquired HIV-1 infection. CONCLUSIONS: Despite a long history of maternal infection, multiple antiretroviral regimens and, perhaps, the development of drug-resistant viruses, the risk of mother-to-child transmission does not seem to have increased among the second-generation of HIV-1 exposed infants.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Birth Weight; Cesarean Section; Child; Female; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Italy; Male; Pediatrics; Pregnancy; Pregnancy Complications, Infectious; Pregnancy Outcome; Prospective Studies; Viral Load; Young Adult; Zidovudine

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Sodium dichloroacetate exhibits anti-leukemic activity in B-chronic lymphocytic leukemia (B-CLL) and synergizes with the p53 activator Nutlin-3. - Agnoletto, Chiara; Melloni, Elisabetta; Casciano, Fabio; Rigolin, Gian Matteo; Rimondi, Erika; Celeghini, Claudio; Brunelli, Laura; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
The anti-leukemic activity of the mitochondria-targeting small molecule sodium dichloroacetate (DCA), used alone and in association with the small molecule inhibitor of the p53/MDM2 interaction Nutlin-3, was analyzed in primary B-chronic lymphocytic leukemia (B-CLL) samples (n=22), normal peripheral blood cells (n=10) and in p53wild-type EHEB, JVM-2, JVM-3 B lymphoblastoid cell lines. DCA exhibited a dose-dependent anti-leukemic activity in both primary B-CLL and B leukemic cell lines with a functional p53 status and showed a synergistic cytotoxic activity when used in combination with Nutlin-3. At the molecular level, DCA positively regulated p53 activity, as documented by post-transcriptional modifications of p53 protein and synergized with Nutlin-3 in increasing the expression of the p53-target genes MDM2, PUMA, TIGAR and in particular p21. The potential role of p21 in mediating the DCA+Nutlin-3 anti-leukemic activity was underscored in knocking-down experiments. Indeed, transfection of leukemic cells with p21 siRNAs significantly decreased the DCA+Nutlin-3-induced cytotoxicity. Taken together, our data emphasize that DCA is a molecule that merits to be further evaluated as a chemotherapeutic agent for B-CLL, likely in combination with other therapeutic compounds.
Keywords: Aged; Aged, 80 and over; Dichloroacetic Acid; Drug Synergism; Female; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Piperazines; Tumor Suppressor Protein p53

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

TNF-α SNP rs1800629 and risk of relapse in childhood acute lymphoblastic leukemia: relation to immunophenotype. - Franca, Raffaella; Rebora, Paola; Athanasakis, Emmanouil; Favretto, Diego; Verzegnassi, Federico; Basso, Giuseppe; Tommasini, Alberto; Valsecchi, Maria Grazia; Decorti, Giuliana; Rabusin, Marco (Pharmacogenomics, 2014)
AIM: In the AIEOP-BFM ALL (Associazione Italiana Ematologia Oncologia Pediatrica-Berlin Frankfurt Münster acute lymphoblastic leukemia) 2000 protocol, 70% of relapsed patients had favorable prognostic features and fell within less intensive polychemotherapeutic regimens, suggesting the need for better assessing lower risk stratification. MATERIALS & METHODS: A novel two-phase study design selected 614 children to be genotyped for TNF-α SNP rs1800629 (-308G>A). A weighted Cox model was applied to evaluate the SNP effect on hazard of relapse, adjusting for immunophenotype, risk group, age and gender and including interaction terms. RESULTS: Significant interaction was found with immunophenotypes (p = 0.0007, with minor allele genotypes being adverse genetic markers in B-cell acute lymphoblastic leukemia and protective ones in T-cell acute lymphoblastic leukemia), and also with risk protocols (p = 0.0041, with minor allele genotypes as prognostic factor of relapse for standard risk patients [only one T-cell acute lymphoblastic leukemia in the subgroup analyzed]). CONCLUSION: The presence of at least one A allele in TNF-α SNP rs1800629 should suggest a closer monitoring in B-cell acute lymphoblastic leukemia standard risk patients.
Keywords: Adolescent; Antineoplastic Agents; Child; Child, Preschool; Drug Resistance, Neoplasm; Female; Genotype; Humans; Infant; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Phenotype; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Risk Assessment; Steroids; Tumor Necrosis Factor-alpha

Tramadol can selectively manage moderate pain in children following European advice limiting codeine use. - Marzuillo, Pierluigi; Calligaris, Lorenzo; Barbi, Egidio (Acta Paediatr, 2014)
UNLABELLED: The European Medicine Agency recommendations limiting codeine use in children have created a void in managing moderate pain. We review the evidence on the pharmacokinetic, pharmacodynamic and safety profile of tramadol, a possible substitute for codeine. CONCLUSION: Tramadol appears to be safe in both paediatric inpatients and outpatients. It may be appropriate to limit the current use of tramadol to monitored settings in children with risk factors for respiratory depression, subject to further safety evidence.

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

An unusual long-term complication of transobturator polypropylene mesh. - Sartore, Andrea; Zennaro, Floriana; Banco, Rubina (Arch Gynecol Obstet, 2014)
Serious complications associated with surgical mesh for transvaginal repair of POP, as infections, vaginal mesh exposure, painful mesh shrinkage and dyspareunia, are not rare. A 48-year-old woman underwent the Perigee procedure because of a stage 3 anterior wall prolapse. Eleven months after surgery, the patient became suddenly unable to walk because of a strong pain to the left thigh root after running. The MRI revealed an external obturator left muscle hyperintensity consistent with muscular oedema; the patient was treated with oral corticosteroids with a complete resolution of the pain. We could hypothesize that the posterior arm of the mesh caused a laceration of the muscles of the obturator space with consequent oedema and pain. The use of the meshes in prolapse surgery can cause unexpected long-term complications.
Keywords: Cystocele; Dyspareunia; Female; Glucocorticoids; Humans; Middle Aged; Pelvic Organ Prolapse; Polypropylenes; Postoperative Complications; Prednisone; Surgical Mesh; Treatment Outcome; Vagina

Unusual splice site mutations disrupt FANCA exon 8 definition. - Mattioli, Chiara; Pianigiani, Giulia; De Rocco, Daniela; Bianco, Anna Monica Rosaria; Cappelli, Enrico; Savoia, Anna; Pagani, Franco (Biochim Biophys Acta, 2014)
The pathological role of mutations that affect not conserved splicing regulatory sequences can be difficult to determine. In a patient with Fanconi anemia, we identified two unpredictable splicing mutations that act on either sides of FANCA exon 8. In patients-derived cells and in minigene splicing assay, we showed that both an apparently benign intronic c.710-5T>C transition and the nonsense c.790C>T substitution induce almost complete exon 8 skipping. Site-directed mutagenesis experiments indicated that the c.710-5T>C transition affects a polypyrimidine tract where most of the thymidines cannot be compensated by cytidines. The c.790C>T mutation located in position -3 relative to the donor site induce exon 8 skipping in an NMD-independent manner and complementation experiments with modified U1 snRNAs showed that U1 snRNP is only partially involved in the splicing defect. Our results highlight the importance of performing splicing functional assay for correct identification of disease-causing mechanism of genomic variants and provide mechanistic insights on how these two FANCA mutations affect exon 8 definition.
Keywords: Base Sequence; Cell Line, Tumor; Codon, Nonsense; Exons; Fanconi Anemia Complementation Group A Protein; HeLa Cells; Humans; Introns; Molecular Sequence Data; Mutagenesis, Site-Directed; Ribonucleoproteins, Small Nuclear; RNA Splice Sites; RNA Splicing

Validation of point-of-care testing for coeliac disease in children in a tertiary hospital in north India. - Singh, Prashant; Wadhwa, Nitya; Chaturvedi, Mona K; Bhatia, Vidyut; Saini, Savita; Tandon, Nikhil; Makharia, Govind K; Maki, Markku; Not, Tarcisio; Phillips, Alan; Bhatnagar, Shinjini (Arch Dis Child, 2014)
OBJECTIVE: Some of the conventional serological tests for coeliac disease (CD) are expensive, time-consuming and not readily available in developing countries, leading to a delay in diagnosis. Recently, point-of-care tests (POCT) have been manufactured and tested in Europe but have not been validated in our setting. We therefore aimed to study the diagnostic accuracy of the POCT 'Biocard' test in diagnosing CD in Indian children. DESIGN: Cross-sectional study. SETTING: Tertiary care centre in north India. PATIENTS: Children, aged 2-18 years, with chronic diarrhoea, short stature or refractory anaemia underwent serological testing for CD with antiendomysial antibodies (AEA), antitissue transglutaminase (tTG) antibodies and Biocard test followed by duodenal biopsy irrespective of serological results. CD was diagnosed with positive AEA and duodenal biopsy showing >grade 2 changes using modified Marsh criteria. Those who were both AEA negative and had normal histology were considered CD negative. RESULTS: Of 319 children who underwent the serological testing, 170 agreed for biopsy. Of these, 110 were diagnosed with CD and 30 were found to be CD negative. Remaining 30 had discordant AEA and histology results and were not included in analysis. Biocard test agreed with 92/110 positive and 27/30 negative diagnoses based on reference tests (83.6% sensitivity and 90% specificity). tTG was found to be 93.8% sensitive and 96.4% specific. CONCLUSIONS: We successfully validated the POCT for CD in our setting. It could be used to increase case detection rates in developing countries with a large undiagnosed CD burden.
Keywords: Adolescent; Celiac Disease; Child; Child, Preschool; Cross-Sectional Studies; Female; Humans; India; Male; Point-of-Care Systems; Sensitivity and Specificity; Serologic Tests; Tertiary Care Centers

Acropustulosis of infancy. - Paloni, Giulia; Berti, Irene; Cutrone, Mario (Arch Dis Child Fetal Neonatal Ed, 2013)
Keywords: Acrodermatitis; Diagnosis, Differential; Female; Foot Dermatoses; Hand Dermatoses; Humans; Infant, Newborn

Amenorrhea in women treated with thalidomide: report of two cases and literature review. - Lazzerini, Marzia; Bramuzzo, Matteo; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Ventura, Alessandro (Inflamm Bowel Dis, 2013)
Keywords: Adolescent; Amenorrhea; Colitis, Ulcerative; Crohn Disease; Female; Humans; Review Literature as Topic; Thalidomide

Breastfeeding at NICU discharge: a multicenter Italian study. - Davanzo, Riccardo; Monasta, Lorenzo; Ronfani, Luca; Brovedani, Pierpaolo; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: Human milk is the optimal form of nutrition for infants, especially sick or compromised infants, yet international data suggest that breastfeeding (feeding at the breast) and the use of expressed human milk (mother's and donor's milk) are limited in patients cared for in the neonatal intensive care unit (NICU). OBJECTIVE: The goal of this study was to examine feeding status at hospital discharge among high risk infants. METHODS: We used the 1991 World Health Organization infant feeding definitions, applied to the 72 hour period preceding discharge from the NICU. The study sample consisted of all high risk infants discharged from July 1, 2005, to June 30, 2006 from 13 Italian NICUs. Data on infant feeding in the last 72 hours were collected at discharge from the medical records. RESULTS: We recorded data from 2948 subjects with a median gestational age of 35 weeks (IQR, 32-38), a median birth weight of 2200 g (IQR, 1630-2920) and a median length of stay of 16 days (IQR, 8-33). At discharge, 28% of all infants were fed exclusively with human milk: 31%, 25%, 22% and 33% respectively in the <1500 g, 1500-2000 g, 2000-2499 g and ≥ 2500 g birth weight categories. The proportion of infants not fed with human milk varied from 6 to 82% across different centers. CONCLUSION: Our study found limited breastfeeding and use of human milk among the NICU infants at discharge. At discharge, infants with a birth weight 1500-2499 g were fed exclusively with human milk less than those in higher or lower birth weight categories.
Keywords: Breast Feeding; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Intensive Care Units, Neonatal; Italy; Logistic Models; Multivariate Analysis; Patient Discharge

A comparative analysis of serologic parameters and oxidative stress in osteoarthritis and rheumatoid arthritis: reply to Mishra and colleagues. - Girardelli, M; Bianco, A M; Marcuzzi, A; Crovella, S (Rheumatol Int, 2013)
In chronic diseases such as rheumatoid arthritis and osteoarthritis, the progression of the disease is characterized by stress oxidative, inflammation, and elevated levels of cholesterol. In mevalonate kinase deficiency, an auto-inflammatory disease, the correlation between inflammation and cholesterol levels is opposite. The metabolic pathway that underlies the production of cholesterol is the mevalonate pathway; it is also essential for the biosynthesis of isoprenoids involved in the control of several cell functions. This divergence of cholesterol levels, associated with these two inflammatory disorders, is probably due to a different etiology, pathogenesis, and progression.
Keywords: Arthritis, Rheumatoid; Female; Humans; Inflammation Mediators; Lipids; Male; Osteoarthritis; Oxidative Stress

Does EMLA cream application interfere with the success of venipuncture or venous cannulation? A prospective multicenter observational study. - Schreiber, S; Ronfani, L; Chiaffoni, G P; Matarazzo, L; Minute, M; Panontin, E; Poropat, F; Germani, C; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Venipuncture and intravenous cannulation are the most common painful procedures performed on children. The most widely used topical anesthetic is eutectic mixture of local anesthetics (EMLA). EMLA use is associated with a transient cutaneous vasoconstriction which can make it difficult to identify veins. We assessed with a prospective, multicenter, observational study whether EMLA interferes with venipuncture and intravenous cannulation. The primary study outcome was a success at first attempt in the course of venipuncture or venous cannulation. The study enrolled 388 children; 255 of them received EMLA and 133 did not. Eighty-six percent of procedures were successful at the first attempt in the EMLA group and 76.7 % in the no EMLA group. CONCLUSION: In this study, EMLA use did not interfere with the success of venipuncture or venous cannulation in children.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Humans; Lidocaine; Logistic Models; Male; Ointments; Phlebotomy; Prilocaine; Prospective Studies; Vasoconstriction

Family history in early-onset inflammatory bowel disease. - Bianco, Anna Monica; Zanin, Valentina; Monasta, Lorenzo; Martelossi, Stefano; Marcuzzi, Annalisa; Crovella, Sergio (J Gastroenterol, 2013)
Keywords: Colitis, Ulcerative; Crohn Disease; Female; Humans; Male

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

A novel CRYBB2 missense mutation causing congenital autosomal dominant cataract in an Italian family. - Faletra, Flavio; d'Adamo, Adamo Pio; Pensiero, Stefano; Athanasakis, Emmanouil; Catalano, Dario; Bruno, Irene; Gasparini, Paolo (Ophthalmic Genet, 2013)
Congenital cataract is a leading cause of visual impairment in children and brings approximately 10% of childhood blindness worldwide. Molecular analysis revealed ~60 loci to be associated with several phenotypes of childhood cataracts. Until now, more than 30 loci and 18 genes on different chromosomes have been associated with autosomal dominant congenital cataract (ADCC). Here, we present a three-generation Italian family with a non syndromic ADCC. A linkage analysis carried out using HumanCytoSNP-12 DNA Analysis BeadChip led us to identify ten genomic regions virtually involved in the disease. All the genes located in these regions were scored for possible relationship with ADCC and, according to a strict clinical and genetic selection, 4 genes have been analyzed. A novel sequence variant was found in the CRYBB2 gene (p.Ser143Phe). This variant affects a conserved aminoacid in the third Greek key motif of the protein, cosegregates with the disease phenotype in all affected individuals and is not present both in the unaffected family members and 100 healthy control subjects. Finally, we identified the first CRYBB2 mutation in an Italian family causing a clinical picture of ADCC.
Keywords: Amino Acid Sequence; beta-Crystallin B Chain; Cataract; DNA Mutational Analysis; Female; Genes, Dominant; Genetic Linkage; Genotype; Humans; Italy; Male; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype

Pain in cognitively impaired children: a focus for general pediatricians. - Massaro, M; Pastore, S; Ventura, A; Barbi, E (Eur J Pediatr, 2013)
UNLABELLED: Pain in children with cognitive impairment and cerebral palsy is a particularly relevant issue due to its high prevalence and impact on quality of life. We review available evidence about prevalence of pain, causes and specific treatment, recognition and use of specific pain scales, physiology, and consequences of pain in this subset of patients. CONCLUSIONS: Pain is very common and is a critical determinant of quality of life in children with cognitive impairment and cerebral palsy. The diseases and associated complications that frequently expose these patients to pain can be treated and pain prevented. For patients with communication difficulties, appropriate, effective, validated tools are available and should be used to diagnose pain in itself, to >choose analgesic treatment and to determine effectiveness of these therapies. The level of awareness of pediatricians towards this issue seems to be quite low.
Keywords: Analgesics; Cerebral Palsy; Child; Cognition Disorders; Humans; Pain; Pain Measurement; Quality of Life

Patients affected by metabolic syndrome show decreased levels of circulating platelet derived growth factor (PDGF)-BB. - Tisato, Veronica; Toffoli, Barbara; Monasta, Lorenzo; Bernardi, Stella; Candido, Riccardo; Zauli, Giorgio; Secchiero, Paola (Clin Nutr, 2013)
BACKGROUND & AIMS: The development and/or progression of metabolic syndrome (MetS) in overweight and obese individuals have been associated to low-grade inflammation, but few studies have simultaneously analyzed the circulating levels of several cytokines. METHODS: In this pilot study, a group of 27 cytokines and growth factors was analyzed in the serum of obese patients (n=40) diagnosed for MetS in comparison with sex- and age-matched control subjects without MetS (n=53) by using a multiplex immunoassay. Release of cytokines was measured in culture supernatants of human primary endothelial cells, THP-1 macrophagic cells and HuH-7 hepatoma cells upon exposure to a high fat mixture. RESULTS: While the majority of cytokines did not show significant differences between the investigated groups, the circulating levels of CXCL10/IP-10 and IL-6 were higher in the MetS group versus overweight control group. In contrast, PDGF-BB serum levels were significantly decreased in MetS patients. The in vitro addition of a high fat mixture increased the release of IL-6 and/or CXCL10/IP-10 in the culture supernatant of human primary endothelial cells and THP-1 macrophagic cells, while the same mixture significantly decreased the release of PDGF-BB by human THP-1 macrophagic and HuH-7 hepatoma cells. CONCLUSIONS: The current demonstration that MetS is associated with decrease of the pro-fibrotic PDGF cytokine is a completely novel finding, which adds complexity to the interplay between inflammation and fibrosis in patients affected by MetS.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; Cell Line, Tumor; Chemokine CXCL10; Endothelial Cells; Female; Humans; Interleukin-6; Linear Models; Male; Metabolic Syndrome X; Middle Aged; Obesity; Pilot Projects; Proto-Oncogene Proteins c-sis; RNA, Messenger; Young Adult

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Is treatment with hydroxychloroquine effective in surfactant protein C deficiency? - Rabach, Ingrid; Poli, Furio; Zennaro, Floriana; Germani, Claudio; Ventura, Alessandro; Barbi, Egidio (Arch Bronconeumol, 2013)
We present the case of two twin brothers with surfactant protein C deficiency who were treated with hydroxychloroquine for three years, with apparent success. The exact physiopathology of this disease is not known and there is no specific treatment for it. There is merely news from a few previous descriptions in the literature about the use of hydroxychloroquine for surfactant protein C deficiency with satisfactory results. Two years after the treatment was withdrawn, the twins were evaluated once again: they presented no new infections, growth and general state were normal and chest CT showed a notable additional reduction in the interstitial pneumopathy. These data seem to cast some doubt on the efficacy of hydroxychloroquine, and they suggest that the clinical improvement was simply the natural evolution of the disease.
Keywords: Disease Progression; Diseases in Twins; Dyspnea; Failure to Thrive; Humans; Hydroxychloroquine; Infant, Newborn; Male; Pulmonary Alveolar Proteinosis; Pulmonary Surfactant-Associated Protein C; Respiratory Insufficiency; Tomography, X-Ray Computed; Twins, Monozygotic

Under pressure. - De Cunto, Angela; Berti, Irene; Minute, Marta; Longo, Giorgio (Eur J Pediatr, 2013)
Physical urticaria is a rare but challenging subset of chronic urticaria. Wheals of pressure urticaria are typically delayed in appearance. A pressure test can easily be done to confirm the diagnosis.
Keywords: Child; Humans; Male; Pressure; Urticaria

Adverse effects during specific oral tolerance induction: in home phase. - Barbi, E; Longo, G; Berti, I; Matarazzo, L; Rubert, L; Saccari, A; Lenisa, I; Ronfani, L; Radillo, O; Ventura, A (Allergol Immunopathol (Madr), 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach for severe food allergies. There are little data in the literature regarding the home-phase of SOTI, not only with regard to type and frequency of adverse reactions but also regarding the most suitable treatment and protocol. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of the home-phase of an original SOTI protocol in a large group of children with severe cow's milk (CM) allergy, after the hospital "rush" phase. METHODS: The study was conducted by recording in-home phase adverse events, success and failure as reported by parents, and calling families. Adverse reactions were treated following the International Guidelines, arbitrarily modified by introducing nebulised epinephrine for respiratory reactions, oral beclomethasone for acute gastric pain and oral cromolyn for recurrent gastric pain. RESULTS: Out of 140 patients, 132 were contacted; eight were inaccessible (follow-up 2-84 months). The number of adverse reactions was 1 in every 100 doses. The reactions were treated with nebulised epinephrine (221 reactions), IM epinephrine (6 reactions), and other drugs. Patients with high specific IgE levels (greater than 100 kU(A)/L) and lower CM dose (less than 5 ml) at the end of in-hospital phase showed a higher risk both for number of reactions and use of nebulised epinephrine. CONCLUSIONS: The home phase of SOTI was characterised by a significant number of adverse reactions, mostly managed with an acceptable rate of side effects. Nebulised epinephrine played a pivotal role in respiratory reactions.
Keywords: Adolescent; Adult; Age Factors; Allergens; Child; Child, Preschool; Desensitization, Immunologic; Epinephrine; Female; Food Hypersensitivity; Humans; Immune Tolerance; Immunoglobulin E; Male; Milk Hypersensitivity; Nebulizers and Vaporizers

Adverse effects during specific oral tolerance induction: in-hospital "rush" phase. - Barbi, E; Longo, G; Berti, I; Neri, E; Saccari, A; Rubert, L; Matarazzo, L; Montico, M; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Specific oral tolerance induction (SOTI) is a promising approach in the treatment of severe food allergies. Different protocols have demonstrated its efficacy. Nevertheless, SOTI is still considered an experimental method and should be limited to highly controlled settings. AIMS: To define the incidence and severity of adverse reactions, possible risk factors, and the safety and effectiveness of nebulized epinephrine as a first-line treatment of respiratory reactions during in-hospital SOTI for cow's milk allergy. MATERIALS AND METHODS: A retrospective study was conducted by reviewing the medical records of patients admitted for SOTI beginning in 2001. Reactions were classified as mild, moderate and severe on a partially modified Clark scale. Adverse reactions were treated following the International Guidelines with the introduction of nebulized epinephrine for level four reactions. RESULTS: Of 209 patients, 17 were excluded due to the absence of objective reactions. The remaining 192 were classified as follows: Mild Reactions (Clark Scale 1 to 3): 100 patients received either no treatment, oral antihistamines or nebulized steroids; Moderate Reactions (Clark Scale 4): 87 patients treated with nebulized epinephrine and, depending on their symptoms, oral antihistamines, corticosteroids (nebulized, oral or IV) or nebulized beta 2 agonists; Severe Reactions (Clark Scale 5): 5 children, 4 of whom initially underwent one nebulization of epinephrine and eventually required an IM dose. The fifth patient was immediately treated with IM epinephrine due to hypotension. DISCUSSION: adverse reactions during this in-hospital SOTI protocol were frequent but easily manageable. Nebulized epinephrine can play a relevant role in the treatment of respiratory reactions.
Keywords: Administration, Inhalation; Anaphylaxis; Animals; Bronchodilator Agents; Child; Desensitization, Immunologic; Epinephrine; Humans; Milk; Milk Hypersensitivity; Retrospective Studies

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult

Alteration of liver enzymes is a feature of the MYH9-related disease syndrome. - Pecci, Alessandro; Biino, Ginevra; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Annamaria; Noris, Patrizia; Ramenghi, Ugo; Loffredo, Giuseppe; Fabris, Fabrizio; Momi, Stefania; Magrini, Umberto; Pirastu, Mario; et al. (PLoS One, 2012)
BACKGROUND: MYH9-related disease (MYH9-RD) is a rare autosomal dominant genetic syndrome characterized by congenital thrombocytopenia associated with the risk of developing progressive nephropathy, sensorineural deafness, and presenile cataract. During the collection of a large case-series of patients with MYH9-RD we noticed several cases with unexplained elevation of liver enzymes. Our aim was to evaluate if the alteration of liver tests is a feature of the MYH9-RD and to define its clinical significance. METHODS AND FINDINGS: Data concerning liver tests, prospectively recorded in the Italian Registry for MYH9-RD, were collected and compared with those of three control populations: patients with autoimmune thrombocytopenia, patients with inherited thrombocytopenias other than MYH9-RD, and the participants to a large epidemiologic survey in an Italian geographic isolate. Thirty-eight of 75 evaluable MYH9-RD patients (50.7%) showed an elevation of ALT and/or AST, and 17 of 63 (27.0%) an increase of GGT. The increases ranged from 1.9 ± 0.7 to 2.7 ± 1.6 fold the upper normal limit. The prevalence of liver test alterations was significantly higher in MYH9-RD patients than in each of the control populations, with odds ratios ranging from 8.2 (95% CIs 2.2-44.8) to 24.7 (14.8-40.8). Clinical follow-up and more detailed liver studies of a subset of patients, including ultrasound liver scan, liver elastography and liver biopsy in one case, did not show any significant structural damage or evolution towards liver insufficiency. CONCLUSIONS: Elevation of liver enzymes is a frequent and previously unrecognized feature of the MYH9-RD syndrome; however, this defect does not appear to have poor prognostic value.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Aged; Aged, 80 and over; Biopsy; Case-Control Studies; Child; Child, Preschool; Demography; Female; Follow-Up Studies; Humans; Immunohistochemistry; Infant; Liver; Liver Function Tests; Male; Middle Aged; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Odds Ratio; Syndrome; Young Adult

Anti-leukemic activity of dasatinib in both p53(wild-type) and p53(mutated) B malignant cells. - Bosco, Raffaella; Rabusin, Marco; Voltan, Rebecca; Celeghini, Claudio; Corallini, Federica; Capitani, Silvano; Secchiero, Paola (Invest New Drugs, 2012)
The multi-kinase inhibitor dasatinib induced a variable but significant decrease of viability in both p53(wild-type) (EHEB, JVM-2, JVM-3) and p53(mutated) (MEC-1, MEC-2, BJAB) prolymphocytic B leukemic cells, due to a combination of cell cycle block in G1 and apoptosis. Antibody phospho-kinase array analysis revealed that dasatinib inhibited the phosphorylation of various kinases, including ERK1/2 and p38/MAPK as well as of STAT3 transcription factors, in both p53(wild-type) and p53(mutated) cells. Therefore, dasatinib might offer a novel therapeutic strategy not only for p53(wild-type), but also for p53(mutated) B malignancies that have the worst prognosis and urgently need innovative therapeutic approaches.
Keywords: Antineoplastic Agents; Apoptosis; B-Lymphocytes; Cell Line, Tumor; Cell Survival; G1 Phase Cell Cycle Checkpoints; Granulocyte Precursor Cells; Humans; Leukemia, Prolymphocytic, B-Cell; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Mutation; p38 Mitogen-Activated Protein Kinases; Phosphorylation; Protein Kinase Inhibitors; Pyrimidines; STAT3 Transcription Factor; Thiazoles; Time Factors; Tumor Suppressor Protein p53

Asbestos and SV40 in malignant pleural mesothelioma from a hyperendemic area of north-eastern Italy. - Comar, Manola; Zanotta, Nunzia; Pesel, Giuliano; Visconti, Patrizia; Maestri, Iva; Rinaldi, Rosa; Crovella, Sergio; Cortale, Maurizio; De Zotti, Renata; Bovenzi, Massimo (Tumori, 2012)
AIMS AND BACKGROUND: Malignant mesothelioma is a fatal cancer of increasing incidence in north-eastern Italy. Together with asbestos, the polyomavirus SV40 was hypothesized to contribute to the onset of malignant mesothelioma. To investigate the putative role of SV40 in the individual susceptibility to asbestos-induced malignant mesothelioma, we conducted a molecular epidemiological study on a series of malignant mesothelioma patients from an area in north-eastern Italy hyperendemic for malignant pleural mesothelioma. METHODS AND STUDY DESIGN: We collected 63 mesothelioma samples from incidence cases of patients diagnosed with malignant pleural mesothelioma in the period 2009-2010. DNA was extracted from patients' tissue biopsies using the BioRobot EZ1 Qiagen workstation. SV40 sequence detection and quantification was performed by specific real time PCR. The 74.6% of the 63 enrolled patients had a history of asbestos exposure. The epithelioid histotype was more prevalent in males (64.0%) and the mixed in females (61.5%) who showed significantly higher cancer co-morbidity (46.1% vs 12%, P = 0.005). SV40 was detected in 22% of MM tumors, with a low viral load. In SV40-positive patients, a threefold increased risk of asbestos exposure was observed, more evident in females (OR 4.32) than in males (OR 1.20). CONCLUSIONS: Our findings indicate that a high prevalence of SV40 was present in malignant mesothelioma incident cases from an area hyperendemic for malignant mesothelioma in north-eastern Italy. Although asbestos is considered the main risk factor in malignant mesothelioma onset, a role for SV40 could be hypothesized.
Keywords: Adult; Aged; Asbestos; Carcinogens; Disease Susceptibility; DNA, Viral; Endemic Diseases; Female; Humans; Italy; Male; Mesothelioma; Middle Aged; Pleural Neoplasms; Polyomavirus Infections; Real-Time Polymerase Chain Reaction; Risk Factors; Simian virus 40; Tumor Virus Infections; Viral Load

Association between BclI polymorphism in the NR3C1 gene and in vitro individual variations in lymphocyte responses to methylprednisolone. - Cuzzoni, Eva; De Iudicibus, Sara; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (Br J Clin Pharmacol, 2012)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT: In vitro lymphocyte steroid sensitivity has been suggested as a useful tool to predict in vivo response to glucocorticoid treatment in different inflammatory chronic diseases. A correlation between genetic polymorphisms and clinical response to glucocorticoids has been demonstrated in these patients. WHAT THIS STUDY ADDS: The BclI polymorphism in the glucocorticoid receptor (NR3C1) gene is associated with higher methylprednisolone potency in vitro. The combined evaluation of the in vitro sensitivity to methylprednisolone and BclI polymorphism could represent an aid for physicians to adjust therapy a priori. AIM To evaluate the association between the in vitro sensitivity of peripheral blood mononuclear cells (PBMCs) to methylprednisolone (MP) and the presence of genetic polymorphisms involved in glucocorticoid (GC) response. METHODS: In vitro MP inhibition of the proliferation of lymphocytes stimulated with concanavalin A was determined. Non linear regression of dose-response data was performed computing the MP concentration required to reduce proliferation to 50% (IC(50) ). The maximum inhibition achievable at the highest MP concentration (I(max) ) was also calculated. Moreover, the Taqman technique was used to analyze the BclI polymorphism in the NR3C1 gene and the Leu155His polymorphism in the NALP1 gene. RESULTS: A significant association between the BclI mutated genotype and an increased in vitro sensitivity to GCs was observed. CONCLUSIONS: The a priori evaluation of the BclI polymorphism, associated with a lymphocyte proliferation assay, could represent a useful diagnostic tool for the optimization of steroid treatment.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Apoptosis Regulatory Proteins; Cyclin D1; Dose-Response Relationship, Drug; Female; Genotype; Glucocorticoids; Humans; Lymphocytes; Male; Methylprednisolone; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Glucocorticoid; Young Adult

Autoimmune-polyendocrinopathy-candidiasis-ectodermal-dystrophy in Calabria: clinical, immunological and genetic patterns. - Betterle, C; Ghizzoni, L; Cassio, A; Baronio, F; Cervato, S; Garelli, S; Barbi, E; Tonini, G (J Endocrinol Invest, 2012)
UNLABELLED: Autoimmune polyendocrinopathy-candidiasis-ectodermal- dystrophy (APECED), also known as autoimmune polyendocrine syndrome type 1 (APS-1), is a very rare disease. Diagnosis requires the presence of at least two of three major clinical features: chronic mucocutaneous candidiasis, chronic hypoparathyroidism, and Addison's disease. DESIGN: In this study, we analyzed Autoimmune Regulator (AIRE) gene mutations and genotype-phenotype correlation in APECED patients originating from Calabria, a region in the south of Italy. PATIENTS AND METHODS: Four patients and their first-degree relatives were evaluated for clinical manifestations, autoantibody presence and AIRE gene mutations. RESULTS: Three patients carried a homozygous W78R mutation on exon 2, typical of patients with APECED from Apulia; the fourth patient had a homozygous R203X mutation on exon 5, typical of APECED patients from Sicily. Clinical disease expression showed wide variability. Analysis of relatives allowed the identification of 6 heterozygotes, none of whom showed major findings of APECED. CONCLUSIONS: No AIRE gene mutations specific to Calabria were found in patients with APS-1, but mutations similar to those in patients from Apulia and Sicily. Heterozygosity for AIRE gene mutation is not associated with major findings of APECED.
Keywords: Adolescent; Adult; Autoantibodies; Child; Female; Genetic Association Studies; Heterozygote; Homozygote; Humans; Italy; Male; Mutation; Polyendocrinopathies, Autoimmune; Prognosis; Sicily; Transcription Factors; Young Adult

Avoidable interruptions during drug administration in an intensive rehabilitation ward: improvement project. - Buchini, Sara; Quattrin, Rosanna (J Nurs Manag, 2012)
AIMS: To record the frequency of interruptions and their causes, to identify 'avoidable' interruptions and to build an improvement project to reduce 'avoidable' interruptions. BACKGROUND: In Italy each year 30,000-35,000 deaths per year are attributed to health-care system errors, of which 19% are caused by medication errors. The factors that contribute to drug management error also include interruptions and carelessness during treatment administration. METHODS: A descriptive study design was used to record the frequency of interruptions and their causes and to identify 'avoidable' interruptions in an intensive rehabilitation ward in Northern Italy. A data collection grid was used to record the data over a 6-month period. RESULTS: A total of 3000 work hours were observed. During the study period 1170 interruptions were observed. The study identified 14 causes of interruption. CONCLUSIONS: The study shows that of the 14 cases of interruptions at least nine can be defined as 'avoidable'. An improvement project has been proposed to reduce unnecessary interruptions and distractions to avoid making errors. IMPLICATIONS FOR NURSING MANAGEMENT: An additional useful step to reduce the incidence of treatment errors would be to implement the use of a single patient medication sheet for the recording of drug prescription, preparation and administration and also the incident reporting.
Keywords: Attention; Drug Therapy; Feasibility Studies; Humans; Intensive Care Units; Italy; Medication Errors; Nursing Administration Research; Nursing Evaluation Research; Nursing Staff, Hospital; Patient Safety; Quality Assurance, Health Care; Rehabilitation Nursing; Safety Management; Time Factors

Burden of disease caused by otitis media: systematic review and global estimates. - Monasta, Lorenzo; Ronfani, Luca; Marchetti, Federico; Montico, Marcella; Vecchi Brumatti, Liza; Bavcar, Alessandro; Grasso, Domenico; Barbiero, Chiara; Tamburlini, Giorgio (PLoS One, 2012)
BACKGROUND: Otitis media (OM) is a leading cause of health care visits and drugs prescription. Its complications and sequelae are important causes of preventable hearing loss, particularly in developing countries. Within the Global Burden of Diseases, Injuries, and Risk Factors Study, for the year 2005 we estimated the incidence of acute OM, chronic suppurative OM, and related hearing loss and mortality for all ages and the 21 WHO regional areas. METHODS: We identified risk factors, complications and sequelae of OM. We carried out an extensive literature review (Medline, Embase, Lilacs and Wholis) which lead to the selection of 114 papers comprising relevant data. Data were available from 15 of the 21 WHO regions. To estimate incidence and prevalence for all countries we adopted a two stage approach based on risk factors formulas and regression modelling. RESULTS: Acute OM incidence rate is 10.85% i.e. 709 million cases each year with 51% of these occurring in under-fives. Chronic suppurative OM incidence rate is 4.76 ‰ i.e. 31 million cases, with 22.6% of cases occurring annually in under-fives. OM-related hearing impairment has a prevalence of 30.82 per ten-thousand. Each year 21 thousand people die due to complications of OM. CONCLUSIONS: Our study is the first attempt to systematically review the available information and provide global estimates for OM and related conditions. The overall burden deriving from AOM, CSOM and their sequelae is considerable, particularly in the first five years of life and in the poorest countries. The findings call for incorporating OM-focused action within preventive and case management strategies, with emphasis on the more affected.
Keywords: Cost of Illness; Hearing Loss; Humans; Internationality; Otitis Media

A case of familial hemiplegic migraine associated with a novel ATP1A2 gene mutation. - De Cunto, Angela; Bensa, Marco; Tonelli, Alessandra (Pediatr Neurol, 2012)
Hemiplegic migraine constitutes an unusual form, characterized by periodic attacks of migraine with a motor component (hemiplegia). Familial forms are dominantly inherited, and are attributable to mutations in genes encoding proteins involved in ion transportation, including ATP1A2, which codes for the α-2 isoform of the sodium-potassium adenosine triphosphatase, a P-type cation transport adenosine triphosphatase, and responsible for the so-called familial hemiplegic migraine type 2. We describe a 9-year-old boy affected by familial hemiplegic migraine, with a novel ATP1A2 gene mutation (c.1799T>C p.V600A) in exon 13. Long-term treatment with flunarizine resulted in a good clinical response and the prevention of further attacks.
Keywords: Amino Acid Sequence; Child, Preschool; Humans; Male; Migraine with Aura; Molecular Sequence Data; Mutation; Pedigree; Sodium-Potassium-Exchanging ATPase

Chemerin regulates NK cell accumulation and endothelial cell morphogenesis in the decidua during early pregnancy. - Carlino, Claudia; Trotta, Eleonora; Stabile, Helena; Morrone, Stefania; Bulla, Roberta; Soriani, Alessandra; Iannitto, Maria Luisa; Agostinis, Chiara; Mocci, Carlo; Minozzi, Massimo; Aragona, Cesare; Perniola, Giorgia; et al. (J Clin Endocrinol Metab, 2012)
CONTEXT: Although decidual natural killer (NK) cell accumulation and vascular remodeling are critical steps to ensure successful pregnancy, the molecular mechanisms controlling these events are poorly defined. OBJECTIVE: Herein we analyzed whether chemerin, a recently identified chemoattractant involved in many pathophysiological processes, could be expressed in the uterine compartment and could regulate events relevant for the good outcome of pregnancy. DESIGN: Chemerin expression in human primary culture of stromal (ST) cells, extravillous trophoblast cells, and decidual endothelial cells (DEC) was analyzed by RT-PCR, ELISA, and Western blot. Migration through ST or DEC of peripheral blood and decidual (d) NK cells from pregnant women was performed using a transwell assay. A DEC capillary-like tube formation assay was used to evaluate endothelial morphogenesis. RESULTS: Chemerin is differentially expressed by decidual cells during early pregnancy being present at high levels in ST and extravillous trophoblast cells but not in DEC. Notably, ST cells from pregnant women exhibit and release higher levels of chemerin as compared with ST cells from menopausal or fertile nonpregnant women. Chemerin can support peripheral blood NK cell migration through both DEC and ST cells. Although dNK cells exhibit lower chemerin receptor (CMKLR1) expression than their blood counterpart, CMKLR1 engagement on dNK cells resulted in both ERK activation and migration through decidual ST cells. Interestingly, DEC also express CMKLR1 and undergo ERK activation and capillary-like tube structure formation upon exposure to chemerin. CONCLUSIONS: Our data indicate that chemerin is up-regulated during decidualization and might contribute to NK cell accumulation and vascular remodeling during early pregnancy.
Keywords: Capillaries; Cell Movement; Chemokines; Decidua; Endothelial Cells; Female; Humans; Killer Cells, Natural; MAP Kinase Signaling System; Neovascularization, Physiologic; Pregnancy; Pregnancy Trimester, First; Receptors, Chemokine; RNA, Messenger; Stromal Cells; Trophoblasts

A child with severe pneumomediastinum and ABCA3 gene mutation: a puzzling connection. - Copertino, Marco; Barbi, Egidio; Poli, Furio; Zennaro, Floriana; Ferrari, Maurizio; Carrera, Paola; Ventura, Alessandro (Arch Bronconeumol, 2012)
Keywords: Anemia; ATP-Binding Cassette Transporters; Child, Preschool; Dyspnea; Genetic Predisposition to Disease; Heterozygote; Humans; Intensive Care; Leukocytosis; Male; Mediastinal Emphysema; Mutation, Missense; Point Mutation; Pulmonary Emphysema; Respiratory Tract Infections; Subcutaneous Emphysema; Tomography, X-Ray Computed

Clarification of the pleiotropic effects of statins on mevalonate pathway and the feedback regulation of isoprenoids requires more comprehensive investigation. - Bianco, Anna Monica; Zanin, Valentina; Marcuzzi, Annalisa; Crovella, Sergio (Cell Biochem Funct, 2012)
Keywords: Carcinoma, Hepatocellular; Enzyme Inhibitors; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Liver Neoplasms; Simvastatin; Terpenes

Clinical and laboratory features of 103 patients from 42 Italian families with inherited thrombocytopenia derived from the monoallelic Ala156Val mutation of GPIbα (Bolzano mutation). - Noris, Patrizia; Perrotta, Silverio; Bottega, Roberta; Pecci, Alessandro; Melazzini, Federica; Civaschi, Elisa; Russo, Sabina; Magrin, Silvana; Loffredo, Giuseppe; Di Salvo, Veronica; Russo, Giovanna; Casale, Maddalena; et al. (Haematologica, 2012)
BACKGROUND: Bernard-Soulier syndrome is a very rare form of inherited thrombocytopenia that derives from mutations in GPIbα, GPIbβ, or GPIX and is typically inherited as a recessive disease. However, some years ago it was shown that the monoallelic c.515C>T transition in the GPIBA gene (Bolzano mutation) was responsible for macrothrombocytopenia in a few Italian patients. DESIGN AND METHODS: Over the past 10 years, we have searched for the Bolzano mutation in all subjects referred to our institutions because of an autosomal, dominant form of thrombocytopenia of unknown origin. RESULTS: We identified 42 new Italian families (103 cases) with a thrombocytopenia induced by monoallelic Bolzano mutation. Analyses of the geographic origin of affected pedigrees and haplotypes indicated that this mutation originated in southern Italy. Although the clinical expression was variable, patients with this mutation typically had a mild form of Bernard-Soulier syndrome with mild thrombocytopenia and bleeding tendency. The most indicative laboratory findings were enlarged platelets and reduced GPIb/IX/V platelet expression; in vitro platelet aggregation was normal in nearly all of the cases. CONCLUSIONS: Our study indicates that monoallelic Bolzano mutation is the most frequent cause of inherited thrombocytopenia in Italy, affecting 20% of patients recruited at our institutions during the last 10 years. Because many people from southern Italy have emigrated during the last century, this mutation may have spread to other countries.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Bernard-Soulier Syndrome; Child; Child, Preschool; Family Health; Female; Heterozygote; Humans; Infant; Italy; Male; Membrane Glycoproteins; Middle Aged; Mutation, Missense; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Genetic; Thrombocytopenia; Thrombopoietin; Tubulin; Young Adult

The clinical interpretation and significance of electronic fetal heart rate patterns 2 h before delivery: an institutional observational study. - Maso, Gianpaolo; Businelli, Caterina; Piccoli, Monica; Montico, Marcella; De Seta, Francesco; Sartore, Andrea; Alberico, Salvatore (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the clinical significance of intrapartum fetal heart rate (FHR) monitoring in low-risk pregnancies according to guidelines and specific patterns. METHODS: An obstetrician, blinded to neonatal outcome, retrospectively reviewed 198 low-risk cases that underwent continuous electronic fetal monitoring (EFM) during the last 2 h before delivery. The tracings were interpreted as normal, suspicious or pathological, according to specific guidelines of EFM and by grouping the different FHR patterns considering baseline, variability, presence of decelerations and bradycardia. The EFM groups and the different FHR-subgroups were associated with neonatal acid base status at birth, as well as the short-term neonatal composite outcome. Comparisons between groups were performed with Kruskal-Wallis test. Differences among categorical variables were evaluated using Fisher's exact test. Significance was set at p < 0.05 level. RESULTS: Significant differences were found for mean pH values in the three EFM groups, with a significant trend from "normal" [pH 7.25, 95 % confidence interval (CI) 7.28-7.32] to "pathological" tracings (pH 7.20, 95 % CI 7.17-7.13). Also the rates of adverse composite neonatal outcome were statistically different between the two groups (p < 0.005). Among the different FHR patterns, tracings with atypical variable decelerations and severe bradycardia were more frequently associated with adverse neonatal composite outcome (11.1 and 26.7 %, respectively). However, statistically significant differences were only observed between the subgroups with normal tracings and bradycardia. CONCLUSIONS: In low-risk pregnancies, there is a significant association between neonatal outcome and EFM classification. However, within abnormal tracings, neonatal outcome might differ according to specific FHR pattern.
Keywords: Acidosis; Bradycardia; Female; Fetal Blood; Fetal Monitoring; Heart Rate, Fetal; Humans; Hydrogen-Ion Concentration; Infant, Newborn; Labor, Obstetric; Predictive Value of Tests; Pregnancy; Pregnancy Outcome; Retrospective Studies; Single-Blind Method; Statistics, Nonparametric; Time Factors

Coeliac disease diagnosis: ESPGHAN 1990 criteria or need for a change? Results of a questionnaire. - Ribes-Koninckx, C; Mearin, M L; Korponay-Szabó, I R; Shamir, R; Husby, S; Ventura, A; Branski, D; Catassi, C; Koletzko, S; Mäki, M; Troncone, R; Zimmer, K P (J Pediatr Gastroenterol Nutr, 2012)
BACKGROUND AND OBJECTIVES: A revision of criteria for diagnosing coeliac disease (CD) is being conducted by The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN). In parallel, we have performed a survey aimed to evaluate present practices for CD among paediatric gastroenterologists and to learn their views on the need for modification of present criteria for CD diagnosis. PATIENTS AND METHODS: Questionnaires were distributed to experienced paediatric gastroenterologists (ESPGHAN members) via the Internet. RESULTS: Overall, 95 valid questionnaires were available for analysis, pertaining to 28 different countries, with the majority of responders treating patients with CD for >15 years. Only about 12% of the responders comply with present criteria, noncompliance being related mainly to the challenge policy. Approximately 90% request a revision and modification of the present criteria. Forty-four percent want to omit the small bowel biopsy in symptomatic children with positive anti-tissue transglutaminase immunoglobulin (Ig) A or endomysial IgA antibodies, especially if they are DQ2/DQ8 positive. For silent cases detected by screening with convincingly positive anti-tissue transglutaminase IgA or EMA IgA, about 30% consider that no small bowel biopsy should be required in selected cases. Adding human leukocyte antigen typing in the diagnostic workup was asked for by 42% of the responders. As for gluten challenge, a new policy is advocated restricting its obligation to cases whenever the diagnosis is doubtful or unclear. CONCLUSIONS: Based on these opinions, revision of the ESPGHAN criteria for diagnosing CD is urgently needed.
Keywords: Adolescent; Adult; Biopsy; Celiac Disease; Child; Child, Preschool; Glutens; Guideline Adherence; Guidelines as Topic; Health Care Surveys; Humans; Immunoglobulin A; Intestine, Small; Physician's Practice Patterns; Questionnaires; Societies, Medical; Transglutaminases; Young Adult

A common genetic background could explain early-onset Crohn's disease. - Bianco, Anna Monica; Zanin, Valentina; Girardelli, Martina; Magnolato, Andrea; Martelossi, Stefano; Martellossi, Stefano; Tommasini, Alberto; Marcuzzi, Annalisa; Crovella, Sergio (Med Hypotheses, 2012)
Crohn's disease (CD) is a multifactorial disease, in which environmental, microbial and genetic factors play important roles. CD is characterized by a chronic granulomatous inflammation by necrotic scarring with aspects of full-thickness wall. In spite of affecting mainly young adults, sometimes, CD can be present in the first year of life (early onset Crohn disease, EOCD) showing an unpredictable course and being often more severe than at older ages. In this paper we propose the hypothesis that EOCD patients should be analyzed using a Mendelian approach with family studies aimed to identify new loci directly involved in the early onset Crohn's disease. So we will leave the classic association study approach used until now for the identification of genes responsible for susceptibility to CD and propose linkage family analysis as alternative and powerful tool for the identification of new genetic variants associated with familiar cases of EOCD.
Keywords: Crohn Disease; Genetic Linkage; Genetic Predisposition to Disease; Humans; Models, Biological

De novo 911 Kb interstitial deletion on chromosome 1q43 in a boy with mental retardation and short stature. - Perrone, M D; Rocca, M S; Bruno, I; Faletra, F; Pecile, V; Gasparini, P (Eur J Med Genet, 2012)
Patients with distal deletions of chromosome 1q have a recognizable syndrome that includes microcephaly, hypoplasia or agenesis of the corpus callosum, and psychomotor retardation. Although these symptoms have been attributed to deletions of 1q42-1q44, the minimal chromosomal region involved has not yet defined. In this report, we describe a 7 years old male with mental retardation, cryptorchid testes, short stature and alopecia carrying only an interstitial de novo deletion of 911 Kb in the 1q43 region (239,597,095-240,508,817) encompassing three genes CHRM3, RPS7P5 and FMN2.
Keywords: Child; Chromosomes, Human, Pair 1; Dwarfism; Humans; Intellectual Disability; Male; Sequence Deletion

DEFB1 gene 5' untranslated region (UTR) polymorphisms in inflammatory bowel diseases. - Zanin, Valentina; Segat, Ludovica; Bianco, Anna Monica; Padovan, Lara; Tavares, Nathalia de Alencar Cunha; Crovella, Sergio (Clinics (Sao Paulo), 2012)
Keywords: 5' Untranslated Regions; Adult; Antimicrobial Cationic Peptides; beta-Defensins; Case-Control Studies; Colitis, Ulcerative; Crohn Disease; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Inflammatory Bowel Diseases; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide

Diagnosed child, treated child: food challenge as the first step toward tolerance induction in cow's milk protein allergy. - Longo, G; Berti, I; Barbi, E; Calligaris, L; Matarazzo, L; Radillo, O; Ronfani, L; Ventura, A (Eur Ann Allergy Clin Immunol, 2012)
BACKGROUND: Food challenge is required to assess tolerance in cow milk (CM) allergy. A positive challenge contraindicates the reintroduction of CM. Specific oral tolerance induction (SOTI) is a promising treatment. METHODS: All children admitted for a challenge were prospectively enrolled. To those tolerating between 2 and 150 ml a SOTI protocol was offered. Outcome, adverse reactions, parents' satisfaction were recorded. RESULTS: Out of 245 challenged patients, 175 reacted 122 out of 125, able to tolerate a minimum dose of 2 ml, underwent SOTI. After one year 75.4% were in an unrestricted diet, 16.1% tolerated between 5 and 150 ml, 8.5% stopped SOTI. Side effects were mild, parents' satisfaction was very high. CONCLUSIONS: The majority of children tolerating limited amounts of CM at the challenge acquires tolerance with SOTI without relevant side effects. Maintaining on an exclusion diet partially tolerant children should be considered debatable.
Keywords: Administration, Oral; Adolescent; Animals; Cattle; Child; Child, Preschool; Humans; Immune Tolerance; Infant; Milk Hypersensitivity; Milk Proteins; Self Administration

The dietary paradox in food allergy: yesterday's mistakes, today's evidence and lessons for tomorrow. - Badina, Laura; Barbi, Egidio; Berti, Irene; Radillo, Oriano; Matarazzo, Lorenza; Ventura, Alessandro; Longo, Giorgio (Curr Pharm Des, 2012)
During the last decades the prevalence of food allergy has significantly increased among children and antigen avoidance still remains the standard care for the management of this condition. Most reactions are IgE-mediated with a high risk of anaphylaxis requiring emergency medications in case of inadvertent ingestion. Recent studies showed that continuous administration of the offending food, rather than an elimination diet, could promote the development and maintenance of oral tolerance. Indeed, intestinal transit of food proteins and their interaction with gut-associated lymphoid tissue (GALT) is the essential prerequisite for oral tolerance. On the contrary, low-dose cutaneous exposure to environmental foods in children with atopic dermatitis and altered skin barrier facilitates allergic sensitization. The timing and the amount of cutaneous and oral exposure determine whether a child will have allergy or tolerance. Furthermore, previous preventive strategies such as the elimination diet during pregnancy and breastfeeding, prolonged exclusive breastfeeding and delayed weaning to solid foods did not succeed in preventing the development of food allergy. On the other hand, there could be an early narrow window of immunological opportunity to expose children to allergenic foods and induce natural tolerance. Finally, the gradual exposure to the offending food through special protocols of specific oral tolerance induction (SOTI) may be a promising approach to a proactive treatment of food allergy.
Keywords: Anaphylaxis; Antigens; Breast Feeding; Child; Dermatitis, Atopic; Female; Food Hypersensitivity; Humans; Immunoglobulin E; Pregnancy; Time Factors

The effect of clodronate on a mevalonate kinase deficiency cellular model. - Zanin, Valentina; Marcuzzi, Annalisa; Piscianz, Elisa; Vuch, Josef; Bianco, Anna Monica; Monasta, Lorenzo; Decorti, Giuliana; Crovella, Sergio (Inflamm Res, 2012)
BACKGROUND: A potential anti-inflammatory effect of clodronate--an aminobisphosphonate--was described to antagonize the pro-inflammatory effects of the block in the mevalonate pathway, the main feature of a rare auto-inflammatory disease called mevalonate kinase deficiency (MKD). OBJECTIVE: In this study we evaluated the potential anti-inflammatory effect of clodronate in MKD--a still orphan drug pediatric disease. METHODS: We studied some biological parameters, nitric oxide production using Griess reagents and programmed cell death by flow cytometry, as common inflammatory parameters in MKD, in the presence of different doses of clodronate (1, 10 and 100 μM). RESULTS: In our cellular model and in monocytes from patients with MKD, clodronate induced an increase in programed cell death and nitric oxide production in comparison with non-treated cells. CONCLUSION: Our findings suggest that clodronate does not have an anti-inflammatory effect as previously reported but that it increases the epiphenomena of this pediatric disease.
Keywords: Adolescent; Adult; Alendronate; Animals; Anti-Inflammatory Agents; Apoptosis; Cell Line; Cells, Cultured; Child; Clodronic Acid; Female; Humans; Inflammation; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Models, Biological; Monocytes; Nitric Oxide; Young Adult

Effects of hormonal contraception on vaginal flora. - De Seta, Francesco; Restaino, Stefano; De Santo, Davide; Stabile, Guglielmo; Banco, Rubina; Busetti, Marina; Barbati, Giulia; Guaschino, Secondo (Contraception, 2012)
BACKGROUND: The sector of the market that deals with contraception offers a long list of different contraceptive methods. Within the estroprogestinic choice, the routes of administration are oral, transdermic and vaginal one. Even though efficacy is comparable with these methods, secondary and adverse effects are directly involved in the acceptability of the method. STUDY DESIGN: This was a prospective comparative study. During 1 year, we enrolled 60 asymptomatic women who voluntarily requested combined oral contraception (COC) or combined contraceptive vaginal ring (CCVR group). After a baseline study of vaginal milieu prior to starting hormonal contraception, we performed a follow-up. For each woman, we examined vaginal pH; quantification of leukocytes, lactobacilli, Candida and cocci on saline microscopy fluid; Gram stain with Nugent score and the presence of vaginal infection [culture for Trichomonas vaginalis, albicans and nonalbicans Candida, Group B Streptococcus (GBS)]. RESULTS: At the end of follow-up, there was a little change of vaginal milieu in both groups. We noted an increase of lactobacilli in the CCVR users and an increase of GBS in COC users. CONCLUSION: CCVR compared to COC users showed an increase of the number of lactobacilli in vaginal flora. It means that an increase of leukorrhea in that group could be protective in terms of prevention of vaginal imbalance/infection.
Keywords: Administration, Intravaginal; Adolescent; Adult; Bacterial Load; Candida; Candida albicans; Contraceptive Devices, Female; Contraceptives, Oral, Combined; Female; Humans; Hydrogen-Ion Concentration; Lactobacillus; Leukocyte Count; Middle Aged; Prospective Studies; Streptococcus agalactiae; Trichomonas vaginalis; Vagina

Effects of prone and supine position on cerebral blood flow in preterm infants. - Bembich, Stefano; Oretti, Chiara; Travan, Laura; Clarici, Andrea; Massaccesi, Stefano; Demarini, Sergio (J Pediatr, 2012)
We evaluated the effect of prone and supine position on cerebral blood flow (CBF) in stable preterm infants. CBF, PO(2), and PCO(2) were measured in the two positions. Peripheral oxygenation increased and CBF decreased in prone position. We speculate that CBF autoregulation may compensate for increased peripheral oxygenation, by decreasing CBF.
Keywords: Cerebrovascular Circulation; Female; Humans; Infant, Newborn; Infant, Premature; Male; Prone Position; Regional Blood Flow; Supine Position

The effects of uterine fundal pressure (Kristeller maneuver) on pelvic floor function after vaginal delivery. - Sartore, Andrea; De Seta, Francesco; Maso, Gianpaolo; Ricci, Giuseppe; Alberico, Salvatore; Borelli, Massimo; Guaschino, Secondo (Arch Gynecol Obstet, 2012)
PURPOSE: To evaluate the role of uterine fundal pressure during the second stage of labor (Kristeller maneuver) on pelvic floor dysfunction (urinary and anal incontinence, genital prolapse, pelvic floor strength). METHODS: 522 primiparous women, enrolled 3 months after vaginal delivery, were divided in two groups: group A (297 women) identifies the women who received Kristeller maneuvers with different indications (e.g. fetal distress, failure to progress, mother exhaustion), group B (225 women) the women without maneuver. Participants were questioned about urogynecological symptoms and examined by Q-tip test, digital test, vaginal perineometry and uroflowmetric stop test score. RESULTS: Mediolateral episiotomies, dyspareunia and perineal pain were significantly higher in Kristeller group, whereas urinary and anal incontinence, genital prolapse and pelvic floor strength were not significantly different between the groups. CONCLUSIONS: Kristeller maneuver does not modify puerperal pelvic floor function but increases the rate of episiotomies.
Keywords: Delivery, Obstetric; Dyspareunia; Dystocia; Episiotomy; Fatigue; Fecal Incontinence; Female; Fetal Distress; Humans; Labor Stage, Second; Pain, Postoperative; Pelvic Floor; Pelvic Organ Prolapse; Perineum; Pregnancy; Pressure; Puerperal Disorders; Urinary Incontinence; Uterus

Efficacy of rifaximin vaginal tablets in treatment of bacterial vaginosis: a molecular characterization of the vaginal microbiota. - Cruciani, Federica; Brigidi, Patrizia; Calanni, Fiorella; Lauro, Vittoria; Tacchi, Raffaella; Donders, Gilbert; Peters, Klaus; Guaschino, Secondo; Vitali, Beatrice (Antimicrob Agents Chemother, 2012)
Bacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, double-blind, randomized, placebo-controlled study. An integrated molecular approach based on quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the effects of vaginal tablets containing the antibiotic. An increase in members of the genus Lactobacillus and a decrease in the BV-related bacterial groups after the antibiotic treatment were demonstrated by qPCR. PCR-DGGE profiles confirmed the capability of rifaximin to modulate the composition of the vaginal microbial communities and to reduce their complexity. This molecular analysis supported the clinical observation that rifaximin at 25 mg/day for 5 days represents an effective treatment to be used in future pivotal studies for the treatment of BV.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Double-Blind Method; Female; Humans; Lactobacillus; Metagenome; Middle Aged; Rifamycins; RNA, Ribosomal, 16S; Vagina; Vaginal Creams, Foams, and Jellies; Vaginosis, Bacterial; Young Adult

Endoscopic treatment of primary vesicoureteral reflux. - Pennesi, Marco; L'erario, Ines; Barbi, Egidio (N Engl J Med, 2012)
Keywords: Female; Humans; Ureteroscopy; Vesico-Ureteral Reflux

The energy balance positively regulates the levels of circulating TNF-related apoptosis inducing ligand in humans. - Biolo, Gianni; Secchiero, Paola; De Giorgi, Sara; Tisato, Veronica; Zauli, Giorgio (Clin Nutr, 2012)
BACKGROUND & AIMS: Although decreased levels of circulating TRAIL have been associated to cardiovascular risk and overall mortality, the mechanisms controlling TRAIL levels in physiopathological conditions are currently unknown. The aim of the present study was to investigate whether changes in the energy intake and insulin sensitivity may influence circulating TRAIL, and to analyze potential relationships between circulating TRAIL and changes in fat mass in healthy subjects receiving hypocaloric or hypercaloric diets. METHODS: Three distinct groups of participants were studied, at the end of a 14-day (n = 9), 35-day (n = 30) or 60-day (n = 16) period of experimental bed rest to induce insulin resistance and during controlled ambulation, after receiving eucaloric, hypocaloric or hypercaloric diets. RESULTS: After bed rest conditions, energy restriction significantly decreased circulating TRAIL, while overfeeding significantly increased TRAIL levels with respect to eucaloric control subjects. Moreover, a positive correlation was found between levels of circulating TRAIL and energy intake as well as between circulating TRAIL and energy balance, as determined by changes in fat mass in these subjects. CONCLUSIONS: Circulating levels of TRAIL exhibit a clear-cut positive correlation with the energy intake and balance in healthy subjects during experimental physical inactivity.
Keywords: Adult; Apoptosis; Bed Rest; Cross-Over Studies; Diet; Energy Intake; Energy Metabolism; Female; Humans; Insulin Resistance; Male; Motor Activity; Risk Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Establishing the Baby-Friendly Community Initiative in Italy: development, strategy, and implementation. - Bettinelli, Maria Enrica; Chapin, Elise M; Cattaneo, Adriano (J Hum Lact, 2012)
BACKGROUND: The Baby-Friendly Hospital Initiative (BFHI), developed by the World Health Organization and the United Nations Children's Fund (UNICEF) to promote breastfeeding in maternity facilities worldwide, has had a global impact on breastfeeding outcomes, but other interventions are needed both before and after hospital discharge to meet the recommended targets at 6 months. The Baby-Friendly Community Initiative (BFCI), a multifaceted program for community-based breastfeeding promotion that is complementary to the BFHI, addresses this challenge. OBJECTIVE: To describe the development, strategy, and implementation of the BFCI in Italy. METHODS: In 2006, UNICEF Italy created a working group to develop the BFCI for the Italian health system. A review of the different BFCI models worldwide was conducted. A preliminary adaptation of tools to Italian community health care settings was developed in 2007, when the Italian BFCI Seven Steps were published. Two years later, UNICEF Italy launched the Standards for Best Practice for both hospitals and communities, based on 2009 BFHI and UNICEF UK BFCI materials. OUTCOMES: The main outcome was to promote this process in Italian regional health systems and develop tools to assess compliance with the BFCI criteria. There is now one fully accredited Baby-Friendly Community in Italy, and 17 other communities are working on the various stages. CONCLUSIONS: The BFCI, a complex program that involves participation, training, audits, a continuous flow of feedback, and provision of resources for health workers and families, is now a reality in Italy.
Keywords: Breast Feeding; Continuity of Patient Care; Delivery Rooms; Female; Health Policy; Humans; Infant; Infant Care; Infant Welfare; Infant, Newborn; Italy; Maternal Health Services; Organizational Policy; Outcome and Process Assessment (Health Care); Practice Guidelines as Topic; Pregnancy; Program Development; Program Evaluation; United Nations; World Health Organization

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Exhaled nitric oxide as a guide to management of asthma in pregnancy. - Bibalo, Chiara; Badina, Laura; Longo, Giorgio; Ventura, Alessandro (Lancet, 2012)
Keywords: Asthma; Breath Tests; Female; Glucocorticoids; Humans; Nitric Oxide; Pregnancy; Pregnancy Complications

Extra-large letter spacing improves reading in dyslexia. - Zorzi, Marco; Barbiero, Chiara; Facoetti, Andrea; Lonciari, Isabella; Carrozzi, Marco; Montico, Marcella; Bravar, Laura; George, Florence; Pech-Georgel, Catherine; Ziegler, Johannes C (Proc Natl Acad Sci U S A, 2012)
Although the causes of dyslexia are still debated, all researchers agree that the main challenge is to find ways that allow a child with dyslexia to read more words in less time, because reading more is undisputedly the most efficient intervention for dyslexia. Sophisticated training programs exist, but they typically target the component skills of reading, such as phonological awareness. After the component skills have improved, the main challenge remains (that is, reading deficits must be treated by reading more--a vicious circle for a dyslexic child). Here, we show that a simple manipulation of letter spacing substantially improved text reading performance on the fly (without any training) in a large, unselected sample of Italian and French dyslexic children. Extra-large letter spacing helps reading, because dyslexics are abnormally affected by crowding, a perceptual phenomenon with detrimental effects on letter recognition that is modulated by the spacing between letters. Extra-large letter spacing may help to break the vicious circle by rendering the reading material more easily accessible.
Keywords: Attention; Awareness; Child; Dyslexia; Form Perception; France; Humans; Italy; Language; Pattern Recognition, Visual; Phonetics; Reading; Vision, Ocular; Visual Fields

First trimester maternal serum PIGF, free β-hCG, PAPP-A, PP-13, uterine artery Doppler and maternal history for the prediction of preeclampsia. - Di Lorenzo, G; Ceccarello, M; Cecotti, V; Ronfani, L; Monasta, L; Vecchi Brumatti, L; Montico, M; D'Ottavio, G (Placenta, 2012)
OBJECTIVE: To evaluate the detection of pregnancy hypertensive disorders by integrating maternal history, serum biomarkers and uterine artery Doppler in the first trimester. METHODS: We prospectively recruited 2118 women that underwent an 11-13 weeks aneuploidy screening. We gathered information on maternal history, uterine artery Doppler and serum biomarkers (PAPP-A, PlGF, PP-13 and free β-hCG). Models were developed for the prediction of overall preeclampsia (PE), early-onset PE, late-onset PE and gestational hypertension (GH). For each outcome, we performed a multivariate logistic regression starting from the saturated model: adopting a step-down procedure we excluded all factors not statistically significant (p > 0.05). Sensitivity models only for statistically significant parameters were calculated from the ROC curves for fixed false-positive rates (FPR). RESULTS: Among 2118 women, 46 (2.17%) developed GH and 25 (1.18%) were diagnosed with PE, including 12 (0.57%) early-onset PE and 13 (0.61%) late-onset PE. For a fixed FPR of 10 and 5%, serum PlGF, free β-hCG and chronic hypertension identified respectively 67 and 75% of women who developed early-onset PE. In the model for the prediction of overall PE the combination of the uterine artery Doppler pulsatility index (UtA PI) with PlGF and chronic hypertension reached a sensitivity of 60% for a 20% of FPR. CONCLUSION: An integration of maternal characteristics and first trimester maternal serum biomarkers (free β-hCG and PlGF) provided a possible screening for early-onset PE. In the overall PE model, UtA PI turned out to be statistically significant but did not improve the detection rate.
Keywords: Adult; Biological Markers; Chorionic Gonadotropin, beta Subunit, Human; Cohort Studies; Female; Galectins; Humans; Hypertension, Pregnancy-Induced; Pre-Eclampsia; Pregnancy; Pregnancy Complications; Pregnancy Proteins; Pregnancy Trimester, First; Pregnancy-Associated Plasma Protein-A; Prospective Studies; Ultrasonography, Prenatal; Uterine Artery; Uterus

Formation of membrane-defined compartments by tick-borne encephalitis virus contributes to the early delay in interferon signaling. - Miorin, Lisa; Albornoz, Amelina; Baba, Marycelin M; D'Agaro, Pierlanfranco; Marcello, Alessandro (Virus Res, 2012)
Interferons are key mediators of the innate antiviral response of the cell against viral infections. Viruses on the other hand have evolved various strategies to delay innate immunity in order to establish a productive infection. In this work we analyzed the pathway of interferon induction by the tick-borne encephalitis virus. We initially observed a consistent delay of interferon induction following virus replication. RIG-I, but not MDA5, and nuclear translocation of IRF3 were eventually required for interferon activation pointing to a defect in pattern recognition receptor's signaling. However, viral proteins could not directly inhibit the pathway suggesting an indirect mechanism. We found that dsRNA replication intermediates and replicated viral RNA localized to membrane-defined perinuclear compartments that resisted RNAse treatment. Thus, initial escape from innate immunity involved the formation of replication vesicles that may function as a barrier to pattern recognition receptors.
Keywords: Cell Membrane; Encephalitis Viruses, Tick-Borne; Humans; Immune Evasion; Interferons; Receptors, Pattern Recognition; RNA, Viral; Signal Transduction

Frequency of human papillomavirus types 16, 18, 31, and 33 and sites of cervical lesions in gynecological patients from Recife, Brazil. - Baldez da Silva, M F P T; Guimarães, V; Silva, M A R; Medeiros do Amaral, C M; Beçak, W; Stocco, R C; Freitas, A C; Crovella, S (Genet Mol Res, 2012)
Human papilloma virus (HPV) is a well-established cause of cervical cancer. While many studies have been performed so far on HPV viral biology, mode of infection and prevention measures, scanty information is available on lesion sites of infected women and the incidence of viral types at specific locations. We looked for a possible relationship between the most common viral types (HPVs 16, 18, 31, 33) found in Recife, PE, Brazil, and lesion sites. We examined 396 HPV-positive women at the Gynecological Unit of the IMIP at Recife; 288 women were positive for HPV 16, 18, 31, or 33, present as a single-virus type or as co-infection. HPV 16 was the most frequent virus type found in the vulva, vagina, uterine cervix-vagina, and uterine cervix. HPV 31 was the second prevalent virus type in vulva, vagina, uterine cervix-vagina, uterine cervix, and mole. HPVs 18 and 33 were present with similar frequencies in the mole-vulva region. Among the co-infections, HPV 16/18 and HPV16/31 were the most frequent in our study group, followed by HPV 16/33.
Keywords: Adolescent; Adult; Brazil; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; Papillomavirus Infections; Uterine Cervical Diseases; Young Adult

From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome

Functional single-nucleotide polymorphisms in the DEFB1 gene are associated with systemic lupus erythematosus in Southern Brazilians. - Sandrin-Garcia, P; Brandão, L A C; Guimarães, R L; Pancoto, J A T; Donadi, E A; Lima-Filho, J L de; Segat, L; Crovella, S (Lupus, 2012)
Systemic lupus erythematosus (SLE) is an autoimmune disease that results in inflammation and tissue damage. The etiology of SLE remains unknown, but recent studies have shown that the innate immune system may have a role in SLE pathogenesis through the secretion of small cationic peptides named defensins. The aim of the study was to determine the possible involvement in SLE of three functional single nucleotide polymorphisms (SNPs) (c.-52G>A, c.-44C>G and c.-20G>A) in the 5'UTR region of DEFB1 gene, by analyzing them in a population of 139 SLE patients and 288 healthy controls. The c.-52G>A SNP showed significant differences in allele and genotype frequency distribution between SLE patients and controls (p = 0.01 and p = 0.02 respectively) indicating protection against SLE (A allele, OR = 0.68, AA genotype OR = 0.51). Significant differences were also observed for c.-44C>G SNP, the C/G genotype being associated with susceptibility to SLE (OR = 1.60, p = 0.04). Moreover, statistically significant differences between patients and controls were found for two DEFB1 haplotypes (GCA and GGG, p = 0.01 and p = 0.02 respectively). When considering DEFB1 SNPs and SLE clinical and laboratory manifestations, significant association was found with neuropsychiatric disorders, immunological alterations and anti-DNA antibodies. In conclusion, our results evidence a possible role for the c.-52G>A and c.-44C>G DEFB1 polymorphisms in SLE pathogenesis, that can be considered as possible risk factors for development of disease and disease-related clinical manifestations. Additional studies are needed, to corroborate these results as well as functional studies to understand the biological role of these SNPs in the pathogenesis of SLE.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma. - Mazzoni, Elisa; Corallini, Alfredo; Cristaudo, Alfonso; Taronna, Angelo; Tassi, Gianfranco; Manfrini, Marco; Comar, Manola; Bovenzi, Massimo; Guaschino, Roberto; Vaniglia, Francesca; Magnani, Corrado; Casali, Ferruccio; et al. (Proc Natl Acad Sci U S A, 2012)
Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV)40 infection has also been suggested. SV40 is a DNA tumor virus found in some studies to be associated at high prevalence with MPM. SV40 sequences have also been detected, although at a lower prevalence than in MPM, in blood specimens from healthy donors. However, some studies have failed to reveal SV40 footprints in MPM and its association with this neoplasm. These conflicting results indicate the need for further investigations with new approaches. We report on the presence of antibodies in serum samples from patients affected by MPM that specifically react with two different SV40 mimotopes. The two SV40 peptides used in indirect ELISAs correspond to viral capsid proteins. ELISA with the two SV40 mimotopes gave overlapping results. Our data indicate that in serum samples from MPM-affected patients (n = 97), the prevalence of antibodies against SV40 viral capsid protein antigens is significantly higher (26%, P = 0.043) than in the control group (15%) represented by healthy subjects (n = 168) with the same median age (66 y) and sex. Our results suggest that SV40 is associated with a subset of MPM and circulates in humans.
Keywords: Amino Acid Sequence; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mesothelioma; Molecular Sequence Data; Pleural Neoplasms; Pregnancy; Simian virus 40

Identification of a New Mutation (L46P) in the Human NOG Gene in an Italian Patient with Symphalangism Syndrome. - Athanasakis, E; Biarnés, X; Bonati, M T; Gasparini, P; Faletra, F (Mol Syndromol, 2012)
Proximal symphalangism (SYM1) is a joint morphogenesis disorder characterized by stapes ankylosis, proximal interphalangeal joint fusion, skeletal anomalies and conductive hearing loss. Noggin is a bone morphogenetic protein (BMP) antagonist essential for normal bone and joint development in humans and mice. Autosomal dominant mutations have been described in the NOG gene, encoding the noggin protein. We analyzed an Italian sporadic patient with SYM1 due to a novel NOG mutation (L46P) based on a c.137T>C transition. A different pathogenic mutation in the same codon (L46D) has been previously described in an in vivo chicken model. An in silico model shows a decreased binding affinity between noggin and BMP7 for both L46D and L46P compared to the wild type. Therefore, this codon should play an important role in BMP7 binding activity of the noggin protein and consequently to the joint morphogenesis.

Inflammation profile of four early onset Crohn patients. - Marcuzzi, Annalisa; Girardelli, Martina; Bianco, Anna Monica; Martelossi, Stefano; Magnolato, Andrea; Tommasini, Alberto; Crovella, Sergio (Gene, 2012)
Crohn disease (CD) is a multifactorial disorder affecting mainly young adults. Sometimes, however, it can present in the first year of life (Early onset Crohn disease (EOCD)) showing an unpredictable course and can often be more severe than at older ages. Some cases have been associated to an underlying primary immunodeficiency such as IL10R deficiency. We studied the functional response to IL-10 and the genotype of IL-10 receptor in four patients with early onset crohn-like colitis. We found an IL10R variant, which may be associated with a decreased response to the cytokine in one patient. Further studies to determine its pathogenic effect should be performed. In addition IL-10 mediated inhibition of LPS-induced TNFα expression was measured in patient's monocytes.
Keywords: Crohn Disease; Cytokines; Humans; Inflammation; Monocytes; Nod2 Signaling Adaptor Protein; Polymorphism, Genetic; Receptors, Interleukin-10; Tumor Necrosis Factor-alpha

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

International collaboration as a tool for diagnosis of patients with inherited thrombocytopenia in the setting of a developing country. - Glembotsky, A C; Marta, R F; Pecci, A; De Rocco, D; Gnan, C; Espasandin, Y R; Goette, N P; Negro, F; Noris, P; Savoia, A; Balduini, C L; Molinas, F C; et al. (J Thromb Haemost, 2012)
BACKGROUND: Inherited thrombocytopenias (ITs) are heterogeneous genetic disorders that frequently represent a diagnostic challenge. The requirement of highly specialized tests for diagnosis represents a particular problem in resource-limited settings. To overcome this difficulty, we applied a diagnostic algorithm and developed a collaboration program with a specialized international center in order to increase the diagnostic yield in a cohort of patients in Argentina. METHODS: Based on the algorithm, initial evaluation included collection of clinical data, platelet size, blood smear examination and platelet aggregation tests. Confirmatory tests were performed according to diagnostic suspicion, which included platelet glycoprotein expression, immunofluorescence for myosin-9 in granulocytes and platelet thrombospondin-1 and molecular screening of candidate genes. RESULTS: Thirty-one patients from 14 pedigrees were included; their median age was 32 (4-72) years and platelet count 72 (4-147)×10(9) L(-1). Autosomal dominant inheritance was found in nine (64%) pedigrees; 10 (71%) had large platelets and nine (29%) patients presented with syndromic forms. A definitive diagnosis was made in 10 of 14 pedigrees and comprised MYH9-related disease in four, while classic and monoallelic Bernard-Soulier syndrome, gray platelet syndrome, X-linked thrombocytopenia, thrombocytopenia 2 (ANKRD26 mutation) and familial platelet disorder with predisposition to acute myelogenous leukemia were diagnosed in one pedigree each. CONCLUSIONS: Adoption of an established diagnostic algorithm and collaboration with an expert referral center proved useful for diagnosis of IT patients in the setting of a developing country. This initiative may serve as a model to develop international networks with the goal of improving diagnosis and care of patients with these rare diseases.
Keywords: Adolescent; Adult; Aged; Algorithms; Argentina; Biological Markers; Child; Child, Preschool; Cooperative Behavior; Developing Countries; DNA Mutational Analysis; Feasibility Studies; Female; Flow Cytometry; Fluorescent Antibody Technique; Genetic Predisposition to Disease; Genetic Testing; Health Services Accessibility; Hematologic Tests; Heredity; Humans; International Cooperation; Italy; Male; Middle Aged; Molecular Motor Proteins; Myosin Heavy Chains; Pedigree; Phenotype; Platelet Count; Platelet Function Tests; Predictive Value of Tests; Prognosis; Referral and Consultation; Thrombocytopenia; Thrombospondin 1; Young Adult

Letter: inflammatory bowel disease, complementary and alternative medicine, and genetics. - Bianco, A M; Vuch, J; Girardelli, M; Zanin, V; Marcuzzi, A; Crovella, S (Aliment Pharmacol Ther, 2012)
Keywords: Complementary Therapies; Female; Humans; Inflammatory Bowel Diseases; Male; Medication Adherence

Lingual schwannoma in pediatric patients. - Manna, Francesco; Barbi, Egidio; Murru, Flora; Bussani, Rossana (J Craniofac Surg, 2012)
We present the case of a 15-year-old boy who presented to our emergency department because of a soft lesion growing on the back of his tongue. On examination, a vegetant mass on the posteromidline lingual part of the body of the tongue was noticed: it was not painful, even if the boy reported discomfort because of its size; there was no bleeding or signs of infection. The magnetic resonance imaging showed the lesion as trilobated and capsulated, but was not diriment to define a diagnosis; excisional biopsy was performed under general anesthesia, and the mass was identified as a schwannoma. Schwannoma, or neurilemmoma, is a benign tumor originating from Schwann cells of the nerve sheath surrounding peripheral nerves. It is slow-growing, usually solitary, and encapsulated. Intraoral schwannomas are rare and account for 1% of lesions of the head and neck region. There is no sex predilection. The symptoms depend on size and location of the tumor. Recurrence is rare after complete surgical resection. The present study aimed to retrospectively describe our experience with a case of neurilemmoma of the tongue presenting in childhood, the diagnostic methods used, the surgical decision, and the treatment outcome and to analyze the data and review the literature available on this type of tumor. The etiology, clinical presentation, differential diagnosis, and management are discussed.
Keywords: Adolescent; Diagnosis, Differential; Humans; Magnetic Resonance Imaging; Male; Neurilemmoma; Tongue Neoplasms

Lovastatin-induced apoptosis is modulated by geranylgeraniol in a neuroblastoma cell line. - Marcuzzi, Annalisa; Zanin, Valentina; Piscianz, Elisa; Tricarico, Paola Maura; Vuch, Josef; Girardelli, Martina; Monasta, Lorenzo; Bianco, Anna Monica; Crovella, Sergio (Int J Dev Neurosci, 2012)
Mevalonic aciduria (MA), the most severe form of mevalonate kinase deficiency (MKD), is still an orphan drug disease and the pathogenetic mechanisms underlying neuronal dysfunction is still poorly understood. In our study we have investigated the apoptotic mechanism mediated by the exposure of the cultured neuroblastoma cell line, SH-SY5Y, to lovastatin in absence or in presence of the isoprenoid, geranylgeraniol, with the aim of unraveling the pathogenesis of MA. Lovastatin, blocks the mevalonate pathway inhibiting the 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR), an enzyme of the mevalonate pathway upstream the mevalonate kinase enzyme, reproducing biochemical features similar to those found in MKD. We demonstrate that apoptosis in neuronal lovastatin treated-cells is induced by the mitochondrial pathway, with caspase-9 as the initiator and caspase-3 as the effector caspase. The presence of geranylgeraniol modulates both the caspase-9 and caspase-3 activity in a dose-dependent way, confirming that this isoprenoid enters the mevalonate pathway, is metabolized and finally is able to by-pass the statin biochemical block reconstituting the mevalonate pathway. According to our findings, it should not be the time course adopted that modulates the apoptotic response but rather the isoprenoid itself. Being aware that our results have been obtained using a biochemical model of MKD, and not cells from patients with the disease, we believe our findings increase the knowledge of MA pathogenesis, and may possibly contribute to the development of novel therapeutic strategies.
Keywords: Analysis of Variance; Apoptosis; Caspases; Cell Line, Tumor; Diterpenes; Dose-Response Relationship, Drug; Drug Interactions; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lovastatin; Neuroblastoma; Time Factors

Lutein and zeaxanthin supplementation in preterm infants to prevent retinopathy of prematurity: a randomized controlled study. - Dani, Carlo; Lori, Ilaria; Favelli, Federica; Frosini, Saverio; Messner, Hubert; Wanker, Petra; De Marini, Sergio; Oretti, Chiara; Boldrini, Antonio; Massimiliano, Ciantelli; Bragetti, Patrizia; Germini, Cristiana (J Matern Fetal Neonatal Med, 2012)
OBJECTIVES: Lutein and its isomer zeaxanthin (L/Z) function in the eye as antioxidant agents and blue-light filters. Our aim was to evaluate whether their administration could help decrease the occurrence of retinopathy of prematurity (ROP) in preterm infants. METHODS: Infants with gestational age ≤32 weeks were randomly assigned to receive a daily dose of L/Z (0.14 + 0.006 mg) or placebo until discharge. RESULTS: ROP occurrence was similar in the L/Z (11/58; 19%) and placebo (15/56; 27%) groups, as the occurrence of ROP at each stage and the need of eye surgery. CONCLUSION: L/Z supplementation was ineffective in preventing ROP in preterm infants and did not affect the outcome at discharge of our patients.
Keywords: Antioxidants; Drug Administration Schedule; Drug Combinations; Female; Humans; Infant, Newborn; Infant, Premature; Logistic Models; Lutein; Male; Retinopathy of Prematurity; Risk Factors; Treatment Outcome; Xanthophylls; Zeaxanthins

Management of cryptorchidism: a survey of clinical practice in Italy. - Marchetti, Federico; Bua, Jenny; Tornese, Gianluca; Piras, Gianni; Toffol, Giacomo; Ronfani, Luca (BMC Pediatr, 2012)
BACKGROUND: An evidence-based Consensus on the treatment of undescended testis (UT) was recently published, recommending to perform orchidopexy between 6 and 12 months of age, or upon diagnosis and to avoid the use of hormones. In Italy, current practices on UT management are little known. Our aim was to describe the current management of UT in a cohort of Italian children in comparison with the Consensus guidelines. As management of retractile testis (RT) differs, RT cases were described separately. METHODS: Ours is a retrospective, multicenter descriptive study. An online questionnaire was filled in by 140 Italian Family Paediatricians (FP) from Associazione Culturale Pediatri (ACP), a national professional association of FP. The questionnaire requested information on all children with cryptorchidism born between 1/01/2004 and 1/01/2006. Data on 169 children were obtained. Analyses were descriptive. RESULTS: Overall 24% of children were diagnosed with RT, 76% with UT. Among the latter, cryptorchidism resolved spontaneously in 10% of cases at a mean age of 21.6 months. Overall 70% of UT cases underwent orchidopexy at a mean age of 22.8 months (SD 10.8, range 1.2-56.4), 13% of whom before 1 year. The intervention was performed by a paediatric surgeon in 90% of cases, with a success rate of 91%. Orchidopexy was the first line treatment in 82% of cases, while preceded by hormonal treatment in the remaining 18%. Hormonal treatment was used as first line therapy in 23% of UT cases with a reported success rate of 25%. Overall, 13 children did not undergo any intervention (mean age at last follow up 39.6 months). We analyzed the data from the 5 Italian Regions with the largest number of children enrolled and found a statistically significant regional difference in the use of hormonal therapy, and in the use of and age at orchidopexy. CONCLUSIONS: Our study showed an important delay in orchidopexy. A quarter of children with cryptorchidism was treated with hormonal therapy. In line with the Consensus guidelines, surgery was carried out by a paediatric surgeon in the majority of cases, with a high success rate.
Keywords: Child, Preschool; Chorionic Gonadotropin; Cryptorchidism; Gonadotropin-Releasing Hormone; Guideline Adherence; Humans; Infant; Italy; Male; Middle Aged; Orchiopexy; Pediatrics; Physician's Practice Patterns; Practice Guidelines as Topic; Questionnaires; Retrospective Studies; Treatment Outcome

Mannose-binding lectin and MBL-associated serine protease-2 gene polymorphisms in a Brazilian population from Rio de Janeiro. - Ferraroni, N R; Segat, L; Guimarães, R L; Brandão, L A C; Crovella, S; Constantino-Silva, R N; Loja, C; da Silva Duarte, A J; Grumach, A S (Int J Immunogenet, 2012)
Mannose-binding lectin (MBL) is a protein able to bind to carbohydrate patterns on pathogen membranes; upon MBL binding, its' associated serine protease MBL-associated serine protease type 2 (MASP2) is autoactivated, promoting the activation of complement via the lectin pathway. For both MBL2 and MASP2 genes, the frequencies of polymorphisms are extremely variable between different ethnicities, and this aspect has to be carefully considered when performing genetic studies. While polymorphisms in the MBL-encoding gene (MBL2) have been associated, depending upon ethnicity, with several diseases in different populations, little is known about the distribution of MASP2 gene polymorphisms in human populations. The aim of our study was thus to determine the frequencies of MBL2 (exon 1 and promoter) and MASP2 (p.D371Y) polymorphisms in a Brazilian population from Rio de Janeiro. A total of 294 blood donor samples were genotyped for 27 polymorphisms in the MBL2 gene by direct sequencing of a region spanning from the promoter polymorphism H/L rs11003125 to the rs1800451 polymorphism (at codon 57 in the first exon of the gene). Genotyping for MASP2 p.D371Y was carried out using fluorogenic probes. To our knowledge, this is the first study reporting the prevalence of the MASP2 p.D371Y polymorphism in a Brazilian population. The C allele frequency 39% is something intermediate between the reported 14% in Europeans and 90% in Sub-Saharan Africans. MBL2 polymorphisms frequencies were quite comparable to those previously reported for admixed Brazilians. Both MBL2 and MASP2 polymorphisms frequencies reported in our study for the admixed Brazilian population are somehow intermediate between those reported in Europeans and Africans, reflecting the ethnic composition of the southern Brazilian population, estimated to derive from an admixture of Caucasian (31%), African (34%) and Native American (33%) populations. In conclusion, our population genetic study describes the frequencies of MBL2 and MASP2 functional SNPs in a population from Rio de Janeiro, with the aim of adding new information concerning the distribution of these SNPs in a previously unanalysed Brazilian population, thus providing a new genetic tool for the evaluation of the association of MBL2 and MASP2 functional SNPs with diseases in Brazil, with particular emphasis on the state of Rio de Janeiro.
Keywords: Adolescent; Adult; Brazil; Ethnic Groups; Exons; Female; Fluorescent Dyes; Gene Frequency; Genetics, Population; Genome, Human; HapMap Project; Humans; Male; Mannose-Binding Lectin; Mannose-Binding Protein-Associated Serine Proteases; Middle Aged; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Sequence Analysis, DNA; Young Adult

MBL interferes with endovascular trophoblast invasion in pre-eclampsia. - Agostinis, Chiara; Bossi, Fleur; Masat, Elisa; Radillo, Oriano; Tonon, Maddalena; De Seta, Francesco; Tedesco, Francesco; Bulla, Roberta (Clin Dev Immunol, 2012)
The spiral arteries undergo physiologic changes during pregnancy, and the failure of this process may lead to a spectrum of pregnancy disorders, including pre-eclampsia. Our recent data indicate that decidual endothelial cells (DECs), covering the inner side of the spiral arteries, acquire the ability to synthesize C1q, which acts as a link between endovascular trophoblast and DECs favouring the process of vascular remodelling. In this study, we have shown that sera obtained from pre-eclamptic patients strongly inhibit the interaction between extravillous trophoblast (EVT) and DECs, preventing endovascular invasion of trophoblast cells. We further demonstrated that mannose-binding lectin (MBL), one of the factor increased in pre-eclamptic patient sera, strongly inhibits the interaction of EVT with C1q interfering with the process of EVT adhesion to and migration through DECs. These data suggest that the increased level of MBL in pre-eclampsia may contribute to the failure of the endovascular invasion of trophoblast cells.
Keywords: Cell Communication; Decidua; Endothelial Cells; Female; Humans; Mannose-Binding Lectin; Pre-Eclampsia; Pregnancy; Transendothelial and Transepithelial Migration; Trophoblasts

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Mevalonate kinase deficiency: disclosing the role of mevalonate pathway modulation in inflammation. - Marcuzzi, Annalisa; Crovella, Sergio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Gattorno, Marco; Frenkel, Joost (Curr Pharm Des, 2012)
Inflammation is a highly regulated process involved both in the response to pathogens as well as in tissue homeostasis. In recent years, a complex network of proteins in charge of inflammation control has been revealed by the study of hereditary periodic fever syndromes. Most of these proteins belong to a few families and share the capability of sensing pathogen-associated and damageassociated molecular patterns. By interacting with each other, these proteins participate in the assembly of molecular platforms, called inflammasomes, which ultimately lead to the activation of cytokines, to the transcription of inflammatory genes or to the induction of cell apoptosis. Among hereditary periodic fever syndromes, mevalonate kinase deficiency (MKD) is the sole in which the phenotype did not directly associate with a deficiency of these proteins, but with a metabolic defect of the mevalonate pathway, highlighting the importance of this metabolic pathway in the inflammation control. Noteworthy, drugs acting on this pathway can greatly influence the inflammatory response. The modulation of inflammation by mevalonate pathway is of interest, since it may involve mechanisms not directly referable to inflammasomes. MKD provides a model to study these mechanisms and possibly to develop new classes of anti-inflammatory drugs.
Keywords: Animals; Anti-Inflammatory Agents; Apoptosis; Cytokines; Drug Design; Hereditary Autoinflammatory Diseases; Humans; Inflammasomes; Inflammation; Mevalonate Kinase Deficiency; Mevalonic Acid

Molecular analysis of HEXA gene in Argentinean patients affected with Tay-Sachs disease: possible common origin of the prevalent c.459+5A>G mutation. - Zampieri, Stefania; Montalvo, Annalisa; Blanco, Mariana; Zanin, Irene; Amartino, Hernan; Vlahovicek, Kristian; Szlago, Marina; Schenone, Andrea; Pittis, Gabriela; Bembi, Bruno; Dardis, Andrea (Gene, 2012)
Tay-Sachs disease (TSD) is a recessively inherited disorder caused by the deficient activity of hexosaminidase A due to mutations in the HEXA gene. Up to date there is no information regarding the molecular genetics of TSD in Argentinean patients. In the present study we have studied 17 Argentinean families affected by TSD, including 20 patients with the acute infantile form and 3 with the sub-acute form. Overall, we identified 14 different mutations accounting for 100% of the studied alleles. Eight mutations were novel: 5 were single base changes leading to drastic residue changes or truncated proteins, 2 were small deletions and one was an intronic mutation that may cause a splicing defect. Although the spectrum of mutations was highly heterogeneous, a high frequency of the c.459+5G>A mutation, previously described in different populations was found among the studied cohort. Haplotype analysis suggested that in these families the c.459+5G>A mutation might have arisen by a single mutational event.
Keywords: Child; Cohort Studies; Female; Hexosaminidase A; Humans; Infant; Male; Mutation; Tay-Sachs Disease

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

More on professionals' attitudes on blood-tinged milk: a survey from Italy. - Bua, J; Travan, L; Davanzo, R; Demarini, S (J Perinatol, 2012)
Keywords: Attitude of Health Personnel; Breast Feeding; Clinical Protocols; Female; Humans; Intensive Care Units, Neonatal; Intensive Care, Neonatal; Male; Milk, Human; Professional Practice

MYH9-related disorders: report on a patient of Greek origin presenting with macroscopic hematuria and presenile cataract, caused by an R1165C mutation. - Economou, Marina; Batzios, Spyros P; Pecci, Alessandro; Printza, Nikoletta; Savoia, Anna; Barozzi, Serena; Theodoridou, Stamatia; Teli, Aikaterini; Psillas, Georgios; Zafeiriou, Dimitrios I (J Pediatr Hematol Oncol, 2012)
Myosin heavy chain-9 (MYH9)-related disorders represent a heterogenous group of hereditary diseases caused by mutations in the gene encoding the heavy chain of nonmuscle myosin IIA. May-Hegglin anomaly and Fechtner, Sebastian, and Epstein syndromes are the four phenotypes of the disease, characterized by congenital macrothrombocytopenia and distinguished by different combinations of clinical signs that may include glomerulonephritis, sensorineural hearing loss, and presenile cataract. The spectrum of mutations responsible for the disease is wide and the existence of genotype-phenotype correlation remains a critical issue. We report the first case of an MYH9-RD in a patient of Greek origin presenting with macroscopic hematuria and presenile cataract caused by a p.R1165C mutation. The same mutation was present in the patient's father, who exhibited no extrahematological features of the disease. The p.R1165C mutation is one of the MYH9 alterations whose prognostic significance is still poorly defined. Thus, the patients described add to the limited existing data on the MYH9 mutations and their resultant phenotypes.
Keywords: Adolescent; Cataract; Diagnosis, Differential; DNA Mutational Analysis; Greece; Hematuria; Humans; Male; Molecular Motor Proteins; Myosin Heavy Chains; Point Mutation

New insights in the sugarcane transcriptome responding to drought stress as revealed by superSAGE. - Kido, Éderson Akio; Ferreira Neto, José Ribamar Costa; Silva, Roberta Lane de Oliveira; Pandolfi, Valesca; Guimarães, Ana Carolina Ribeiro; Veiga, Daniela Truffi; Chabregas, Sabrina Moutinho; Crovella, Sergio; Benko-Iseppon, Ana Maria (ScientificWorldJournal, 2012)
In the scope of the present work, four SuperSAGE libraries have been generated, using bulked root tissues from four drought-tolerant accessions as compared with four bulked sensitive genotypes, aiming to generate a panel of differentially expressed stress-responsive genes. Both groups were submitted to 24 hours of water deficit stress. The SuperSAGE libraries produced 8,787,315 tags (26 bp) that, after exclusion of singlets, allowed the identification of 205,975 unitags. Most relevant BlastN matches comprised 567,420 tags, regarding 75,404 unitags with 164,860 different ESTs. To optimize the annotation efficiency, the Gene Ontology (GO) categorization was carried out for 186,191 ESTs (BlastN against Uniprot-SwissProt), permitting the categorization of 118,208 ESTs (63.5%). In an attempt to elect a group of the best tags to be validated by RTqPCR, the GO categorization of the tag-related ESTs allowed the in silico identification of 213 upregulated unitags responding basically to abiotic stresses, from which 145 presented no hits after BlastN analysis, probably concerning new genes still uncovered in previous studies. The present report analyzes the sugarcane transcriptome under drought stress, using a combination of high-throughput transcriptome profiling by SuperSAGE with the Solexa sequencing technology, allowing the identification of potential target genes during the stress response.
Keywords: Droughts; Gene Expression Profiling; Heat-Shock Response; Plant Proteins; Saccharum; Transcriptome

NLRP1 polymorphisms in patients with asbestos-associated mesothelioma. - Girardelli, Martina; Maestri, Iva; Rinaldi, Rosa R; Tognon, Mauro; Boldorini, Renzo; Bovenzi, Massimo; Crovella, Sergio; Comar, Manola (Infect Agent Cancer, 2012)
UNLABELLED: BACKGROUND: An increasing incidence of malignant mesothelioma (MM) cases in patients with low levels of asbestos exposure suggests the interference of alternative cofactors. SV40 infection was detected, as co-morbidity factor, only in 22% of asbestos-MM patients from a North-Eastern Italy area. An additional mechanism of injury related to asbestos exposure in MM development has been recently associated to inflammatory responses, principally driven by interleukin (IL)-1 beta (ß) activated within the inflammasome complex.NLRP3 inflammosome has been described as the intracellular sensor for asbestos able to induce inflammasome activation and IL-1ß secretion while NLRP1 is expressed in lung epithelial cells and alveolar macrophages and contributes to the immune response and to survival/apoptosis balance. This study proposes to evaluate the impact of known NLRP3 and NLRP1 polymorphisms in the individual susceptibility to asbestos-induced mesothelioma in subjects from a hyperendemic area for MM. METHODS: 134 Italian patients with diagnosis of mesothelioma due (MMAE, n=69) or not (MMAF, n=65) to asbestos, 256 healthy Italian blood donors and 101 Italian healthy subjects exposed to asbestos (HCAE) were genotyped for NLRP1 (rs2670660 and rs12150220) and NLRP3 (rs35829419 and rs10754558) polymorphisms. RESULTS: While NLRP3 SNPs were not associated to mesothelioma, the NLRP1 rs12150220 allele T was significantly more frequent in MMAE (0.55) than in HCAE (0.41) (p=0.011; OR=1.79) suggesting a predisponent effect of this allele on the development of mesothelioma. This effect was amplified when the NLRP1 rs2670660 allele was combined with the NLRP1 rs12150220 allele (p=0.004; OR=0.52). CONCLUSION: Although NLRP3 SNPs was not involved in mesothelioma predisposition, these data proposed NLRP1 as a novel factor possibly involved in the development of mesothelioma.

Oral rehabilitation of children with ectodermal dysplasia. - Montanari, Marco; Callea, Michele; Battelli, Filippo; Piana, Gabriela (BMJ Case Rep, 2012)
The aim of this study was to describe the clinical treatment of young patients, affected by ectodermal dysplasia (ED), and to possibly establish clinical guidelines. The study design was case series. ED syndromes (EDs) are a heterogeneous group of inherited diseases characterised by abnormal development of tissues of ectodermal origin. The most common form of EDs is X linked hypohidrotic ED (HED). Characteristic triad of HED is oligo-anodontia, hypotricosis, hypo-anhydrosis. Oligo-anodontia is one of the most severe impairment, since it affects chewing, swallowing, speech, esthetics and social relation. Early prosthetic rehabilitation (at 2-3 years of age), with partial or complete dentures, is essential to improve oral function and reduce the social impairment.
Keywords: Child; Child, Preschool; Denture, Complete; Denture, Partial; Ectodermal Dysplasia 1, Anhidrotic; Esthetics, Dental; Humans; Male; Mastication; Speech

Pegylated TRAIL retains anti-leukemic cytotoxicity and exhibits improved signal transduction activity with respect to TRAIL. - Gonelli, Arianna; Radillo, Oriano; Drioli, Sara; Rimondi, Erika; Secchiero, Paola; Maria Bonora, Gian (Invest New Drugs, 2012)
To improve the pharmacokinetic profile of tumor necrosis factor-related apoptosis inducing ligand (TRAIL) an N-terminal specific pegylation was performed to generate pegylated TRAIL (PEG-TRAIL). In in vitro experiments, we found that although PEG-TRAIL was slightly less efficient than recombinant TRAIL in promoting leukemic cell apoptosis, it showed an improved ability to promote migration of bone-marrow mesenchymal stem cells and to elicit the ERK1/2 intracellular signal transduction pathway. Overall, these data suggest that TRAIL pegylation retains, or even enhances, the biological activities of TRAIL relevant for its therapeutic applications.
Keywords: Antineoplastic Agents; Apoptosis; Caspase 3; Cell Movement; Dose-Response Relationship, Drug; HL-60 Cells; Humans; Leukemia; Mesenchymal Stromal Cells; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 3; Phosphorylation; Polyethylene Glycols; Recombinant Fusion Proteins; Signal Transduction; Time Factors; TNF-Related Apoptosis-Inducing Ligand

Pelvic inflammatory disease (PID) from Chlamydia trachomatis versus PID from Neisseria gonorrhea: from clinical suspicion to therapy. - De Seta, F; Banco, R; Turrisi, A; Airoud, M; De Leo, R; Stabile, G; Ceccarello, M; Restaino, S; De Santo, D (G Ital Dermatol Venereol, 2012)
Pelvic inflammatory disease (PID) is the most significant complication of sexually transmitted infections in childbearing-age women and it represents an important public health problem because of its long-term sequelae (chronic pelvic pain, tubal infertility, ectopic pregnancy). Prior to the mid 1970s PID was considered a monoetiologic infection, due primarily to Neisseria gonorrhea. Now it is well documented as a polymicrobial process, with a great number of microrganisms involved. In addition to Neisseria gonorrhea and Chlamydia trachomatis, other vaginal microrganisms (anaerobes, Gardnerella vaginalis, Haemophilus influenzae, enteric Gram negative rods, Streptococco agalactie, Mycoplasma genitalium) also have been associated with PID. There is a wide variation in PID clinical features; the type and severity of symptoms vary by microbiologic etiology. Women who have chlamydial PID seem more likely than women who have gonococcal PID to be asymptomatic. Since clinical diagnosis is imprecise, the suspicion of PID should be confirmed by genital assessment for signs of inflammation or infection, blood test and imaging evaluation. Laparoscopic approach is considered the gold standard. According to the polymicrobial etiology of PID, antibiotic treatment must provide broad spectrum coverage of likely pathogens. Early administration of antibiotics is necessary to reduce the risk of long-term sequelae.
Keywords: Chlamydia Infections; Chlamydia trachomatis; Female; Gonorrhea; Humans; Neisseria gonorrhoeae; Pelvic Inflammatory Disease

Peroxidase-like activity of ferruginous bodies isolated by exploiting their magnetic property. - Borelli, Violetta; Trevisan, Elisa; Vita, Francesca; Bottin, Cristina; Melato, Mauro; Rizzardi, Clara; Zabucchi, Giuliano (J Toxicol Environ Health A, 2012)
Ferruginous bodies (FB) are polymorphic structures whose formation is macrophage dependent, and are composed of a core, which may consist of an asbestos fiber coated with proteins, among which ferritin is the main component. Within ferritin, the ferric and ferrous ions are coordinated as ferrihydrite, which is the main iron (Fe) storage compound. However, when ferritin accumulates in some tissues following Fe overload it also contains magnetite along with ferrihydrite, which endows it with magnetic properties. Recently studies showed that magnetite exerts peroxidase-like activity, and since ferruginous bodies display magnetic properties, it was postulated that these particular structures may also contain magnetite within the ferritin coating, and thus may also exert peroxidase-like activity. Histochemical analysis for peroxidase of isolated FB smears demonstrated positive staining. Samples isolated from 4 different autopsy lung fragments were also able to oxidize 3,3',5,5'-tetramethyl-benzidine to a blue colored compound that absorbs at 655 nm. This activity was (1) azide and heat insensitive with optimal pH from 5 to 6, and (2) highly variable, changing more than 25-fold from one sample to another. These findings, together with evidence that the peroxidase-like activity of ferruginous bodies has a hydrogen peroxide and substrate requirement different from that of human myeloperoxidase, can exclude that this enzyme gives a significant contribution to the formation of FB. Standard Fe-rich asbestos fibers also express a peroxidase-like activity, but this appears negligible compared to that of ferruginous bodies. Strong acidification of standard Fe-containing asbestos fibers or magnetically isolated ferruginous bodies liberates a high amount of peroxidase-like activity, which is probably accounted for by the release of Fe ions. Further, FB also damage mesothelial cells in vitro. Data suggest that FB exert peroxidase-like activity and cytotoxic activity against mesothelial cells, and hence may be an important factor in pathogenesis of asbestos-related diseases.
Keywords: Air Pollutants, Occupational; Asbestos; Asbestosis; Benzidines; Catalysis; Cell Line; Chromogenic Compounds; Cytotoxins; Ferric Compounds; Ferritins; Ferrosoferric Oxide; Humans; Hydrogen-Ion Concentration; Lung; Magnetic Phenomena; Mesothelioma; Mineral Fibers; Oxidation-Reduction; Peroxidases; Respiratory Mucosa

Phylloid pattern of hypomelanosis closely related to chromosomal abnormalities in the 13q detected by SNP array analysis. - Faletra, F; Berti, I; Tommasini, A; Pecile, V; Cleva, L; Alberini, E; Bruno, I; Gasparini, P (Dermatology, 2012)
Phylloid hypomelanosis is a distinct type of pigmentary mosaicism characterized by congenital hypochromic macules resembling a floral ornament with various elements such as round or oval patches, asymmetrical macules similar to begonia leaves, or oblong lesions. It has been found to be predominantly associated with abnormalities in chromosome 13 and sometimes as-sociated with different extracutaneous abnormalities. Here, we report 2 new cases of phylloid hypomelanosis due to mosaicism involving chromosome 13. The first one is a mosaicism for a supernumerary marker belonging to chromosome 13 and the second one is the first report of phylloid hypomelanosis associated with a mosaic deletion of 13q. Because of the extremely low level of mosaicism in these 2 cases, SNP array analysis on skin fibroblasts was carried out, showing a 13q21.33-q34 duplication (71,024,411-115,103,529) and a 13q13.3-q34 (38,368,012-115,103,529) deletion. Both cases underline on the one hand the strict connection between phylloid hypomelanosis and anomalies of chromosome 13, and on the other hand the relevance of the SNP array analysis on skin fibroblasts in the detection of low-level mosaicism.
Keywords: Chromosomes, Human, Pair 13; Humans; Hypopigmentation; Male; Mosaicism; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Potential role of TRAIL in the management of autoimmune diabetes mellitus. - Bernardi, Stella; Norcio, Alessia; Toffoli, Barbara; Zauli, Giorgio; Secchiero, Paola (Curr Pharm Des, 2012)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to the immune-mediated destruction of pancreatic β-cells, whose incidence has been steadily increasing during the last decades. Insulin replacement therapy can treat T1DM, which, however, is still associated with substantial morbidity and mortality. For this reason, great effort is being put into developing strategies that could eventually prevent and/or cure this disease. These strategies are mainly focused on blocking the immune system from attacking β-cells together with functional islet restoration either by regeneration or transplantation. Recent experimental evidences suggest that TNFrelated apoptosis-inducing ligand (TRAIL), which is an immune system modulator protein, could represent an interesting candidate for the cure for T1DM and/or its complications. Here we review the evidences on the potential role of TRAIL in the management of T1DM.
Keywords: Animals; Autoimmunity; Diabetes Mellitus, Type 1; Humans; Hypoglycemic Agents; Insulin; Insulin-Secreting Cells; Islets of Langerhans; TNF-Related Apoptosis-Inducing Ligand

A red baby should not be taken too lightly. - Faletra, Flavio; Bruno, Irene; Berti, Irene; Pastore, Serena; Pirrone, Angela; Tommasini, Alberto (Acta Paediatr, 2012)
AIM: To identify clinical and laboratory features that can drive the differential diagnosis of a primary immunodeficiency diseases in patients with ectodermal defects. METHODS: Analysis of selected teaching cases. RESULTS: We identified four exemplary cases that allowed to point out specific clues. CONCLUSIONS: A careful evaluation of immune and ectodermal signs is the key to the diagnosis. Therefore, a multidisciplinary approach can lead to diagnosis and to an appropriate treatment in most of the cases.
Keywords: Child, Preschool; Dermatitis; Ectodermal Dysplasia; Female; Humans; Immunologic Deficiency Syndromes; Infant; Male; Netherton Syndrome; Severe Combined Immunodeficiency; Skin

RICH (rapidly involuting congenital hemangioma): not only a definition of wealth. - Abate, Maria Valentina; Davanzo, Riccardo; Bibalo, Chiara; Zennaro, Floriana; Berti, Irene (J Pediatr, 2012)
Keywords: Female; Hemangioma; Humans; Infant, Newborn; Skin Neoplasms

Sedation with intranasal midazolam of Angolan children undergoing invasive procedures. - Kawanda, Lumana; Capobianco, Ivan; Starc, Meta; Felipe, Daniel; Zanon, Davide; Barbi, Egidio; Munkela, Nadine; Rodrigues, Verónica; Malundo, Lúis; Not, Tarcisio (Acta Paediatr, 2012)
AIM: Ambulatory surgery is a daily requirement in poor countries, and limited means and insufficient trained staff lead to the lack of attention to the patient's pain. Midazolam is a rapid-onset, short-acting benzodiazepine which is used safely to reduce pain in children. We evaluated the practicability of intranasal midazolam sedation in a suburban hospital in Luanda (Angola), during the surgical procedures. METHODS: Intranasal midazolam solution was administered at a dose of 0.5 mg/kg. Using the Ramsay's reactivity score, we gave a score to four different types of children's behaviour: moaning, shouting, crying and struggling, and the surgeon evaluated the ease of completing the surgical procedure using scores from 0 (very easy) to 3 (managing with difficulty). RESULTS: Eighty children (median age, 3 years) were recruited, and 140 surgical procedures were performed. Fifty-two children were treated with midazolam during 85 procedures, and 28 children were not treated during 55 procedures. We found a significant difference between the two groups on the shouting, crying and struggling parameters (p < 0.001). The mean score of the ease of completing the procedures was significantly different among the two groups (p < 0.0001). CONCLUSION: These results provide a model of procedural sedation in ambulatory surgical procedures in poor countries, thus abolishing pain and making the surgeon's job easier.
Keywords: Administration, Intranasal; Adolescent; Ambulatory Surgical Procedures; Angola; Child; Child Behavior; Child, Preschool; Conscious Sedation; Crying; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Prospective Studies

Serum amyloid A and cholesterol: a pivotal role on inflammation. - Tricarico, Paola Maura; Marcuzzi, Annalisa; Zanin, Valentina; Kleiner, Giulio; Bianco, Anna Monica; Crovella, Sergio (Amyloid, 2012)
Keywords: Animals; Humans; Serum Amyloid A Protein

Should cardiac involvement be included in the criteria for diagnosis of Churg Strauss syndrome? - Amaddeo, Alessandro; Ventura, Alessandro; Marchetti, Federico; Benettoni, Alessandra; Londero, Margherita (J Pediatr, 2012)
Keywords: Adolescent; Churg-Strauss Syndrome; Heart Diseases; Humans; Male

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

State of art and recent developments of anti-cancer strategies based on TRAIL. - Bernardi, Stella; Secchiero, Paola; Zauli, Giorgio (Recent Pat Anticancer Drug Discov, 2012)
Multicellular organisms require apoptosis whereby the human body eliminates unnecessary and/or damaged cells. Apoptosis, or programmed cell death, can indeed be considered as a constitutive anti-cancer mechanism that seems to be defective in more than 50% of cancers. Molecular insights on the biology of the apoptotic process have led to the development of new anti-cancer strategies aiming at recovering and stimulating this process. Preclinical and clinical studies of our and other groups have demonstrated that targeting the extrinsic apoptotic pathway by various death receptors agonists is a safe and effective anti-cancer strategy, which thus may become a new cornerstone of cancer therapy. Here, we review the most recent acquisitions and patents on TRAIL or TRAIL mimetics, as well as the combination therapies that could be used with them.
Keywords: Animals; Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Apoptosis; Clinical Trials as Topic; Humans; Mice; Neoplasms; Receptors, Death Domain; TNF-Related Apoptosis-Inducing Ligand

Stem cells in severe infantile spinal muscular atrophy (SMA1). - Carrozzi, Marco; Amaddeo, Alessandro; Biondi, Andrea; Zanus, Caterina; Monti, Fabrizio; Alessandro, Ventura (Neuromuscul Disord, 2012)
Keywords: Humans; Spinal Muscular Atrophies of Childhood; Stem Cell Transplantation; Stem Cells; Treatment Outcome

The submerged dyslexia iceberg: how many school children are not diagnosed? Results from an Italian study. - Barbiero, Chiara; Lonciari, Isabella; Montico, Marcella; Monasta, Lorenzo; Penge, Roberta; Vio, Claudio; Tressoldi, Patrizio Emanuele; Ferluga, Valentina; Bigoni, Anna; Tullio, Alessia; Carrozzi, Marco; Ronfani, Luca (PLoS One, 2012)
BACKGROUND: Although dyslexia is one of the most common neurobehavioral disorders affecting children, prevalence is uncertain and available data are scanty and dated. The objective of this study is to evaluate the prevalence of dyslexia in an unselected school population using clearly defined and rigorous diagnostic criteria and methods. METHODS: Cross sectional study. We selected a random cluster sample of 94 fourth grade elementary school classes of Friuli Venezia Giulia, a Region of North Eastern Italy. We carried out three consecutive levels of screening: the first two at school and the last at the Neuropsychiatry Unit of a third level Mother and Child Hospital. The main outcome measure was the prevalence of dyslexia, defined as the number of children positive to the third level of screening divided by the total number of children enrolled. RESULTS: We recruited 1774 children aged 8-10 years, of which 1528 received parents' consent to participate. After applying exclusion criteria, 1357 pupils constituted the final working sample. The prevalence of dyslexia in the enrolled population ranged from 3.1% (95% CI 2.2-4.1%) to 3.2% (95% CI 2.4-4.3%) depending on different criteria adopted. In two out of three children with dyslexia the disorder had not been previously diagnosed. CONCLUSIONS: This study shows that dyslexia is largely underestimated in Italy and underlines the need for reliable information on prevalence, in order to better allocate resources both to Health Services and Schools.
Keywords: Area Under Curve; Child; Cross-Sectional Studies; Delayed Diagnosis; Dyslexia; Female; Humans; Italy; Male; Neuropsychological Tests; Prevalence; Questionnaires; ROC Curve

Successful induction of oral tolerance in Netherton syndrome. - Pastore, Serena; Gorlato, Gaia; Berti, Irene; Barbi, Egidio; Ventura, Alessandro (Allergol Immunopathol (Madr), 2012)
Keywords: Allergens; Alopecia; Child, Preschool; Desensitization, Immunologic; Disease-Free Survival; Eczema; Female; Food Hypersensitivity; Hair Follicle; Humans; Immune Tolerance; Immunoglobulin E; Infant, Newborn; Mouth; Netherton Syndrome; Treatment Outcome

TNF-related apoptosis-inducing ligand significantly attenuates metabolic abnormalities in high-fat-fed mice reducing adiposity and systemic inflammation. - Bernardi, Stella; Zauli, Giorgio; Tikellis, Christos; Candido, Riccardo; Fabris, Bruno; Secchiero, Paola; Cooper, Mark E; Thomas, Merlin C (Clin Sci (Lond), 2012)
TRAIL [TNF (tumour necrosis factor)-related apoptosis-inducing ligand] has recently been shown to ameliorate the natural history of DM (diabetes mellitus). It has not been determined yet whether systemic TRAIL delivery would prevent the metabolic abnormalities due to an HFD [HF (high-fat) diet]. For this purpose, 27 male C57bl6 mice aged 8 weeks were randomly fed on a standard diet, HFD or HFD+TRAIL for 12 weeks. TRAIL was delivered weekly by intraperitoneal injection. Body composition was evaluated; indirect calorimetry studies, GTT (glucose tolerance test) and ITT (insulin tolerance test) were performed. Pro-inflammatory cytokines, together with adipose tissue gene expression and apoptosis, were measured. TRAIL treatment reduced significantly the increased adiposity associated with an HFD. Moreover, it reduced significantly hyperglycaemia and hyperinsulinaemia during a GTT and it improved significantly the peripheral response to insulin. TRAIL reversed the changes in substrate utilization induced by the HFD and ameliorated skeletal muscle non-esterified fatty acids oxidation rate. This was associated with a significant reduction of pro-inflammatory cytokines together with a modulation of adipose tissue gene expression and apoptosis. These findings shed light on the possible anti-adipogenic and anti-inflammatory effects of TRAIL and open new therapeutic possibilities against obesity, systemic inflammation and T2DM (Type 2 DM).
Keywords: Adiposity; Animals; Apoptosis; Calorimetry; Cytokines; Dietary Fats; Energy Intake; Glucose Tolerance Test; Hyperglycemia; Hyperinsulinism; Inflammation; Inflammation Mediators; Male; Mice; Mice, Inbred C57BL; Oxidation-Reduction; Palmitic Acid; Real-Time Polymerase Chain Reaction; TNF-Related Apoptosis-Inducing Ligand

TRAIL as biomarker and potential therapeutic tool for cardiovascular diseases. - Bernardi, Stella; Milani, Daniela; Fabris, Bruno; Secchiero, Paola; Zauli, Giorgio (Curr Drug Targets, 2012)
This review focuses on TNF-related apoptosis-inducing ligand (TRAIL), also called Apo2 ligand, a protein belonging to the TNF superfamily. TRAIL can be found either in its transmembrane or circulating form, and its mostly studied peripheral effect is the induction of cellular apoptosis. Here, we discuss the evidences supporting the use of TRAIL as biomarker of cardiovascular diseases as well as the evidences showing the potential beneficial therapeutic effects of TRAIL on cardiovascular diseases and diabetes.
Keywords: Biological Markers; Cardiovascular Diseases; Humans; Prognosis; TNF-Related Apoptosis-Inducing Ligand

TRAIL shows potential cardioprotective activity. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Zacchigna, Serena; Fabris, Bruno; Secchiero, Paola (Invest New Drugs, 2012)
Recent clinical trials carried out in patients with advanced cancer have shown that recombinant TRAIL administration is usually safe and well tolerated when used either alone or in association with chemotherapeutic drugs. Notably, anticancer chemotherapy can be associated to cardiomiopathy. We have here demonstrated that TRAIL (administrated as either recombinant soluble TRAIL or as AAV-TRAIL expression viral vector) reduced the development of cardiomyopathy in the ApoE(-/-) diabetic mouse model. These data suggest, for the first time, that therapeutically administration of TRAIL might have a cardioprotective effect.
Keywords: Animals; Apolipoproteins E; Apoptosis; Cardiotonic Agents; Diabetes Mellitus, Experimental; Diabetes Mellitus, Type 1; Diabetic Cardiomyopathies; Fibrosis; Male; Mice; Mice, Knockout; Recombinant Proteins; TNF-Related Apoptosis-Inducing Ligand

Treatment with pamidronate for osteoporosis complicating long-term intestinal failure. - Pastore, S; Londero, M; Barbieri, F; Di Leo, G; Paparazzo, R; Ventura, A (J Pediatr Gastroenterol Nutr, 2012)
Long-term home parenteral nutrition (PN) is a potential risk for developing osteoporosis. Various attempts have been made to treat bone disease both by modifying the composition of PN and by administering hormones, such as calcitonin, parathyroid hormone, and sexual hormones. Bisphosphonates are recognized as a medication useful for the treatment of several bone disorders associated with excessive reabsorption. Nevertheless, there have been no paediatric studies on bisphosphonates use for intestinal failure-associated bone disease. Our study includes 6 paediatric patients receiving extremely long-term home PN (at least 3 years) who showed radiological and clinical signs of osteoporosis. Diagnosis of bone disease was made after a median period of 127.5 PN months. Treatment consisted in 2 cycles of intravenous pamidronate, 30 mg/m once per month for 6 months consecutively. They all showed a significant improvement in bone mineral density, evaluated after 6 and 12 months of pamidronate treatment. In our sample anthropometrical variables (weight, height, and body mass index) are not related with the z-score trend. Our patients had normal levels of calcium, phosphorus, and vitamin D, and proper nutrient intake. At the last follow-up, dual-energy x-ray absorptiometry scan showed that no patients had a z-score lower than -2.5; moreover, nobody developed bone fractures during the 108-month follow-up. The patients did not have any prominent adverse effect. Finally, in our experience, pamidronate is effective for improving bone mineral density and safe in patients with intestinal failure-associated bone disease.
Keywords: Absorptiometry, Photon; Adolescent; Bone Density; Bone Density Conservation Agents; Child; Child, Preschool; Diphosphonates; Female; Humans; Intestinal Diseases; Male; Osteoporosis; Parenteral Nutrition, Home

Videogame playing as distraction technique in course of venipuncture. - Minute, M; Badina, L; Cont, G; Montico, M; Ronfani, L; Barbi, E; Ventura, A (Pediatr Med Chir, 2012)
BACKGROUND: Needle-related procedures (venipuncture, intravenous cannulation) are the most common source of pain and distress for children. Reducing needle related pain and anxiety could be important in order to prevent further distress, especially for children needing multiple hospital admissions. The aim of the present open randomized controlled trial was to investigate the efficacy of adding an active distraction strategy (videogame) to EMLA premedication in needle-related pain in children. METHODS: One-hundred and nine children (4 -10 years of age) were prospectively recruited to enter in the study. Ninety-seven were randomized in two groups: CC group (conventional care: EMLA only) as control group and AD group (active distraction: EMLA plus videogame) as intervention group. Outcome measures were: self-reported pain by mean of FPS-R scale (main study outcome), observer-reported pain by FLACC scale, number of attempts for successful procedure. RESULTS: In both groups FPS-R median rate was 0 (interquartile range: 0-2), with significant pain (FPS-R > 4) reported by 9% of subjects. FLACC median rate was 1 in both groups (interquartile range 0-3 in CC group; 0-2 in AD group). The percentage of children with major pain (FLACC > 4) was 18% in CC group and 9% in AD group (p = 0.2). The median of necessary attempts to succeed in the procedures was 1 (interquartile range 1-2) in both groups.. CONCLUSION: Active distraction doesn't improve EMLA analgesia for iv cannulation and venipuncture. Even though, it resulted in an easily applicable strategy appreciated by children. This technique could be usefully investigated in other painful procedures.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Humans; Lidocaine; Male; Pain; Phlebotomy; Prilocaine; Prospective Studies; Video Games

Young girl with apical ballooning heart syndrome. - Berton, E; Vitali-Serdoz, L; Vallon, P; Maschio, M; Gortani, G; Benettoni, A (Int J Cardiol, 2012)
Keywords: Child; Diagnosis, Differential; Electrocardiography; Female; Humans; Takotsubo Cardiomyopathy

Β-hexosaminidase over-expression affects lysosomal glycohydrolases expression and glycosphingolipid metabolism in mammalian cells. - Tancini, Brunella; Magini, Alessandro; Bortot, Barbara; Polchi, Alice; Urbanelli, Lorena; Sonnino, Sandro; Severini, Giovanni Maria; Emiliani, Carla (Mol Cell Biochem, 2012)
Lysosomes are not only degrading organelles but also involved in other critical cellular processes. In addition, active lysosomal glycohydrolases have been detected in an extra-lysosomal compartment: the presence of glycohydrolases on the plasma membrane (PM) has been widely demonstrated, and a possible role on the modification of the cell surface glycosphingolipids (GSL) participating in the modulation of cell functions such as cell-to-cell interactions and signal transduction pathways has been proposed. On this basis, the coordinated expression of lysosomal glycohydrolases and their translocation to the PM appear to be crucial for many cellular events. In this paper, we report evidence for the existence of a coordinated mechanism regulating the expression/activity of both lysosomal and PM-associated glycohydrolases. We show that the over-expression of the acidic glycohydrolase β-hexosaminidase α-subunit in mouse NIH/3T3 fibroblasts induces the increased expression of the Hex β-subunit necessary to form the active isoenzyme dimers as well as of other glycohydrolases participating in the GSL catabolism, such as β-galactosidase and β-glucocerebrosidase. More interestingly, this regulatory effect was also extended to the PM-associated hydrolases. In addition, transfected cells displayed a rearrangement of the GSL expression pattern that cannot be simply explained by the increased activity of a single enzyme. These observations clearly indicate that the expression level of metabolically related glycohydrolases is regulated in a coordinated manner and this regulation mechanism also involves the PM-associated isoforms.
Keywords: Animals; beta-Hexosaminidase alpha Chain; Cell Membrane; Exocytosis; Fibroblasts; Glycoside Hydrolases; Glycosphingolipids; Humans; Lysosomes; Mice; NIH 3T3 Cells; Transfection

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Association of tumor necrosis factor-related apoptosis-inducing ligand with total and cardiovascular mortality in older adults. - Volpato, Stefano; Ferrucci, Luigi; Secchiero, Paola; Corallini, Federica; Zuliani, Giovanni; Fellin, Renato; Guralnik, Jack M; Bandinelli, Stefania; Zauli, Giorgio (Atherosclerosis, 2011)
OBJECTIVE: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits biological activity on vascular cells in vitro. Rapid variation of circulating TRAIL levels occurs during acute coronary ischemia, suggesting that biological pathways involving TRAIL may be activated during ischemic heart disease. However, whether differential levels of soluble TRAIL in normal individuals are associated with adverse health outcomes has not been investigated. We tested the hypothesis that TRAIL levels predict mortality in a population based sample of community dwelling men and women. METHODS: Plasma TRAIL level was measured by ELISA at baseline in 1282 adults (mean age 68 years) enrolled in the InCHIANTI study. Vital status was ascertained over the six-year follow-up. RESULTS: In multivariable Cox regression analysis adjusted for potential confounders including prevalent cardiovascular diseases (CVD), ankle-brachial index, electrocardiogram abnormalities, and inflammatory markers, baseline TRAIL levels were inversely related to all-cause mortality (p=0.008). In stratified analyses, the prognostic effect of TRAIL level was strong and highly significant in participants with prevalent CVD (N=321), (lowest versus highest quartile: HR 3.1; 95% CI 1.5-6.5) while it was negligible in those free of CVD (p value for the interaction term between CVD status and TRAIL levels=0.038). Similar findings were obtained when CVD mortality was considered as the outcome of interest. CONCLUSIONS: In older patients with CVD, low levels of TRAIL were associated with increased risk of death over a period of 6 years. Lower concentration of circulating TRAIL may be related to the clinical evolution of older adults with CVD.
Keywords: Adult; Aged; Ankle Brachial Index; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Italy; Male; Middle Aged; TNF-Related Apoptosis-Inducing Ligand

Circulating TRAIL shows a significant post-partum decline associated to stressful conditions. - Zauli, Giorgio; Monasta, Lorenzo; Rimondi, Erika; Vecchi Brumatti, Liza; Radillo, Oriano; Ronfani, Luca; Montico, Marcella; D'Ottavio, Giuseppina; Alberico, Salvatore; Secchiero, Paola (PLoS One, 2011)
BACKGROUND: Since circulating levels of TNF-related apoptosis inducing ligand (TRAIL) may be important in the physiopathology of pregnancy, we tested the hypothesis that TRAIL levels change at delivery in response to stressful conditions. METHODS/PRINCIPAL FINDINGS: We conducted a longitudinal study in a cohort of 73 women examined at week 12, week 16, delivery and in the corresponding cord blood (CB). Serum TRAIL was assessed in relationship with maternal characteristics and to biochemical parameters. TRAIL did not vary between 12 (67.6±27.6 pg/ml, means±SD) and 16 (64.0±16.2 pg/ml) weeks' gestation, while displaying a significant decline after partum (49.3±26.4 pg/ml). Using a cut-off decline >20 pg/ml between week 12 and delivery, the subset of women with the higher decline of circulating TRAIL (41.7%) showed the following characteristics: i) nullipara, ii) higher age, iii) operational vaginal delivery or urgent CS, iv) did not receive analgesia during labor, v) induced labor. CB TRAIL was significantly higher (131.6±52 pg/ml) with respect to the corresponding maternal TRAIL, and the variables significantly associated with the first quartile of CB TRAIL (<90 pg/ml) were higher pre-pregnancy BMI, induction of labor and fetal distress. With respect to the biochemical parameters, maternal TRAIL at delivery showed an inverse correlation with C-reactive protein (CRP), total cortisol, glycemia and insulin at bivariate analysis, but only with CRP at multivariate analysis. CONCLUSIONS: Stressful partum conditions and elevated CRP levels are associated with a decrease of circulating TRAIL.
Keywords: Adult; Biological Markers; C-Reactive Protein; Female; Fetal Blood; Fetal Distress; Humans; Labor, Obstetric; Logistic Models; Multivariate Analysis; Postpartum Period; Pregnancy; Pregnancy Outcome; Statistics, Nonparametric; Stress, Physiological; TNF-Related Apoptosis-Inducing Ligand

Clinical and genetic aspects of Bernard-Soulier syndrome: searching for genotype/phenotype correlations. - Savoia, Anna; Pastore, Annalisa; De Rocco, Daniela; Civaschi, Elisa; Di Stazio, Mariateresa; Bottega, Roberta; Melazzini, Federica; Bozzi, Valeria; Pecci, Alessandro; Magrin, Silvana; Balduini, Carlo L; Noris, Patrizia (Haematologica, 2011)
BACKGROUND: Bernard-Soulier syndrome is a severe bleeding disease due to a defect of GPIb/IX/V, a platelet complex that binds the von Willebrand factor. Due to the rarity of the disease, there are reports only on a few cases compromising any attempt to establish correlations between genotype and phenotype. In order to identify any associations, we describe the largest case series ever reported, which was evaluated systematically at the same center. DESIGN AND METHODS: Thirteen patients with the disease and seven obligate carriers were enrolled. We collected clinical aspects and determined platelet features, including number and size, expression of membrane glycoproteins, and ristocetin induced platelet aggregation. Mutations were identified by direct sequencing of the GP1BA, GP1BB, and GP9 genes and their effect was shown by molecular modeling analyses. RESULTS: Patients all had a moderate thrombocytopenia with giant platelets and a bleeding tendency whose severity varied among individuals. Consistent with expression levels of GPIbα always lower than 10% of control values, platelet aggregation was absent or severely reduced. Homozygous mutations were identified in the GP1BA, GP1BB and GP9 genes; six were novel alterations expected to destabilize the conformation of the respective protein. Except for obligate carriers of a GP9 mutation with a reduced GPIb/IX/V expression and defective aggregation, all the other carriers had no obvious anomalies. CONCLUSIONS: Regardless of mutations identified, the patients' bleeding diathesis did not correlate with thrombocytopenia, which was always moderate, and platelet GPIbα expression, which was always severely impaired. Obligate carriers had features similar to controls though their GPIb/IX/V expression showed discrepancies. Aware of the limitations of our cohort, we cannot define any correlations. However, further investigations should be encouraged to better understand the causes of this rare and underestimated disease.
Keywords: Adolescent; Adult; Amino Acid Sequence; Bernard-Soulier Syndrome; Blood Platelets; Cell Shape; Child; Child, Preschool; Female; Genetic Association Studies; Genetic Markers; Hemorrhage; Homozygote; Humans; Italy; Male; Membrane Glycoproteins; Middle Aged; Molecular Sequence Data; Platelet Aggregation; Platelet Count; Platelet Glycoprotein GPIb-IX Complex; Point Mutation; Polymerase Chain Reaction; Ristocetin; Thrombocytopenia; von Willebrand Factor; Young Adult

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Comparison of propofol versus propofol-ketamine combination in pediatric oncologic procedures performed by non-anesthesiologists. - Chiaretti, Antonio; Ruggiero, Antonio; Barbi, Egidio; Pierri, Filomena; Maurizi, Palma; Fantacci, Claudia; Bersani, Giulia; Riccardi, Riccardo (Pediatr Blood Cancer, 2011)
BACKGROUND: Limited data are available on the best option (short acting sedatives, opioids, or ketamine) in oncologic procedural sedation performed by non-anesthesiologists. The aim of the present prospective study is to compare the safety and efficacy of propofol-ketamine versus propofol alone, managed by trained pediatricians, in children with cancer undergoing painful procedures. PROCEDURES: Data on 121 children with acute lymphatic leukemia (ALL) undergoing procedural sedations (lumbar punctures and bone marrow aspirations) were prospectively collected and included drug doses, side effects, pain assessment, and sedation degree. Children were randomly assigned to one of the two groups: P (n = 62) receiving propofol alone and K (n = 59) in whom a ketamine-propofol combination was used. RESULTS: In group K, the total dose of propofol required was significantly lower than in group P (3.9 ± 3.6 mg/kg vs. 5.1 ± 3.6 mg/kg; P < 0.001). The incidence of hypotension was also significantly lower (11% vs. 39%; P < 0.001). Major O(2) desaturations (defined as SatO(2) < 88%) occurred principally in group P (7 vs. 1; P = 0.05). Both best analgesia and shorter recovery time were obtained with the propofol-ketamine association. No differences were observed in the degree of sedation and in the awakening quality score between the two groups. CONCLUSIONS: The combination of propofol and ketamine produced statistically significant clinical advantages combined with a higher profile of safety in children with cancer undergoing painful procedures.
Keywords: Biopsy, Needle; Bone Marrow Examination; Child; Conscious Sedation; Female; Humans; Hypnotics and Sedatives; Ketamine; Male; Neoplasms; Pediatrics; Physicians; Propofol; Spinal Puncture

Compliance with the gluten-free diet: the role of locus of control in celiac disease. - Bellini, Anna; Zanchi, Chiara; Martelossi, Stefano; Di Leo, Grazia; Not, Tarcisio; Ventura, Alessandro (J Pediatr, 2011)
OBJECTIVES: To verify whether subjects with celiac disease (CD) have a different locus of control (LoC) compared with healthy subjects, and to evaluate the relationship between LoC and compliance with a prescribed gluten-free diet (GFD) and quality of life (QoL). STUDY DESIGN: We studied 156 subjects on a GFD (mean age, 10 years) and 353 healthy controls (mean age, 12 years). All subjects completed tests on the Nowicki-Strickland Locus of Control Scale; the subjects with CD also completed a questionnaire to measure compliance with dietary treatment and the disease's impact on QoL. RESULTS: There was no difference in LoC values between patients with CD and controls. Subjects with CD with good dietary compliance had a more internal LoC compared with those who were not compliant (P = .01). Patients who reported a satisfactory QoL had a more internal LoC compared with those who reported negative affects on QoL due to CD (P = .01). CONCLUSIONS: Our study confirms the usefulness of the LoC concept for identifying those patients who might be at risk for dietary transgression. Given the enhanced, psychological, and social well being that can result from adherence to a GFD, educational and psychological support can help internalize the LoC in those patients at risk for dietary transgression.
Keywords: Adolescent; Age Factors; Case-Control Studies; Celiac Disease; Child; Diet, Gluten-Free; Female; Humans; Internal-External Control; Italy; Male; Patient Compliance; Quality of Life

Concentrated midazolam for intranasal administration: a pilot study. - Calligaris, Lorenzo; Davide, Zanon; Alessandra, Maestro; De Bortoli, Romina; Chiaretti, Antonio; Barbi, Egidio (Pediatr Emerg Care, 2011)
Keywords: Administration, Intranasal; Child; Child, Preschool; Conscious Sedation; Dose-Response Relationship, Drug; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Pain; Pilot Projects; Preoperative Care

Cryptic genetic gluten intolerance revealed by intestinal antitransglutaminase antibodies and response to gluten-free diet. - Not, Tarcisio; Ziberna, Fabiana; Vatta, Serena; Quaglia, Sara; Martelossi, Stefano; Villanacci, Vincenzo; Marzari, Roberto; Florian, Fiorella; Vecchiet, Monica; Sulic, Ana-Marija; Ferrara, Fortunato; Bradbury, Andrew; et al. (Gut, 2011)
BACKGROUND AND OBJECTIVE: Antitransglutaminase (anti-TG2) antibodies are synthesised in the intestine and their presence seems predictive of future coeliac disease (CD). This study investigates whether mucosal antibodies represent an early stage of gluten intolerance even in the absence of intestinal damage and serum anti-TG2 antibodies. METHODS: This study investigated 22 relatives of patients with CD genetically predisposed to gluten intolerance but negative for both serum anti-TG2 antibodies and intestinal abnormalities. Fifteen subjects were symptomatic and seven were asymptomatic. The presence of immunoglobulin A anti-TG2 antibodies in the intestine was studied by creating phage-antibody libraries against TG-2. The presence of intestinal anti-TG2 antibodies was compared with the serum concentration of the intestinal fatty acid-binding protein (I-FABP), a marker for early intestinal mucosal damage. The effects of a 12-month gluten-free diet on anti-TG2 antibody production and the subjects' clinical condition was monitored. Twelve subjects entered the study as controls. RESULTS: The intestinal mucosa appeared normal in 18/22; 4 had a slight increase in intraepithelial lymphocytes. Mucosal anti-TG2 antibodies were isolated in 15/22 subjects (68%); in particular symptomatic subjects were positive in 13/15 cases and asymptomatic subjects in 2/7 cases (p=0.01). No mucosal antibodies were selected from the controls' biopsies. There was significant correlation between the presence of intestinal anti-TG2 antibodies and positive concentrations of I-FABP (p=0.0008). After a gluten-free diet, 19/22 subjects underwent a second intestinal biopsy, which showed that anti-TG2 antibodies had disappeared in 12/15 (p=0.002), while I-FABP decreased significantly (p<0.0001). The diet resolved both extraintestinal and intestinal symptoms. CONCLUSIONS: A new form of genetic-dependent gluten intolerance has been described in which none of the usual diagnostic markers is present. Symptoms and intestinal anti-TG2 antibodies respond to a gluten free-diet. The detection of intestinal anti-TG2 antibodies by the phage-antibody libraries has an important diagnostic and therapeutic impact for the subjects with gluten-dependent intestinal or extraintestinal symptoms. Clinical trial number NCT00677495.
Keywords: Adolescent; Adult; Antibodies, Anti-Idiotypic; Asymptomatic Diseases; Celiac Disease; Child; Child, Preschool; Diet, Gluten-Free; Fatty Acid-Binding Proteins; Female; Genetic Predisposition to Disease; GTP-Binding Proteins; Health Status; Humans; Intestinal Mucosa; Male; Middle Aged; Peptide Library; Transglutaminases; Young Adult

Daily practice of mechanical ventilation in Italian pediatric intensive care units: a prospective survey. - Wolfler, Andrea; Calderoni, Edoardo; Ottonello, Giancarlo; Conti, Giorgio; Baroncini, Simonetta; Santuz, Pierantonio; Vitale, Pasquale; Salvo, Ida (Pediatr Crit Care Med, 2011)
OBJECTIVES: To assess how children requiring endotracheal intubation are mechanically ventilated in Italian pediatric intensive care units (PICUs). DESIGN: A prospective, national, observational, multicenter, 6-month study. SETTING: Eighteen medical-surgical PICUs. PATIENTS: A total of 1943 consecutive children, aged 0-16 yrs, admitted between November 1, 2006 and April 30, 2007. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Data on cause of respiratory failure, length of mechanical ventilation (MV), mode of ventilation, use of specific interventions were recorded for all children requiring endotracheal intubation for >24 hrs. Children were stratified for age, type of patient, and cause of respiratory failure. A total of 956 (49.2%) patients required MV via an endotracheal tube; 673 (34.6%) were ventilated for >24 hrs. The median length of MV was 4.5 days for all patients. If postoperative patients were excluded, the median time was 5 days. Bronchiolitis (6.7%), pneumonia (6.7%), and upper airway obstruction (5.3%) were the most frequent causes of acute respiratory failure, and altered mental status (9.2%) was the most frequent reason for MV. The overall mortality was 6.7% with highest rates for heart disease (nonoperative), sepsis, and acute respiratory distress syndrome (26.1%, 22.2%, and 16.7% respectively). Length of stay, associated chronic disease, severity score on admission, and PICU mortality were significantly higher in children who received MV (p < .05) than in children who did not. Controlled MV and pressure support ventilation + synchronized intermittent mandatory ventilation were the most frequently used modes of ventilatory assistance during PICU stay. CONCLUSIONS: Mechanical ventilation is frequently used in Italian PICUs with almost one child of two requiring endotracheal intubation. Children treated with MV represent a more severe category of patients than children who are breathing spontaneously. Describing the standard care and how MV is performed in children can be useful for future clinical studies.
Keywords: Adolescent; Child; Child, Preschool; Clinical Protocols; Female; Humans; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Intubation, Intratracheal; Italy; Male; Prospective Studies; Respiration, Artificial; Respiratory Insufficiency

Dasatinib plus Nutlin-3 shows synergistic antileukemic activity in both p53 wild-type and p53 mutated B chronic lymphocytic leukemias by inhibiting the Akt pathway. - Zauli, Giorgio; Voltan, Rebecca; Bosco, Raffaella; Melloni, Elisabetta; Marmiroli, Sandra; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To analyze the effect of the combination of Dasatinib, a multikinase inhibitor, plus Nutlin-3, a nongenotoxic activator of the p53 pathway, in primary B chronic lymphocytic leukemia (B-CLL) patient samples and B leukemic cell line models. EXPERIMENTAL DESIGN: The induction of cytotoxicity was evaluated in both primary B-CLL cell samples (n = 20) and in p53(wild-type) (EHEB, JVM-2) and p53(deleted/mutated) (MEC-2, BJAB) B leukemic cell lines. The role of Akt in modulating leukemic cell survival/apoptosis in response to Dasatinib or Dasatinib + Nutlin-3 was documented by functional experiments carried out using specific pharmacological inhibitors and by overexpression of membrane-targeted constitutively active form of Akt. RESULTS: The combination of Dasatinib + Nutlin-3 exhibited a synergistic cytotoxicity in the majority (19 out of 20) of B-CLL samples, including patients carrying 17p- (n = 4), and in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. At the molecular level, Dasatinib significantly counteracted the Nutlin-3-mediated induction of the p53 transcriptional targets MDM2 and p21 observed in p53(wild-type) leukemic cells. Conversely, Nutlin-3 did not interfere with the ability of Dasatinib to decrease the phosphorylation levels of ERK1/2, p38/MAPK, and Akt in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. A critical role of Akt downregulation in mediating the antileukemic activity of Dasatinib and Dasatinib + Nutlin-3 was demonstrated in experiments carried out by specifically modulating the Akt pathway. CONCLUSIONS: These findings suggest that Dasatinib + Nutlin-3 might represent an innovative therapeutic combination for both p53(wild-type) and p53(deleted/mutated) B-CLL.
Keywords: Antineoplastic Agents; Apoptosis; Cell Line, Tumor; Cell Survival; Down-Regulation; Drug Synergism; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Mutation; Piperazines; Protein Kinase Inhibitors; Protein Kinases; Proto-Oncogene Proteins c-akt; Pyrimidines; Thiazoles; Transcription, Genetic; Tumor Suppressor Protein p53

Diagnosis and treatment of pediatric chronic osteomyelitis in developing countries: prospective study of 96 patients treated in Kenya. - Mantero, E; Carbone, M; Calevo, M G; Boero, S (Musculoskelet Surg, 2011)
The authors carried out a prospective study on 96 patients they treated in Kenya for chronic osteomyelitis from 2000 to 2009. All the patients received orthopedic surgery and antibiotic therapy, when possible based on the antibiotic sensitivity test. Among the 90 patients with at least 12 months' follow-up, 11 had osteomyelitis relapse (12.2%) and recovery rate was therefore 87.8% with no resulting disability. Risk factors for osteomyelitis relapse were investigated and previous treatment with beta-lactamines, predisposing to onset of methycillin-resistant Staphylococcus aureus (MRSA) infections (P = 0.03, OR = 5.74), and onset of osteomyelitis in the metaepiphyseal region (P < 0.0001) resulted statistically significant. Aim of the study was to evaluate the validity of our treatment of chronic osteomyelitis in Kenya on the basis of outcome.
Keywords: Adolescent; Algorithms; Anti-Bacterial Agents; Child; Chronic Disease; Developing Countries; Female; Follow-Up Studies; Humans; Kenya; Male; Methicillin-Resistant Staphylococcus aureus; Microbial Sensitivity Tests; Osteomyelitis; Prospective Studies; Recurrence; Reproducibility of Results; Risk Factors; Staphylococcal Infections; Treatment Outcome

Echocardiographic detection of early myocardial calcification in acute neonatal myocarditis due to Coxsackie virus type B. - Benettoni, Alessandra; Berton, Emanuela (Pediatr Cardiol, 2011)
Keywords: Coronary Vessels; Electrocardiography; Humans; Male; Myocardial Infarction; Myocarditis

Endothelial progenitor cells, bronchopulmonary dysplasia and other short-term outcomes of extremely preterm birth. - Paviotti, Giulia; Fadini, Gian Paolo; Boscaro, Elisa; Agostini, Carlo; Avogaro, Angelo; Chiandetti, Lino; Baraldi, Eugenio; Filippone, Marco (Early Hum Dev, 2011)
AIM: To evaluate the impact of endothelial progenitor cells (EPCs), a subset of committed circulatory stem cells, on the development of bronchopulmonary dysplasia (BPD) and other short term outcomes in a cohort of extremely premature newborns. METHODS: Progenitor cells were quantified by flow cytometry at birth in 36 neonates born <=28 weeks of gestation and at 36 postmenstrual weeks in 18 of them. Cells expressing the stemness markers CD34, CD133, or both were defined as circulating progenitor cells (CPCs). EPCs were defined as CPCs co-expressing the endothelial marker KDR. RESULTS: Mean (SD) gestational age and birth weight of the infants studied were 26.2(1.5) weeks and 761.6(171.8) grams, respectively. EPC levels at birth did not differ between infants who subsequently developed BPD (n=9) and those who did not (n=24) [CD34(+)KDR(+) EPCs: 81(34-41) vs 80(56-110), p=0.7] and were not correlated with the duration of mechanical ventilation or O2-dependence, nor with the need of surfactant replacement. Infants with a hemodynamically significant patent ductus arteriosus (PDA) (n=22) had significantly lower EPC levels at birth than those with no PDA (n=11) [CD34(+)KDR(+) cells: 47(34-92) vs 142(84.5-221), p=0.008]. Data from the 18 infants studied both at birth and at 36 postmenstrual weeks showed that, while CPCs sharply decline over time, levels of all EPCs phenotypes are preserved after delivery. CONCLUSIONS: Levels of EPCs at birth did not affect the risk of developing BPD in our group of extremely premature neonates. However, the association between low EPC counts at birth and PDA may be clinically relevant, and deserves further studies.
Keywords: Blood Cell Count; Bronchopulmonary Dysplasia; Cohort Studies; Ductus Arteriosus, Patent; Endothelial Cells; Female; Flow Cytometry; Humans; Infant, Newborn; Infant, Premature; Italy; Pregnancy; Prospective Studies; Regression Analysis; Stem Cells

Epidemiological and molecular assessment of a measles outbreak in a highly vaccinated population of northeast Italy. - D'Agaro, P; Molin, G Dal; Gallo, T; Rossi, T; Santon, D; Busetti, M; Comar, M; Campello, C (Epidemiol Infect, 2011)
Two distinct measles outbreaks, unrelated from the epidemiological point of view but caused by genetically related strains, occurred in the Friuli Venezia Giulia region of northeastern Italy. Forty-two cases were reported during the period April-May 2008. In the first outbreak the index case was a teacher who introduced the virus into the Pordenone area, involving eight adolescents and young adults. The other concomitant outbreak occurred in the city of Trieste with 33 cases. The containment of the epidemics can be explained by the high MMR vaccine coverage in an area where the first dose was delivered to 93·4% and the second dose to 88·3% of the target children. Phylogenetic analysis of 14 measles virus strains showed that they belonged to a unique D4 genotype indistinguishable from the MVs/Enfield.GBR/14.07 strain, probably introduced from areas (i.e. Piedmont and Germany) where this genotype was present or had recently caused a large epidemic.
Keywords: Adolescent; Adult; Chi-Square Distribution; Child; Child, Preschool; Community-Acquired Infections; Disease Outbreaks; Female; Humans; Immunization Schedule; Infant; Italy; Male; Measles; Measles Vaccine; Measles virus; Middle Aged; Molecular Epidemiology; Phylogeny

Fine tuning of protein kinase C (PKC) isoforms in cancer: shortening the distance from the laboratory to the bedside. - Bosco, R; Melloni, E; Celeghini, C; Rimondi, E; Vaccarezza, M; Zauli, G (Mini Rev Med Chem, 2011)
The serine/threonine protein kinase C (PKC) family was first identified as intracellular receptor(s) for the tumor promoting agents phorbol esters. Thirty years after the discovery of PKC, the role of specific PKC isoforms has been described in relationship with an altered pattern of expression in different types of cancer and a good number of small molecule inhibitors (inhibitory peptides, antisense oligonucleotides or natural compounds) targeting PKC are now available. Despite all these achievements and a huge amount of basic research studies on the biochemical regulation of PKC, there has been a delay in clinical trials with drugs targeting PKC function. This delay is easily explained taking into account the extreme biological complexity of the PKC family of isoforms and the incomplete understanding of the specific role of each PKC isozyme in different types of cancers. Some of the difficulties in developing pharmacological compounds selectively tuning the different PKCs have started to be overcome. In this review, the growing evidences of the role of the PKC isoforms α, βII, δ, ε, ζ and ι is in promoting or counteracting tumor progression will be discussed in relationship with promising therapeutic perspectives.
Keywords: Antineoplastic Agents; Biological Products; Enzyme Inhibitors; Humans; Isoenzymes; Neoplasms; Oligonucleotides, Antisense; Peptides; Protein Kinase C

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Frequency distribution of HLA DQ2 and DQ8 in celiac patients and first-degree relatives in Recife, northeastern Brazil. - Castro-Antunes, Margarida Maria; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Guimarães, Rafael Lima; Motta, Maria Eugênia Farias Almeida; Silva, Giselia Alves Pontes da (Clinics (Sao Paulo), 2011)
AIMS: The aim of this study was to evaluate the frequencies of the HLA genotypes DQ2 and DQ8 and the alleles A1*05, A1*0201, B1*0201 and B1*0302 in individuals with celiac disease in Recife, northeastern Brazil. METHODS: HLA DQ2 and DQ8 genotyping was performed for 73 individuals with celiac disease and 126 first-degree relatives with negative transglutaminase serology. The alleles DQA1*05, DQA1*0201, DQB1*02 and DQB1*0302 were identified by sequencing using specific primers and the EU-DQ kit from the Eurospital Laboratory, Trieste, Italy and double-checked by the All Set SPP kit (Dynal). RESULTS: Among the 73 cases, 50 (68.5%) had the genotype DQ2, 13 (17.8%) had DQ8, 5 (6.8%) had DQ2 and DQ8, and 5 did not have any of these genotypes. Among the 5 negative individuals, four had the B1*02 allele and one did not have any of the alleles studied. B1*02 was the most frequent allele in both groups (94% in the patients and 89% in the control relatives). CONCLUSIONS: In this study, celiac disease was associated with the genotypes DQ2 and DQ8. DQ2 predominated, but the distribution of the frequencies was different from what has been found in European populations and was closer to what has been found in the Americas. The high frequencies of the HLA genotypes DQ2 and DQ8 that were found in first-degree relatives would make it difficult to use these HLA genotypes for routine diagnosis of celiac disease in this group.
Keywords: Adolescent; Adult; Brazil; Celiac Disease; Chi-Square Distribution; Child; Child, Preschool; Cross-Sectional Studies; Europe; Family; Female; Gene Frequency; Genetic Predisposition to Disease; HLA-DQ Antigens; Humans; Infant; Male; Middle Aged; Young Adult

Frequency of HLA B*5701 allele carriers in abacavir treated-HIV infected patients and controls from northeastern Brazil. - Crovella, Sergio; Biller, Lara; Santos, Sergio; Salustiano, Ana; Brandão, Lucas; Guimarães, Rafael; Segat, Ludovica; Lima Filho, Jose Luiz de; Arraes, Luiz Claudio (Clinics (Sao Paulo), 2011)
Keywords: Adolescent; Adult; Anti-HIV Agents; Brazil; Case-Control Studies; Dideoxynucleosides; Drug Hypersensitivity; Female; Gene Frequency; Genotype; HIV Infections; HLA-B Antigens; Humans; Male; Middle Aged; Real-Time Polymerase Chain Reaction; Young Adult

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Gastroesophageal reflux disease at any cost: a dangerous paediatric attitude. - Taddio, Andrea; Bersanini, Chiara; Basile, Lucio; Fontana, Massimo; Ventura, Alessandro (Acta Paediatr, 2011)
Keywords: Diagnostic Errors; Gastroesophageal Reflux; Humans; Inappropriate Prescribing; Infant; Infant, Newborn; Male; Proton Pump Inhibitors; Spasms, Infantile

Gastrointestinal Foxp3 expression in normal, inflammatory and neoplastic conditions. - Villanacci, Vincenzo; Not, Tarcisio; Nascimbeni, Riccardo; Ferrara, Fortunato; Tommasini, Alberto; Manenti, Stefania; Antonelli, Elisabetta; Bassotti, Gabrio (Pathology, 2011)
BACKGROUND: Foxp3(+) regulatory T lymphocytes (T-regs) represent an important regulatory cell subset in inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract. METHODS: Inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract (189 cases) were studied with the evaluation of Foxp3 regulatory T cells based on immunohistochemistry. RESULTS: Few Foxp3(+) cells were found in controls and inflammatory conditions (oesophagitis, gastritis, coeliac disease, inflammatory bowel disease); in preneoplastic and neoplastic conditions the number of Foxp3(+) cells was significatively increased. CONCLUSIONS: In normal conditions the number of mucosal lymphocytes is very low throughout the gastro-intestinal tract; in active coeliac disease patients or on a gluten-free diet, only a slight increase in Foxp3(+) cells may be found. Gastrointestinal cancers are associated with higher Foxp3(+) cell proportion, compared with microscopically normal tissue and with precancerous conditions. However, it is uncertain whether the increase in these regulatory cells is a cause or a consequence of tumour progression.
Keywords: Adult; Aged; Celiac Disease; Cell Count; Disease Progression; Esophagitis; Female; Forkhead Transcription Factors; Gastric Mucosa; Gastritis; Humans; Inflammatory Bowel Diseases; Lymphocytes; Male; Middle Aged; Precancerous Conditions; Stomach Diseases; Stomach Neoplasms; Young Adult

Genetic predictors of glucocorticoid response in pediatric patients with inflammatory bowel diseases. - De Iudicibus, Sara; Stocco, Gabriele; Martelossi, Stefano; Londero, Margherita; Ebner, Egle; Pontillo, Alessandra; Lionetti, Paolo; Barabino, Arrigo; Bartoli, Fiora; Ventura, Alessandro; Decorti, Giuliana (J Clin Gastroenterol, 2011)
BACKGROUND: Glucocorticoids (GCs) are used in moderate-to-severe inflammatory bowel diseases (IBD) but their effect is often unpredictable. AIM: To determine the influence of 4 polymorphisms in the GC receptor [nuclear receptor subfamily 3, group C, member 1 (NR3C1)], interleukin-1β (IL-1β), and NACHT leucine-rich-repeat protein 1 (NALP1) genes, on the clinical response to steroids in pediatric patients with IBD. METHODS: One hundred fifty-four young IBD patients treated with GCs for at least 30 days and with a minimum follow-up of 1 year were genotyped. The polymorphisms considered are the BclI in the NR3C1 gene, C-511T in IL-1β gene, and Leu155His and rs2670660/C in NALP1 gene. Patients were grouped as responder, dependant, and resistant to GCs. The relation between GC response and the genetic polymorphisms considered was examined using univariate, multivariate, and Classification and Regression Tree (CART) analysis. RESULTS: Univariate analysis showed that BclI polymorphism was more frequent in responders compared with dependant patients (P=0.03) and with the combined dependant and resistant groups (P=0.02). Moreover, the NALP1 Leu155His polymorphism was less frequent in the GC responsive group compared with resistant (P=0.0059) and nonresponder (P=0.02) groups. Multivariate analysis comparing responders and nonresponders confirmed an association between BclI mutated genotype and steroid response (P=0.030), and between NALP1 Leu155His mutant variant and nonresponders (P=0.033). An association between steroid response and male sex was also observed (P=0.034). In addition, Leu155His mutated genotype was associated with steroid resistance (P=0.034). Two CART analyses supported these findings by showing that BclI and Leu155His polymorphisms had the greatest effect on steroid response (permutation P value=0.046). The second CART analysis also identified age of disease onset and male sex as important variables affecting response. CONCLUSIONS: These results confirm that genetic and demographic factors may affect the response to GCs in young patients with IBD and strengthen the importance of studying high-order interactions for predicting response.
Keywords: Adolescent; Child; Drug Resistance; Female; Follow-Up Studies; Genotype; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Multivariate Analysis; Polymorphism, Genetic; Receptors, Glucocorticoid; Regression Analysis; Retrospective Studies; Sex Factors; Treatment Outcome

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Glutamine-enriched nutrition does not reduce mucosal morbidity or complications after stem-cell transplantation for childhood malignancies: a prospective randomized study. - Uderzo, Cornelio; Rebora, Paola; Marrocco, Emanuela; Varotto, Stefania; Cichello, Francesca; Bonetti, Maurizio; Maximova, Natalia; Zanon, Davide; Fagioli, Franca; Nesi, Francesca; Masetti, Riccardo; Masetti, Roberto; et al. (Transplantation, 2011)
BACKGROUND: Intravenous glutamine-enriched solution seems to be effective in posttransplant period in decreasing the severity and duration of mucositis. The aim of this randomized study was to determine the benefit of glutamine supplementation both on mucosal morbidity and in posttransplant associated complications. METHODS: Children undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) for malignant hematological diseases were randomly assigned to standard total parenteral nutrition (S-TPN) or glutamine-enriched (GE)-TPN solution consisting of 0.4 g/kg/day of l-alanine-glutamine dipeptide. This treatment started on the day of HSCT and ended when the patients could orally cover more than 50% of their daily energy requirements. The severity and the rate of post-HSCT mucositis were based on World Health Organization criteria. All the analyses were conducted on intention-to-treat principle. RESULTS: One hundred twenty consecutive patients (83 men; median age, 8.1 years) were enrolled. The mean duration of treatment was 23.5 and 23 days in the two treatment arms. The mean calorie intake was 1538 kcal/d in the S-TPN group and 1512 kcal/d in GE-TPN group. All patients were well nourished before and after HSCT. Mucositis occurred in 91.4% and 91.7% of patients in S-TPN and GE-TPN arm, respectively (P=0.98). Odds ratio adjusted by type of HSCT was 0.98 (95% confidence interval, 0.26-2.63). Type and duration of analgesic treatment, clinical outcome (engraftment, graft versus host disease, early morbidity, and mortality, relapse rate up to 180 days post-HSCT) were not significantly different in the two treatment arms. CONCLUSION: GE-TPN solution does not affect mucositis and outcome in well-nourished HSCT allogeneic patients.
Keywords: Adolescent; Analgesia; Child; Child, Preschool; Double-Blind Method; Female; Glutamine; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Mucositis; Mucous Membrane; Neoplasms; Odds Ratio; Parenteral Nutrition; Prospective Studies; Recurrence; Stem Cells; Treatment Outcome

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

High prevalence of BK polyomavirus sequences in human papillomavirus-16-positive precancerous cervical lesions. - Comar, Manola; Bonifacio, Daniela; Zanconati, Fabrizio; Di Napoli, Michela; Isidoro, Erica; Martini, Fernanda; Torelli, Lucio; Tognon, Mauro (J Med Virol, 2011)
High- and low-grade cervical lesions were analyzed for the presence of polyomavirus (PYV) and human papillomavirus (HPV) sequences. In precancerous cervical lesions, the overall prevalence of PYV sequences was 44% (41/93). Specifically, among the PYV-positive samples, 83% (34/41) tested positive for BK polyomavirus (BKV) sequences, whereas 17% (7/41) were positive for JC-virus. None of the samples were positive for simian virus 40. The presence of BKV DNA in high-grade squamous intraepithelial lesions was confirmed by in situ PCR. BKV sequences were detected more frequently in high-grade squamous intraepithelial lesions, together with the genotype HPV-16. The association of BKV with precancerous cervical lesions suggests that this polyomavirus participates with HPV-16 in the cell transformation process. Alternatively, BKV might multiply better in HPV-16-positive cells from precancerous cervical lesions than in HPV-16-negative cells.
Keywords: Adult; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; JC Virus; Middle Aged; Oncogene Proteins, Viral; Papillomavirus Infections; Precancerous Conditions; Simian virus 40; Uterine Cervical Diseases

High-throughput genotyping robot-assisted method for mutation detection in patients with hypertrophic cardiomyopathy. - Bortot, Barbara; Athanasakis, Emmanouil; Brun, Francesca; Rizzotti, Diego; Mestroni, Luisa; Sinagra, Gianfranco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
Hypertrophic cardiomyopathy (HCM) is the most frequent autosomal dominant genetic heart muscle disease and the most common cause of sudden cardiac death in young people (under 30 y of age), who are often unaware of their underlying condition. Genetic screening is now considered a fundamental tool for clinical management of HCM families. However, the high genetic heterogeneity of HCM makes genetic screening very expensive. Here, we propose a new high-throughput genotyping method based on a HCM 96-well sequencing plate for the analysis of 8 of the most frequent HCM-causing sarcomeric genes by automating several processes required for direct sequencing, using a commercially available robotic systems and routinely used instruments. To assess the efficiency of the robot-assisted method, we have analyzed the entire coding sequence and flanking intronic sequences of the 8 sarcomeric genes in samples from 18 patients affected by HCM and their relatives, which revealed 9 different mutations, 3 of which were novel. The automated, robot-assisted assembling of polymerase chain reaction, purification of polymerase chain reaction products, and assembly of sequencing reactions resulted in a substantial saving of time, reagent costs, and reduction of human errors, and can therefore be proposed as a primary strategy for mutation identification in HCM genetic screening in many medical genetic laboratories.
Keywords: Cardiomyopathy, Hypertrophic; DNA Mutational Analysis; Genetic Predisposition to Disease; Genetic Testing; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Muscle Proteins; Mutation; Robotics

Horizontal gaze palsy and progressive scoliosis without ROBO3 mutations. - Abu-Amero, Khaled K; Faletra, Flavio; Gasparini, Paolo; Parentin, Fulvio; Pensiero, Stefano; Alorainy, Ibrahim A; Hellani, Ali M; Catalano, Dario; Bosley, Thomas M (Ophthalmic Genet, 2011)
BACKGROUND: To describe clinical and genetic observations in a patient with horizontal gaze palsy and progressive scoliosis (HGPPS) without identified mutations in the ROBO3 gene. MATERIALS AND METHODS: Neurologic and orthopedic evaluation of the proband; sequencing all exons, exon-intron boundaries, and promoter region of ROBO3 in the proband and his mother. Array CGH was also carried out in the proband and his mother to evaluate possible chromosomal deletion(s) and/or duplication(s). RESULTS: The proband had complete horizontal gaze restriction with full vertical gaze and small amplitude horizontal pendular nystagmus. He also had severe scoliosis and brainstem hypoplasia pathognomonic of HGPPS. However, complete sequencing of ROBO3 twice in both forward and reverse directions did not reveal any mutations. Array CGH investigation revealed no chromosomal abnormalities. CONCLUSIONS: This patient had clinical and neuroimaging characteristics considered pathognomonic of HGPPS and yet did not have ROBO3 mutations. A clinical misdiagnosis is unlikely in the absence of facial weakness (typical of Moebius syndrome), deafness (typical of the HOXA1 spectrum), or mental retardation (typical of other central decussation abnormalities). It is perhaps more likely that a phenotype identical to HGPPS can be caused by abnormalities in ROBO3 splice variant expression, by mutations of a gene other than ROBO3, or by some environmental or epigenetic factor(s) inhibiting the action of ROBO3 or its protein product in the developing brainstem.
Keywords: Child; Humans; Kyphosis; Magnetic Resonance Imaging; Male; Mutation; Ocular Motility Disorders; Oculomotor Nerve Diseases; Pedigree; Receptors, Immunologic; Scoliosis

In vivo distribution of β2 glycoprotein I under various pathophysiologic conditions. - Agostinis, Chiara; Biffi, Stefania; Garrovo, Chiara; Durigutto, Paolo; Lorenzon, Andrea; Bek, Alpan; Bulla, Roberta; Grossi, Claudia; Borghi, Maria O; Meroni, Pierluigi; Tedesco, Francesco (Blood, 2011)
In vitro studies have documented β2 glycoprotein I (β2GPI) binding to endothelial cells (ECs) and trophoblast using antiphospholipid antibodies. The in vivo binding of β2GPI to these cells and the conditions that favor their interaction have not been investigated. We analyzed the in vivo distribution of cyanine 5.5-labeled β2GPI in mice and evaluated the effect of pregnancy and circulating antibodies on its tissue localization. The signal was detected in the liver by whole body scan and ex vivo analysis. The β2GPI failed to bind to the vascular endothelium and reacted only with the ECs of uterine vessels. In pregnant mice the protein was localized on ECs and trophoblast at the embryo implantation sites. Immunized mice showed a similar β2GPI biodistribution to naive mice but the immunized pregnant animals exhibited a significant increase in fetal loss associated with C3 and C9 deposition at the implantation sites. Treatment of mice with LPS after β2GPI-Cy5.5 injection promoted protein localization on gut and brain ECs associated with IgG, C1q, and C9 deposition in immunized mice. These findings indicate that β2GPI binding to EC requires priming with pro-inflammatory factors which is not needed for uterine and placental localization probably dependent on hormonal changes.
Keywords: Animals; beta 2-Glycoprotein I; Complement C1q; Complement C3; Complement C9; Endothelial Cells; Endothelium, Vascular; Female; Fetal Death; Humans; Mice; Mice, Inbred BALB C; Pregnancy; Trophoblasts; Uterus

Interventions for the prevention of overweight and obesity in preschool children: a systematic review of randomized controlled trials. - Monasta, L; Batty, G D; Macaluso, A; Ronfani, L; Lutje, V; Bavcar, A; van Lenthe, F J; Brug, J; Cattaneo, A (Obes Rev, 2011)
The objective of this study was to analyse interventions for the prevention of overweight and obesity in children under 5 years of age. We carried out a systematic review focusing exclusively on randomized controlled trials (RCTs). Data sources include Medline, Cochrane Library, EMBASE, CINHAL, PsychInfo and Web of Science. Data were extracted from seventeen articles describing seven RCTs identified through electronic search, screening of references in systematic reviews, own files and contact with authors. RCTs were assessed with the Jadad scale. Four trials were carried out in preschool settings, one with an exclusive educational component, two with an exclusive physical activity component and one with both. Two trials were family-based, with education and counselling for parents and children. The remaining trial was carried out in maternity hospitals, with a training intervention on breastfeeding. None of the interventions had an effect in preventing overweight and obesity. The failure to show an effect may be due to the choice of outcomes, the quality of the RCTs, the suboptimal implementation of the interventions, the lack of focus on social and environmental determinants. More rigorous research is needed on interventions and on social and environmental factors that could impact on lifestyle.
Keywords: Child Nutrition Sciences; Child Nutritional Physiological Phenomena; Child, Preschool; Exercise; Female; Health Promotion; Humans; Life Style; Male; Obesity; Overweight; Randomized Controlled Trials as Topic

Intranasal lidocaine and midazolam for procedural sedation in children. - Chiaretti, Antonio; Barone, Giuseppe; Rigante, Donato; Ruggiero, Antonio; Pierri, Filomena; Barbi, Egidio; Barone, Giovanni; Riccardi, Riccardo (Arch Dis Child, 2011)
OBJECTIVE: To evaluate the safety and efficacy of a sedation protocol based on intranasal lidocaine spray and midazolam (INM) in children who are anxious and uncooperative when undergoing minor painful or diagnostic procedures, such as peripheral line insertion, venipuncture, intramuscular injection, echocardiogram, CT scan, audiometry testing and dental examination and extractions. PATIENTS AND DESIGN: 46 children, aged 5-50 months, received INM (0.5 mg/kg) via a mucosal atomiser device. To avoid any nasal discomfort a puff of lidocaine spray (10 mg/puff) was administered before INM. The child's degree of sedation was scored using a modified Ramsay sedation scale. A questionnaire was designed to evaluate the parents' and doctors' opinions on the efficacy of the sedation. Statistical analysis was used to compare sedation times with children's age and weight. RESULTS: The degree of sedation achieved by INM enabled all procedures to be completed without additional drugs. Premedication with lidocaine spray prevented any nasal discomfort related to the INM. The mean duration of sedation was 23.1 min. The depth of sedation was 1 on the modified Ramsay scale. The questionnaire revealed high levels of satisfaction by both doctors and parents. Sedation start and end times were significantly correlated with age only. No side effects were recorded in the cohort of children studied. CONCLUSIONS: This study has shown that the combined use of lidocaine spray and atomised INM appears to be a safe and effective method to achieve short-term sedation in children to facilitate medical care and procedures.
Keywords: Administration, Intranasal; Anesthetics, Local; Anxiety; Child, Preschool; Conscious Sedation; Diagnostic Techniques and Procedures; Female; Humans; Hypnotics and Sedatives; Infant; Lidocaine; Male; Midazolam; Minimally Invasive Surgical Procedures; Nebulizers and Vaporizers; Nose Diseases; Prospective Studies

Long-term clinical profile of children with the low-penetrance R92Q mutation of the TNFRSF1A gene. - Pelagatti, M A; Meini, A; Caorsi, R; Cattalini, M; Federici, S; Zulian, F; Calcagno, G; Tommasini, A; Bossi, G; Sormani, M P; Caroli, F; Plebani, A; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To analyze the long-term impact of the R92Q mutation of TNFRSF1A in children with periodic fever, in comparison with children with tumor necrosis factor receptor-associated periodic syndrome (TRAPS) with TNFRSF1A structural mutations and children with periodic fever of unknown origin fulfilling the criteria for periodic fever, aphthosis, pharyngitis, and adenitis syndrome (PFAPA). METHODS: The extracellular region of TNFRSF1A was analyzed in 720 consecutive children with periodic fever, using denaturing high-performance liquid chromatography and DNA sequencing. Followup data on 11 pediatric patients with TNFRSF1A structural mutations (cysteine or T50M), 23 pediatric patients with an R92Q substitution, and 64 pediatric patients with PFAPA were collected during routine clinic visits. The 50-item Child Health Questionnaire was used to assess health-related quality of life (HRQOL). RESULTS: The frequency of typical TRAPS-related clinical manifestations was significantly lower and the impact of the disease on HRQOL was significantly reduced in patients with the R92Q mutation compared with TRAPS patients carrying structural mutations of TNFRSF1A. Followup data on 11 TRAPS patients with TNFRSF1A structural mutations (mean followup 7.9 years), 16 patients with theR92Q substitution (mean followup 7.3 years), and 64 patients with PFAPA (mean followup 5.2 years) were available. Patients with R92Q mutations and patients with PFAPA displayed a higher rate of self-resolution or amelioration of the fever episodes than did TRAPS patients with structural mutations. CONCLUSION: Although some cases may progress to a more chronic disease course, the majority of children with an R92Q mutation of the TNFRSFA1 gene show a milder disease course than that in children with TNFRSFA1 structural mutations and have a high rate of spontaneous resolution and amelioration of the recurrent fever episodes.
Keywords: Adolescent; Antirheumatic Agents; Biological Therapy; Child; Child, Preschool; Familial Mediterranean Fever; Female; Fever; Follow-Up Studies; Genotype; Health Surveys; Humans; Infant; Interleukin 1 Receptor Antagonist Protein; Longitudinal Studies; Lymphadenitis; Male; Mutation; Pharyngitis; Quality of Life; Receptors, Tumor Necrosis Factor; Receptors, Tumor Necrosis Factor, Type I; Recurrence; Retrospective Studies; Steroids; Syndrome

Mannose binding lectin gene (MBL2) functional polymorphisms are associated with systemic lupus erythematosus in southern Brazilians. - Sandrin-Garcia, Paula; Brandão, Lucas André Cavalcanti; Coelho, Antônio Victor Campos; Guimarães, Rafael Lima; Pancoto, João Alexandre Trés; Segat, Ludovica; Donadi, Eduardo Antônio; de Lima-Filho, José Luiz; Crovella, Sergio (Hum Immunol, 2011)
Susceptibility to systemic lupus erythematosus (SLE) has been associated with immunologic, environmental, and genetic factors. To uncover a possible association between MBL2 gene polymorphisms and SLE, we analyzed functional polymorphisms in the promoter and first exon of the MBL2 gene in 134 Brazilian SLE patients and 101 healthy controls. Genotype and allele frequencies of MBL2 A/O polymorphism were significantly different between patients and controls, and the O allele was associated with an increased risk of SLE. An association between low mannose binding lectin (MBL) producer combined genotypes and increased risk for SLE was also reported. Furthermore, when stratifying SLE patients according to clinical and laboratory data, an association between the A/O genotype and nephritic disorders and between the X/Y genotype and antiphospholipid syndrome was evident. Combined genotypes responsible for low MBL production were more frequently observed in SLE patients with nephritis. Our results indicate MBL2 polymorphisms as possible risk factors for SLE development and disease-related clinical manifestations.
Keywords: Adolescent; Adult; Aged; Brazil; DNA Mutational Analysis; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Lupus Erythematosus, Systemic; Male; Mannose-Binding Lectin; Middle Aged; Polymorphism, Genetic; Population Groups; Promoter Regions, Genetic

Mannose-binding lectin gene (MBL-2) polymorphism in oral lichen planus. - Barkokebas, Andreza; de Albuquerque T Carvalho, Alessandra; de Souza, Paulo Roberto Eleutério; Gomez, Ricardo Santiago; Xavier, Guilherme Machado; Ribeiro, Camila Maria Beder; Crovella, Sergio; Porter, Stephen Ross; Leão, Jair Carneiro (Clin Oral Investig, 2011)
TNF-α may be associated with the etiopathogenesis of oral lichen planus (OLP), and it has been suggested that polymorphism of mannose-binding lectin (MBL) increases the in vitro production of TNF- α. The aim of the present study was to assess the relevance of genetic diversity of MBL in OLP. The study sample comprised 90 individuals, 45 OLP patients and 45 healthy volunteers. MBL-2 gene was amplified using real-time PCR. Frequency of A/A genotype was 55.6% in OLP and 53.3% in healthy volunteers. Likewise, A/0 heterozygote genotype was found in 42.2% and 35.6%; 2.2% and 11.1%, had the recessive 0/0 genotype respectively. Frequencies of the "A" and "0" alleles were 77% and 23% in the OLP group and 71.2% in control group. There were no statistically significant differences regarding genotype frequency (p = 0.546) or allele frequency (p = 0.497). In conclusion, no significant association was found between polymorphism of MBL-2 gene and OLP.
Keywords: Adolescent; Adult; Aged; Female; Gene Expression Regulation; Gene Frequency; Genes, Recessive; Genetic Variation; Genotype; Heterozygote; Homozygote; Humans; Lichen Planus, Oral; Male; Mannose-Binding Lectin; Middle Aged; Mutation; Polymorphism, Genetic; Real-Time Polymerase Chain Reaction; Tumor Necrosis Factor-alpha; Young Adult

Mast cells are critically involved in serum-mediated vascular leakage in chronic urticaria beyond high-affinity IgE receptor stimulation. - Bossi, F; Frossi, B; Radillo, O; Cugno, M; Tedeschi, A; Riboldi, P; Asero, R; Tedesco, F; Pucillo, C (Allergy, 2011)
BACKGROUND: Chronic urticaria (CU) is one of the most common skin disorders whose pathogenic mechanisms are not fully clarified. Autoimmune aetiology can be ascribed to 45% of patients with CU, and basophil histamine release is positive in 40% of cases. Our aim was to use a novel approach to evaluate the serum permeabilizing effect to identify the mediators of endothelial cell (EC) leakage and to define the role of mast cells (MCs) in the process. METHODS: Permeabilizing activity of sera from 19 patients with CU and 11 healthy blood donors was evaluated by measuring serum-induced degranulation of two MC lines, expressing (LAD2) or lacking (HMC-1) the IgE receptor. Mast cell supernatant (SN) was then incubated with an EC monolayer, and endothelial permeability was evaluated by Fluorescein isothiocyanate-bovine serum albumin leakage in a transwell system. RESULTS: All 19 patient sera failed to induce direct EC leakage, but 15/19 and 17/19 promoted degranulation of HMC-1 and LAD2, respectively. Interestingly, 85% of autologous serum skin test-negative sera were able to cause MC degranulation. Also, 17/19 SNs from HMC-1 and all SNs from LAD2 incubated with CU sera increased endothelial permeability. Endothelial cell leakage remained unchanged after Ig depletion and was prevented by antihistamine, platelet-activating factor or leukotriene antagonist. CONCLUSIONS: Our study shows that CU sera are able to degranulate MCs through an IgE- and IgG-independent mechanism. The nature of histamine-releasing factors involved is still unclear, but our finding opens new ways to the understanding of the pathogenesis of CU, particularly in patients not showing circulating autoantibodies to FcεRI or IgE.
Keywords: Adult; Aged; Capillary Permeability; Chronic Disease; Endothelial Cells; Female; Histamine Release; Humans; Male; Mast Cells; Middle Aged; Receptors, IgE; Serum; Urticaria; Young Adult

miR-34a induces the downregulation of both E2F1 and B-Myb oncogenes in leukemic cells. - Zauli, Giorgio; Voltan, Rebecca; di Iasio, Maria Grazia; Bosco, Raffaella; Melloni, Elisabetta; Sana, Maria Elena; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To elucidate new molecular mechanisms able to downregulate the mRNA levels of key oncogenes, such as B-Myb and E2F1, in a therapeutic perspective. EXPERIMENTAL DESIGN: B-Myb and E2F1 mRNA levels were evaluated in primary B chronic lymphocytic leukemia (B-CLL, n = 10) and acute myeloid leukemia (AML, n = 5) patient cells, in a variety of p53(wild-type) and p53(mutated/deleted) leukemic cell lines, as well as in primary endothelial cells and fibroblasts. Knockdown experiments with siRNA for p53 and E2F1 and overexpression experiments with miR34a were conducted to elucidate the role of these pathways in promoting B-Myb downregulation. RESULTS: In vitro exposure to Nutlin-3, a nongenotoxic activator of p53, variably downregulated the expression of B-Myb in primary leukemic cells and in p53(wild-type) myeloid (OCI, MOLM) and lymphoblastoid (SKW6.4, EHEB) but not in p53(mutated) (NB4, BJAB, MAVER) or p53(deleted) (HL-60) leukemic cell lines. The transcriptional repression of B-Myb was also observed in primary normal endothelial cells and fibroblasts. B-Myb downregulation played a critical role in the cell-cycle block in G(1) phase induced by Nutlin-3, as shown by transfection experiments with specific siRNA. Moreover, we have provided experimental evidence suggesting that miR-34a is a central mediator in the repression of B-Myb both directly and through E2F1. CONCLUSIONS: Owing to the role of B-Myb and E2F1 transcription factors in controlling cell-cycle progression of leukemic cells, the downregulation of these oncogenes by miR-34a suggests the usefulness of therapeutic approaches aimed to modulate the levels of miR-34a.
Keywords: Base Sequence; Cell Cycle Proteins; Cell Line, Tumor; Cells, Cultured; Down-Regulation; E2F1 Transcription Factor; Gene Expression Regulation, Leukemic; HCT116 Cells; HL-60 Cells; Humans; Imidazoles; Leukemia; MicroRNAs; Models, Biological; Oncogenes; Piperazines; Sequence Homology, Nucleic Acid; Trans-Activators; Transfection

Molecular targets for selective killing of TRAIL-resistant leukemic cells. - Zauli, Giorgio; Bosco, Raffaella; Secchiero, Paola (Expert Opin Ther Targets, 2011)
INTRODUCTION: TNF-related apoptosis-inducing ligand (TRAIL) is a member of the TNF family of cytokines, and shows promising therapeutic activity against solid tumors and lymphomas, in a variety of Phase I and II clinical trials. In contrast, primary leukemias have shown poor susceptibility to TRAIL-mediated cytotoxicity, suggesting the need for sensitizing TRAIL-resistant leukemic cells, by combining soluble recombinant TRAIL either with chemotherapeutic drugs, or with targeted small molecules. AREAS COVERED: This review discusses potential therapeutic applications of combinations able to restore the sensitivity of leukemic cells to either recombinant TRAIL or anti-TRAIL-receptor agonistic antibodies for the treatment of hematological malignancies. EXPERT OPINION: Up-to-date knowledge of the most innovative anti-leukemic therapies including functional screening of specific-sensitizers, enhancing TRAIL-mediated cytotoxicity. Strategies aimed to enhance TRAIL-mediated apoptosis, include the combination of novel sensitizers, functionally identified from libraries of pharmaceutically active, synthetic or naturally derived compounds. Other approaches aim to employ the administration of stem cells engineered to express TRAIL, in the leukemic stem cell niche, and promise to be a successful treatment with reduced specific toxicity.
Keywords: Humans; Leukemia; TNF-Related Apoptosis-Inducing Ligand

A multicenter, case-control study on risk factors for antepartum stillbirth. - Facchinetti, Fabio; Alberico, Salvatore; Benedetto, Chiara; Cetin, Irene; Cozzolino, Sabrina; Di Renzo, Gian Carlo; Del Giovane, Cinzia; Ferrari, Francesca; Mecacci, Federico; Menato, Guido; Tranquilli, Andrea L; Baronciani, Dante (J Matern Fetal Neonatal Med, 2011)
OBJECTIVE: As the influence of socio-demographic variables, lifestyle and medical conditions on the epidemiology of stillbirth (SB) is modified by population features, we aimed at investigating the role played by these factors on the incidence of SB in a developed country. STUDY DESIGN: Multivariate logistic regression analysis (OR with 95% CI) was utilized in a prospective multicentre nested case-control study to compare in a 1:2 ratio stillborn of >22 weeks gestation with matched for gestational age live-born (LB) infants. Intrapartum SB were excluded. RESULTS: Two hundred fifty-four consecutive SBs and 497 LBs were enrolled. Socio-demographic variables were equally distributed. Fetal malformations (7.96, 2.69-23.55), severe intrauterine growth restriction (IUGR) (birthweight ≤ 5(th) %ile) (4.32, 2.27?8.24), BMI > 25 (2.87, 1.90-4.33), and preeclampsia (PE, 0.40, 0.21-0.77) were recognized as independent predictors for SB. At term, only BMI > 25 was associated with SB (7.70, 2.9-20.5). CONCLUSION: Fetal malformations, severe IUGR and maternal BMI > 25 were associated with a significant increase in the risk of SB; PE presented instead a protective role. Maternal BMI > 25 was the only risk factor for SB identified in term pregnancies.
Keywords: Adult; Case-Control Studies; Cause of Death; Congenital Abnormalities; Female; Fetal Death; Fetal Growth Retardation; Humans; Infant, Newborn; Male; Obstetric Labor Complications; Pre-Eclampsia; Pregnancy; Risk Factors; Stillbirth; Young Adult

A multicenter, randomized, placebo-controlled trial of levetiracetam in children and adolescents with newly diagnosed absence epilepsy. - Fattore, Cinzia; Boniver, Clementina; Capovilla, Giuseppe; Cerminara, Caterina; Citterio, Antonietta; Coppola, Giangennaro; Costa, Paola; Darra, Francesca; Vecchi, Marilena; Perucca, Emilio (Epilepsia, 2011)
PURPOSE: To evaluate the potential efficacy of levetiracetam as an antiabsence agent in children and adolescents with newly diagnosed childhood or juvenile absence epilepsy. METHODS: Patients were randomized in a 2:1 ratio to receive de novo monotherapy with levetiracetam (up to 30 mg/kg/day) or placebo for 2 weeks under double-blind conditions. Responder status (primary end point) was defined as freedom from clinical seizures on days 13 and 14 and from electroencephalographic (EEG) seizures during a standard EEG recording with hyperventilation and intermittent photic stimulation on day 14. The double-blind phase was followed by an open-label follow-up. KEY FINDINGS: Nine of 38 patients (23.7%) were responders in the levetiracetam group, compared with one of 21 (4.8%) in the placebo group (p = 0.08). Seven of 38 patients (18.4%) were free from clinical and EEG seizures during the last 4 days of the trial (including 24-h EEG monitoring on day 14) compared with none of the patients treated with placebo (p = 0.04). Seventeen patients remained seizure-free on levetiracetam after 1 year follow-up. Of the 41 patients who discontinued levetiracetam due to lack of efficacy (n = 39) or adverse events (n = 2), 34 became seizure-free on other treatments. SIGNIFICANCE: Although superiority to placebo just failed to reach statistical significance for the primary end point, the overall findings are consistent with levetiracetam having modest efficacy against absence seizures. Further controlled trials exploring larger doses and an active comparator are required to determine the role of levetiracetam in the treatment of absence epilepsy.
Keywords: Adolescent; Age Factors; Anticonvulsants; Child; Child, Preschool; Double-Blind Method; Drug Resistance; Epilepsy, Absence; Female; Humans; Male; Outcome Assessment (Health Care); Piracetam

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in the 5' UTR of ANKRD26, the ankirin repeat domain 26 gene, cause an autosomal-dominant form of inherited thrombocytopenia, THC2. - Pippucci, Tommaso; Savoia, Anna; Perrotta, Silverio; Pujol-Moix, Núria; Noris, Patrizia; Castegnaro, Giovanni; Pecci, Alessandro; Gnan, Chiara; Punzo, Francesca; Marconi, Caterina; Gherardi, Samuele; Loffredo, Giuseppe; et al. (Am J Hum Genet, 2011)
THC2, an autosomal-dominant thrombocytopenia described so far in only two families, has been ascribed to mutations in MASTL or ACBD5. Here, we show that ANKRD26, another gene within the THC2 locus, and neither MASTL nor ACBD5, is mutated in eight unrelated families. ANKRD26 was also found to be mutated in the family previously reported to have an ACBD5 mutation. We identified six different ANKRD26 mutations, which were clustered in a highly conserved 19 bp sequence located in the 5' untranslated region. Mutations were not detected in 500 controls and are absent from the 1000 Genomes database. Available data from an animal model and Dr. Watson's genome give evidence against haploinsufficiency as the pathogenetic mechanism for ANKRD26-mediated thrombocytopenia. The luciferase reporter assay suggests that these 5' UTR mutations might enhance ANKRD26 expression. ANKRD26 is the ancestor of a family of primate-specific genes termed POTE, which have been recently identified as a family of proapoptotic proteins. Dysregulation of apoptosis might therefore be the pathogenetic mechanism, as demonstrated for another thrombocytopenia, THC4. Further investigation is needed to provide evidence supporting this hypothesis.
Keywords: Ankyrin Repeat; Base Sequence; Chromosome Breakage; Chromosome Disorders; Conserved Sequence; Female; Genes, Dominant; Genetic Loci; Haploinsufficiency; Humans; Male; Molecular Sequence Data; Mutation; Pedigree; Thrombocytopenia

Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, Daniele; Arzuffi, Paola; Zordan, Mauro; Da Re, Caterina; Lamperti, Costanza; Benna, Clara; d'Adamo, Pio; Diodato, Daria; Costa, Rodolfo; Mariotti, Caterina; Uziel, Graziella; Smiderle, Cristina; et al. (Nat Genet, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.
Keywords: Adult; Animals; Brain; Codon, Nonsense; Drosophila melanogaster; Electron Transport Complex III; Female; Gene Knockdown Techniques; Humans; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Nervous System Diseases

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

Neuromotor deficits in developmental coordination disorder: evidence from a reach-to-grasp task. - Biancotto, Marina; Skabar, Aldo; Bulgheroni, Maria; Carrozzi, Marco; Zoia, Stefania (Res Dev Disabil, 2011)
Developmental coordination disorder (DCD) has been classified as a specific learning disability, nonetheless the underlying cognitive mechanisms are still a matter of discussion. After a summary of the main hypotheses on the principal neuromotor causes of DCD, this study applies a causal model framework to describe the possible coexistence of more than one deficit in this disorder. For this purpose, kinematic analysis was applied to an ecological task, the reach-to-grasp action, introducing the manipulation of three variables: vision, distance and object size. After a thorough neurological and neuropsychological evaluation, 9 children with DCD (7-9 years old) were selected and compared to 27 age-matched control children. The results suggest that children with DCD have a normal neurological characterization of the reaching and grasping movements, in terms of proximal to distal action, but their grasping aperture (MGA) was always wider with respect to controls, particularly when vision was not allowed. In addition, the performance of children with DCD was always slower, more dependent on vision and more variable than that of controls. The MGA of children with DCD could be explained by a deficit in the internal construction of movement for a forward model, while slowness could be related to a control problem in the neuronal firing of the muscles. The idea of a possible coexistence of these two deficits is discussed in accordance to a causal model framework and also addressed considering recent neurophysiologic evidences.
Keywords: Analysis of Variance; Biomechanical Phenomena; Child; Female; Humans; Male; Motor Skills Disorders; Psychometrics; Psychomotor Performance; Reaction Time; Space Perception

Non-invasive assessment of hemispheric language dominance by optical topography during a brief passive listening test: a pilot study. - Bembich, Stefano; Demarini, Sergio; Clarici, Andrea; Massaccesi, Stefano; Grasso, Domenico Loenardo (Med Sci Monit, 2011)
BACKGROUND: The Wada test is usually used for pre-surgical assessment of language lateralization. Considering its invasiveness and risk of complications, alternative methods have been proposed but they are not always applicable to non-cooperative patients. In this study we explored the possibility of using optical topography (OT)--a multichannel near-infrared system--for non-invasive assessment of hemispheric language dominance during passive listening. MATERIAL/METHODS: Cortical activity was monitored in a sample of healthy, adult Italian native speakers, all right-handed. We assessed changes in oxy-haemoglobin concentration in temporal, parietal and posterior frontal lobes during a passive listening of bi-syllabic words and vowel-consonant-vowel syllables lasting less then 3 minutes. Activated channels were identified by t tests. RESULTS: Left hemisphere showed significant activity only during the passive listening of bi-syllabic words. Specifically, the superior temporal gyrus, the supramarginal gyrus and the posterior inferior parietal lobe were activated. CONCLUSIONS: During passive listening of bi-syllabic words, right handed healthy adults showed a significant activation in areas already known to be involved in speech comprehension. Although more research is needed, OT proved to be a promising alternative to the Wada test for non-invasive assessment of hemispheric language lateralization, even if using a particularly brief trial, which has been designed for future applications with non-cooperative subjects.
Keywords: Acoustic Stimulation; Adult; Cerebrum; Diagnostic Techniques and Procedures; Dominance, Cerebral; Female; Humans; Language; Male; Middle Aged; Oxyhemoglobins; Pilot Projects; Spectroscopy, Near-Infrared

Osteoprotegerin induces morphological and functional alterations in mouse pancreatic islets. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Sabato, Nicoletta; Carretta, Renzo; Corallini, Federica; Secchiero, Paola; Zauli, Giorgio; Fabris, Bruno (Mol Cell Endocrinol, 2011)
Although serum osteoprotegerin (OPG) is significantly increased in diabetic subjects, its potential role in beta cell dysfunction has not been investigated. This study aimed to assess the effect of full-length OPG administered in vivo in mice on pancreatic islet structure and function and its interaction with the renin-angiotensin system (RAS). OPG-treated mice showed increased islet monocyte/macrophage infiltration, fibrosis and apoptosis with reduction of islet function. The remodeling of islet architecture was associated with increased pancreatic expression of components of the RAS, growth factor genes (transforming growth factor β and connective tissue growth factor) and inflammatory molecules (monocyte chemotactic protein-1 and vascular adhesion molecule type 1). Prevention of these changes with improvement of insulin secretion was observed in ramipril treated animals. Our data suggest that OPG might play an important role in promoting beta cell dysfunction and that the upregulation of the local RAS represents one possible mechanism responsible for the OPG-induced beta cell dysfunction.
Keywords: Animals; Apoptosis; Blood Glucose; Blood Pressure; Body Weight; Cell Lineage; Cell Movement; Chemokine CCL2; Connective Tissue Growth Factor; Fibrosis; Gene Expression Regulation; Humans; Insulin; Islets of Langerhans; Macrophages; Mice; Monocytes; Organ Size; Osteoprotegerin; Peptidyl-Dipeptidase A; Receptor, Angiotensin, Type 1; Systole; Transforming Growth Factor beta; Vascular Cell Adhesion Molecule-1

Osteoprotegerin promotes vascular fibrosis via a TGF-β1 autocrine loop. - Toffoli, Barbara; Pickering, Raelene J; Tsorotes, Despina; Wang, Bo; Bernardi, Stella; Kantharidis, Phillip; Fabris, Bruno; Zauli, Giorgio; Secchiero, Paola; Thomas, Merlin C (Atherosclerosis, 2011)
BACKGROUND: This study was designed to evaluate the potential role of osteoprotegerin (OPG) in arterial fibrosis. METHODS: Aortic samples were analyzed after in vivo treatment of ApoE(-/-) mice with recombinant human OPG. Mouse vascular smooth muscle cells (VSMC) were exposed in vitro to recombinant OPG and analyzed for markers of inflammation and fibrosis, such as fibronectin, collagen I, III, IV and transforming growth factor-β1 (TGF-β1). Conversely, the potential modulation of endogenous OPG expression and release by VSMC was analyzed in response to different pro-atherosclerotic cytokines, TGF-β1, platelet derived growth factor (PDGF) and angiogensin II (Ang II). RESULTS: In vivo treatment with human OPG induced signs of fibrosis and up-regulated the arterial expression of TGF-β1. Consistently, in vitro treatment of VSMC with human OPG induced the expression of fibronectin, collagen type I, III, IV, metalloprotein-2 (MMP-2) and MMP-9, as well as of TGF-β1. On the other hand, exposure to recombinant TGF-β1 promoted the expression/release of endogenous OPG and mediated the increase of OPG release induced by PDGF and Ang II in VSMC. CONCLUSIONS: Taken together, these data support a pathogenic role for OPG in the development and progression of atherosclerotic lesions and suggest the existence of a vicious circle between TGF-β1 and OPG.
Keywords: Animals; Apolipoproteins E; Cell Proliferation; Collagen; Fibronectins; Fibrosis; Gene Expression Regulation; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; Osteoprotegerin; Platelet-Derived Growth Factor; Transforming Growth Factor beta1

Periodontal infection and preterm birth: successful periodontal therapy reduces the risk of preterm birth. - Di Mario, S; Spettoli, D; Alessandrini, C; Erenbourg, A; Ronfani, L; Basevi, V (BJOG, 2011)
Keywords: Female; Humans; Periodontal Diseases; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Randomized Controlled Trials as Topic; Risk Factors

Phospholipase C-β3 is a key modulator of IL-8 expression in cystic fibrosis bronchial epithelial cells. - Bezzerri, Valentino; d'Adamo, Pio; Rimessi, Alessandro; Lanzara, Carmen; Crovella, Sergio; Nicolis, Elena; Tamanini, Anna; Athanasakis, Emmanouil; Tebon, Maela; Bisoffi, Giulia; Drumm, Mitchell L; Knowles, Michael R; et al. (J Immunol, 2011)
Respiratory insufficiency is the major cause of morbidity and mortality in patients affected by cystic fibrosis (CF). An excessive neutrophilic inflammation, mainly orchestrated by the release of IL-8 from bronchial epithelial cells and amplified by chronic bacterial infection with Pseudomonas aeruginosa, leads to progressive tissue destruction. The anti-inflammatory drugs presently used in CF patients have several limitations, indicating the need for identifying novel molecular targets. To address this issue, we preliminarily studied the association of 721 single nucleotide polymorphisms from 135 genes potentially involved in signal transduction implicated in neutrophil recruitment in a cohort of F508del homozygous CF patients with either severe or mild progression of lung disease. The top ranking association was found for a nonsynonymous polymorphism of the phospholipase C-β3 (PLCB3) gene. Studies in bronchial epithelial cells exposed to P. aeruginosa revealed that PLCB3 is implicated in extracellular nucleotide-dependent intracellular calcium signaling, leading to activation of the protein kinase Cα and Cβ and of the nuclear transcription factor NF-κB p65. The proinflammatory pathway regulated by PLCB3 acts by potentiating the Toll-like Receptors' signaling cascade and represents an interesting molecular target to attenuate the excessive recruitment of neutrophils without completely abolishing the inflammatory response.
Keywords: Adenosine Triphosphate; Calcium; Cell Line, Transformed; Cystic Fibrosis; Enzyme Activation; Epithelial Cells; Gene Expression; Gene Frequency; Genotype; Green Fluorescent Proteins; Host-Pathogen Interactions; Humans; Interleukin-8; Isoenzymes; Lung Diseases; Microscopy, Fluorescence; Phospholipase C beta; Polymorphism, Single Nucleotide; Protein Kinase C; Protein Kinase C beta; Pseudomonas aeruginosa; RNA Interference; Toll-Like Receptors; Transcription Factor RelA

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

Prevalence of anaemia in children with thromboembolism in IBD. - Bramuzzo, Matteo; Lazzerini, Marzia (Arch Dis Child, 2011)
Keywords: Anemia, Iron-Deficiency; Female; Humans; Male; Stroke

Procalcitonin in detecting neonatal nosocomial sepsis. - Auriti, Cinzia; Fiscarelli, Ersilia; Ronchetti, Maria Paola; Argentieri, Marta; Marrocco, Gabriella; Quondamcarlo, Anna; Seganti, Giulio; Bagnoli, Francesco; Buonocore, Giuseppe; Serra, Giovanni; Bacolla, Gianfranco; Mastropasqua, Savino; et al. (Arch Dis Child Fetal Neonatal Ed, 2011)
OBJECTIVE: To investigate the accuracy of procalcitonin (PCT) as a diagnostic marker of nosocomial sepsis (NS) and define the most accurate cut-off to distinguish infected from uninfected neonates. SETTING: Six neonatal intensive care units (NICUs). PATIENTS: 762 neonates admitted to six NICUs during a 28-month observational study for whom at least one serum sample was taken on admission. MAIN OUTCOME MEASURES: Positive and negative predictive values at different PCT cut-off levels. RESULTS: The overall probability of an NS was doubled or more if PCT was >0.5 ng/ml. In very-low-birth-weight (VLBW) infants, a cut-off of >2.4 ng/ml gave a positive predictive value of NS near to 50% with a probability of a false-positive diagnosis of NS in about 10% of the patients. CONCLUSIONS: In VLBW neonates, a serum PCT value >2.4 ng/ml prompts early empirical antibiotic therapy, while in normal-birth-weight infants, a PCT value ≤2.4 ng/ml carries a low risk of missing an NS.

[Proteomic applications in gynecology-obstetrics]. - De Seta, F; Banco, R; Guaschino, S; De Santo, D; Turrisi, A; Piva, C (Minerva Ginecol, 2011)
Proteomics has recently emerged as a powerful approach both for discovering biomarkers as well as for understanding the physiopathology of unclear gynecological-obstetrical disorders. Currently, several biological fluids and fetal tissues were successfully tested, including maternal plasma, amniotic fluid, cervical-vaginal fluid, urine, saliva, placental trophoblast, amnio-chorionic membranes and cord blood. The potential of proteomics on the polycystic ovary syndrome (PCOS) involves biomarkers discovery for a more accurate diagnosis of the syndrome and identification, within the patients with PCOS, those who respond more easily to treatment and those who will be at increased risk for future metabolic complications. The proteomic approach applied to patients with endometriosis would allow not only a non-invasive early diagnosis, but also a staging of the disease and a prediction of infertility risk. Proteomics also involves oncological field, in order to discover biomarkers that allow early diagnosis and prognosis of female genital malignancies. In addition to this, proteomics could be used to understand and predict obstetrical complications such as recurrent spontaneous abortion, preterm birth and preeclampsia. However, further studies are needed on a larger cohort of patients to introduce these biomarkers in clinical practice.
Keywords: Endometriosis; Female; Genital Diseases, Female; Genital Neoplasms, Female; Humans; Polycystic Ovary Syndrome; Pregnancy; Pregnancy Complications; Proteomics

Quality of maternal and neonatal care in Albania, Turkmenistan and Kazakhstan: a systematic, standard-based, participatory assessment. - Tamburlini, Giorgio; Siupsinskas, Gelmius; Bacci, Alberta (PLoS One, 2011)
BACKGROUND: Progress in maternal and neonatal mortality has been slow in many countries despite increasing access to institutional births, suggesting deficiencies in the quality of care. We carried out a systematic assessment of the quality of maternal and newborn care in three CEE/CIS countries, using an innovative approach to identify priority issues and promote action. METHODS: A standard-based tool, covering over 400 items grouped in 13 main areas ranging from support services to case management, was used to assess a sample of ten maternity hospitals in Albania, Kazakhstan and Turkmenistan. Sources of information were visit to services, medical records, observation of cases, and interviews with staff and mothers. A score (range 0 to 3) was attributed to each item and area of care. The assessment was carried out by a multidisciplinary team of international and national professionals. Local managers and staff provided the necessary information and were involved in discussing the findings and the priority actions. RESULTS: Quality of care was found to be substandard in all 13 areas. The lowest scores (between one and two) were obtained by: management of normal labour, delivery, obstetric complications and sick babies; infection prevention; use of guidelines and audits; monitoring and follow-up. Neonatal care as a whole scored better than obstetric care. Interviewed mothers identified lack of information, insufficient support during labour and lack of companionship as main issues. Actions to improve quality of care were identified at facility as well as at central level and framed according to main health system functions. CONCLUSIONS: Quality of care is a key issue to improve maternal and neonatal outcomes, particularly in countries such as CEE/CIS where access to institutional births is nearly universal. Approaches that involve health professionals and managers in comprehensive, action-oriented assessments of quality of care are promising and should be further supported.
Keywords: Albania; Child Health Services; Female; Humans; Infant, Newborn; Kazakhstan; Maternal Health Services; Pregnancy; Quality of Health Care; Turkmenistan

Quantification of heteroplasmic mitochondrial DNA mutations for DNA samples in the low picogram range by nested real-time ARMS-qPCR. - Biffi, Stefania; Bortot, Barbara; Carrozzi, Marco; Severini, Giovanni Maria (Diagn Mol Pathol, 2011)
In many mitochondrial diseases, different clinical manifestations are related to tissue-specific distribution of mutated mitochondrial DNA (mtDNA). In this study, we describe an assay for the determination of mutated mtDNA copy number in small clinical samples, using standard polymerase chain reaction (PCR) followed by SYBR Green real-time allelic-specific PCR [amplification refractory mutation system-quantitative PCR (ARMS-qPCR)]. To assess the degree of heteroplasmy in a patient harboring 2 cosegregating mtDNA mutations (4415A>G and 9922A>C) starting from picogram amounts of DNA, we first amplified the mutated target sequence by standard PCR, and then analyzed it by real-time ARMS-qPCR. To validate this method, we analyzed by real-time ARMS-qPCR the PCR amplification products derived from different mixtures containing known proportions of mutant and wild-type cloned mtDNA fragments. The correlation coefficient of 0.994 between expected and observed values for the percentage of mutant A4415G confirms that the relative proportion of mutated and wild-type mtDNA was maintained after the first PCR amplification. This method allows the precise quantification of heteroplasmic mutations in DNA samples extracted from hairs, urine, small stomach biopsies, and, more importantly, single-muscle fiber, with a limit of detection close to 0.5%. This nested real-time ARMS-PCR represents a rapid, efficient, and less expensive method for the detection and quantification of heteroplasmic mutant mtDNA, even in very small clinical samples.
Keywords: Child; DNA, Mitochondrial; Humans; Mitochondrial Diseases; Mutation; Polymerase Chain Reaction; Sensitivity and Specificity

Recent advances in the therapeutic perspectives of Nutlin-3. - Secchiero, Paola; Bosco, Raffaella; Celeghini, Claudio; Zauli, Giorgio (Curr Pharm Des, 2011)
Nutlin-3 is a small molecule inhibitor of the MDM2/p53 interaction, which leads to the non-genotoxic p53 stabilization, activation of cell cycle arrest and apoptosis pathways. A series of recent studies have strengthened the concept that selective, non-genotoxic p53 activation by Nutlin-3 might represent an alternative to the current cytotoxic chemotherapy, in particular for pediatric tumors and for hematological malignancies, which retain a high percentage of p53(wild-type) status at diagnosis. Like most other drugs employed in cancer therapy, it will be unlikely that Nutlin-3 will be used as a monotherapy. In this respect, Nutlin-3 shows a synergistic cytotoxic effect when used in combination with innovative drugs, such as TRAIL or bortozemib. Although Nutlin-3 is currently in phase I clinical trial for the treatment of retinoblastoma, its effects on normal tissues and cell types remain largely to be determined and will require further investigation in the future years.
Keywords: Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Drug Synergism; Genes, p53; Humans; Imidazoles; Neoplasms; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Recent advances in the understanding and management of MYH9-related inherited thrombocytopenias. - Balduini, Carlo L; Pecci, Alessandro; Savoia, Anna (Br J Haematol, 2011)
MYH9-related disease (MYH9-RD) is one of the most frequent forms of inherited thrombocytopenia. It is transmitted in an autosomal dominant fashion and derives from mutations of MYH9, the gene for the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia with mild bleeding tendency and may develop kidney dysfunction, deafness and cataracts later in life. The term MYH9-RD encompasses four autosomal-dominant thrombocytopenias that were previously described as distinct disorders, namely May-Hegglin Anomaly, Sebastian, Fechtner and Epstein syndromes. Thrombocytopenia is usually mild and derives from complex defects of megakaryocyte maturation and platelet formation. It is easily diagnosed, in that the presence of giant platelets in peripheral blood raises the suspicion of MYH9-RD and a simple immunofluorescence test on blood films confirms the diagnostic hypothesis. However, genotype/phenotype correlations have been recognized and mutation screening is therefore required to define the risk of acquiring extra-haematological defects. Results of a small clinical study suggested that a non-peptide thrombopoietin mimetic might greatly benefit both thrombocytopenia and bleeding tendency of MYH9-RD patients.
Keywords: Animals; Disease Models, Animal; Genetic Predisposition to Disease; Genotype; Humans; Mice; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Myosin Type II; Phenotype; Thrombocytopenia

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

The role of mannose-binding lectin gene polymorphisms in susceptibility to HIV-1 infection in Southern Brazilian patients. - da Silva, Gabriela Kniphoff; Guimarães, Rafael; Mattevi, Vanessa Suñé; Lazzaretti, Rosmeri Kuhmmer; Sprinz, Eduardo; Kuhmmer, Regina; Brandão, Lucas; Crovella, Sergio; Chies, José Artur Bogo (AIDS, 2011)
OBJECTIVE: This study investigates the role of mannose-binding lectin (MBL) in the susceptibility to HIV-1 infection analyzing polymorphisms located at the MBL2 promoter and exon 1 regions. MATERIALS AND METHODS: The prevalence of MBL2 variant alleles was investigated in 410 HIV-1-infected patients from the South Brazilian HIV cohort and in 345 unexposed uninfected healthy individuals. The promoter variants were genotyped using polymerase chain reaction with sequence-specific primers (PCR-SSP) and exon 1 variants were analyzed by real-time PCR using a melting temperature assay and were confirmed by PCR-restriction fragment length polymorphism (RFLP). MBL2 genotypic and allelic frequencies were compared between HIV-1-infected patients and controls using the chi-squared tests. RESULTS: The analyses were performed subdividing the individuals according to their ethnic origin. Among Euro-derived individuals a higher frequency of the LX/LX genotype was observed in patients when compared to controls (P < 0.001). The haplotypic analysis also showed a higher frequency of the haplotypes associated with lower MBL levels among HIV-1-infected patients (P = 0.0001). Among Afro-derived individuals the frequencies of LY/LY and HY/HY genotypes were higher in patients when compared to controls (P = 0.009 and P = 0.02). CONCLUSIONS: An increased frequency of MBL2 genotypes associated with low MBL levels was observed in Euro-derived patients, suggesting a potential role for MBL in the susceptibility to HIV-1 infection in Euro-derived individuals.
Keywords: Adult; Aged; Brazil; Female; Genetic Predisposition to Disease; HIV Infections; HIV-1; Humans; Lectins, C-Type; Male; Mannose-Binding Lectin; Mannose-Binding Lectins; Middle Aged; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Cell Surface; Young Adult

Safety and efficacy of high-dose acarbose treatment for dumping syndrome. - De Cunto, Angela; Barbi, Egidio; Minen, Federico; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2011)
Dumping syndrome (DS) is a complication of Nissen fundoplication. Dietary strategies can ameliorate symptoms, but this approach is not always foolproof. Limited evidence reports the efficacy of acarbose for children who are unresponsive to feeding manipulations. We report 8 patients with DS aged between 7 and 24 months. In 4 of 8 nutritional strategies failed, and acarbose treatment was started. The initial dose was 25 mg for meals, and increased until postprandial glucose was stable. In 3 of 4 children the final dose was higher than previously reported, without adverse effects. Acarbose is useful to treat DS in cases of failure of dietary strategies.
Keywords: Acarbose; Child, Preschool; Dumping Syndrome; Female; Humans; Hyperglycemia; Hypoglycemic Agents; Infant; Male; Postprandial Period; Treatment Outcome

Setting research priorities to reduce global mortality from childhood pneumonia by 2015. - Rudan, Igor; El Arifeen, Shams; Bhutta, Zulfiqar A; Black, Robert E; Brooks, Abdullah; Chan, Kit Yee; Chopra, Mickey; Duke, Trevor; Marsh, David; Pio, Antonio; Simoes, Eric A F; Tamburlini, Giorgio; et al. (PLoS Med, 2011)
Keywords: Biomedical Research; Child, Preschool; Humans; Infant; Infant, Newborn; Pneumonia

The significance of mannose-binding lectin gene polymorphisms on the risk of BK virus coinfection in women with human papillomavirus-positive cervical lesions. - Comar, Manola; Segat, Ludovica; Crovella, Sergio; Bovenzi, Massimo; Cortini, Enzo; Tognon, Mauro (Hum Immunol, 2011)
The simultaneous detection of oncogenic human papillomavirus (HPV) and BK virus (BKV) has been recently reported in cervical cancers, suggesting that these viruses may act together in the process of cell transformation; host genetic polymorphisms may also influence virus persistence/reactivation. To disclose a possible role of the gene encoding for the mannose-binding lectin, MBL2, in susceptibility to BKV infection, we analyzed functional polymorphisms in the first exon of MBL2 in women stratified for the presence/absence of BKV and affected by different grades of HPV-induced cervical precancerous lesions. All BKV-positive samples were also HPV positive (HPV 16), and all presented with high-grade squamous intraepithelial lesions. The MBL2 A allele was significantly more frequent in BKV-negative patients than in BKV-positive patients. These data indicate a possible role for the A allele in conferring protection to BKV infection in high-risk HPV-positive women (odds ratio 0.40, 95% confidence interval 0.20-0.85, p = 0.01).
Keywords: Adult; Aged; Alleles; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA Fingerprinting; DNA, Viral; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Human papillomavirus 16; Humans; Italy; Mannose-Binding Lectin; Odds Ratio; Papillomavirus Infections; Polymorphism, Genetic; Polyomavirus Infections; Risk; Viral Load

A singular case of congenital self-healing histiocytosis with skin, liver and atypical eye involvement. - Parentin, Fulvio; Ventura, Giovanna; Pastore, Serena; Kiren, Valentina; Bibalo, Chiara; Pensiero, Stefano; Lepore, Loredana (Ocul Immunol Inflamm, 2011)
PURPOSE: To describe a rare case of congenital self-healing Langerhans cell histiocytosis (CSHLCH) presenting with atypical eye involvement. DESIGN: Case report. METHODS: A female newborn presented with purpuric lesions over the trunk, limbs, and face. Liver ultrasonography revealed hypoechogenic lesions with blurred borders. Biomicroscopy showed right posterior synechiae with fibrinoid deposits on the lens. At 7 months she presented with right acute glaucoma. RESULTS: Biomicroscopy showed the presence of inflammatory pseudo-membrane covering the anterior surface of the lens, iris, and iridocorneal angle. Ab externo trabeculotomy was performed; access to the anterior chamber with capsulorrhexis forceps permitted a peeling of the pseudo-membrane with normalization of the intraocular pressure. Histologic examination of the membrane revealed an inflammatory tissue with CD1a and S-100 positive histiocytic cells. CONCLUSIONS: This is the first case of CSHLCH describing acute glaucoma secondary to a pseudo-inflammatory membrane with typical histiocytic cells, occluding the iridocorneal angle.
Keywords: Antigens, CD1; Convalescence; Female; Glaucoma; Histiocytosis, Langerhans-Cell; Humans; Infant; Intraocular Pressure; Iridocorneal Endothelial Syndrome; Liver Diseases; S100 Proteins; Skin Diseases; Trabeculectomy

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

Splicing mutations in glycogen-storage disease type II: evaluation of the full spectrum of mutations and their relation to patients' phenotypes. - Zampieri, Stefania; Buratti, Emanuele; Dominissini, Silvia; Montalvo, Anna Lisa; Pittis, Maria Gabriela; Bembi, Bruno; Dardis, Andrea (Eur J Hum Genet, 2011)
Glycogen-storage disease type II is an autosomal recessive-inherited disorder due to the deficiency of acid α-glucosidase. A large number of mutations in the acid α-glucosidase gene have been described to date. Among them, ~15% are variations that may affect mRNA splicing process. In this study, we have for the first time comprehensively reviewed the available information on splicing mutations of the acid α-glucosidase gene and we have evaluated their possible impact on the splicing process using different in silico approaches. Out of the 39 different GAA-sequence variations described, an in silico analysis using seven different programs showed that 97% of them are predicted to have an impact on the splicing process. Moreover, this analysis showed a quite good correlation between the impact of the mutation on the splicing process and the clinical phenotype. In addition, we have performed the functional characterization of three novel sequence variants found in Italian patients and still uncharacterized. Using a minigene system, we have confirmed their pathogenic nature. In conclusion, this study has shown that in silico analysis represents a useful tool to select mutations that affect the splicing process of the acid α-glucosidase gene and provides an updated picture of all this kind of mutations reported till now.
Keywords: alpha-Glucosidases; Cell Line; Computational Biology; DNA Mutational Analysis; Exons; Glycogen Storage Disease Type II; Humans; Introns; Mutagenesis, Site-Directed; Mutation; Phenotype; RNA Splicing

Successful treatment of acne with isotretinoin in chronic granulomatous disease. - Barbi, Egidio; Berti, Irene; Minute, Marta; Zennaro, Floriana (Eur J Dermatol, 2011)
Keywords: Acne Vulgaris; Adult; Anti-Infective Agents; Comorbidity; Dermatologic Agents; Granulomatous Disease, Chronic; Humans; Isotretinoin; Male; Trimethoprim-Sulfamethoxazole Combination

Thromboembolism in pediatric inflammatory bowel disease: systematic review. - Lazzerini, Marzia; Bramuzzo, Matteo; Maschio, Massimo; Martelossi, Stefano; Ventura, Alessandro (Inflamm Bowel Dis, 2011)
BACKGROUND: Several studies suggest an increased risk of venous and arterial thromboembolism (TE) in adults with inflammatory bowel disease (IBD) compared to the general population. We performed a systematic review of studies on incidence and characteristic of TE in children with IBD. METHODS: We searched Medline, LILACS, EMBASE, POPLINE, CINHAL, and reference lists of identified articles, without language restrictions, in August 2010. RESULTS: Population studies suggest that there is an increased risk of TE in children with IBD compared to controls. TE occurred in children with IBD in all age ranges, mostly (82.8%) during active disease, and more frequently in children with ulcerative colitis (odds ratio [OR] 3.7, 95% confidence interval [CI] 1.8-7.6). At least one specific risk factor for TE was recognized in 50% of cases; two risk factors were present in 24%. Out of 92 published cases of TE in children with IBD, 54.3% occurred in cerebral site, 26% in the limbs, 13% in the abdominal vessels, and the remaining in the retina and lungs. After a first episode of TE, an early recurrence was observed in 11.4% of children, a late recurrence in 10%. A number of different therapeutic schemes were used. Overall mortality was 5.7% and was mostly associated with cerebral TE. CONCLUSIONS: Population studies are needed to clarify the risk of TE in children with IBD, the relative weight of other risk factors, the characteristics of the events, and to define guidelines of therapy and prophylaxis.
Keywords: Adult; Child; Humans; Inflammatory Bowel Diseases; Risk Factors; Thromboembolism

A 3'UTR SNP in NLRP3 gene is associated with susceptibility to HIV-1 infection. - Pontillo, Alessandra; Brandão, Lucas A; Guimarães, Rafael L; Segat, Ludovica; Athanasakis, Emmanouil; Crovella, Sergio (J Acquir Immune Defic Syndr, 2010)
OBJECTIVES: Innate immunity genes polymorphisms are known to be involved in the multifactorial susceptibility to HIV-1 infection. Recently it has been hypothesized that inflammasomes could play an important role in the host response to viruses. The aim of our study is to verify if single-nucleotide polymorphisms (SNPs) in genes encoding for NALPs-innate immune receptors that form molecular complexes leading to the production of IL-1beta and the activation of immune response-could influence the individual susceptibility to HIV-1. DESIGN: We performed an association study analyzing 2 NLRP1 and NLRP3 SNPs in HIV-1 vertically infected Brazilian children (n = 135), HIV-1-infected Brazilain adults (n = 192) and HIV-1-positive Italian seropositive subjects (n = 192). RESULTS: The 3'UTR NLRP3 rs10754558 SNP was associated with HIV-1 infection in all the studied groups. The frequency of rs10754558 G allele was differently distributed within seropositive subjects (HIV+) and controls, and in particular the GG genotype was less frequent in HIV+. CONCLUSIONS: susceptibility to HIV-1 infection is associated with a 3'UTR NLRP3 polymorphism. This is the first report linking SNPs in the NALPs with HIV-1 infection, and further epidemiologic and functional studies are needed to deeper investigate the role of inflammasome in the susceptibility to HIV-1 infection.
Keywords: Adult; Brazil; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Male; Middle Aged; Polymorphism, Single Nucleotide; Pregnancy; Young Adult

Abatacept improves health-related quality of life, pain, sleep quality, and daily participation in subjects with juvenile idiopathic arthritis. - Ruperto, Nicolino; Lovell, Daniel J; Li, Tracy; Sztajnbok, Flavio; Goldenstein-Schainberg, Claudia; Scheinberg, Morton; Penades, Inmaculada Calvo; Fischbach, Michael; Alcala, Javier Orozco; Hashkes, Philip J; Hom, Christine; Jung, Lawrence; et al. (Arthritis Care Res (Hoboken), 2010)
OBJECTIVE: To assess health-related quality of life (HRQOL) in abatacept-treated children/adolescents with juvenile idiopathic arthritis (JIA). METHODS: In this phase III, double-blind, placebo-controlled trial, subjects with active polyarticular course JIA and an inadequate response/intolerance to ≥1 disease-modifying antirheumatic drug (including biologics) received abatacept 10 mg/kg plus methotrexate (MTX) during the 4-month open-label period (period A). Subjects achieving the American College of Rheumatology Pediatric 30 criteria for improvement (defined "responders") were randomized to abatacept or placebo (plus MTX) in the 6-month double-blind withdrawal period (period B). HRQOL assessments included 15 Child Health Questionnaire (CHQ) health concepts plus the physical (PhS) and psychosocial summary scores (PsS), pain (100-mm visual analog scale), the Children's Sleep Habits Questionnaire, and a daily activity participation questionnaire. RESULTS: A total of 190 subjects from period A and 122 from period B were eligible for analysis. In period A, there were substantial improvements across all of the CHQ domains (greatest improvement was in pain/discomfort) and the PhS (8.3 units) and PsS (4.3 units) with abatacept. At the end of period B, abatacept-treated subjects had greater improvements versus placebo in all domains (except behavior) and both summary scores. Similar improvement patterns were seen with pain and sleep. For participation in daily activities, an additional 2.6 school days/month and 2.3 parents' usual activity days/month were gained in period A responders with abatacept, and further gains were made in period B (1.9 versus 0.9 [P = 0.033] and 0.2 versus -1.3 [P = 0.109] school days/month and parents' usual activity days/month, respectively, in abatacept- versus placebo-treated subjects). CONCLUSION: Improvements in HRQOL were observed with abatacept, providing real-life tangible benefits to children with JIA and their parents/caregivers.
Keywords: Adolescent; Arthritis, Juvenile; Child; Double-Blind Method; Female; Health Status; Humans; Immunoconjugates; Male; Pain; Quality of Life; Questionnaires; Sleep Stages

Acute respiratory failure in a child after talc inhalation. - Patarino, Federica; Norbedo, Stefania; Barbi, Egidio; Poli, Furio; Furlan, Stefano; Savron, Fabio (Respiration, 2010)
Keywords: Female; Humans; Infant; Inhalation Exposure; Respiratory Insufficiency; Talc

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

Beta defensin-1 gene (DEFB1) polymorphisms are not associated with atopic dermatitis in children and adolescents from northeast Brazil (Recife, Pernambuco). - Segat, Ludovica; Guimarães, Rafael L; Brandão, Lucas A C; Rocha, Cintia R C; Zanin, Valentina; Trevisiol, Chiara; de Lima Filho, José Luiz; Crovella, Sergio (Int J Dermatol, 2010)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease resulting from the interplay between environmental, immunological and genetic factors. In our study, we investigated the role of three single nucleotide polymorphisms (SNPs) at 5'-UTR of DEFB1 gene, encoding for the human beta defensin-1, on the susceptibility to develop AD in a group of Brazilian children and adolescents. METHODS: Three SNPs, -20 G/A (rs11362), -44 C/G (rs1800972), and -52 G/A (rs1799946) at 5'-UTR of DEFB1 gene were genotyped in two groups of children and adolescents, one affected by AD (96 subjects), the other healthy (191 individuals), from northeast Brazil. RESULTS: -44 C/G frequencies were comparable between the two groups. The -20 GG genotype was more frequent in AD subjects than in healthy controls; the -52 GG, conversely, was more frequent in healthy controls than in AD. However, both these differences did not reach statistical significance. Also, association between SNPs and AD severity has been shown. The analysis of DEFB1 haplotypes did not highlight any association of the three SNPs with AD development or disease severity. CONCLUSIONS: Our results seem to exclude a role for the -44 C/G DEFB1 SNPs on the pathogenesis and severity of AD, while for the -20 C/G and -52 G/A, even if not statistically significant, we evidenced a slight trend for susceptibility (-20 GG) and protection (-52 GG) for the development of AD. However, as controversial findings have been reported in the literature, the role of DEFB1 in the development of AD and in the severity of the phenotype deserves further investigation.
Keywords: Adolescent; beta-Defensins; Brazil; Child; Child, Preschool; Dermatitis, Atopic; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Infant; Male; Polymorphism, Single Nucleotide; Risk Factors

A child with pain after mild trauma. - Londero, Margherita; Pastore, Serena; Zanazzo, Giulio A; Bruno, Irene; Ventura, Alessandro (J Pediatr, 2010)
Keywords: Antigens, CD; Antigens, CD31; Antigens, CD34; Antigens, Differentiation, Myelomonocytic; Biopsy; Child; Factor VIII; Fingers; Hand Injuries; Hemangioendothelioma; Humans; Immunohistochemistry; Injury Severity Score; Male; Osteolysis; Pain; Pain Measurement; S100 Proteins; Vascular Neoplasms

Design and development of a computer program for the evaluation of the healthcare executive - biomed 2010. - Zotti, Daniel; Bava, Michele; Delendi, Mauro (Biomed Sci Instrum, 2010)
According to the Italian law which regulates executive healthcare contracts, the professional evaluation is mandatory. The goal of the periodic evaluation is to enhance and motivate the professional involved. In addition this process should 1. increase the sense of duty towards the patients, 2. become aware of ones own professional growth and aspirations and 3. enhance the awareness of the healthcare executive regarding the companys strategies. To satisfy these requirements a data sheet has been modeled for every evaluated subject, divided in two sections. In the first part, the chief executive officer (CEO) scores: 1. behavioral characteristics, 2. multidisciplinary collaboration and involvement, 3. organizational skills, 4. professional quality and training, 5. relationships with the citizens. The scores for these fields are decided by the CEO. In the second part the CEO evaluates: 1. quantitative job dimension, 2.technology innovation, 3. scientific and educational activities. The value scores of these fields are decided by the CEO together with the professional under evaluation. A previously established correction coefficient can be used for all the scores. This evaluation system model has been constructed according to the enhancement quality approaches (Deming cycle) and a web-based software has been developed on a Linux platform using LAMP technology and php programming techniques. The program replicates all the evaluation process creating different profiles of authentications and authorizations which can then give to the evaluator the possibility to make lists of the professionals to evaluate, to upload documents regarding their activities and goals, to receive individual documents in automatically generated folders, to change the correction coefficients, to obtain year by year the individual scores. The advantages of using this web-based software include easy data consultation and update, the implementation of IT security issues, the easy portability and scalability of the system itself in different contexts even beyond healthcare.

Determinants of nosocomial infection in 6 neonatal intensive care units: an Italian multicenter prospective cohort study. - Auriti, Cinzia; Ronchetti, Maria Paola; Pezzotti, Patrizio; Marrocco, Gabriella; Quondamcarlo, Anna; Seganti, Giulio; Bagnoli, Francesco; De Felice, Claudio; Buonocore, Giuseppe; Arioni, Cesare; Serra, Giovanni; Bacolla, Gianfranco; et al. (Infect Control Hosp Epidemiol, 2010)
BACKGROUND: Nosocomial infections are still a major cause of morbidity and mortality among neonates admitted to neonatal intensive care units (NICUs). OBJECTIVE: To describe the epidemiology of nosocomial infections in NICUs and to assess the risk of nosocomial infection related to the therapeutic procedures performed and to the clinical characteristics of the neonates at birth and at admission to the NICU, taking into account the time between the exposure and the onset of infection. DESIGN: A multicenter, prospective cohort study. PATIENTS AND SETTING: A total of 1,692 neonates admitted to 6 NICUs in Italy were observed and monitored for the development of nosocomial infection during their hospital stay. METHODS: Data were collected on the clinical characteristics of the neonates admitted to the NICUs, their therapeutic interventions and treatments, their infections, and their mortality rate. The cumulative probability of having at least 1 infection and the cumulative probability of having at least 1 infection or dying were estimated. The hazard ratio (HR) for the first infection and the HR for the first infection or death were also estimated. RESULTS: A total of 255 episodes of nosocomial infection were diagnosed in 217 neonates, yielding an incidence density of 6.9 episodes per 1,000 patient-days. The risk factors related to nosocomial infection in very-low-birth-weight neonates were receipt of continuous positive airway pressure (HR, 3.8 [95% confidence interval CI, 1.7-8.1]), a Clinical Risk Index for Babies score of 4 or greater (HR, 2.2 [95% CI, 1.4-3.4]), and a gestational age of less than 28 weeks (HR, 2.1 [95% CI, 1.2-3.8]). Among heavier neonates, the risk factors for nosocomial infection were receipt of parenteral nutrition (HR, 8.1 [95% CI, 3.2-20.5]) and presence of malformations (HR, 2.3 [95% CI, 1.5-3.5]). CONCLUSIONS: Patterns of risk factors for nosocomial infection differ between very-low-birth-weight neonates and heavier neonates. Therapeutic procedures appear to be strong determinants of nosocomial infection in both groups of neonates, after controlling for clinical characteristics.
Keywords: Bacteremia; Birth Weight; Cross Infection; Gestational Age; Hospitals, University; Humans; Incidence; Infant, Newborn; Infant, Very Low Birth Weight; Intensive Care Units, Neonatal; Italy; Length of Stay; Proportional Hazards Models; Prospective Studies; Risk Factors; Sepsis; Time Factors

Does infant gastro-oesophageal reflux really deserve medical attention? - Declich, V; Badina, L; Ventura, A (Arch Dis Child, 2010)
Keywords: Beds; Gastroesophageal Reflux; Humans; Infant; Infant Care; Posture; Prognosis

Eltrombopag for the treatment of the inherited thrombocytopenia deriving from MYH9 mutations. - Pecci, Alessandro; Gresele, Paolo; Klersy, Catherine; Savoia, Anna; Noris, Patrizia; Fierro, Tiziana; Bozzi, Valeria; Mezzasoma, Anna Maria; Melazzini, Federica; Balduini, Carlo L (Blood, 2010)
Platelet transfusion is currently the primary medical treatment for reducing thrombocytopenia in patients with inherited thrombocytopenias. To evaluate whether stimulating megakaryopoiesis could increase platelet count in these conditions, we treated patients with a severe thrombocytopenia induced by MYH9 mutations (MYH9-related disease) with a nonpeptide thrombopoietin receptor agonist, eltrombopag. Twelve adult patients with MYH9-RD and platelet counts of less than 50 × 10(9)/L received 50 mg of eltrombopag orally per day for 3 weeks. Patients who achieved a platelet count higher than 150 × 10(9)/L stopped therapy, those with 100 to 150 platelets × 10(9)/L continued treatment at the same eltrombopag dose for 3 additional weeks, while those with less than 100 platelets × 10(9)/L increased the eltrombopag dose to 75 mg for 3 weeks. Major responses (platelet count of at least 100 × 10(9)/L or 3 times the baseline value) were obtained in 8 patients, minor responses (platelet counts at least twice the baseline value) in 3. One patient did not respond. Bleeding tendency disappeared in 8 of 10 patients with bleeding symptoms at baseline. Mild adverse events were reported in 2 patients. The availability of thrombopoietin mimetics opened new prospects in the treatment of inherited thrombocytopenias. This study is registered at www.clinicaltrials.gov as NCT01133860 (European Union Drug Regulating Authorities Clinical Trials number 2008-001903-42).
Keywords: Administration, Oral; Adolescent; Adult; Benzoates; Dose-Response Relationship, Drug; Female; Genetic Predisposition to Disease; Humans; Hydrazines; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Platelet Aggregation; Platelet Count; Pyrazoles; Receptors, Thrombopoietin; Survival Rate; Thrombocytopenia; Treatment Outcome; Young Adult

Emx2 and Foxg1 inhibit gliogenesis and promote neuronogenesis. - Brancaccio, Marco; Pivetta, Chiara; Granzotto, Marilena; Filippis, Carol; Mallamaci, Antonello (Stem Cells, 2010)
Neural stem cells (NSCs) give rise to all cell types forming the cortex: neurons, astrocytes, and oligodendrocytes. The transition from the former to the latter ones takes place via lineage-restricted progenitors in a highly regulated way. This process is mastered by large sets of genes, among which some implicated in central nervous system pattern formation. The aim of this study was to disentangle the kinetic and histogenetic roles exerted by two of these genes, Emx2 and Foxg1, in cortico-cerebral precursors. For this purpose, we set up a new integrated in vitro assay design. Embryonic cortical progenitors were transduced with lentiviral vectors driving overexpression of Emx2 and Foxg1 in NSCs and neuronal progenitors. Cells belonging to different neuronogenic and gliogenic compartments were labeled by spectrally distinguishable fluoroproteins driven by cell type-specific promoters and by cell type-specific antibodies and were scored via multiplex cytofluorometry and immunocytofluorescence. A detailed picture of Emx2 and Foxg1 activities in cortico-cerebral histogenesis resulted from this study. Unexpectedly, we found that both genes inhibit gliogenesis and promote neuronogenesis, through distinct mechanisms, and Foxg1 also dramatically stimulates neurite outgrowth. Remarkably, such activities, alone or combined, may be exploited to ameliorate the neuronal output obtainable from neural cultures, for purposes of cell-based brain repair.
Keywords: Animals; Cell Differentiation; Cell Enlargement; Cells, Cultured; Female; Forkhead Transcription Factors; Homeodomain Proteins; Mice; Nerve Tissue Proteins; Neurogenesis; Neuroglia; Neurons; Stem Cells; Transcription Factors

Epidemiological and molecular assessment of a rubella outbreak in North-Eastern Italy. - D'Agaro, Pierlanfranco; Dal Molin, Gianna; Zamparo, Emanuela; Rossi, Tatiana; Micuzzo, Michele; Busetti, Marina; Santon, Daniela; Campello, Cesare (J Med Virol, 2010)
From January to June 2008, a rubella outbreak involving 111 laboratory confirmed cases occurred in the Friuli Venezia Giulia (FVG) region of North-Eastern Italy. The outbreak occurred initially in two residential homes for young adults disabled mentally and physically. Subsequently, the epidemic spread to the general population. Young adult cohorts were mostly affected and the mean age of the patients was 26.8 years; the majority of cases were male (73.8%), with a mean age of 26.6 years in males and 27.4 in females. Three pregnant women had a primary infection and two had their pregnancies terminated. Genotyping of 16 isolates showed the circulation of RUBV 2B, a genotype originating from Asia and South Africa and now present in Europe. In addition, molecular analysis revealed a well defined space-temporal spread of two viruses showing distinct sequences. A seroepidemiological survey carried out in a city within the same geographical area showed that the proportion of women of childbearing age still susceptible to rubella virus was 5.5%, fairly close to the figure (<5%) expected by 2010.
Keywords: Adolescent; Adult; Antibodies, Viral; Disease Outbreaks; Epidemics; Female; Genotype; Humans; Immunoglobulin G; Italy; Male; Pregnancy; Pregnancy Complications, Infectious; Rubella; Rubella virus; Young Adult

Ethnobotanical bioprospection of candidates for potential antimicrobial drugs from Brazilian plants: state of art and perspectives. - Benko-Iseppon, Ana Maria; Crovella, Sergio (Curr Protein Pept Sci, 2010)
Despite of the high biological diversity and traditional use of medicinal plants in Brazil, no comprehensive ethnobotanic review of plants with potential antimicrobial effects is available. In the present work own field information is aggregated with a literature review, identifying 433 Brazilian plant species potentially useful for identification of antimicrobial peptides. They included mainly woody species, distributed on 100 plant families (93 angiosperms and 7 pteridophytes) and 266 genera, covering all Brazilian regions and ecosystems. Main plant parts and indications for their use are presented and discussed, revealing the high potential that these plants present for the future planning strategies regarding the future development of antimicrobial drugs.
Keywords: Anti-Infective Agents; Biodiversity; Brazil; Ethnobotany; Plants

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Expression and association data strongly support JARID2 involvement in nonsyndromic cleft lip with or without cleft palate. - Scapoli, Luca; Martinelli, Marcella; Pezzetti, Furio; Palmieri, Annalisa; Girardi, Ambra; Savoia, Anna; Bianco, Anna Monica; Carinci, Francesco (Hum Mutat, 2010)
Nonsyndromic cleft lip with or without cleft palate (CL/P) affects approximately 1 in 1,000 births. Genetic studies have provided evidence for the role of several genes and candidate loci in clefting; however, conflicting results have frequently been obtained and much have to be done to unravel the complex genetics of CL/P. In the present investigation we have focused on the candidate region in 6p23, a region that have been found linked to CL/P in several investigations, in the attempt to find out the susceptibility gene provisionally named OFC1. Gene expression experiments in mice embryo of positional candidate genes revealed that JARID2 was highly and specifically expressed in epithelial cells in merging palatal shelves. A family-based linkage disequilibrium study confirmed the pivotal role of JARID2 in orofacial development and strongly supports a role for this gene in CL/P etiology (multiallelic haplotype test P=6 x 10(-5)). Understanding the molecular role of JARID2 within facial development may offer additional information to further unravel the complex genetics of CL/P.
Keywords: Animals; Cleft Lip; Cleft Palate; DNA Mutational Analysis; Family Health; Female; Gene Expression; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Haplotypes; Humans; In Situ Hybridization; Linkage Disequilibrium; Male; Mice; Mice, Inbred C57BL; Mutation; Nerve Tissue Proteins; Palate; Polycomb Repressive Complex 2; Polymorphism, Single Nucleotide; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction

Eye movement impairment recovery in a Gaucher patient treated with miglustat. - Accardo, Agostino; Pensiero, Stefano; Ciana, Giovanni; Parentin, Fulvio; Bembi, Bruno (Neurol Res Int, 2010)
In Gaucher Disease (GD) the enzyme (imiglucerase) replacement therapy (ERT) is not able to stop the progression of the neurological involvement, while the substrate reduction therapy (SRT), performed by N-Butyldeoxynojirimycin (miglustat), is an alternative that should be evaluated. Two sisters, presenting the same genotype (R353G/R353G), were diagnosed as suffering from GD; one of them later developed neurological alterations identified by quantitative saccadic eye movements analysis. The aim of the study was to quantitatively measure the miglustat effects in this GD neurological patient. Eye movement analysis during subsequent controls was performed by estimating the characteristic parameters of saccadic main sequence. The study demonstrates that the SRT alone can be effective in GD3. Moreover, it confirms that quantitative eye movement analysis is able to precociously identify also slight neurological alterations, permitting more accurate GD classification.

First case in Italy of acquired resistance to oseltamivir in an immunocompromised patient with influenza A/H1N1v infection. - Campanini, Giulia; Piralla, Antonio; Rovida, Francesca; Puzelli, Simona; Facchini, Marzia; Locatelli, Franco; Minoli, Lorenzo; Percivalle, Elena; Donatelli, Isabella; Baldanti, Fausto (J Clin Virol, 2010)
A pandemic influenza A/H1N1v strain with the neuraminidase H274Y mutation was detected in nasal secretions of a 2-year-old leukemic patient with influenza-like illness after 18 days of treatment with oseltamivir. At baseline, no drug-resistant virus was found, while 4 days after treatment initiation a mixture of wild-type and mutated virus was detected. After treatment interruption, the wild type influenza virus re-emerged and became prevalent in nasal secretions after a few days, suggesting the lower fitness of the mutated virus strain. The patient slowly improved concurrently with a decrease in virus load, which resulted negative 42 days after diagnosis. No other drug-resistant influenza A/H1N1v virus strains have been detected in Italy (up to the end of November 2009) since the first case of the novel A/H1N1v virus was identified in the country (May 2009).
Keywords: Amino Acid Substitution; Antiviral Agents; Bodily Secretions; Child, Preschool; Drug Resistance, Viral; Female; Humans; Immunocompromised Host; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Molecular Sequence Data; Mutation, Missense; Neuraminidase; Nose; Oseltamivir; RNA, Viral; Sequence Analysis, DNA; Treatment Outcome; Viral Load; Viral Proteins; Withholding Treatment

A G to C transversion at the last nucleotide of exon 25 of the MYH9 gene results in a missense mutation rather than in a splicing defect. - Vettore, Silvia; De Rocco, Daniela; Gerber, Bernhard; Scandellari, Raffaella; Bianco, Anna Monica; Balduini, Carlo L; Pecci, Alessandro; Fabris, Fabrizio; Savoia, Anna (Eur J Med Genet, 2010)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disorder caused by mutations in MYH9, the gene encoding the heavy chain of non-muscle myosin IIA. Patients present with congenital macrothrombocytopenia and inclusion bodies in neutrophils and might develop sensorineural deafness, presenile cataract, and/or progressive nephropathy leading to end-stage renal failure. In two families with macrothrombocytopenia we identified a novel c.3485G > C mutation in the last nucleotide of exon 25. Bioinformatic tools for splice site prediction and minigene functional test predicted splicing anomalies of exon 25. However, analysis of RNA purified from patient's peripheral blood did not allowed us to detect any anomalies, suggesting that RNA processing is correct at least in this tissue. Therefore, we concluded that c.3485G > C leads to a novel missense mutation (p.Arg1162Thr) of myosin-9, which resulted to be slightly degraded in patient platelets. A precise definition of the effect of mutations is fundamental to improve our knowledge into the pathogenetic mechanisms responsible for the disease.
Keywords: Adolescent; Adult; Blood Platelets; Computational Biology; Exons; Female; Humans; Inclusion Bodies; Kidney Failure, Chronic; Molecular Motor Proteins; Mutation, Missense; Myosin Heavy Chains; Neutrophils; Nonmuscle Myosin Type IIA; Nucleotides; RNA Splicing; Thrombocytopenia

Gestational diabetes and fetal growth acceleration: induction of labour versus expectant management. - Alberico, S; Businelli, C; Wiesenfeld, U; Erenbourg, A; Maso, G; Piccoli, M; Ronfani, L (Minerva Ginecol, 2010)
AIM: The aim of the study was to compare elective induction of labour at 38 weeks versus expectant management in A1 and A2 gestational diabetes (GDM) pregnancies with fetal growth acceleration. Primary outcome of the study was C-section (CS) rate, while secondary outcomes were macrosomia incidence and adverse perinatal outcomes. METHODS: A retrospective cohort study was carried out. Data were collected between 1996 and 2006 and evaluated through patients' records analysis. Differences between the two study groups were investigated using non-parametric tests for continuous variables and χ2 test for categorical ones. RESULTS: There was no significant difference between induction and expectant management in terms of caesarean section rate. A trend favoring women in the induction group in terms of incidence of macrosomia and neonatal outcomes was identified, but results were not statistically significant. CONCLUSION: Labour induction at 38 weeks in GDM patients with fetal growth acceleration does not seem to determine an increased incidence of C-section in comparison to expectant management, particularly in case of maternal obesity.
Keywords: Adult; Body Mass Index; Cesarean Section; Diabetes, Gestational; Elective Surgical Procedures; Female; Fetal Development; Fetal Macrosomia; Gestational Age; Humans; Incidence; Infant, Newborn; Italy; Labor, Induced; Medical Records; Obesity; Pregnancy; Pregnancy Outcome; Retrospective Studies; Risk Factors; Statistics, Nonparametric; Watchful Waiting

Hepatic glycogenosis in an adolescent with diabetes. - Bua, Jenny; Marchetti, Federico; Faleschini, Elena; Ventura, Alessandro; Bussani, Rossana (J Pediatr, 2010)
Keywords: Adolescent; Diabetes Mellitus, Type 1; Female; Glycogen Storage Disease; Humans; Liver Diseases

Incidence of bacteremias and invasive mycoses in children with acute non-lymphoblastic leukemia: results from a multi-center Italian study. - Castagnola, Elio; Rossi, Mario R; Cesaro, Simone; Livadiotti, Susanna; Giacchino, Mareva; Zanazzo, Giulio; Fioredda, Francesca; Beretta, Chiara; Ciocchello, Francesca; Carli, Modesto; Putti, Maria Caterina; Pansini, Valeria; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: Data on the epidemiology of bacteremias and invasive fungal diseases (IFD) in children with acute myeloid leukemia (AML) are scarce. DESIGN AND METHODS: In a multi-center, retrospective study, we analyzed proportion, rate per 1,000 person-days at risk, and cumulative risk of bacteremias and IFD in children with AML. RESULTS: Between January 1998 and December 2005, 240 children were treated for AML at 8 Italian Centers, for a total of 521 treatment courses and 63,232 person-days at risk. Bacteremia was observed in 32% of treatment courses and IFD was seen in 10% (P < 0.0001), with rates of 2.62 and 0.84, respectively (P < 0.001). There was a significantly higher frequency of IFD during relapse treatment: proportion 15% versus 9% (P = 0.05), rate 2.10 versus 0.64 (P = 0.008) and cumulative risk 32% versus 12% (P = 0.007), while there were no differences in the proportion, rate and cumulative risk of bacteremia during front-line or relapse treatment. The epidemiology of bacteremias and IFD was different during front-line therapy for M3 as compared to other types of AML, but the differences were not statistically significant. CONCLUSIONS: Severe infectious complications are frequent during the treatment of pediatric AML, especially during relapse treatment, and bacteremias are more frequent than IFD.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bacteremia; Child; Female; Follow-Up Studies; Humans; Incidence; Italy; Leukemia, Myeloid, Acute; Male; Mycoses; Neoplasm Recurrence, Local; Retrospective Studies

Individual differences in prefrontal cortex activity during perception of bitter taste using fNIRS methodology. - Bembich, Stefano; Lanzara, Carmela; Clarici, Andrea; Demarini, Sergio; Tepper, Beverly J; Gasparini, Paolo; Grasso, Domenico L (Chem Senses, 2010)
Although bitter taste has a crucial role in nutrition by preventing the ingestion of toxic foods, there are few studies on bitter taste neuroimaging. To identify cortical areas involved in bitter taste perception and to determine if individual differences in taste sensitivity to 6-n-propylthiouracil (PROP) are represented in the brain by different cortical activation patterns, we examined 48 healthy volunteers using functional near-infrared spectroscopy. Participants rated the perceived intensity of filter paper disks impregnated with PROP and NaCl during the imaging procedure and were then classified as PROP tasters and nontasters. We monitored cortical activity in both the anterior and posterior regions of the dorsolateral prefrontal cortex (DLPFC) and in the ventrolateral prefrontal cortex (VLPFC). No activity was detected in the anterior DLPFC in any of the participants. However, during the administration of PROP, significant cortical activation was detected in the more posterior regions of the left DLPFC and in the left and right VLPFC but only in PROP tasters. PROP nontasters showed no cortical activity in these areas. These data suggest that the prefrontal cortex is involved in the conscious perception of the bitter taste of PROP and that the pattern of activity is consistent with individual differences in the ability to taste this compound. Thus, the PROP phenotype is associated with fundamental differences in cortical taste processing.
Keywords: Adult; Eating; Female; Food Preferences; Humans; Individuality; Male; Perception; Phenotype; Prefrontal Cortex; Propylthiouracil; Sodium Chloride; Spectroscopy, Near-Infrared; Taste; Taste Threshold; Young Adult

Insights into the binding of Phenyltiocarbamide (PTC) agonist to its target human TAS2R38 bitter receptor. - Biarnés, Xevi; Marchiori, Alessandro; Giorgetti, Alejandro; Lanzara, Carmela; Gasparini, Paolo; Carloni, Paolo; Born, Stephan; Brockhoff, Anne; Behrens, Maik; Meyerhof, Wolfgang (PLoS One, 2010)
Humans' bitter taste perception is mediated by the hTAS2R subfamily of the G protein-coupled membrane receptors (GPCRs). Structural information on these receptors is currently limited. Here we identify residues involved in the binding of phenylthiocarbamide (PTC) and in receptor activation in one of the most widely studied hTAS2Rs (hTAS2R38) by means of structural bioinformatics and molecular docking. The predictions are validated by site-directed mutagenesis experiments that involve specific residues located in the putative binding site and trans-membrane (TM) helices 6 and 7 putatively involved in receptor activation. Based on our measurements, we suggest that (i) residue N103 participates actively in PTC binding, in line with previous computational studies. (ii) W99, M100 and S259 contribute to define the size and shape of the binding cavity. (iii) W99 and M100, along with F255 and V296, play a key role for receptor activation, providing insights on bitter taste receptor activation not emerging from the previously reported computational models.
Keywords: Amino Acid Sequence; Calcium; Cell Line; Computational Biology; Dose-Response Relationship, Drug; Humans; Intracellular Space; Ligands; Models, Molecular; Molecular Sequence Data; Mutagenesis, Site-Directed; Phenylthiourea; Protein Binding; Protein Structure, Secondary; Receptors, G-Protein-Coupled

JCV/BKV and SV40 viral load in lymphoid tissues of young immunocompetent children from an area of north-east Italy. - Comar, Manola; Zanotta, Nunzia; Bovenzi, Massimo; Campello, Cesare (J Med Virol, 2010)
Polyomavirus infection occurring during childhood is followed by a lifelong latency in immunocompetent subjects. The major site of polyomavirus persistence are the uroepithelial cells which leads to oral transmission. It has recently been hypothesized that tonsils could be a possible reservoir. The role of tonsil, adenoid, and peripheral blood mononuclear cells (PBMCs) as possible sites of JCV, BKV, and SV40 latency in young healthy children was assessed. Two hundred fifteen fresh specimens, including 57 tonsil, 80 adenoid, and 78 PBMC samples from 80 immunocompetent children (mean age 4.8 years) were analyzed to determine the viral load by quantitative real-time PCR. The human herpes virus 6 (HHV-6) was tested as a lymphotropic reference virus. Polyomavirus was detected in 5/80 (6.2%) children while HHV-6 infection affected 27/80 children (33.7%) (P < 0.001). SV40 was detected in one adenoid sample, while footprints of BKV were found in one adenoid and three tonsil samples. JCV was never found in all samples. Polyomavirus sequences were not detected in the 78 blood samples. One adenoid and two tonsils from three children (1.4%) were positive for both polyomavirus and HHV-6. Infections were characterized by low replication rates ranging typically from 1 x 10e(2)/5.5 x 10e(4) to 6.8 x 10e(3)/8.5 x 10e(4) viral copies/number of cells. In conclusion, tonsils and adenoids of children could effectively harbor BKV and SV40, although only very few cells proved to be infected. Nevertheless, the low prevalence of polyomavirus, in comparison with the lymphotropic HHV-6, suggests that these tissues are unlikely to be the preferred site of polyomavirus latency, at least in younger children.
Keywords: Adenoids; BK Virus; Carrier State; Child; Child, Preschool; Female; Herpesvirus 6, Human; Humans; Immunocompetence; Italy; JC Virus; Male; Neutrophils; Palatine Tonsil; Polyomavirus Infections; Simian virus 40; Viral Load; Virus Latency

Long-term observational, non-randomized study of enzyme replacement therapy in late-onset glycogenosis type II. - Bembi, Bruno; Pisa, Federica Edith; Confalonieri, Marco; Ciana, Giovanni; Fiumara, Agata; Parini, Rossella; Rigoldi, Miriam; Moglia, Arrigo; Costa, Alfredo; Carlucci, Annalisa; Danesino, Cesare; Pittis, Maria Gabriela; et al. (J Inherit Metab Dis, 2010)
OBJECTIVES: Type II glycogenosis (GSDII) is a lysosomal storage disorder due to acid alpha-glucosidase (GAA) deficiency. Enzyme replacement therapy (ERT) with human recombinant alpha-glucosidase (rhGAA) has been demonstrated to be effective in the treatment of infantile forms of GSDII, but little information is available concerning late-onset phenotypes. Long-term follow-up studies are not available at present. The aim of this study was to evaluate the ERT long-term effects in late-onset GSDII. METHODS: Twenty-four patients, including 7 juveniles and 17 adults, received bi-weekly infusion of rhGAA (20 mg/kg) for at least 36 months. Clinical conditions, muscular function (6-min walking test, 6MWT; Walton scale, WS), respiratory function (vital capacity, VC; forced expiratory volume, FEV1; arterial pCO(2)), and muscle enzymes were assessed every 6 months. RESULTS: The 6MWT improved in both juvenile and adult patients (p = 0.01, p = 0.0002, respectively), as well as in patients with moderate to severe muscle function impairment (WS >3.5; p = 0.002). An overall improvement in WS was also observed (p = 0.0003). VC and FEV1 remained unchanged, while pCO(2) decreased (p = 0.017). Muscle enzymes decreased significantly (p < 0.0001). Two patients (8%) showed transient secondary events during ERT. CONCLUSIONS: Long-term ERT with rhGAA was shown to be safe, well tolerated, and effective in improving motor function and in stabilizing respiratory function in late-onset GSDII. The response pattern showed a progressive clinical improvement during the follow-up period in juvenile patients, while in adults it reached and maintained a plateau after the first year of treatment.
Keywords: Adolescent; Adult; Age of Onset; Aged; alpha-Glucosidases; Child; Enzyme Replacement Therapy; Female; Follow-Up Studies; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Observation; Time Factors; Treatment Outcome; Young Adult

Mannose-binding lectin is produced by vaginal epithelial cells and its level in the vaginal fluid is influenced by progesterone. - Bulla, R; De Seta, F; Radillo, O; Agostinis, C; Durigutto, P; Pellis, V; De Santo, D; Crovella, S; Tedesco, F (Mol Immunol, 2010)
Mannose-binding lectin (MBL) is a recognition molecule of the complement (C) system and binds to carbohydrate ligands present on a wide range of pathogenic bacteria, viruses, fungi, and parasites. MBL has been detected in the cervico-vaginal cavity where it can provide a first-line defence against infectious agents colonizing the lower tract of the reproductive system. Analysis of the cervico-vaginal lavage (CVL) obtained from 11 normal cycling women at different phases of the menstrual cycle revealed increased levels of MBL in the secretive phase. Part of this MBL derives from the circulation as indicated by the presence of transferrin in CVL tested as a marker of vascular and tissue permeability. The local synthesis of MBL is suggested by the finding that its level is substantially higher than that of transferrin in the secretive phase. The contribution of endometrium is negligible since the MBL level did not change before and after hysterectomy. RT-PCR and in situ RT-PCR analysis showed that the vaginal tissue, and in particular the basal layer of the epithelium, is a source of MBL which binds to the basal membrane and to cells of the outer layers of the epithelium. In conclusion, we have shown that MBL detected in CVL derives both from plasma as result of transudation and from local synthesis and its level is progesterone dependent increasing in the secretive phase of the menstrual cycle.
Keywords: Adolescent; Adult; Body Fluids; Enzyme-Linked Immunosorbent Assay; Epithelial Cells; Female; Humans; Immunohistochemistry; Mannose-Binding Lectin; Menstrual Cycle; Progesterone; Reverse Transcriptase Polymerase Chain Reaction; Vagina; Young Adult

Mode of delivery in HIV-infected pregnant women and prevention of mother-to-child transmission: changing practices in Western Europe. - Boer, K; England, K; Godfried, M H; Thorne, C (HIV Med, 2010)
OBJECTIVES: The aim of the study was to examine temporal and geographical patterns of mode of delivery in the European Collaborative Study (ECS), identify factors associated with elective caesarean section (CS) delivery in the highly active antiretroviral therapy (HAART) era and explore associations between mode of delivery and mother-to-child transmission (MTCT). METHODS: The ECS is a cohort study in which HIV-infected pregnant women are enrolled and their infants prospectively followed. Data on 5238 mother-child pairs (MCPs) enrolled in Western European ECS sites between 1985 and 2007 were analysed. RESULTS: The elective CS rate increased from 16% in 1985-1993 to 67% in 1999-2001, declining to 51% by 2005-2007. In 2002-2004, 10% of infants were delivered vaginally, increasing to 34% by 2005-2007. During the HAART era, women in Belgium, the United Kingdom and the Netherlands were less likely to deliver by elective CS than those in Italy and Spain [adjusted odds ratio (AOR) 0.07; 95% confidence interval (CI) 0.04-0.12]. The MTCT rate in 2005-2007 was 1%. Among MCPs with maternal HIV RNA<400 HIV-1 RNA copies/mL (n=960), elective CS was associated with 80% decreased MTCT risk (AOR 0.20; 95% CI 0.05-0.65) adjusting for HAART and prematurity. Two infants born to 559 women with viral loads <50 copies/mL were infected, one of whom was delivered by elective CS (MTCT rate 0.4%; 95% CI 0.04-1.29). CONCLUSIONS: Our findings suggest that elective CS prevents MTCT even at low maternal viral loads, but the study was insufficiently powered to enable a conclusion to be drawn as to whether this applies for viral loads <50 copies/mL. Diverging mode of delivery patterns in Europe reflect uncertainties regarding the risk-benefit balance of elective CS for women on successful HAART.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Cesarean Section; Delivery, Obstetric; Epidemiologic Methods; Europe; Female; HIV Infections; Humans; Infant; Infant, Newborn; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Prenatal Care; Reverse Transcriptase Inhibitors; Substance Abuse, Intravenous; Viral Load; Young Adult; Zidovudine

Modeling the effect of 3 missense AGXT mutations on dimerization of the AGT enzyme in primary hyperoxaluria type 1. - Robbiano, Angela; Frecer, Vladimir; Miertus, Jan; Zadro, Cristina; Ulivi, Sheila; Bevilacqua, Elena; Mandrile, Giorgia; De Marchi, Mario; Miertus, Stanislav; Amoroso, Antonio (J Nephrol, 2010)
INTRODUCTION: Mutations of the AGXT gene encoding the alanine:glyoxylate aminotransferase liver enzyme (AGT) cause primary hyperoxaluria type 1 (PH1). Here we report a molecular modeling study of selected missense AGXT mutations: the common Gly170Arg and the recently described Gly47Arg and Ser81Leu variants, predicted to be pathogenic using standard criteria. METHODS: Taking advantage of the refined 3D structure of AGT, we computed the dimerization energy of the wild-type and mutated proteins. RESULTS: Molecular modeling predicted that Gly47Arg affects dimerization with a similar effect to that shown previously for Gly170Arg through classical biochemical approaches. In contrast, no effect on dimerization was predicted for Ser81Leu. Therefore, this probably demonstrates pathogenic properties via a different mechanism, similar to that described for the adjacent Gly82Glu mutation that affects pyridoxine binding. CONCLUSION: This study shows that the molecular modeling approach can contribute to evaluating the pathogenicity of some missense variants that affect dimerization. However, in silico studies--aimed to assess the relationship between structural change and biological effects--require the integrated use of more than 1 tool.
Keywords: Amino Acid Sequence; Female; Humans; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Protein Multimerization; Transaminases

Molecular surveillance of pandemic influenza A(H1N1) viruses circulating in Italy from May 2009 to February 2010: association between haemagglutinin mutations and clinical outcome. - Puzelli, S; Facchini, M; De Marco, M A; Palmieri, A; Spagnolo, D; Boros, S; Corcioli, F; Trotta, D; Bagnarelli, P; Azzi, A; Cassone, A; Rezza, G; et al. (Euro Surveill, 2010)
Haemagglutinin sequences of pandemic influenza A(H1N1) viruses circulating in Italy were examined, focusing on amino acid changes at position 222 because of its suggested pathogenic relevance. Among 169 patients, the D222G substitution was detected in three of 52 (5.8%) severe cases and in one of 117 (0.9%) mild cases, whereas the D222E mutation was more frequent and evenly distributed in mild (31.6%) and severe cases (38.4%). A cluster of D222E viruses among school children confirms reported human-to-human transmission of viruses mutated at amino acid position 222.
Keywords: Adolescent; Adult; Age Distribution; Aged; Amino Acid Substitution; Child; Child, Preschool; Female; Hemagglutinins; Humans; Infant; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Male; Middle Aged; Mutation; Pandemics; Population Surveillance; Reverse Transcriptase Polymerase Chain Reaction; Severity of Illness Index; Sex Distribution; Young Adult

Multidrug resistant Pseudomonas aeruginosa infection in children undergoing chemotherapy and hematopoietic stem cell transplantation. - Caselli, Désirée; Cesaro, Simone; Ziino, Ottavio; Zanazzo, Giulio; Manicone, Rosaria; Livadiotti, Susanna; Cellini, Monica; Frenos, Stefano; Milano, Giuseppe M; Cappelli, Barbara; Licciardello, Maria; Beretta, Chiara; et al. (Haematologica, 2010)
Pseudomonas aeruginosa is one leading gram-negative organism associated with nosocomial infections. Bacteremia is life-threatening in the immunocompromised host. Increasing frequency of multi-drug-resistant (MDRPA) strains is concerning. We started a retrospective survey in the pediatric hematology oncology Italian network. Between 2000 and 2008, 127 patients with Pseudomonas aeruginosa bacteremia were reported from 12 centers; 31.4% of isolates were MDRPA. Death within 30 days of a positive blood culture occurred in 19.6% (25/127) of total patients; in patients with MDRPA infection it occurred in 35.8% (14/39). In the multivariate analysis, only MDRPA had significant association with infection-related death. This is the largest series of Pseudomonas aeruginosa bacteremia cases from pediatric hematology oncology centers. Monitoring local bacterial isolates epidemiology is mandatory and will allow empiric antibiotic therapy to be tailored to reduce fatalities.
Keywords: Adolescent; Antineoplastic Agents; Bacteremia; Child; Child, Preschool; Drug Resistance, Multiple; Female; Hematopoietic Stem Cell Transplantation; Humans; Immunocompromised Host; Infant; Infant, Newborn; Italy; Male; Pseudomonas aeruginosa; Pseudomonas Infections; Retrospective Studies; Young Adult

Multiple segmental absence of intestinal musculature presenting as spontaneous isolated perforation in an extremely low-birth-weight infant. - Oretti, Chiara; Bussani, Rossana; Janes, Augusta; Demarini, Sergio (J Pediatr Surg, 2010)
Defect of the intestinal musculature is a rare condition. It may cause intestinal perforation or obstruction. It manifests itself mainly in the neonatal period and usually affects preterm infants. We describe one such case, which was first diagnosed as a spontaneous isolated intestinal perforation. Emergency laparotomy was performed and showed multiple perforations, with accompanying peritonitis and ascites. Pathologic examination showed partial or complete absence of the musculature, particularly of the inner circular layer, with fibrous tissue in the regions of missing muscle, and abnormal vasculature. The myenteric plexus was absent in areas of muscle loss but present in other sites. These findings suggest that the absence of muscle may not represent a congenital malformation but may be secondary to ischemic injury.
Keywords: Diseases in Twins; Female; Humans; Ileum; Infant, Extremely Low Birth Weight; Infant, Newborn; Infant, Premature; Intestinal Atresia; Intestinal Perforation; Laparotomy; Muscle, Smooth; Myenteric Plexus; Rare Diseases

MYH9-related disease: Report on five German families and description of a novel mutation. - Savoia, Anna; Germeshausen, Manuela; De Rocco, Daniela; Henschel, Bettina; Kratz, Christian P; Kuhlen, Michaela; Rath, Bettina; Steuhl, Klaus-Peter; Wermes, Cornelia; Ballmaier, Matthias (Ann Hematol, 2010)
Keywords: Adult; Aged; Child; Chromosome Disorders; DNA Mutational Analysis; Germany; Humans; Infant; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Young Adult

Neonatal jaundice and breastfeeding reputation. - Bramuzzo, Matteo; Davanzo, Riccardo (J Hum Lact, 2010)
Keywords: Bottle Feeding; Breast Feeding; Female; Humans; Infant, Newborn; Jaundice, Neonatal; Lactation Disorders; Milk, Human; Risk Factors

Predictors of poor response to methotrexate in polyarticular-course juvenile idiopathic arthritis: analysis of the PRINTO methotrexate trial. - Vilca, Iris; Munitis, Pablo Garcia; Pistorio, Angela; Ravelli, Angelo; Buoncompagni, Antonella; Bica, Blanca; Campos, Lucia; Häfner, Renate; Hofer, Michael; Ozen, Seza; Huemer, Christian; Bae, Sang Cheol; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To determine whether baseline demographic, clinical, articular and laboratory variables predict methotrexate (MTX) poor response in polyarticular-course juvenile idiopathic arthritis. METHODS: Patients newly treated for 6 months with MTX enrolled in the Paediatric Rheumatology International Trials Organization (PRINTO) MTX trial. Bivariate and logistic regression analyses were used to identify baseline predictors of poor response according to the American College of Rheumatology pediatric (ACR-ped) 30 and 70 criteria. RESULTS: In all, 405/563 (71.9%) of patients were women; median age at onset and disease duration were 4.3 and 1.4 years, respectively, with anti-nuclear antibody (ANA) detected in 259/537 (48.2%) patients. With multivariate logistic regression analysis, the most important determinants of ACR-ped 70 non-responders were: disease duration > 1.3 years (OR 1.93), ANA negativity (OR 1.77), Childhood Health Assessment Questionnaire (CHAQ) disability index > 1.125 (OR 1.65) and the presence of right and left wrist activity (OR 1.55). Predictors of ACR-ped 30 non-responders were: ANA negativity (OR 1.92), CHAQ disability index > 1.14 (OR 2.18) and a parent's evaluation of child's overall well-being < or = 4.69 (OR 2.2). CONCLUSION: The subgroup of patients with longer disease duration, ANA negativity, higher disability and presence of wrist activity were significantly associated with a poorer response to a 6-month MTX course.
Keywords: Adolescent; Antibodies, Antinuclear; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Disability Evaluation; Female; Follow-Up Studies; Humans; Immunosuppressive Agents; Male; Methotrexate; Prognosis; Treatment Outcome

Prepregnancy BMI influences maternal and fetal outcomes in women with isolated gestational hyperglycaemia: a multicentre study. - Lapolla, A; Bonomo, M; Dalfrà, M G; Parretti, E; Mannino, D; Mello, G; Di Cianni, G (Diabetes Metab, 2010)
AIM: This multicentre study analyzed the maternal and fetal outcomes of women who had one elevated 3-h oral glucose tolerance test (isolated gestational hyperglycaemia [IGH]). METHODS: From 1999 to 2003, data were collected for 606 IGH women from 31 Italian obstetric or diabetic centres, including time and mode of delivery, gestational hypertension, preeclampsia, eclampsia, congenital malformations, and neonatal mortality and morbidity, to compare them with the general pregnant Italian population. A prognostic model for the outcome of pregnancy was constructed, and the concurrence of certain specified conditions was considered a positive outcome, whereas pregnancies that failed to meet one or more of the stated conditions were classified as "complicated". RESULTS: Macrosomia was significantly more frequent in women with IGH than in the normal pregnant population (10.7 vs 7.4%, respectively; P=0.003). Stillbirth and neonatal mortality rates did not differ from those in normal pregnancies, while a slight rise in the frequency of major malformations was not statistically significant (1.48 vs 0.89%, respectively; P<0.11). Multivariate logistic analyses confirmed that the prepregnancy body mass index (BMI) was an independent predictor of a complicated pregnancy. As for fetal growth, multivariate logistic analyses according to BMI showed that being overweight or obese were strong predictors of macrosomia. CONCLUSION: These findings in a large cohort of Italian women with IGH confirm the detrimental effect of even minimally altered glucose tolerance on fetal outcome. Also, prepregnancy obesity plays an important role in raising the risk of adverse perinatal outcomes in such patients.
Keywords: Adult; Blood Glucose; Body Mass Index; Female; Fetal Macrosomia; Glucose Tolerance Test; Humans; Hyperglycemia; Italy; Models, Statistical; Obesity; Pregnancy; Pregnancy Complications; Pregnancy Outcome; Prognosis; Retrospective Studies; Risk Factors; Time Factors

Progress towards the achievement of MDG4 in the Commonwealth of Independent States: uncertain data, clear priorities. - Cattaneo, Adriano; Gafurov, Ilkhom; Bomestar, Tamara; Bacci, Marianna; Kumar, Sanjiv; Popovic, Dragoslav; Tamburlini, Giorgio (Health Res Policy Syst, 2010)
Data on under five mortality in the twelve countries of the Commonwealth of Independent States show important fluctuations over time due to variations in quality of data, definitions of neonatal deaths and methods of mortality estimation. Despite the uncertainties regarding mortality trends, the analysis of health and social information from different sources offers clues to identify priority areas and key strategic directions for accelerating the achievement of the 4th Millennium Development Goal. Neonatal deaths represent from 40% to over 50% of under five deaths in all these countries. Maternal mortality was above 50 per 100,000 in 2005, despite the good coverage with antenatal care and births assisted by skilled birth attendants. The scanty information on quality of perinatal care indicates widespread substandard care at all levels. Stunting in children under five is above 10% in ten out of twelve countries and coexists with emerging overweight. Exclusivity and duration of breastfeeding fall short of what is recommended. There are important inequalities in child and maternal mortality, malnutrition and access and use of health services within countries. Taken as a whole, the available information clearly indicates that priority should be given to improvement of the health of women in reproductive age and of the quality of perinatal care, including the establishment of reliable data collection systems. To achieve this, action will need to focus on strengthening the capacity of the health system to improve the technical content of service provision, and on improving access and appropriate use of services by the most disadvantaged groups. The involvement of other sectors will be necessary to improve reproductive health and nutrition at community level and to tackle inequity. Comparisons between countries with similar socioeconomic background but different health policies seem to indicate that gradual progression towards universal coverage with essential health care through a national health insurance system is associated with larger reduction of child mortality than troubled transition towards a privatized and unregulated health system.

Splenomegaly as presentation of a wandering spleen. - Maschio, Massimo; Cozzi, Giorgio; Sanabor, Daniela; Zennaro, Floriana; Gloria, Pelizzo; Barbi, Egidio (J Pediatr, 2010)
Keywords: Child; Female; Humans; Splenomegaly; Wandering Spleen

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Breastfeed Rev, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low-income settings, the original KMC modelis implemented. This consists of continuous (24 h/day; 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding and, adequate follow up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC modelin all types of settings was discussed at the 7th International Workshop on KMC Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents'role, modification of the NICU environment, performance of care in KMC, and KMCin case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.

State of the art and recommendations. Kangaroo mother care: application in a high-tech environment. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Peláez, J G; Sizun, J; et al. (Acta Paediatr, 2010)
UNLABELLED: Since Kangaroo Mother Care (KMC) was developed in Colombia in the 1970s, two trends in clinical application emerged. In low income settings, the original KMC model is implemented. This consists of continuous (24 h/day, 7 days/week) and prolonged mother/parent-infant skin-to-skin contact; early discharge with the infant in the kangaroo position; (ideally) exclusive breastfeeding; and, adequate follow-up. In affluent settings, intermittent KMC with sessions of one or a few hours skin-to-skin contact for a limited period is common. As a result of the increasing evidence of the benefits of KMC for both infants and families in all intensive care settings, KMC in a high-tech environment was chosen as the topic for the first European Conference on KMC, and the clinical implementation of the KMC model in all types of settings was discussed at the 7th International Workshop on KMC. Kangaroo Mother Care protocols in high-tech Neonatal Intensive Care Units (NICU) should specify criteria for initiation, kangaroo position, transfer to/from KMC, transport in kangaroo position, kangaroo nutrition, parents' role, modification of the NICU environment, performance of care in KMC, and KMC in case of infant instability. CONCLUSION: Implementation of the original KMC method, with continuous skin-to-skin contact whenever possible, is recommended for application in high-tech environments, although scientific evaluation should continue.
Keywords: Attitude of Health Personnel; Female; Humans; Infant Care; Infant, Newborn; Intensive Care Units, Neonatal; Male; Parent-Child Relations; Practice Guidelines as Topic; Professional-Patient Relations; Role; Skin; Visitors to Patients

[Strategies for cardiovascular prevention in children]. - Spinelli, Angela; Nardone, Paola; Lamberti, Anna; Baglio, Giovanni (G Ital Cardiol (Rome), 2010)
Keywords: Body Mass Index; Cardiovascular Diseases; Child; Diet, Mediterranean; Food Habits; Humans; Life Style; Motor Activity; Obesity; Overweight; Patient Education as Topic; Population Surveillance; Questionnaires; Risk Factors

Therapeutic strategy in p47-phox deficient chronic granulomatous disease presenting as inflammatory bowel disease. - Freudenberg, Folke; Wintergerst, Uwe; Roesen-Wolff, Angela; Albert, Michael H; Prell, Christine; Strahm, Brigitte; Koletzko, Sibylle; Ehl, Stephan; Roos, Dirk; Tommasini, Alberto; Ventura, Alessandro; Belohradsky, Bernd H; et al. (J Allergy Clin Immunol, 2010)
Keywords: Age of Onset; Anti-Bacterial Agents; Antibodies, Monoclonal; Child; Drug Therapy, Combination; Gene Deletion; Granulomatous Disease, Chronic; Humans; Inflammatory Bowel Diseases; Male; NADPH Oxidase; Steroids; Treatment Outcome; Vidarabine

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Ticks and Lyme borreliosis in an alpine area in northeast Italy. - Nazzi, F; Martinelli, E; Del Fabbro, S; Bernardinelli, I; Milani, N; Iob, A; Pischiutti, P; Campello, C; D'Agaro, P (Med Vet Entomol, 2010)
A 2-year study was conducted in a mountainous area of northeast Italy to evaluate the occurrence and distribution of ticks, as well as to assess the prevalence of the spirochaete Borrelia burgdorferi sensu lato. All ticks collected were Ixodes ricinus L. (Parasitiformes: Ixodidae). In general, most nymphs and adult ticks were collected from April to July. Tick density was highly variable among sites; however, two areas with different infestation levels were recognized. Prevalences of B. burgdorferi s.l. in nymphal stages were rather variable between sites; overall the prevalence of infected nymphs in the whole area was slightly higher than 20%. The prevalence of B. burgdorferi s.l. in nymphs does not seem to be correlated with nymph density. The correlation between the incidence of Lyme borreliosis (reported human cases/1000 inhabitants/year) and Borrelia prevalence in nymphs was not significant, although a significant correlation was found between borreliosis incidence and nymph density.
Keywords: Animals; Borrelia burgdorferi; Climate; Ecology; Humans; Incidence; Italy; Ixodes; Lyme Disease; Nymph; Population Density; Prevalence; Seasons; Ticks

Toward a consensus on guiding principles for health systems strengthening. - Swanson, Robert C; Bongiovanni, Annette; Bradley, Elizabeth; Murugan, Varnee; Sundewall, Jesper; Betigeri, Arvind; Nyonator, Frank; Cattaneo, Adriano; Harless, Brandi; Ostrovsky, Andrey; Labonté, Ronald (PLoS Med, 2010)
Keywords: Global Health; Humans; Public Health

Towards universal Kangaroo Mother Care: recommendations and report from the First European conference and Seventh International Workshop on Kangaroo Mother Care. - Nyqvist, K H; Anderson, G C; Bergman, N; Cattaneo, A; Charpak, N; Davanzo, R; Ewald, U; Ibe, O; Ludington-Hoe, S; Mendoza, S; Pallás-Allonso, C; Ruiz Peláez, J G; et al. (Acta Paediatr, 2010)
UNLABELLED: The hallmark of Kangaroo Mother Care (KMC) is the kangaroo position: the infant is cared for skin-to-skin vertically between the mother's breasts and below her clothes, 24 h/day, with father/substitute(s) participating as KMC providers. Intermittent KMC (for short periods once or a few times per day, for a variable number of days) is commonly employed in high-tech neonatal intensive care units. These two modalities should be regarded as a progressive adaptation of the mother-infant dyad, ideally towards continuous KMC, starting gradually and progressively with intermittent KMC. The other components in KMC are exclusive breastfeeding (ideally) and early discharge in kangaroo position with strict follow-up. Current evidence allows the following general statements about KMC in affluent and low-income settings: KMC enhances bonding and attachment; reduces maternal postpartum depression symptoms; enhances infant physiologic stability and reduces pain, increases parental sensitivity to infant cues; contributes to the establishment and longer duration of breastfeeding and has positive effects on infant development and infant/parent interaction. Therefore, intrapartum and postnatal care in all types of settings should adhere to a paradigm of nonseparation of infants and their mothers/families. Preterm/low-birth-weight infants should be regarded as extero-gestational foetuses needing skin-to-skin contact to promote maturation. CONCLUSION: Kangaroo Mother Care should begin as soon as possible after birth, be applied as continuous skin-to-skin contact to the extent that this is possible and appropriate and continue for as long as appropriate.
Keywords: Congresses as Topic; Female; Global Health; Humans; Infant Care; Infant, Newborn; Male; Parent-Child Relations; Practice Guidelines as Topic; Randomized Controlled Trials as Topic; Skin

Use of ketamine continuous infusion for pediatric sedation in septic shock. - Barbi, Egidio; Rizzello, Elisa; Taddio, Andrea (Pediatr Emerg Care, 2010)
Keywords: Anesthetics, Dissociative; Child; Conscious Sedation; Humans; Infusions, Intravenous; Ketamine; Male; Shock, Septic

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult

A web-based system for total parenteral nutrition prescription in a pediatric hospital - biomed 2010. - Bava, Michele; Bradashia, Fulvio; Rovere, Francesca; Maestro, Alessandra; Vecchi Brumatti, Liz; Accardo, Agostino; Paparazzo, Rossella; Zanon, Davide (Biomed Sci Instrum, 2010)
otal Parenteral Nutrition (TPN) is defined as feeding a patient by infusing nutrients intravenously, bypassing the usual process of eating and digestion. There are two kinds of TPN: short-term TPN may be used when a patient's digestive system is temporarily nonfunctional because of an interruption in its continuity; long-term TPN is used to treat patients with an impairment or a lack in nutrient absorption. TPN has extended the life of children born with nonexistent or severely deformed digestive organs and is a vital support for these patients. In Burlos Pediatric Department, pediatricians fill in a pharmacy request form in which nutritional needs are included for each patient. Subsequently, clinical pharmacists evaluate the patients individual data and decide which TPN formula to prepare. To enhance the TPN prescription process, an intranet web-based system has been developed to replicate the original paper-based forms. The software, developed in PHP and based on open source tools and services, has been constructed according to pharmacists requirements. These professionals, together with the Hospital Information System technicians, thanks to the availability of affordable instruments, perceive the advantages that such a system would have in improving clinical practice and quality of care. The system was devised with the goal to avoid common reading errors, to improve the correct text comprehension, to ensure prescription preparation, administration and tracking. According to a process of total quality control, the system reduces clinical risks regarding issues such as the correct and rapid availability of medical prescriptions and the incorrect identification of the patients. In comparison with paper-based TPN prescriptions, electronic-based forms have reduced the incidence of errors, the possible lack of patient data and reading misunderstandings. Regarding future improvements, IT technicians are defining the procedures to implement digital signature and medical aspects of the electronic TPN medical prescriptions.

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal

Delineation of the intimate details of the backbone conformation of pyridine nucleotide coenzymes in aqueous solution. - Bose, K S; Sarma, R H (Biochem Biophys Res Commun, 1975)
Keywords: Fourier Analysis; Magnetic Resonance Spectroscopy; Models, Molecular; Molecular Conformation; NAD; NADP; Structure-Activity Relationship; Temperature

Metal substitutions incarbonic anhydrase: a halide ion probe study. - Smith, R J; Bryant, R G (Biochem Biophys Res Commun, 1975)
Keywords: Animals; Binding Sites; Cadmium; Carbonic Anhydrases; Cattle; Humans; Hydrogen-Ion Concentration; Magnetic Resonance Spectroscopy; Mercury; Protein Binding; Protein Conformation; Zinc